Comparative analysis of contemporary remote sensing techniques and species distribution modelling in predicting spatial distribution of coastal habitats - Louise Forsblom; Ari-Pekka Jokinen; Dimitry Van der Zande; Mihailo Azhar; Dimitar Berov; Jacob Carstensen; Vivi Drakopoulou; Vasilis Gerakaris; Hege Gundersen; Jonne Kotta; Valeria Mobilia; Nadia Papadopoulou; et al. (Remote Sensing of Environment, 2026)

Starch modification and protein complexation synergistically strengthen hydrocolloid networks and limit enzymatic hydrolysis in gluten-free noodles - Babatunde Olawoye; Oladapo Fisoye Fagbohun; Folasade Olabimpe Adeboyejo; Boluwatife Martins Okedepo; Gladys Damilola Obalowo; Christopher Olayinka Adedoyin; Omototade Richard Ogunremi; Folasade O. Afolabi; Oseni Peter Kadiri (Food Hydrocolloids, 2026)

A fuzzy inference system approach for habitat suitability index modeling: A case study of Bachman’s sparrow - Cassio Auguto Ussi Monti; Casey Eugene Phillips; Joseph Peter Roise; John Paul McTague; Christopher Moorman; Rachel Cook (Ecological Modelling, 2026)

Salinity and sediment stress: Metabolic responses in the leaf oyster, Isognomon ephippium - Christopher J. Klaas; Conor A. Hendrickson; Peter Butcherine; Victoria J. Cole; Kirsten Benkendorff (Marine Environmental Research, 2026)

Global perspectives on the curricular integration of nature-based solutions in hydrology and water resources management education - Mark Bryan Alivio; Kristina Potočki; Pavel Raška; Peter Ameh Adegede; Tanveer Mehedi Adyel; Hafzullah Aksoy; Mary Bourke; Yonca Cavus; Mariana Madruga de Brito; Moctar Dembélé; Ashraf M. Elmoustafa; Kristian Förster; et al. (Journal of Cleaner Production, 2026)

Brown skua Catharacta antarctica breeding distribution and population trends on sub-Antarctic Marion Island, 1987–2023: implications of alien invasive species - Michelle M. Risi; Christopher W. Jones; Maëlle Connan; Eleanor A. Weideman; Lucy K. Smyth; Mia Cerfonteyn; Stephen Hunter; Peter G. Ryan (Polar Biology, 2026)
Predator-prey relationships on islands are often profoundly altered by invasive species. Brown skuas Catharacta antarctica are predator-scavengers at sub-Antarctic islands, where their population dynamics are linked to food availability. On Marion Island, skua population size and breeding distribution appear to have shifted in response to changes in burrowing petrel populations, which were severely impacted by feral cat Felis catus predation before cats were eradicated in 1991. We compare estimates of brown skua population size, breeding distribution, and fledgling production on Marion Island from studies conducted between 2010 and 2023 to earlier studies before cats were eradicated, including an extensive survey in 1987–1988. With increased search effort in 2023, we recorded 983 breeding territories, exceeding the 1987–1988 estimate of 878 territories, despite a slight decrease in average production, from 1.26 fledglings per pair per year in 1987–1988 to 1.10 between 2010 and 2022 ( n = 3 surveys). Most notably, there has been a shift in the distribution of breeding sites: territories in coastal areas where skuas mainly prey on penguins have increased by 39% since 1987–1988, whereas they decreased by 31% at inland sites where petrels are the main prey. This coastward shift is surprising given the modest recovery in petrel numbers since cats were eradicated and recent decreases in penguin populations. These counterintuitive findings establish a baseline for monitoring ecological change on Marion Island. As we expect more impacts associated with climate change, highly pathogenic avian influenza and invasive species management, regular surveys of predators such as brown skuas become increasingly valuable.

Water-Level Rise and Nonmonotonic Salinity Change Across Louisiana Coastal Wetlands Over Fifteen Years - Jin Ikeda; Peter Bacopoulos; Linoj Vijayan; Shu Gao; Christopher E. Kees (Estuaries and Coasts, 2026)
Long-term monitoring is vital to understanding how coastal wetlands respond to environmental changes. Using 15 years (2008–2022) of hourly water-level and salinity data from over 300 Coastwide Reference Monitoring System (CRMS) stations in Louisiana, USA, this study quantifies annual and decadal trends in water levels and salinity across nine basins and five vegetation types. The variations and trends were evaluated using a 12-month moving average method. Water levels increased statewide at 13.9 mm yr -1 , leading to an increase in inundation depth of 5.9 mm yr -1 . The influence of local climatic drivers (sea surface temperature, river flow, precipitation, and wind) varies with local hydrogeomorphic settings. In marine-influenced saline and brackish marshes, water levels covaried more strongly with surface temperature in the Gulf of Mexico. Concurrently, elevated river flows and local precipitation further increased water levels in freshwater marshes and swamps. Salinity levels showed high sensitivity to freshwater inputs and steadily decreased from 2011 to 2020, consistent with increased freshwater inputs. These results indicate that salinity responses in deltaic wetlands are possibly non-monotonic and strongly modulated by freshwater variability, even under ongoing sea-level rise. This comprehensive study on one of the most vulnerable coastal wetland systems provides insights into future coastal wetland responses and resilience broadly. Also, the automated, data-driven workflow provides transferable inputs to process-based modeling, enabling scenario evaluation and resilience planning in dynamic coastal wetlands.

Effects of pre-spawning heat stress on the fecundity of Acropora aspera - Morane Le Nohaic; Christopher Doropoulos; Selina Ward; Peter J. Mumby (Coral Reefs, 2026)
Repeated bleaching events driven by heat stress have caused extensive coral mortality and declines in survivors’ reproductive output, undermining reef recovery. On the Great Barrier Reef, heat stress events currently coincide with early oogenesis in many abundant taxa; with climate change, earlier onsets are expected to increasingly overlap later gametogenic stages. How coral reproduction responds as gametes mature in warmer waters remains unclear. To address this, we quantified the effects of heat stress during late gametogenesis on the fecundity of Acropora aspera . Using an ex situ experiment, gravid colonies were exposed to nine treatments combining three temperatures (Control + 1, + 2 °C) and three durations (3, 6, 9 weeks). Gravid polyp probability, polyp egg counts, egg volume, and testis volume were assessed at spawning. Responses were trait- and duration-specific. Sperm production was most sensitive, with testis volume declining ~ threefold under + 2 °C for 9 weeks relative to controls (0.056 mm 3 vs 0.160 mm 3 ); the same exposure nearly halved gravid polyp probability (0.015 vs 0.026 in Controls). However, 6-week exposure at + 2 °C increased sperm production (0.174 mm 3 ), highlighting the influence of exposure duration. In contrast, longer exposure to heat stress increased egg volume, which nearly doubled at + 1 °C (0.176 mm 3 vs 0.098 mm 3 in Controls); while egg counts remained stable, suggesting a strategy favouring better provisioned rather than numerous eggs. Nevertheless, larger gamete volumes may reflect stress-induced physiological changes rather than improved quality. These findings demonstrate that heat intensity, duration, and timing jointly shape coral reproductive investment, highlighting the complexity of predicting future reef recovery under climate change.

Soil macropore characteristics and hydro-physical properties improved by diversified crop rotations and cover cropping in long-term no-till cropping systems - Sainfort Vital; Sutie Xu; Xi Zhang; Namrata Ghimire; Peter Sexton; Mengistu Geza; Christopher Graham; Lan Xu (Soil and Tillage Research, 2026)

The relative contributions of baseline hydroperiod, event-driven exceedances, and tropical-cyclone extremes to marsh accretion in microtidal regimes - Shabnam Mirheidarian; Peter Bacopoulos; Christopher E. Kees (Estuarine, Coastal and Shelf Science, 2026)

Inspiratory muscle loading with dyspnea limits simulated driving performance in young adults - Mary Frost; Jared So; Crystal Huang; Owen Kwok; Ryan Lui; Christopher Williams; Peter Rassam; Manjiri Kulkarni; Anson He; Dmitry Rozenberg; W. Darlene Reid (European Journal of Applied Physiology, 2026)

Quantitative assessment of knowledge gaps and research priorities for understanding and managing population irruptions of crown-of-thorns starfish (Acanthaster cf. solaris) on Australia’s Great Barrier Reef - Morgan S. Pratchett; Peter C. Doll; Christopher Cvitanovic; Shaun K. Wilson; Russell C. Babcock; Yves-Marie Bozec; Deborah Burn; Maria Byrne; Carolina Castro-Sanguino; Carla C. M. Chen; Scott A. Condie; Zara-Louise Cowan; et al. (Coral Reefs, 2026)
Despite extensive research on the western Pacific crown-of-thorns starfish (CoTS; Acanthaster cf. solaris ), especially from Australia’s Great Barrier Reef (GBR), there are persistent knowledge gaps that constrain understanding and management. Given renewed population irruptions of CoTS on the GBR, alongside escalating climate impacts and direct anthropogenic pressures, a quantitative assessment of knowledge gaps was undertaken to identify research priorities and guide future efforts. In this study, 27 experts independently scored 206 research questions across seven Themes and 39 topics, based on four different criteria ( Knowledge gap , Feasibility , Urgency , and Applicability ). These questions were ultimately rationalized into 170 distinct questions, with scores aggregated across merged questions. Management was the highest scoring Theme for Urgency , Applicability , and overall. All but six of the 20 top-ranked questions were from the Management Theme and mainly related to Culling and/ or Monitoring. Most questions (158 out of 170) also scored highly for Feasibility , suggesting that there are existing methods and technical capability available to advance the extensive and diverse range of research questions that were posed, if resources were made available. This quantitative assessment provides guidance on the prioritization of potential research that could improve management of CoTS populations to improve coral protection outcomes on the GBR. This study also suggests that there are limited constraints to undertaking necessary research to address many of the persistent knowledge gaps relating to CoTS.

Fine-scale spatial variability, seasonal dynamics, and decadal trends of mercury contamination in Southern New England estuarine and coastal fishes - David L. Taylor; Colby C. Peters; Christopher Parkins; M. Conor McManus (Marine Pollution Bulletin, 2026)

Bundesweite Entwicklung der Grundwasserstände seit 1991: Langzeittrends, Variabilität und Auswirkungen der jüngsten Trockenphase - Maria Wetzel; Stefan Broda; Mariana Gomez; Markus Zaepke; Patrick Clos; Stefan Kunz; Tanja Liesch; Marc Ohmer; Bastian Habbel; Michel Wingering; Bernhard Pitschka; Antje Roucka; et al. (Grundwasser, 2026)
Zusammenfassung Die Studie untersucht die Entwicklung der Grundwasserstände in Deutschland anhand von 5844 Messstellen sowie deren Reaktionsdynamik gegenüber klimatologischen Antrieben im Referenzzeitraum 1991–2020. Zusätzlich wird die Entwicklung seit 2018 im Kontext der außergewöhnlichen Dürreperiode betrachtet, um die Reaktionsfähigkeit und Vulnerabilität der Grundwassersysteme gegenüber extremen klimatischen Bedingungen zu bewerten. Erstmals erfolgt diese Auswertung bundesweit einheitlich und in enger Zusammenarbeit mit den zuständigen Landesbehörden. An 43 % der untersuchten Messstellen werden signifikante Trends festgestellt, überwiegend in Form fallender Grundwasserstände mit einem Medianrückgang von 0,9 cm pro Jahr. Dies entspricht einem jährlichen Rückgang von 0,5 %, bezogen auf die Spannweite der jeweiligen Grundwasserganglinie. Diese Entwicklungen sind deutschlandweit erkennbar, jedoch regional unterschiedlich ausgeprägt und überwiegend klimatisch bedingt. Um Unterschiede in der Reaktionsdynamik systematisch zu erfassen, werden die Messstellen anhand ihrer Autokorrelationslängen in vier Dynamikklassen eingeteilt. Mit abnehmender Dynamik zeigt sich für den Referenzzeitraum eine Zunahme langfristiger Trends (von −0,3 % pro Jahr in Dynamikklasse 1 bis −1,16 % pro Jahr in Klasse 4) sowie eine höhere Persistenz klimatischer Effekte. Träge Systeme reagieren verzögert und sind damit nachhaltiger von Niedrigständen betroffen (Median: 9,8 Monate), während schnell reagierende Systeme kürzere Niedrigstandsphasen (Median: 2,2 Monate) aufweisen und sich rascher erholen. Besonders in der Entwicklung seit 2018 werden diese Unterschiede deutlich: Rund 60 % der trägen Messstellen weisen über fünf Jahre hinweg anhaltend niedrige Grundwasserstände auf, wobei etwa 20 % neue Niedrigstände erreichen und damit unterhalb der Minimalwerte der Referenzperiode liegen. Die Ergebnisse verdeutlichen den engen Zusammenhang zwischen klimatischer Variabilität und Grundwasserdynamik und bilden eine Grundlage für die fortlaufende Bewertung der Grundwasserstandsentwicklung in Deutschland.

Global fits and the search for new physics: past, present and future - Peter Athron; Csaba Balázs; Jon Butterworth; Christopher Chang; Andrew Fowlie; Tomás Gonzalo; Adil Jueid; Anders Kvellestad; Michele Lucente; Farvah Mahmoudi; Gregory D. Martinez; Are Raklev; et al. (Science Bulletin, 2026)

Evaluation of the retention process of bile acids by cell surface of inactivated Lacticaseibacillus rhamnosus GG using spray drying under in vitro digestion simulation - Douglas Xavier-Santos; Rodrigo Dias Requião; Paulo César Martins Alves; Christopher Schmidt; Thomas Kurth; Adriane Elisabete Costa Antunes; Stephanie Bader-Mittermaier; Peter Eisner; Anderson S. Sant’Ana (Food Bioscience, 2026)

Smooth Gradients or Defined Fronts: Characterizing Within-Marsh Spatial Variability of CO2 Fluxes - Lena K. Champlin; Emily Wilson; Kenneth B. Raposa; Jason S. Goldstein; Ashley Hamilton; Jason S. Krumholz; Christopher R. Peter; Megan C. Tyrrell; Jamie M. P. Vaudrey; Robinson W. Fulweiler (Estuaries and Coasts, 2026)

Deficient arsenic methylation and global proteomic reprogramming in human keratinocytes during arsenic-induced skin carcinogenesis - Alexandra N. Nail; Mayukh Banerjee; Manting Xu; Caitlin H. Reynolds; Miroslav Stýblo; Peter H. Cable; Daniel W. Wilkey; Michael L. Merchant; Ana P. Ferragut Cardoso; Shelia D. Thomas; J. Christopher States (Archives of Toxicology, 2026)
Chronic inorganic arsenic (iAs) exposure affects > 220 million people worldwide and skin cancer is a hallmark of long-term iAs exposure. Limited information exists regarding arsenic methylation by human keratinocytes and how methylation influences skin carcinogenesis. Inorganic arsenite (iAs III ) and its methylated metabolites disrupt diverse zinc finger proteins, leading to differential toxicity patterns. We examined arsenic methylation capacity in non-malignant human keratinocytes and interrogated proteomic remodeling across three stages of iAs III induced malignant transformation using the well-established preclinical HaCaT model. Arsenic methylation was assessed by hydride generation cryotrapping inductively coupled-mass spectrometry and global proteomic changes were analyzed by tandem-mass tagging liquid chromatography-tandem mass spectrometry. Primary, hTERT-immortalized and HaCaT human keratinocytes exhibited negligible arsenic methylation, with iAs III comprising at least 98.5% of total intracellular arsenic, attributable to minimal expression of arsenite methyltransferase. Proteomic profiling identified over 275 differentially expressed proteins at each stage of transformation, including multiple zinc finger proteins implicated in cell cycle control, RNA metabolism, and genome stability. Ingenuity® Pathway Analysis revealed progressive, coordinated disruption of cancer-associated pathways and regulatory networks over the transformation timeline, including zinc-coordinating upstream regulators that may explain widespread pathway dysregulation. Collectively, our findings suggest that iAs III promotes skin carcinogenesis by disrupting C3H1- and C4-type zinc finger protein-centered regulatory networks that coordinate cancer-associated signaling and metabolic pathways in human keratinocytes, highlighting key candidates for future mechanistic studies.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Toward multi-class detection and localization of contamination in cotton fields: Comparing EfficientDet, Faster R-CNN ResNet50, SSD MobileNet V2, and YOLOv11 - Sean P. Donohoe; Femi Peter Alege; Christopher D. Delhom (Computers and Electronics in Agriculture, 2026)

Mesoscale eddies in the subpolar North Atlantic: their ecological importance and conservation significance - Lea-Anne Henry; Jason Cleland; Anna Gebruk; René Schubert; Alice Della Penna; Peter Gaube; Christian Mohn; Brynn Devine; Arne Biastoch; Camille M.L.S. Pagniello; Keno Ferter; George Wolff; et al. (Progress in Oceanography, 2026)

Microvertebrates from the Cliff End Bone Bed (Wealden, Lower Cretaceous), East Sussex, UK - Johnny Clavo Yamahuchi; Elizabeth Cook; Christopher J. Duffin; Peter A. Austen; Steven C. Sweetman; Pamela G. Gill; Claudia Hildebrandt; Tim Tomkinson; Michael J. Benton (Proceedings of the Geologists' Association, 2026)

Hydrodynamics and short-term morphodynamics of hybrid terrace configuration in a tidally restored impoundment subject to relative sea-level rise - L. Casey Jones; Peter Bacopoulos; Linoj Vijayan; Christopher E. Kees (Ecological Engineering, 2026)

Synergistic Effects of Acetic Acid and Ethanol on Offspring Production and Gallery Expansion by Fungus-Farming Ambrosia Beetles - Christopher M. Ranger; Julie A. Baniszewski; Nisha Patwa; Hsin-Ho Wei; Sudhan Pachhain; Jessi A. Raubenolt; Madeline Altland; Juan Carlos Cambronero-Heinrichs; Vipaporn Phuntumart; Michael E. Reding; Davide Rassati; Ian W. Keesey; et al. (Journal of Chemical Ecology, 2026)
Wood-boring ambrosia beetles and their offspring obligately depend on cultivated fungi that they maintain within host trees. Stressed trees produce at least two potent antimicrobials, ethanol and acetic acid, which typically suppress the growth of most fungi. Ethanol facilitates the growth of ambrosia beetles’ fungal mutualists and thus aids in host colonization; however, acetic acid’s effects are unknown. Here, we evaluated the effects of acetic acid on tunneling and offspring production by two exotic ambrosia beetle species, Xylosandrus germanus and Anisandrus maiche . Cut wood stems (i.e., bolts) were infused with water alone, 5% ethanol, or mixtures of 5% ethanol with acetic acid at various dilutions. Infestations by X. germanus and A. maiche resulted in more frass, larvae, pupae, and adults in the combined 5% ethanol-acetic acid treatment, than in the 5% ethanol alone or water control treatments. X-ray micro-computed tomography revealed that bolts infused with this 5% ethanol-acetic acid mixture had larger insect gallery volumes than those with only 5% ethanol, which in turn were larger than the water control. A positive relationship was found between frass ejected by each beetle and gallery volume across all experiments. This study demonstrates that acetic acid and ethanol synergistically increase offspring production while facilitating gallery expansion by the larvae. Understanding how ambrosia beetles utilize stress-induced compounds within host trees to benefit their fungiculture could lead to novel management strategies for these invasive insects.

Brightness, colour, polarisation: a multi-instrument observation campaign of the Gorizont-6 satellite - Robert J.S. Airey; Paul Chote; Klaas Wiersema; Ioannis Apergis; James McCormac; James A. Blake; Benjamin F. Cooke; Isobel S. Lockley; Peter J. Wheatley; Daniel Bayliss; Samuel Gill; Christopher A. Watson; et al. (Advances in Space Research, 2026)

Goals and trends in space exploration: An overview of the panel on exploration sessions at the committee on space research general assembly 2024 - André Galli; Heather Smith; Michel Blanc; Bernard Foing; Hélène Boithias; Scott J. Bolton; Soyoung Chung; Athena Coustenis; Eric Dautriat; Jean-Pierre de Vera; Peter Doran; François Dubrulle; et al. (Life Sciences in Space Research, 2026)

Corrigendum to “Historical range of wildfire regime in black pine forests outside actual target of public policies” [J. Environ. Manag. 394 (2025) 127671] - Justin Badeau; Peter Z. Fulé; Frédéric Guibal; Serena Felix; Amandine Burguet-Moretti; Pasquale Moneglia; Christopher Carcaillet (Journal of Environmental Management, 2026)

Are there enough native tree seed sources to meet forest restoration targets? A spatially explicit assessment in tropical Asia - Riina Jalonen; Tobias Fremout; Rekha R. Warrier; Vivi Yuskianti; Enrique Tolentino; Cristino Tiburan; Md. Zahidur Rahman Miah; Md. Tauhidor Rahaman; Peter Wilkie; Dede J. Sudrajat; Denny; Christopher J. Kettle (Biological Conservation, 2026)

Population Genomics of a Cosmopolitan Weed Provides Insights Into Its Local Adaptation and Recent Demographic History - Marilia Souza Lucas; Christoph Rosche; Isabell Hensen; Stefan G. Michalski; Dávid U. Nagy; Diana Gamba; Renske E. Onstein; Karime Abidkulova; Mohammad Al‐Gharaibeh; Ali A. Al‐Namazi; Sirwan Babaei; Fernando Bastida; et al. (Molecular Ecology, 2026)
Invasive plant species present a growing ecological and economic challenge, and often adapt rapidly to their novel environments through complex demographic and evolutionary processes. Invasion genomics offers powerful tools to disentangle these processes, but most studies rely on geographically narrow sampling across native and non‐native ranges. Erigeron canadensis is a cosmopolitan weed native to North America that has successfully invaded diverse climates worldwide. We used double‐digest restriction site‐associated DNA sequencing (ddRADseq) to investigate the genetic diversity and structure of 280 E. canadensis populations across the Northern Hemisphere. We found that native and non‐native populations maintained comparable genetic diversity. Population structure analyses revealed four genetic clusters that were mainly differentiated along latitudinal and aridity gradients. However, one cluster was strongly overrepresented in the non‐native compared to the native range. In the native range, genetic differentiation was shaped by spatial and environmental gradients, while in non‐native regions human‐mediated dispersal and repeated introductions disrupted environmentally driven genetic structure. Migration network analyses revealed limited intercontinental connectivity and a possible role of long‐distance dispersal in within‐range expansions. Genomic offset analyses showed that genotype‐environment mismatches in non‐native populations associated with reduced growth and reproduction. Together, our results indicate that the invasion dynamics of E. canadensis were driven by multiple introductions, population admixture, and lineage sorting, while some genotypes contributed disproportionately to the spread of this invader. The presence of apparent maladaptation suggests that even long‐established invaders may still be evolving in response to their novel environment, raising concerns about potential future expansions.

Prediction of cognitive test scores: a comparison of brain structure, health, demographic, and cognitive data across adulthood - Camilla Mendl-Heinisch; Nora Bittner; Tatiana Miller; Paulo Dellani; Fabian Bamberg; Klaus Berger; Patricia Bohmann; Josua A. Decker; Agnes Flöel; Karin Halina Greiser; Manuela Harries; Jan Kapar; et al. (GeroScience, 2026)
Cognitive performance prediction may help identify early cognitive decline. However, the heterogeneity of research findings impedes the identification of key predictors. This study used 21,877 participants (25–74 years) from the German National Cohort (NAKO Gesundheitsstudie, NAKO) to systematically predict cognitive test scores based on brain structure, demographic, health-related, and cognitive data. Importantly, validation analyses were performed across study sites and external samples (1000BRAINS). Higher predictability was observed in the total sample compared to age-specific subgroups (10% difference in explained variance). Demographic (e.g. age) and cognitive data (e.g. memory) outperformed brain structure (e.g. grey matter volume) and health-related data (e.g. hypertension). Cognitive tests were differentially predictable, most evident between episodic memory and motor speed (R 2 ≤ 0.32 versus R 2 ≤ 0.18). Differences in predictability between age groups finally highlight the importance of comparing prediction outcomes between adult lifespan and age-specific groups to elucidate general and age-sensitive predictors of cognitive test scores.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Cerebellar Time and Relative Time: A Comparator-Based Dynamical Timing Model and its Relevance to Psychopathology and Therapies - Andras Hajnal; Kate Levenberg; Peter Adam; Christopher H. Chen (The Cerebellum, 2026)
Time perception is fundamental to adaptive behavior, providing the scaffold for prediction, coordination, and learning. The cerebellum has long been recognized as a core hub for interval timing, yet its role extends beyond motor control to perceptual chronometry, reinforcement learning, and affective regulation. Here we introduce a novel framework, a Comparator-Based Dynamical Timing (CDT) model which describes distortions of subjective time as transformations that yield compression, dilation, and changes in temporal precision. In this account, subjective time is scaled by a gain factor κ. When κ > 1, subjective time dilates; when κ < 1, subjective time compresses. We synthesize convergent evidence from cerebellar anatomy, physiology, and computational modeling, and show how time distortions in psychiatric, neurodegenerative and neurodevelopmental disorders can be interpreted in the context of altered cerebellar temporal processing. We argue that cerebellar circuits operate in concert with cortical and basal ganglia oscillators in a comparator role, minimizing temporal deviation and maximizing precision. We propose that dysfunction across these interconnected networks contributes to distortions in subjective time perception observed in schizophrenia, bipolar disorder, depression, anxiety, post-traumatic stress disorder, autism spectrum disorder), and motor and movement disorders including Parkinson’s Disease. This framework provides a quantitative tool to predict and monitor the progression of psychiatric and neurodevelopmental/neurodegenerative disorders characterized by disrupted timing networks. Beyond diagnostic utility proposing an EEG-informed approach to track deviations in time perception, it also offers a translational platform for testing novel interventions, including non-invasive neuromodulation such as transcranial magnetic stimulation.

The nitrogen isotopic composition of biotic components in Northern Biscayne Bay and Associated Waterways, South Florida USA: implications for sources of nitrogen - Peter K. Swart; Amel Saied; Sean P. Ahearn; Tiffany Troxler; Maribeth Gidley; Christopher Sinigalliano; Aliza Karim; Elizabeth Kelly; Rachel Silverstein (Environmental Science and Pollution Research, 2026)
Over an approximate twelve-month period, between June 2021 and June 2022, the δ 15 N values of aquatic vegetation and sediments and the δ 18 O and δ 15 N values of the NO 3 − in water samples were analyzed in order to understand the sources and processes affecting nitrogen entering the northern portion of Biscayne Bay, an urban area located to the west of Miami, in the southern United States. Samples were collected from 22 sites, primarily located in waterways feeding into the Bay (Miami River, Little River, Biscayne Canal, and Snake Creek). Additional samples were also collected in the central region of Biscayne Bay, around Virginia Key, Key Biscayne, Coconut Grove, and Matheson Hammock. The highest δ 15 N values were found in algae and plants collected from the Biscayne Canal, Little River, and Miami River, inland sites heavily influenced by land-based source of pollution such as storm water, septic tanks, and industrial runoff, while lower values were measured at the central Biscayne Bay sites. The Little River sites showed a strong seasonality with δ 15 N values of the vegetation ranging from + 8‰ in the wet season to over + 13‰ at the start of the dry season, while the Miami River and Biscayne Canal sites exhibited δ 15 N values of between + 9 to + 13‰ throughout the year. The elevated δ 15 N values are associated with the input of anthropogenic waste, presumed to originate from septic tanks along the canals. Elevation of δ 15 N values in excess of typical values found in humans is driven by fractionation of nitrogen during assimilation, nitrification, denitrification, volatilization of NH 4 + and anaerobic ammonium oxidation in septic tanks with clogged drain fields. We propose that dissolved inorganic nitrogen, derived from septic tanks with elevated δ 15 N values, mixes with nitrogen derived from the natural environment as well as that sourced from artificial fertilizers (both with lower δ 15 N values) to produce pools of nitrogen with intermediate δ 15 N values. These are then further enriched in 15 N during the process of assimilation and nitrification which fractionates the δ 15 N value of the residual NO 3 − . At all locations there is close to a 1:1 relationship between the δ 15 N and δ 18 Ο values of the nitrate, expected as a result of fractionation during assimilation. Mixing between natural sources of nitrogen, or nitrogen arising from anthropogenic sources or other animal waste and nitrogen arising from contamination by fertilizer produces a positive association between NO 3 − concentration and δ 15 N NO3- values at some locations.

Microbial dispersal from a hyperactive sandsheet in the Icelandic Highland - Nathan Hadland; Christopher W. Hamilton; Peter Schroedl; Federica Calabrese; Jeffery Marlow; Solange Duhamel (Science of The Total Environment, 2026)

Understanding the resource potential of natural hydrogen on Earth: Scientific gaps, uncertainties and recommendations - Giuseppe Etiope; Geoffrey S. Ellis; Omid H. Ardakani; Christopher J. Boreham; Peter Klitzke; Antonio Martín-Monge; Humberto L.S. Reis; Alexis S. Templeton; Hyeong Soo Kim; Eric Gaucher; Olivier Sissmann (Earth-Science Reviews, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Transportation noise and self-rated health: Evidence from the German national cohort (NAKO) - S. Claire Slesinski; Gabriele Bolte; Sida Zhuang; Tobia Lakes; Eva Rehfuess; Jeroen Staab; Fabian Bamberg; Hansjörg Baurecht; Heiko Becher; Hermann Brenner; Nadine Glaser; Karin Halina Greiser; et al. (Environmental Research, 2026)

Integrating drone and deep learning technology to monitor floodplain changes in response to environmental flows - William Higgisson; Rui Liu; Alica Tschierschke; Adrian Cobb; Christopher S. Jones; Lyndsey Vivian; Peter Bridgewater (Hydrobiologia, 2026)

Social status as a developmental process in wild vervet monkeys: beyond maternal inheritance - Chloé Vilette; Christina M. Nord; Tyler R. Bonnell; Marcus J. Dostie; Richard McFarland; Christopher Young; S. Peter Henzi; Louise Barrett (Behavioral Ecology and Sociobiology, 2026)

Widespread Shrubification on European Mountain Summits - Thomas Vanneste; Harald Pauli; Stefan Dullinger; Bente J. Graae; Otar Abdaladze; José Luis Benito Alonso; Christopher Andrews; Peter Barančok; Manfred Bardy‐Durchhalter; Haben Blondeel; Pau Carnicero; Emmanuel Corcket; et al. (Global Change Biology, 2026)
Shrubs are expanding across the cold ecosystems of our planet with potentially profound consequences for their biodiversity and functioning. However, evidence is still strongly biased towards the Arctic tundra, while a large‐scale assessment of shrub expansion in alpine areas above the elevational treeline is missing so far. Here we quantified shrub cover changes over the past two decades in 576 permanent plots of 1 m 2 spread across the alpine vegetation belt of Europe's major mountain chains. Total shrub cover clearly increased in the plots with an average rate of about 2.6% per m 2 per decade (95% CI = 1.9%–3.4%), and this expansion was more pronounced for evergreen (2.0% per m 2 per decade, CI = 1.3%–2.7%) than for deciduous species (1.7% per m 2 per decade, CI = 0.9%–2.4%). The magnitude of individual species' cover shifts was positively associated with their plant height, but negatively with their leaf nitrogen content and light affinity. In sum, we show that shrub expansion is a widespread phenomenon also in the alpine zone of European mountains, with potentially far‐reaching consequences for alpine plant dynamics, soil microclimates, snow patterns, carbon cycling, food chains and livelihoods.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Effect of water pressure on bitumen and expelled oil biomarker evolution: Insights from laboratory simulation experiments - Ahmed Khairy; Clement N. Uguna; Waleed Sh. El Diasty; Kenneth E. Peters; Christopher H. Vane; Colin E. Snape; Sherif Farouk; Will Meredith (Organic Geochemistry, 2026)

Caribbean octocoral communities: finding the forest for the trees? - Howard R. Lasker; Lorenzo Bramanti; Peter J. Edmunds; John F. Girard; Nolwenn Pages; Kaitlyn J. Tonra; Christopher D. Wells; Katell Guizien (Coral Reefs, 2026)
Octocorals have increased in abundance on many Caribbean coral reefs, and at some sites, “octocoral forest” may be a better community descriptor than “coral reef.” Implicit to the concept of a forest is that structural elements, i.e., trees, colonies, etc., alter the environment in ways that affect the structural elements themselves and the organisms that inhabit the forest. At what density do the structural elements create the emergent properties of a “forest?” Communities traditionally characterized as hardgrounds and coral reefs around Puerto Rico and St John, US Virgin Islands, varied in density of octocoral colonies from a few to > 100 colonies m −2 in surveys conducted in 2021 and 2022. Canopy cover was correlated with the density of colonies, but among the quadrats with the highest octocoral densities, there was no significant correlation between numbers of colonies and canopy cover. Frontal area, a measure related to the community’s effect on water flow, as well as the volume occupied by colonies followed patterns similar to canopy cover. Vertical profiles of flow velocity were measured from the substratum to 2.3 m above the bottom on a reef on St John where octocoral population density ranged from 0 to 16 colonies m −2 . Profiles of orbital velocity exhibited perturbations which were more pronounced in locations with > 10 colonies m −2 . Using the effect on flow as a criterion, four of the eight surveyed sites would function as octocoral forests. Understanding the density of organisms at which emergent properties appear is essential to understanding the bio-physical interactions affecting the community. Developing explicit definitions of animal forests such as octocoral forests and coral reefs is critical to following the trajectories of these ecosystems in a world of changing climate.

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Asymmetries challenging global biodiversity sciences - Leandro O. Salles; Hussam Zaher; Marcos Tavares; Mario C. C. de Pinna; Rosane G. Collevatti; Krister T. Smith; Diego Pol; Hongyu Yi; Nancy B. Simmons; Christopher J. Tribe; Joaquin Arroyo-Cabrales; Nour-Eddine Jalil; et al. (Systematics and Biodiversity, 2026)

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Minimizing use of nonhuman primates to inform risk to fertility and of adverse pregnancy outcomes with pharmaceuticals - Christopher J. Bowman; Ann Baker; Diann L. Blanset; Kimberly C. Brannen; Gary J. Chellman; Brian Enright; Wendy Halpern; Bethany R. Hannas; Kazushige Maki; Fumito Mikashima; Shermaine Mitchell-Ryan; Eve Mylchreest; et al. (Regulatory Toxicology and Pharmacology, 2026)

Retrospective evaluation of the use of non-human primates for fertility assessment of pharmaceuticals submitted for marketing approval in the EU - Puck Roos; Diann L. Blanset; Peter JK. van Meer; Shermaine Mitchell-Ryan; Peter T. Theunissen; Katie J. Turner; Ronald L. Wange; Christopher J. Bowman (Regulatory Toxicology and Pharmacology, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Waterfowl Move Less in Heterogeneous and Human‐Populated Landscapes, With Implications for Spread of Avian Influenza Viruses - Claire S. Teitelbaum; Diann J. Prosser; Joshua T. Ackerman; Sakib Ahmed; A. B. M. Sarowar Alam; Kazi Zenifar Azmiri; Nyambaya Batbayar; Joël Bêty; Abigail Blake‐Bradshaw; Dmitrijs Boiko; Nelleke H. Buitendijk; Jeffrey J. Buler; et al. (Ecology Letters, 2026)
Animal movements contribute to the spread of infectious diseases and are driven in part by environmental conditions. We investigated the links among the environment, animal movement, and infectious disease dynamics in waterfowl, which are among the primary wildlife hosts of avian influenza viruses. By combining telemetry data on 4606 individuals from 26 waterfowl species with data on land cover, weather, and vegetation, we found that waterfowl moved less in areas of higher land cover heterogeneity and higher human population density. Moreover, predicted waterfowl movement distances were weakly but positively correlated with distances between detections of H5N1 highly pathogenic avian influenza in wild waterfowl, suggesting that environmental conditions might contribute to the spread of this disease via their effects on bird movements. By considering wildlife movements alongside other drivers of infectious disease dynamics, such as livestock production and human mobility, we move closer to predicting outbreaks and informing interventions.

Project Psyche: reference genomes for all Lepidoptera in Europe - Charlotte J. Wright; Niklas Wahlberg; Roger Vila; Marko Mutanen; Pável Matos-Maraví; Kay Lucek; Irena Kleckova; Leonardo Dapporto; Vlad Dincă; Claudia Bruschini; Christopher W. Wheat; Marta Vila; et al. (Trends in Ecology & Evolution, 2025)

Challenges and opportunities integrating remote sensing for mangrove conservation in Papua New Guinea's complex natural and human landscapes - Midhun Mohan; Ewane Basil Ewane; Lara G. Moussa; Michael S. Watt; Peter I. Macreadie; Christopher J. Owers; Daria Agnieszka Karpowicz; Ian Reuben; Willie Doaemo (Regional Studies in Marine Science, 2025)

Bioenergy pathways within United States net-zero CO2 emissions scenarios in the Energy Modeling Forum 37 study - Ronald D. Sands; Liz Wachs; Patrick Lamers; Olivier Bahn; Robert H. Beach; Matthew Binsted; Geoffrey Blanford; Yongxia Cai; Francisco De La Chesnaye; James A. Edmonds; Leonard Göke; Chioke Harris; et al. (Energy and Climate Change, 2025)

Taken with a grain of salt: Resolving evaporite stratigraphy through accessory mineral geochronology - Jiankang Yi; Christopher L. Kirkland; Julien Bourdet; Milo Barham; Martin Danišík; Andrew Feitz; Peter W. Haines; Brad McDonald; Bruno V. Ribeiro; Emanuelle Frery; Claudio Delle Piane (Earth and Planetary Science Letters, 2025)

A versatile and efficient method to quantify purity and degree of substitution in alginate derivatives - Mabel Barreiro Carpio; Peter M. Thompson; Christopher Moody; Joshua G. Pierce; Yevgeny Brudno (Carbohydrate Polymers, 2025)

How Do Patient Outcomes in Mechanical Thrombectomy for Large-Core Stroke Vary Based on Neuroimaging Modalities Used for Patient Selection? A Multicenter Multinational Study - Omar Alwakaa; Rahim Abo Kasem; Felipe Ramirez-Velandia; Aryan Wadhwa; Kimberly Han; Michael R. Levitt; Ali Alaraj; Pascal Jabbour; Joon-Tae Kim; Brian Howard; Ali Alawieh; Stacey Quintero Wolfe; et al. (Translational Stroke Research, 2025)

Extracorporeal photopheresis induces the release of anti-inflammatory fatty acids and oxylipins and suppresses pro-inflammatory sphingosine-1-phosphate - Gerhard Hagn; Ara Cho; Nina Zila; Barbara Sterniczky; Christian Jantschitsch; Dexin Dong; Andrea Bileck; Mariia Koren; Philipp Paulitschke; Thomas Mohr; Robert Knobler; Wolfgang Peter Weninger; et al. (Inflammation Research, 2025)
Aims Extracorporeal photopheresis (ECP) is a UVA-based phototherapy of whole blood and well established as a first line or combination therapy for the treatment of cutaneous T-cell lymphoma, systemic sclerosis, graft-versus-host disease and is used to control organ transplant rejection. While the proapoptotic activity on activated T-cells is evident, the clinical efficacy of this treatment also appears to be based on other yet unknown mechanisms. In this study, we aimed to identify novel mechanisms of ECP regardless of the patient’s background situation. Main methods To better understand the immediate consequences of ECP, we analyzed blood plasma of patients with different ECP indications immediately before and after treatment with regard to proteins and lipid mediators. Key findings While proteome profiling identified substantial inter-individual differences in the protein composition, no significant alteration was detectable upon treatment. In contrast, several fatty acids and lipid mediators were found to be significantly altered by ECP. Remarkably, upregulated lipid mediators including polyunsaturated fatty acids, 12-HEPE and 13-OxoODE have been described to be anti-inflammatory, while the downregulated molecules sphingosine-1-phosphate (S1P) and stearic acid are potent pro-inflammatory mediators. A selective sphingosine-1-phosphate-1 receptor (S1P1) modulator AUY954, which decreases S1P1 and experimentally reduces transplant rejection in vivo, showed greater anti-proliferative activity in human lung fibroblasts from COPD patients compared to normal lung fibroblasts, confirming that this pathway may be important in ECP and its mode of action. Significance and outlook In conclusion, we suggest that the ECP-induced changes in lipid mediators may contribute to the remarkable anti-inflammatory effects of the treatment. Depending on their lipid status, patients may benefit from novel treatment regimens combining ECP with lipid modulators. This could be used for the prevention of transplant organ rejection, the treatment of acute or chronic GvHD or transplant organ rejection and the long-term treatment of various skin diseases. This study uncovers novel mechanisms of ECP, that can be used to establish clinically relevant lipid profiles of patients to support patient stratification, predictive or prognostic purposes and thus personalized medical care in the framework of PPPM practice. A combination with S1P modulators may therefore have beneficial effects.

Impact of environmental gradients on juvenile coral demography across the Great Barrier Reef and Torres Strait - Christopher Doropoulos; Mariana Alvarez-Noriega; Katharina Fabricius; Renata Ferrari; Peter J. Mumby; Sam H. C. Noonan; Melanie Orr; Kinam Salee (Coral Reefs, 2025)
Demographic rates of juvenile corals are critical to reef recovery, yet their variation across environmental gradients remains understudied. Over three years, we assessed juvenile coral vital rates across the Great Barrier Reef (GBR) and Torres Strait (TS), spanning 14° latitude and diverse inshore to offshore environments. Environmental conditions varied, with annual temperatures ranging 24–28 °C, high turbidity in the southern inshore GBR, and elevated chlorophyll a in the southern offshore GBR. Despite these differences, juvenile assemblages of five common coral groups ( Montipora , Acropora , Pocilloporidae, Merulinidae, and Porites ) were broadly similar. Recruitment patterns varied with Acropora highest in southern offshore and central reefs, and Porites in southern offshore and northern reefs. Annual mortality rates were consistent across locations, but taxa-specific negative responses to turf height and sedimentation were observed. Net juvenile density increased by 3 m⁻ 2 yr⁻ 1 , with higher gains for Acropora in southern offshore reefs (3.8 m⁻ 2 yr⁻ 1 ) and Porites in northern offshore reefs (3.5 m⁻ 2 yr⁻ 1 ). Individual survival improved with size, and temperature effects were taxon-dependent—negative for Acropora , neutral for Montipora and Pocilloporidae, and positive for Merulinidae and Porites . Temperature did not correlate with linear growth in any group, but water flow positively influenced growth in most taxa. Fast-growing Acropora and Pocilloporidae showed positive size–growth relationships, unlike slower-growing Merulinidae and Porites . These findings provide baseline demographic data across the GBR and TS, revealing both congruence and divergence with ecological theory. They offer essential input for predictive models, site-specific restoration planning, and evaluating interventions relative to natural background dynamics.

Near‐seabed sediment dynamics and fluxes on Chatham Rise, the effects of seabed disturbance, and implications for deep‐sea bottom trawling and seabed mining - Scott D. Nodder; Christopher A. Eager; Joe O’Callaghan; Daniel Leduc; Sam Davidson; Stacy Deppeler; Grace Frontin‐Rollet; Peter Gerring; Sarah Searson; William Quinn; Steve George; Ron Ovenden; et al. (New Zealand Journal of Marine and Freshwater Research, 2025)
Anthropogenic impacts are increasingly affecting deep‐sea environments, including seafloor sediment disturbances by bottom trawling and seafloor mining. Fieldwork in the ‘Resilience Of Benthic Ecosystems to Sedimentation’ (ROBES) project were conducted in 2018–2020 on the 400 m‐deep Chatham Rise crest, eastern Aotearoa New Zealand. Water column turbidity data, sediment traps on near‐seabed moorings and benthic landers and surficial sediments from multi‐corers provided baseline and post‐impact information following an artificially induced seafloor disturbance event in June 2019 using a modified harrow plough in and around an elongated bathymetric depression, designated as the ‘Butterknife’. During the disturbance, total mass and particulate organic carbon (POC) near‐bed fluxes were elevated above long‐term fluxes (2018–20). Long‐term 2018–19 fluxes were generally less than in 2019–20, driven by interannual oceanographic variations. These results, coupled with 50–100 m‐thick benthic boundary layers, suggest that lateral advection is a dominant process in the resuspension and redistribution of seafloor sediments on the rise. Further research is required to better understand the longer term dynamics of particle transport and deposition in response to human activities, such as bottom trawling or proposed phosphorite seafloor mining, especially in bathyal environments, such as the Chatham Rise.

Spatial and Temporal Variation in Wave Overtopping Across a Coastal Structure Based on One Year of Field Observations - Jennifer Brown; Gerd Masselink; Margaret Yelland; Christopher Stokes; Timothy Poate; Robin Pascal; David Jones; John Walk; Christopher Cardwell; Barry Martin; Peter Ganderton; Julie Gregory; et al. (Journal of Marine Science and Engineering, 2025)
Coastal managers worldwide must prepare for changes in annual wave overtopping events due to climate change and sea-level rise. Research often assesses overtopping discharges by extreme events at a sea wall crest, typically using data from physical models or empirical rules based on scaled experiments. Here, we analyse a unique 1-year field dataset of coastal wave overtopping, from SW England, to determine the number of individual waves, regardless of their size, overtopping two locations across a coastal structure. The coastal conditions causing the most frequent overtopping differ from those driving it landward, complicating hazard communications for multiuse infrastructure. These data are the first field observations covering a year of tide, wave and wind conditions that cause overtopping of a vertical sea wall. Storms have a minimal (

Historical range of wildfire regime in black pine forests outside actual target of public policies - Justin Badeau; Peter Z. Fulé; Frédéric Guibal; Serena Felix; Amandine Burguet-Moretti; Pasquale Moneglia; Christopher Carcaillet (Journal of Environmental Management, 2025)

The Wetland Explorer: A digital tool for improved community engagement with water quality modelling for decision-making - Catharina Landström; Helge Peters; Andrew G. Hughes; Christopher R. Jackson; Andrew A. McKenzie; Liam Spencer; Rebecca Turnpenney; John Bryden (Environmental Science & Policy, 2025)

Challenges and Strategic Recommendations for Enhancing Quantification and Projection of Forest Carbon Dynamics - Holly L. Munro; Christopher W. Woodall; William R. L. Anderegg; Jeff W. Atkins; Colin M. Beier; Bronson P. Bullock; Kendall DeLyser; David D. Diaz; Bianca N.I. Eskelson; Margaret E. K. Evans; John D. Foppert; Bryan C. Foster; et al. (Journal of Forestry, 2025)

Serum Biomarkers in Atlantic Salmon for Differential Diagnosis of Cardiomyopathy Syndrome and Pancreas Disease: Proteomic Identification of Serum Fibrinogen to Enhance Troponin Immunoassay as Optimal Diagnostic Approach - Francesca Riva; Lauren Elaine Black; Kim D. Thompson; Philippe Sourd; Andrei Bordeianu; Christopher C. Chadwick; Hooman Moghadam; Jorge Del‐Pozo; Janina Costa; Richard Burchmore; Nicola Brady; Lewis Moore; et al. (Journal of Fish Diseases, 2025)
Cardiac viral diseases are among the major causes of economic losses in Atlantic salmon ( Salmo salar L.) aquaculture. These include cardiomyopathy syndrome (CMS) caused by piscine myocarditis virus (PMCV) and pancreas disease (PD) caused by Atlantic salmonid alphavirus (SAV). The resulting cardiomyopathies impact fish stock in terms of mortality, quality, growth performance and economic loss. Diagnosis of these diseases is currently based on clinical signs, histopathology and RT‐qPCR. To identify putative biomarkers for use in the health assessment of Atlantic salmon, a quantitative proteomics investigation was undertaken with the aim of differentiating fish with CMS from healthy fish and fish with PD. Serum samples ( n = 9/group) were collected during health assessment from pens where clinical CMS or PD were present and compared to serum from healthy Atlantic salmon. There were 34 differentially abundant proteins (DAPs) in CMS compared to healthy, 66 comparing CMS to PD, and 81 comparing PD to healthy. In relation to healthy samples, most DAPs were shared between CMS and PD, with higher relative abundances observed in PD. An exception to this was serum fibrinogen, which was identified as a putative biomarker for CMS, whereas differentiation of Atlantic salmon with CMS from those with PD was enhanced by the calculation of the ratio of fibrinogen to skeletal troponin C.

The Fraction of Carbon in Soil Organic Matter as a National‐Scale Soil Process Indicator - Sabine Reinsch; Inma Lebron; Lis Wollesen de Jonge; Peter L. Weber; Trine Norgaard; Emmanuel Arthur; Lucas Gomes; Charles Pesch; Karyotis Konstantinos; George Zalidis; Lur Epelde; Marija Romic; et al. (Global Change Biology, 2025)
Soil organic matter (SOM) is an important component of ecosystem carbon stocks. Generally, SOM found in mineral and organo‐mineral soils can be categorised into two fractions: particulate organic matter (POM) and mineral‐associated‐organic matter (MAOM), both of which contain soil organic carbon (SOC). Understanding the relationship between SOC and SOM fractions provides insight into SOM decomposition and SOC storage potential. Here we show an intriguingly tight relationship between the fraction of SOC in SOM (denoted as ), habitat and soil physical properties, as well as SOC stored in POM and MAOM. This opens up new ways to predict spatial variations in the distribution of POC and MAOC using more widely available data as a covariate. By compiling 14 datasets and 9503 measurements from across Europe and globally we analysed across mineral and organic soils, which fell between 0.38 and 0.58, consistent with variation in carbon of major plant components. followed a habitat gradient with lowest median values in Seagrass sediments (0.36 ± 0.09) and Permafrost habitats, followed by croplands (0.47 ± 0.08) and a maximum in semi‐natural habitats (e.g., neutral, acid and calcareous grasslands) (0.56 ± 0.07), with differences between broadleaved (0.50 ± 0.087) and coniferous woodlands (0.53 ± 0.07) which were driven by overall organic matter content. The data show a tight link between vegetation carbon and the contents of SOC and SOM across various habitats, which could be used to inform agricultural soil management, improved land‐use planning (e.g., woodlands), and tracking climate‐related SOC targets.

Zonal endothelial cell heterogeneity underlies murine renal vascular development - Peter M. Luo; Neha H. Ahuja; Christopher Chaney; Danielle Pi; Aleksandra Cwiek; Zaneta Markowska; Chitkale Hiremath; Denise K. Marciano; Karen K. Hirschi; M. Luisa Iruela-Arispe; Thomas J. Carroll; Ondine Cleaver (Angiogenesis, 2025)

Effects of shading aquaculture pools on coral larvae health and production - Christina Langley; Christopher Doropoulos; Dexter dela Cruz; Peter L. Harrison (Aquaculture, 2025)

Techno-economic assessment of ear-hanging and lantern net grow-out techniques in Atlantic Sea scallop, Placopecten magellanicus, aquaculture in the Gulf of Maine - Christopher Noren; Struan Coleman; Christian Brayden; Andrew Chingos; Dana Morse; Andrew Peters; Damian C. Brady (Aquaculture, 2025)

Informal artisanal and small-scale mining in sub-saharan Africa: Policy evolution, sector formalization, and future trajectories - Peter Donkor; Ebenezer Kwadwo Siabi; Samuel Kofi Mensah; Kwasi Frimpong; Christopher Vuu; Emmanuel Kwesi Nyantakyi; Elikplim Sarah Siabi; Albright Boachie- Ameyaw (Resources Policy, 2025)

New approach methodologies for assessing developmental toxicity of pharmaceuticals: Case examples and future directions - Nicola Powles-Glover; Allen R. Kaczor; Steven Van Cruchten; Christopher J. Bowman; Kimberly C. Brannen; Claudia Demarta-Gatsi; Isabelle LeConte; Amer Jamalpoor; Fumito Mikashima; Shermaine Mitchell-Ryan; Dinesh Stanislaus; Peter Theunissen; et al. (Reproductive Toxicology, 2025)

Capability of commercial cleaning procedures to remove food allergens from differing food contact materials and containers using sesame as a target analyte - Christopher A. James; Helen E. Arrowsmith; Marie-Anne L. Clarke; Simon Welham; Peter Rose (Journal of Food Engineering, 2025)

The potential impact of forest loss on drinking water treatment costs in the southeastern U.S. - Arpita Nehra; Justin S. Baker; Peter V. Caldwell; Katherine L. Martin; Travis W. Warziniack; Richard H. Manner; Christopher M. Mihiar; Gregory E. Frey; Jennifer K. Costanza (Forest Policy and Economics, 2025)

Untangling parasite epidemiology of mountain gorillas through historical samples: Strongylid nematodes are friends or foe? - Bethan Mason; Vladislav Ilík; Barbora Červená; Michael Cranfield; Julius Nziza; Benard Ssebide; Kirsten Gilardi; Carine Uwamahoro; Winnie Eckardt; Felix Ndagijimana; Richard Muvunyi; Prosper Uwingeli; et al. (Biological Conservation, 2025)

A urine patch model for evaluating management strategies for reducing nitrogen leaching from pasture-based dairy farms - Christopher Adams; Jacobus Kok; Peter Amer; Pierre C. Beukes (Nutrient Cycling in Agroecosystems, 2025)
Animal urine and urine patch characteristics are important drivers of nitrogen leaching in pasture-based dairy systems and their manipulation offers opportunities to mitigate these losses. We developed a model, based on previous work, to investigate the effect of applying tactical management strategies to reduce nitrogen leaching from urination events during different times of the year. Our model predicted that reducing pasture height or decreasing the volume per urination event to increase the spread of urine in the critical summer and autumn months (January to May) had minimal effect on nitrogen leaching at paddock scale. In contrast, diluting the nitrogen concentration of urine by decreasing dietary nitrogen intake by 30% or increasing total daily urination volume by 40% (while keeping daily nitrogen excreted constant) during these critical months reduced nitrogen leaching by 28% and 13%, respectively. When these dilution strategies were applied for the whole milking season (August to May) reductions of 40% and 22% were achieved. This demonstrates that management strategies can be applied tactically during key times of the year and still achieve considerable nitrogen leaching reductions. This is important for dairy producers who can add substantial reductions to nitrogen leaching from their farm systems, while reducing the management effort and costs by focussing on one key urine characteristic, nitrogen concentration, and only during a limited time of the farm season.

Publisher Correction to: Quantifying intra-urban socio-economic and environmental vulnerability to extreme heat events in Johannesburg, South Africa - Craig Parker; Craig Mahlasi; Tamara Govindasamy; Lebohang Radebe; Nicholas Brian Brink; Christopher Jack; Madina Doumbia; Etienne Kouakou; Matthew Chersich; Guéladio Cissé; Sibusisiwe Makhanya; Aakin Bobola; et al. (International Journal of Biometeorology, 2025)

Quantifying intra-urban socio-economic and environmental vulnerability to extreme heat events in Johannesburg, South Africa - Craig Parker; Craig Mahlasi; Tamara Govindasamy; Lebohang Radebe; Nicholas Brian Brink; Christopher Jack; Madina Doumbia; Etienne Kouakou; Matthew Chersich; Guéladio Cissé; Sibusisiwe Makhanya; Aakin Bobola; et al. (International Journal of Biometeorology, 2025)
Urban populations face increasing vulnerability to extreme heat events, particularly in rapidly urbanising Global South cities where environmental exposure intersects with socioeconomic inequality and limited healthcare access. This study quantifies heat vulnerability across Johannesburg, South Africa, by integrating high-resolution environmental data with socio-economic and health metrics across 135 urban wards. We examine how historical urban development patterns influence contemporary vulnerability distributions using principal component analysis and spatial statistics. Environmental indicators (Land Surface Temperature (LST), vegetation indices, and thermal field variance) were combined with socioeconomic and health variables (including indicators on crowded dwellings and healthcare access, self-reporting of chronic diseases) in a comprehensive vulnerability assessment. Principal Component Analysis revealed three primary dimensions explaining 56.6% (95% CI: 52.4–60.8%) of the total variance: urban heat exposure (31.5%), health status (12.8%), and socio-economic conditions (12.3%). Built-up areas showed weak but significant correlations with heat indices (ρ = 0.28, p < 0.01), while higher poverty levels demonstrated moderate positive correlations with LST (ρ = 0.41, p < 0.001). The spatial analysis identified significant clustering of vulnerability (Global Moran's I = 0.42, p < 0.001), with distinct high-vulnerability clusters in historically disadvantaged areas. Alexandra Township showed the highest vulnerability(HVI score: 0.87, LST: 29.8 °C ± 0.4 °C, NDVI: 0.08 ± 0.02), with factors characterising the high vulnerability in that area including limited healthcare access and extreme heat exposure. Northern suburbs formed a significant low-vulnerability cluster (Mean HVI = 0.23 ± 0.07, p < 0.001), benefiting from greater vegetation coverage and better healthcare access. These findings demonstrate how historical planning decisions continue to shape contemporary environmental health risks, with vulnerability concentrated in areas of limited healthcare access and high extreme heat exposure. Results suggest the need for targeted interventions that address both environmental and social dimensions of heat vulnerability, particularly focusing on expanding healthcare access in identified hotspots and implementing community-scale green infrastructure in high-risk areas. This study provides an evidence-based framework for prioritising heat-resilience initiatives in rapidly urbanising Global South cities while highlighting the importance of addressing historical inequities in urban adaptation planning.

Environmental and Geographic Conditions on the Breeding Grounds Drive Bergmannian Clines in Nightjars - Aaron A. Skinner; Alicia M. Korpach; Susanne Åkesson; Marja H. Bakermans; Erin M. Bayne; Thomas J. Benson; Giovanni Boano; R. Mark Brigham; Simon S. Christiansen; Greg J. Conway; Christina M. Davy; Ruben Evens; et al. (Journal of Biogeography, 2025)
Aim To evaluate (1) whether three migratory nightjar species (Family Caprimulgidae) adhere to Bergmann's rule, (2) whether environmental factors on the breeding or wintering grounds determine body size, and (3) which mechanistic hypotheses best explain Bergmannian patterns in body size. Location North and South America; Europe and Africa. Taxon Eastern whip‐poor‐will ( Antrostomus vociferus ), Common nighthawk ( Chordeiles minor ) and European nightjar ( Caprimulgus europaeus ). Methods We used GPS tracking and morphometric data to assess competing hypotheses explaining variation in body size for each species, based on their breeding ( n = 3388) and wintering ( n = 189) locations. Results All three species exhibited Bergmannian patterns in body size, providing the first evidence that nightjars conform to Bergmann's rule despite adaptations to severe environmental conditions. Environmental and geographic variables at breeding sites were stronger predictors of body size than wintering‐site variables. Although we found partial support for Bergmann's temperature regulation hypothesis, geographic variables, rather than specific environmental factors, emerged as the strongest predictors of body size variation. Main Conclusions Latitude and longitude correlated strongly with environmental variables and migratory distance; thus, these geographical variables likely encompass many factors that influence body size in nightjars. The present study is among the first to use tracking data from individual birds to understand how environmental pressures across the annual cycle are related to body size. Our findings highlight the critical role of geographic breeding‐ground factors in shaping Bergmannian patterns, offering robust evidence to support nearly two centuries of research since Bergmann's rule was first described in 1847.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Species diversity, abundance, and biomass of fish at offshore platforms in the Arabian Gulf - Johan Mølgård Sørensen; Felipe Torquato; Lauren Faulkner; Christopher G. Lowe; Mathieu Carrara; Alexei Godina; Fahad Al-Jamali; Radhouan Ben-Hamadou; Peter Rask Møller; Pedro Range (Frontiers in Marine Science, 2025)
Documented biodiversity associated with offshore oil and gas platforms has led to growing interest in their potential conversion to artificial reefs under Rigs-to-Reefs (RTR) programmes following decommissioning. In this study, we assessed fish assemblages associated with offshore platforms in Qatar’s Al Khalij oilfield for the first time, using remotely operated vehicle (ROV) video surveys. Species diversity, abundance, and biomass were quantified across depth gradients by surveying the full water column around two platforms. A total of 4,474 fishes were recorded, representing 46 taxa, with Carangidae and Serranidae as the most diverse families, and Pinjalo pinjalo , Scomberoides commersonnianus , and Lutjanus argentimaculatus as the most abundant species. Estimated biomass reached 6,184 kg per platform. A clear vertical zonation in species composition was observed, with Carangidae dominating surface layers and Serranidae more prevalent near the seafloor. Structurally complex areas, such as crossbeams and base zones, were identified as local biodiversity hotspots. Notably, Cheilinus trilobatus was recorded for the first time in the Arabian Gulf. Comparisons with previous studies from Qatar’s Al Shaheen oilfield revealed differences in species composition, likely due to variation in platform structure, geographic location, and sampling design. These findings demonstrate the role of platforms as artificial reefs supporting diverse fish communities and highlight the limited knowledge of biodiversity associated with artificial structures in the region. They provide a valuable baseline to inform future RTR decisions in the Arabian Gulf.

Phytoplankton abundance and methane emissions are minimally impacted by environmentally-relevant glyphosate concentrations in small-scale outdoor mesocosms - Christopher F. Frazier; Ted D. Harris; Tonya DelSontro; Hans-Peter Grossart; Belinda S.M. Sturm; Jalynn M. Murry; Andrew Ising (Water Research, 2025)

JNJ-10450232 (NTM-006), A novel non-opioid with structural similarities to acetaminophen, produces relatively long-lasting analgesia after a single dose in patients undergoing 3rd molar extraction - Cathy K. Gelotte; Amy M. Vakil; Brenda A. Zimmerman; Peter Zannikos; Rajesh Mishra; Gary Eichenbaum; Edwin K. Kuffner; Christopher M. Flores (Regulatory Toxicology and Pharmacology, 2025)

An 18 base pair in-frame deletion in the degron tail of IAA2 provides resistance to 2,4-D and dicamba in Brassica tournefortii - Yuanlin Qi; Mahima Krishnan; Matthew Tucker; Peter Boutsalis; Christopher Preston (Pesticide Biochemistry and Physiology, 2025)

OC7 phase I: Toward practical sea-state-dependent modeling of hydrodynamic viscous drag and damping - Lu Wang; Amy Robertson; Jason Jonkman; Yingqian Liao; Petter Andreas Berthelsen; Serag-Eldin Abdelmoteleb; Peter Rohrer; Vishnu Ramachandran Nair Rajasree; Erin Bachynski-Polić; Constance Clement; Cédric Le Cunff; Prokopios Vlachogiannis; et al. (Ocean Engineering, 2025)

Evaluation of the linear mixing model in fluorescence spectroscopy - Peter Hoff; Christopher L. Osburn (Next Research, 2025)

Winter-Spring dynamics of dissolved organic carbon fluxes driven by precipitation in a North Carolina tidal marsh - Marie Cindy Lebrasse; Blake A. Schaeffer; DelWayne R. Bohnenstiehl; Christopher L. Osburn; Megan M. Coffer; Ruoying He; Peter J. Whitman; Wilson B. Salls; David D. Graybill (Estuarine, Coastal and Shelf Science, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Economic costs of invasive carps in the United States: case study and management implications - Eleanor D. Brown; Joseph W. Snapp; Christopher Huber; James Caudill; Peter E. Grigelis (Biological Invasions, 2025)
Biological invasions can have far-reaching impacts and incur enormous monetary costs. Economic considerations play an important role in management decision-making. We used the invasion of U.S. waterways by silver ( Hypophthalmichthys molitrix ) and bighead ( H. nobilis ) carp as a case study of the costs of aquatic invasive species. Although these carps are well-known invaders, published reports on their economic costs are lacking. Our study included market values for commercial fisheries, non-market values for recreational fisheries, and management costs. Our results showed that by 2020, U.S. federal and state agencies had spent nearly $592 million in cumulative management costs. A difference-in-difference model testing for the effect of invasive carp on commercial harvest in invaded versus uninvaded reaches of the Mississippi and Illinois Rivers showed no statistical significance. A benefit transfer analysis of invasion effects on total economic value of recreational fishing, an important ecosystem service, in a heavily invaded section of the Illinois River estimated a total loss of more than $10 million over 10 years. While there are other known impacts on ecosystem services, including alteration of aquatic food webs, plankton communities, and native fish communities, these could not be quantified in economic terms in our analysis.

The expanding use and effectiveness of nonlethal methods for mitigating wolf-cattle conflict - Brooke Jacobs; Peter Kareiva; Christopher Schachtschneider (Rangelands, 2025)

Quantification of the difference in hounsfield units of an electron density phantom between a conventional and standing computed tomography machine - Catherine Beck; Ashleigh V. Morrice-West; Peter Muir; Peta L. Hitchens; R. Christopher Whitton (Veterinary Research Communications, 2025)
In human CT imaging, opportunistic calculation of bone mineral density (BMD) is used to screen for osteoporosis, where BMD is estimated by Hounsfield Units (HU). There is potential to use HU for estimation of BMD in veterinary imaging. However, HU values can vary between different machines and over time. We undertook a serial measurements study to determine (1) the extent of the difference of the mean HU and noise (HU standard deviation) of eight regions of interest (ROI) of an electron density phantom scanned on two CT machines, a Siemens CT (conventional) machine and the Equina by Asto CT (standing) machine; and (2) to determine if the HU values obtained on each machine differed over time. The mean HU from 30 scans of an electron density phantom were generated from each of the two CT machines ( N = 60; conventional and standing). Differences between machines were assessed using a linear mixed effects model. The mean HU of each positive value ROI from the conventional machine was decreased compared with the standing machine ( P < 0.001) and the difference was greatest for the denser phantom inserts. A calibration curve equation utilising the four bone-equivalent insert plugs of the phantom, with known calcium hydroxyapatite (CaHA) concentration, was generated using linear regression to represent CaHA, and therefore BMD, for the conventional machine (CaHA = -29.58 + 0.98xROI mean ) and the standing machine (CaHA = -54.53 + 0.95xROI mean ). For opportunistic calculation of BMD from HU in horses, the differences in HU observed between different CT machines warrants calibration of HU using a bone equivalent phantom.

Opioidergic modulation of monetary incentive delay fMRI responses - Samuel Turton; Peter C.T. Hawkins; Christopher Muller-Pollard; Evangelos Zois; Patricia Conrod; Fernando Zelaya; Mitul A. Mehta (Psychopharmacology, 2025)
Rationale It is hypothesised that modulation of striatal dopaminergic signalling plays a key role in the rewarding effects of opioids. The monetary incentive delay (MID) task is a functional magnetic resonance imaging (fMRI) paradigm used to investigate striatal responses, which may reflect striatal dopamine release, during the anticipation of a financial reward. Objectives We hypothesised that fentanyl would modulate striatal MID task Blood Oxygenation Level Dependent (BOLD) responses, reflecting opioidergic modulation of striatal dopaminergic signalling. Methods 24 right-handed males who undertook four MRI scanning sessions, during which they completed an MID task 15 min after receiving an intravenous infusion of either one of two doses of fentanyl (50 µg/70kg), naloxone (400 µg) or placebo (saline 0.9%), were included in the analyses. End tidal CO 2 data were collected to control for respiratory depression. Results We demonstrated fentanyl induced increases in MID task reward and loss anticipation BOLD compared with placebo and naloxone in both region of interest (ROI) and whole brain analyses. These results were in cortical regions including the lingual gyrus, precuneus, posterior cingulate and frontal pole rather than the striatum. Conclusions Our results show the primary effects of fentanyl on MID anticipation BOLD in regions associated with the preparation of a motor response to a salient visual cue, rather than in regions typically associated with reward processing such as the striatum. This suggests that opioid agonists do not affect striatal activation during the MID task. Tasks using naturalistic rewards, for example feeding, sex or social contact which induce endogenous opioid signalling, may be more appropriate to probe the effects of fentanyl on reward processing. These results are from male participants’ data and therefore may not be generalisable to female participants.

Whole genome sequence of Arthrobacter sp. from Iloilo City landfill soil unveils potential plastic biodegradation genes - Jasmine Velo; Christopher Marlowe Caipang; Albert Noblezada; Lorenz Inri Banabatac; Noel Peter Tan; Victor Marco Emmanuel Ferriols (Biodegradation, 2025)

Conservation benefits of a large marine protected area network that spans multiple ecosystems - Joshua G. Smith; Cori Lopazanski; Christopher M. Free; Julien Brun; Clarissa Anderson; Mark H. Carr; Joachim Claudet; Jenifer E. Dugan; Jacob G. Eurich; Tessa B. Francis; David A. Gill; Scott L. Hamilton; et al. (Conservation Biology, 2025)
Marine protected areas (MPAs) are widely implemented tools for long‐term ocean conservation and resource management. Assessments of MPA performance have largely focused on specific ecosystems individually and have rarely evaluated performance across multiple ecosystems either in an individual MPA or across an MPA network. We evaluated the conservation performance of 59 MPAs in California's large MPA network, which encompasses 4 primary ecosystems (surf zone, kelp forest, shallow reef, deep reef) and 4 bioregions, and identified MPA attributes that best explain performance. Using a meta‐analytic framework, we evaluated the ability of MPAs to conserve fish biomass, richness, and diversity. At the scale of the network and for 3 of 4 regions, the biomass of species targeted by fishing was positively associated with the level of regulatory protection and was greater inside no‐take MPAs, whereas species not targeted by fishing had similar biomass in MPAs and areas open to fishing. In contrast, species richness and diversity were not as strongly enhanced by MPA protection. The key features of conservation effectiveness included MPA age, preimplementation fisheries pressure, and habitat diversity. Important drivers of MPA effectiveness for single MPAs were consistent across MPAs in the network, spanning regions and ecosystems. With international targets aimed at protecting 30% of the world's oceans by 2030, MPA design and assessment frameworks should consider conservation performance at multiple ecologically relevant scales, from individual MPAs to MPA networks.

A glimpse into the Late Cretaceous (Cenomanian) palynology of the Arlington Archosaur Site, Texas, USA - Maria Antonieta Lorente; Christopher Noto; Peter Flaig (Palynology, 2025)

The Harmonized Landsat and Sentinel-2 version 2.0 surface reflectance dataset - Junchang Ju; Qiang Zhou; Brian Freitag; David P. Roy; Hankui K. Zhang; Madhu Sridhar; John Mandel; Saeed Arab; Gail Schmidt; Christopher J. Crawford; Ferran Gascon; Peter A. Strobl; et al. (Remote Sensing of Environment, 2025)

Forest terpenes and stress: Examining the associations of filtered vs. non-filtered air in a real-life natural environment - Chaja M. Levy; Anne M. Riederer; Christopher D. Simpson; Amanda J. Gassett; Abigail J. Gilbert; Michael H. Paulsen; Lalith K. Silva; Deepak Bhandari; Cody A. Newman; Benjamin C. Blount; Peter H. Kahn; Gregory N. Bratman (Environmental Research, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Broadscale reconnaissance of coral reefs from citizen science and deep learning - Christopher L. Lawson; Kathryn M. Chartrand; Chris M. Roelfsema; Aruna Kolluru; Peter J. Mumby (Environmental Monitoring and Assessment, 2025)
Coral reef managers require various forms of data. While monitoring is typically the preserve of scientists, there is an increasing need to collect larger scale, up-to-date data to prioritise limited conservation resources. Citizen science combined with novel technology may achieve data collection at the required scale, but the accuracy and feasibility of new tools must be assessed. Here, we show that a citizen science program that collects large field-of-view benthic images and analyses them using a combination of deep learning and online citizen scientists can produce accurate benthic cover estimates of key coral groups. The deep learning and citizen scientist analysis methods had different but complementary strengths depending on coral category. When the best performing analysis method was used for each category in all images, mean estimates from 8086 images of percent benthic cover of branching Acropora , plating Acropora , and massive-form coral were ~ 99% accurate compared to expert assessment, and > 95% accurate at all coral cover ranges tested. Site-level accuracy of 95% was attainable with 18–80 images. Power analyses showed that up to 114 images per site were needed to detect a 10% absolute difference in coral cover per category (power = 0.8). However, estimates of ‘all other coral’ as a single category achieved 95% accuracy at only 60% of sites and for images with 10–30% coral cover. Overall, emerging technology and citizen science present an attainable tool for collecting inexpensive, widespread data that can complement higher resolution survey programs or be an accessible tool for locations with limited scientific or conservation resources.

Impact of sarcopenia and obesity on skeletal muscle size, gene expression, and mitochondrial function - Hector G. Paez; Christopher R. Pitzer; Jessica L. Halle; Peter J. Ferrandi; James A. Carson; Junaith S. Mohamed; Stephen E. Alway (GeroScience, 2025)
Skeletal muscle is a primary tissue of dysfunction during both aging and obesity. Recently, the coincidence of obesity and aging has gained attention due to the intersection of the obesity epidemic with an aging demographic. Both aging and obesity are associated with marked defects in skeletal muscle metabolic health. Despite these findings, we have a poor understanding of how obesity and aging may interact to impact skeletal muscle mass and metabolic health. Therefore, we investigated the impact of high-fat diet (HFD)-induced obesity on skeletal muscle mass, mitochondrial function, transcriptomics, and whole-body metabolism in young and aged mice. We observed main effects of diet and age on several measures of whole-body metabolic function (VO 2 , VCO 2 , and RER). Complex I-driven mitochondrial proton leak was significantly elevated by HFD-induced obesity across both age groups; however, a main effect of aging for reduced complex I leak was detected in the soleus muscle. Interestingly, aged animals fed a HFD did not exhibit lower muscle mass than chow-fed young animals, but did present with stark increases in muscle triglyceride content and a unique transcriptional response to HFD. HFD-induced obesity impacted the muscle transcriptome differently in the muscles of young and aged mice, indicating that obesity can change altered gene expression with age. Our findings suggest that the presence of obesity can both compound and counteract age-associated changes to muscle mass, gene expression, and mitochondrial function.

Comparing growth of ear-hanging and lantern net cultured Atlantic sea scallops, Placopecten magellanicus, over a complete grow-out cycle to determine optimal harvest timing - Christopher Noren; Struan Coleman; Adam St. Gelais; Dana Morse; Tom Kiffney; Andrew Peters; Damian C. Brady (Aquaculture, 2025)

Skyglow increases cyanobacteria abundance and organic matter cycling in lakes - Jeremy Fonvielle; Lukas Thuile Bistarelli; Yile Tao; Jason N. Woodhouse; Tom Shatwell; Luis A. Villalba; Stella A. Berger; Christopher C.M. Kyba; Jens C. Nejstgaard; Andreas Jechow; Franziska Kupprat; Susanne Stephan; et al. (Water Research, 2025)

Dental microwear and diet of the latest Miocene ape in southern China (Lufengpithecus lufengensis) - Yaobin Fan; Christopher J. Bae; Jianrong Liu; Jiahui Ding; Wei Liao; Wei Wang; Peter S. Ungar (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Escalating threats: house mouse attacks on adult wandering albatrosses spread across Marion Island - Michelle M. Risi; Christopher W. Jones; Maëlle Connan; Rhiannon Gill; Vanessa Stephen; Susan J. Cunningham; Peter G. Ryan (Biological Invasions, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Love Thy Neighbour? Tropical Tree Growth and Its Response to Climate Anomalies Is Mediated by Neighbourhood Hierarchy and Dissimilarity in Carbon‐ and Water‐Related Traits - Daniela Nemetschek; Claire Fortunel; Eric Marcon; Johanna Auer; Vincyane Badouard; Christopher Baraloto; Marion Boisseaux; Damien Bonal; Sabrina Coste; Elia Dardevet; Patrick Heuret; Peter Hietz; et al. (Ecology Letters, 2025)
Taxonomic diversity effects on forest productivity and response to climate extremes range from positive to negative, suggesting a key role for complex interactions among neighbouring trees. To elucidate how neutral interactions, hierarchical competition and resource partitioning between neighbours' shape tree growth and climate response in a highly diverse Amazonian forest, we combined 30 years of tree censuses with measurements of water‐ and carbon‐related traits. We modelled individual tree growth response to climate and neighbourhood to disentangle the relative effect of neighbourhood densities, trait hierarchies and dissimilarities. While neighbourhood densities consistently decreased growth, trait dissimilarity increased it, and both had the potential to influence climate response. Greater water conservatism provided a competitive advantage to focal trees in normal years, but water–spender neighbours reduced this effect in dry years. By underlining the importance of density and trait‐mediated neighbourhood interactions, our study offers a way towards improving predictions of forest dynamics.

Adaptive sampling with PIXL on the Mars Perseverance rover - Peter R. Lawson; Tanya V. Kizovski; Michael M. Tice; Benton C. Clark; Scott J. VanBommel; David R. Thompson; Lawrence A. Wade; Robert W. Denise; Christopher M. Heirwegh; W. Timothy Elam; Mariek E. Schmidt; Yang Liu; et al. (Icarus, 2025)

Land use change and forest management affect soil carbon stocks in the central hardwoods, U.S. - Lucas E. Nave; Kendall DeLyser; Grant M. Domke; Scott M. Holub; John M. Kabrick; Adrienne B. Keller; Patricia Leopold; Matthew P. Peters; Kevin A. Solarik; Christopher W. Swanston (Geoderma Regional, 2025)

Threatened fauna that use blue carbon ecosystems: A review from Australia - Kristian Bell; Siegmund Nuyts; Christopher Bie; Valerie Hagger; Peter Macreadie; Melissa Wartman (Biological Conservation, 2025)

Synergistic effects of plasma S100B and MRI measures of cerebrovascular disease on cognition in older adults - Colleen Pappas; Christopher E. Bauer; Valentinos Zachariou; T. J. Libecap; Beatriz Rodolpho; Tiffany L. Sudduth; Peter T. Nelson; Gregory A. Jicha; Anika MS Hartz; Xingfeng Shao; Danny J. J. Wang; Brian T. Gold (GeroScience, 2025)
There is growing interest in studying vascular contributions to cognitive impairment and dementia (VCID) and developing biomarkers to identify at-risk individuals. A combination of biofluid and neuroimaging markers may better profile early stage VCID than individual measures. Here, we tested this possibility focusing on plasma levels of S100 calcium-binding protein B (S100B), which has been linked with blood–brain-barrier (BBB) integrity, and neuroimaging measures assessing BBB function (water exchange rate across the BBB (k w )) and cerebral small vessel disease (white matter hyperintensities (WMHs)). A total of 74 older adults without dementia had plasma samples collected and underwent cognitive assessment. A subsample had neuroimaging data including diffusion prepared pseudo-continuous arterial spin labeling (DP-pCASL) for assessment of BBB k w and T2-weighted fluid-attenuated inversion recovery (FLAIR) for quantification of WMHs. Results indicated that higher plasma S100B levels were associated with poorer episodic memory performance ( β = − .031, SE = .008, p < .001). Moreover, significant interactions were observed between plasma S100B levels and parietal lobe BBB k w (interaction β = .095, SE = .042, p = .028) and between plasma S100B levels and deep WMH volume (interaction β = − .025, SE = .009, p = .007) for episodic memory. Individuals with the poorest memory performance showed both high plasma S100B and either low BBB k w in the parietal lobe or increased deep WMH burden. Taken together, our results provide support for the combined use of biofluid and neuroimaging markers in the study of VCID.

The effect of high pressure on hydrocarbon generation from Type-I kerogen source rocks: Implications for petroleum system evolution - Ahmed Khairy; Clement N. Uguna; Christopher H. Vane; Waleed Sh. El Diasty; Kenneth E. Peters; Colin E. Snape; Sherif Farouk; Will Meredith (International Journal of Coal Geology, 2025)

What to Measure in Aneurysmal Subarachnoid Haemorrhage Research—An International Delphi Survey - Christopher R. Andersen; Justin Presseau; Bev Shea; Maria Luisa Marti; Madeline McCoy; Gordon Fernie; Lauralyn McIntyre; Anthony Delaney; Michaël Chassé; Victoria Saigle; Shawn Marshall; Dean A. Fergusson; et al. (Translational Stroke Research, 2025)

Spawning and larval development of the mesophotic octocoral Swiftia exserta in aquaria - Julia W. Johnstone; William G. Jenkins; Mackenzy Jankiewicz; Jonathan M. Quigley; Janessy Frometa; Enrique Salgado; Ben Higgins; Amanda W. J. Demopoulos; Christopher L. Gardner; Peter J. Etnoyer; Kristopher G. Benson (Marine Biology, 2025)
The 2010 Deepwater Horizon oil spill injured mesophotic and deep-sea environments over a vast area. In order to restore mesophotic and deep-sea coral species impacted by the spill, information on fundamental ecosystem processes such as reproduction is needed. During expeditions in 2021 and 2022, fragments of the mesophotic octocoral Swiftia exserta were collected from the northern Gulf of Mexico and transported to aquaria at federal facilities in South Carolina, Florida, and Texas. In fall of 2021 and 2022, several of these fragments spawned in captivity, providing an opportunity to learn about their reproduction and inform future restoration activities. Broadcast spawning occurred on 19 and 20 October, 2021, and on 20 days from 29 September to 7 November, 2022. These spawning events permitted detailed observations of spawning behavior and timing, and yielded over 2,400 oocytes. Individual spawns were preceded by a distinctive “spawning posture” in the polyps, lasting between five minutes and two hours, and may have been cued by light. Swiftia exserta larvae settled and developed at comparable rates to other broadcast spawning octocorals, becoming swimming planulae by three days post spawn (dps) and starting to settle by 14 dps. These observations represent the first such records for S. exserta and, more broadly, for any mesophotic coral in the Gulf of Mexico, providing important insights for the restoration of these species. This investigation lays the foundation for future work to explore the influences of seasonal environmental variables, such as light and temperature, on spawning and reproductive seasonality in this species.

Cryptic variation in the sooty albatross Phoebetria fusca: genetic and morphological differences between Atlantic and Indian Ocean birds - Dilini K. Abeyrama; Michelle M. Risi; Maelle Connan; Peter G. Ryan; Christopher W. Jones; Trevor Glass; Alexis M. Osborne; Antje Steinfurth; Andy Schofield; Pierre Pistorius; Danielle Keys; Yves Cherel; et al. (Conservation Genetics, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

A Continuum From Positive to Negative Interactions Drives Plant Species' Performance in a Diverse Community - Lisa Buche; Lauren G. Shoemaker; Lauren M. Hallett; Ignasi Bartomeus; Peter Vesk; Christopher Weiss‐Lehman; Margaret Mayfield; Oscar Godoy (Ecology Letters, 2025)
With many species interacting in nature, determining which interactions describe community dynamics is nontrivial. By applying a computational modeling approach to an extensive field survey, we assessed the importance of interactions from plants (both inter‐ and intra‐specific), pollinators and insect herbivores on plant performance (i.e., viable seed production). We compared the inclusion of interaction effects as aggregate guild‐level terms versus terms specific to taxonomic groups. We found that a continuum from positive to negative interactions, containing mostly guild‐level effects and a few strong taxonomic‐specific effects, was sufficient to describe plant performance. While interactions with herbivores and intraspecific plants varied from weakly negative to weakly positive, heterospecific plants mainly promoted competition and pollinators facilitated plants. The consistency of these empirical findings over 3 years suggests that including the guild‐level effects and a few taxonomic‐specific groups rather than all pairwise and high‐order interactions, can be sufficient for accurately describing species variation in plant performance across natural communities.

Controls on spatial variation in porewater methane concentrations across United States tidal wetlands - Erika L. Koontz; Sarah M. Parker; Alice E. Stearns; Brian J. Roberts; Caitlin M. Young; Lisamarie Windham-Myers; Patricia Y. Oikawa; J. Patrick Megonigal; Genevieve L. Noyce; Edward J. Buskey; R. Kyle Derby; Robert P. Dunn; et al. (Science of The Total Environment, 2024)

A global blueberry phylogeny: Evolution, diversification, and biogeography of Vaccinieae (Ericaceae) - Anna L. Becker; Andrew A. Crowl; James L. Luteyn; Andre S. Chanderbali; Walter S. Judd; Paul S. Manos; Douglas E. Soltis; Stephen A. Smith; Deise J.P. Goncalves; Christopher W. Dick; William N. Weaver; Pamela S. Soltis; et al. (Molecular Phylogenetics and Evolution, 2024)

Agelessness is possible under the disposable soma theory but system complexity makes it unlikely - Christopher W. Rodriguez; Peter W. Reddien (Journal of Theoretical Biology, 2024)

Source apportionment of Volatile Organic Compounds (VOCs) in the South Coast Air Basin (SoCAB) During RECAP-CA - Shenglun Wu; Christopher P. Alaimo; Peter G. Green; Thomas M. Young; Yusheng Zhao; Shang Liu; Toshihiro Kuwayama; Michael J. Kleeman (Atmospheric Environment, 2024)

Reactivity and social rank in male bighorn sheep (Ovis canadensis) - Fabian Rood; Tanisha C. Henry; Magdalena Storkova; Nigel Caulkett; Peter Neuhaus; Christopher Duncan; Kathreen E. Ruckstuhl (Behavioral Ecology and Sociobiology, 2024)

Development of a Simple Analytical Model to Facilitate Preoperative Surgical Planning in Valve-Sparing Aortic Root Replacement - Dominic P. Recco; Shannen B. Kizilski; Wen Zhang; Nicholas E. Kneier; Patrick D. Earley; David M. Hoganson; Christopher W. Baird; Peter E. Hammer (Annals of Biomedical Engineering, 2024)

Coefficients in Taylor's law increase with the time scale of water clarity measurements in a global suite of lakes - Max R. Glines; Renata C. H. Amancio; Mikkel René Andersen; Helen Baulch; Ludmila S. Brighenti; Hannah E. Chmiel; Joel E. Cohen; Elvira de Eyto; Oxana Erina; Heidrun Feuchtmayr; Giovanna Flaim; Andrea Giudici; et al. (Ecology Letters, 2024)
Identifying the scaling rules describing ecological patterns across time and space is a central challenge in ecology. Taylor's law of fluctuation scaling, which states that the variance of a population's size or density is proportional to a positive power of the mean size or density, has been widely observed in population dynamics and characterizes variability in multiple scientific domains. However, it is unclear if this phenomenon accurately describes ecological patterns across many orders of magnitude in time, and therefore links otherwise disparate observations. Here, we use water clarity observations from 10,531 days of high‐frequency measurements in 35 globally distributed lakes, and lower‐frequency measurements over multiple decades from 6342 lakes to test this unknown. We focus on water clarity as an integrative ecological characteristic that responds to both biotic and abiotic drivers. We provide the first documentation that variations in ecological measurements across diverse sites and temporal scales exhibit variance patterns consistent with Taylor's law, and that model coefficients increase in a predictable yet non‐linear manner with decreasing observation frequency. This discovery effectively links high‐frequency sensor network observations with long‐term historical monitoring records, thereby affording new opportunities to understand and predict ecological dynamics on time scales from days to decades.

Towards better understanding the urban environment and its interactions with regional climate change - The WCRP CORDEX Flagship Pilot Study URB-RCC - Gaby S. Langendijk; Tomas Halenka; Peter Hoffmann; Marianna Adinolfi; Aitor Aldama Campino; Olivier Asselin; Sophie Bastin; Benjamin Bechtel; Michal Belda; Angelina Bushenkova; Angelo Campanale; Kwok Pan Chun; et al. (Urban Climate, 2024)

Evaluation of coating materials on the characterization of size and viability of virus-laden particles collected with an Andersen cascade impactor - Lan Wang; My Yang; Yuechen Qiao; Bernard A. Olson; Christopher J. Hogan; Peter C. Raynor; Sagar M. Goyal; Montserrat Torremorell (Journal of Aerosol Science, 2024)

Assessing the recovery of Pinus canariensis stands after wildfires and volcanic eruption on La Palma, Canary Islands - Christopher Shatto; Marvin Kiene; Peter Hofmann; Anna Walentowitz; Vincent Wilkens; Tobias Heuser; Frank Weiser (Forest Ecology and Management, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Roger Payne 1935–2023 - Peter L. Tyack; Christopher W. Clark; Peter T. Madsen; Charles Walcott; Hal Whitehead; Bernd Würsig (Marine Mammal Science, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Improving impact assessments to reduce impacts of deep-sea fisheries on vulnerable marine ecosystems - Laura Kaikkonen; Teresa Amaro; Peter J. Auster; David M. Bailey; James B. Bell; Angelika Brandt; Malcolm R. Clark; Jeffrey C. Drazen; Cherisse Du Preez; Elva Escobar-Briones; Eva Giacomello; Matthew Gianni; et al. (Marine Policy, 2024)

Intercomparison of global foliar trait maps reveals fundamental differences and limitations of upscaling approaches - Benjamin Dechant; Jens Kattge; Ryan Pavlick; Fabian D. Schneider; Francesco M. Sabatini; Álvaro Moreno-Martínez; Ethan E. Butler; Peter M. van Bodegom; Helena Vallicrosa; Teja Kattenborn; Coline C.F. Boonman; Nima Madani; et al. (Remote Sensing of Environment, 2024)

In-situ observations of resident space objects with the CHEOPS space telescope - Nicolas Billot; Stephan Hellmich; Willy Benz; Andrea Fortier; David Ehrenreich; Christopher Broeg; Alexis Heitzmann; Anja Bekkelien; Alexis Brandeker; Yann Alibert; Roi Alonso; Tamas Bárczy; et al. (Journal of Space Safety Engineering, 2024)

Temporal tracking of cysteine 34 oxidation of plasma albumin as a biomarker of muscle damage following a bout of eccentric exercise - Christopher James; Cory W. Dugan; Corrin Boyd; Paul A. Fournier; Peter G. Arthur (European Journal of Applied Physiology, 2024)
Purpose Exercise-induced muscle damage (EIMD) results in the generation of reactive oxygen species (ROS), but little is known about the temporal profile of change in ROS post-EIMD and how ROS levels relate to the onset of and recovery from EIMD. Our primary aim was to examine the effect of EIMD on the pattern of change in the blood level of thiol-oxidised albumin, a marker of oxidative stress. Methods Seven male participants were subjected on separate days to eccentric muscle contraction to cause EIMD or a no-exercise condition. After each session, the participants collected daily dried blood spots to measure thiol-oxidised albumin and returned to the laboratory every 2 days for the assessment of indirect markers of EIMD, namely maximal voluntary contraction (MVC), delayed onset muscle soreness (DOMS), creatine kinase (CK), and myoglobin. Results Eccentric exercise resulted in a significant decrease in MVC and increase in DOMS, CK, myoglobin, and thiol-oxidised albumin with the latter reaching above baseline level within 24–48 h post-exercise. All the markers of EIMD returned to baseline level within 6 days post-exercise, but not the level of thiol-oxidised albumin which remained elevated for 10 days after exercise. There was a moderate correlation between changes in thiol-oxidised albumin and DOMS, but no significant relationship between any other markers of muscle damage. Conclusion The levels of thiol-oxidised albumin increase in response to EIMD and remain elevated for several days post-exercise. The temporal pattern of change in the level of thiol-oxidised albumin suggests that this may be a useful biomarker of muscle repair post-EIMD.

Evaluation of food allergen information, labelling and unintended food allergen presence in imported prepacked foods and drinks purchased online in the UK - Christopher A. James; Simon Welham; Peter Rose (Food Control, 2024)

The climate‐induced changes in the life history of the common cuttlefish in the English Channel - Vladimir Laptikhovsky; Christopher J. Barrett; Peter J. Barry; Chris Firmin; Eleanor MacLeod; Samantha Stott; Rui Vieira (Marine Ecology, 2024)
The population of common cuttlefish Sepia officinalis in the English Channel recently developed two life cycles: annual (spawning 1 y.o.) and biennial (spawning 2 y.o.) instead of the biennial strategy known before, associated with increasing environmental temperatures in recent decades because of climate changes. Both groups differ in the size of mature animals (110–196 mm mantle length vs. 140–262 mm) and the number of chambers in the cuttlebone (60–97 in annual vs. 93–152 in biennial). The annual group represented some 15%–20% of the population, and the proportion of early spawners increased during the reproductive period, from 3%–5% in February/March to 50%–70% in June/July. Among spawning cuttlefish males predominated as ~2:1. Such environmentally driven changes in historical ecology as exemplified by the cuttlefish might be a critical link in the adaptation of the cephalopod life cycles to changing ecosystems.

Amplicon sequencing and shotgun metagenomics reveal functional impacts of aminoethoxyvinylglycine-mediated ripening and cold storage on the microbiome of ‘NY1’ apples - Connor Lane; Yosef Al Shoffe; Peter Schafran; Fay-Wei Li; Jenny Kao-Kniffin; Christopher B. Watkins (Postharvest Biology and Technology, 2024)

COVID-19 and silent hypoxemia in a minimal closed-loop model of the respiratory rhythm generator - Casey O. Diekman; Peter J. Thomas; Christopher G. Wilson (Biological Cybernetics, 2024)
Silent hypoxemia, or “happy hypoxia,” is a puzzling phenomenon in which patients who have contracted COVID-19 exhibit very low oxygen saturation ( $$\text {SaO}_2$$ SaO 2 nucleus tractus solitarii are responsible for the blunted response to hypoxia. Here, we use our model to explore this hypothesis by altering the properties of the gain function representing oxygen sensing inputs to the CPG. We then vary other parameters in the model and show that oxygen carrying capacity is the most salient factor for producing silent hypoxemia. We call for clinicians to measure hematocrit as a clinical index of altered physiology in response to COVID-19 infection.

Optimizing release strategies for red king crab stock enhancement: Effects of release timing - William Christopher Long; Benjamin J. Daly; Peter A. Cummiskey (Fisheries Research, 2024)

Developing simple indicators of nitrogen and phosphorus removal in constructed stormwater wetlands - Christopher Szota; Alistair Danger; Peter J. Poelsma; Belinda E. Hatt; Robert B. James; Alison Rickard; Matthew J. Burns; Frédéric Cherqui; Vaughn Grey; Rhys A. Coleman; Tim D. Fletcher (Science of The Total Environment, 2024)

Densely populated biofilms and linked iron and sulfur cycles in the fractured-rock continental subsurface - Christopher J. Schuler; Amanda Patsis; Scott C. Alexander; David Hsu; William S. Dowd; Woonghee Lee; Sarick L. Matzen; Matthew A. Marcus; Cody S. Sheik; Jill M. McDermott; Peter K. Kang; Cara M. Santelli; et al. (Geochimica et Cosmochimica Acta, 2024)

Verbenone (SPLAT® Verb) delays Ips typographus (L.) infestation and reduces infestation risk and severity in windthrown Norway spruce in Southwest Germany - Tobias Frühbrodt; Helge Löcken; Baoguo Du; Christopher J. Fettig; Peter H.W. Biedermann; Jürgen Kreuzwieser; Tim Burzlaff; Horst Delb (Forest Ecology and Management, 2024)

A comprehensive review of recent advances in the applications and biosynthesis of oxalic acid from bio-derived substrates - Andrew Nosakhare Amenaghawon; Joshua Efosa Ayere; Ubani Oluwaseun Amune; Ifechukwude Christopher Otuya; Emmanuel Christopher Abuga; Chinedu Lewis Anyalewechi; Oseweuba Valentine Okoro; Jude A. Okolie; Peter Kayode Oyefolu; Steve Oshiokhai Eshiemogie; Blessing Esohe Osahon; Melissa Omede; et al. (Environmental Research, 2024)

Long-Term Follow-Up of Cerebral Aneurysms Completely Occluded at 6 Months After Intervention with the Woven EndoBridge (WEB) Device: a Retrospective Multicenter Observational Study - Kareem El Naamani; Panagiotis Mastorakos; Nimer Adeeb; Mathews Lan; James Castiglione; Omaditya Khanna; Jose Danilo Bengzon Diestro; Rachel M. McLellan; Mahmoud Dibas; Justin E. Vranic; Assala Aslan; Hugo H. Cuellar-Saenz; et al. (Translational Stroke Research, 2024)

Depositional and post-depositional architectural elements of the Dar es Salaam Platform, central coastal Tanzania: distribution of petroleum system elements and their implications for petroleum prospectivity - Felister Christopher Nyaki; Emily Barnabas Kiswaka; Olugbenga A. Boboye; Stephen Peter Magohe; Elisante E. Mshiu; Cassy Mtelela (Journal of Sedimentary Environments, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Status and long-term changes of coral reefs around Zanzibar - Ali M. Ussi; Mohammed S. Mohammed; Rashid J. Rashid; Mohammed A. Sheikh; Peter A. Staehr; Christopher A. Muhando; Saleh Yahya; Karsten Dahl (Frontiers in Marine Science, 2024)
Introduction Coral reefs as key ecosystems in Zanzibar are exposed to several anthropogenic and natural stressors. Methods The benthic composition and coverage of coral reefs were investigated on three data sets involving ten coral reefs monitored from 1992 to 2016. Firstly, we investigated differences in the reef composition using data from seven reefs in 2015. Secondly, we analyzed communities on three distinctive reefs (2010 to 2012) to understand the importance of seasons and reef zones (slope, crest and flat) on species abundance. Finally, we investigated long-term changes (1992 to 2016) of five reefs. Results Branching Porites and Acropora , and soft coral order Corallimorpharia, characterized sheltered reef communities. Soft corals and algal species characterized the reef communities exposed to strong hydrodynamic conditions, which also displayed greater cover of rocks and rubbles. The average dissimilarity between reefs ranged between 60% and 75%. The seasonal changes in community structure for reefs near Stone Town were mostly associated with soft coral Corallimorpharia. Indeed, the bare rock and algae distinguished the northern exposed reef from more sheltered reefs. Acropora was a key genus for the sheltered Chumbe reef, which explained between 14% and 18% of the dissimilarities among the three reefs. Hard corals covered between 40% and 70% in most years, with severe declines following El Niño events in 1998 and 2016. The dominating genus Acropora showed a strong decline from the late 1990s’ with signs of recovery at remote reefs compared to reefs closer to human residence. Discussion Our results highlight the importance of seasonality and spatial differences, reflecting differences in human impact and physical exposure and significant long-term changes in coral communities. Continued monitoring of reef health is essential to evaluate the success of ongoing management to sustain the reef services.

Brackish groundwater desalination by constant current membrane capacitive deionization (MCDI): Results of a long-term field trial in Central Australia - Yunyi Zhu; Christopher Miller; Boyue Lian; Yuan Wang; John Fletcher; Hang Zhou; Zhizhao He; Shunzhi Lyu; Megan Purser; Peter Juracich; David Sweeney; T. David Waite (Water Research, 2024)

New Oldowan locality Sare-Abururu (ca. 1.7 Ma) provides evidence of diverse hominin behaviors on the Homa Peninsula, Kenya - Emma M. Finestone; Thomas W. Plummer; Thomas H. Vincent; Scott A. Blumenthal; Peter W. Ditchfield; Laura C. Bishop; James S. Oliver; Andy I.R. Herries; Christopher Vere Palfery; Timothy P. Lane; Elizabeth McGuire; Jonathan S. Reeves; et al. (Journal of Human Evolution, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

A model for community-driven development of best practices: the Ocean Observatories Initiative Biogeochemical Sensor Data Best Practices and User Guide - Hilary I. Palevsky; Sophie Clayton; Heather Benway; Mairead Maheigan; Dariia Atamanchuk; Roman Battisti; Jennifer Batryn; Annie Bourbonnais; Ellen M. Briggs; Filipa Carvalho; Alison P. Chase; Rachel Eveleth; et al. (Frontiers in Marine Science, 2024)
The field of oceanography is transitioning from data-poor to data-rich, thanks in part to increased deployment of in-situ platforms and sensors, such as those that instrument the US-funded Ocean Observatories Initiative (OOI). However, generating science-ready data products from these sensors, particularly those making biogeochemical measurements, often requires extensive end-user calibration and validation procedures, which can present a significant barrier. Openly available community-developed and -vetted Best Practices contribute to overcoming such barriers, but collaboratively developing user-friendly Best Practices can be challenging. Here we describe the process undertaken by the NSF-funded OOI Biogeochemical Sensor Data Working Group to develop Best Practices for creating science-ready biogeochemical data products from OOI data, culminating in the publication of the GOOS-endorsed OOI Biogeochemical Sensor Data Best Practices and User Guide. For Best Practices related to ocean observatories, engaging observatory staff is crucial, but having a “user-defined” process ensures the final product addresses user needs. Our process prioritized bringing together a diverse team and creating an inclusive environment where all participants could effectively contribute. Incorporating the perspectives of a wide range of experts and prospective end users through an iterative review process that included “Beta Testers’’ enabled us to produce a final product that combines technical information with a user-friendly structure that illustrates data analysis pipelines via flowcharts and worked examples accompanied by pseudo-code. Our process and its impact on improving the accessibility and utility of the end product provides a roadmap for other groups undertaking similar community-driven activities to develop and disseminate new Ocean Best Practices.

Impacts of illegal Artisanal and small-scale gold mining on livelihoods in cocoa farming communities: A case of Amansie West District, Ghana - Peter Donkor; Ebenezer Kwadwo Siabi; Kwasi Frimpong; Prince Twum Frimpong; Samuel Kofi Mensah; Christopher Vuu; Elikplim Sarah Siabi; Emmanuel Kwasi Nyantakyi; Felix Agariga; Thomas Atta-Darkwa; Jacob Kofi Mensah (Resources Policy, 2024)

Impact of propagation time on yeast physiology during bottle conditioning of beer on an industrial scale - Brooke A. Dilmetz; Christopher T. Desire; Jon Meneses; Manuela Klingler-Hoffmann; Clifford Young; Peter Hoffmann (Food Chemistry, 2024)

Estimation of Fracture Permeability from Aperture Distributions for Rough and Partially Cemented Fractures - Christopher J. Landry; Maša Prodanović; Zuleima Karpyn; Peter Eichhubl (Transport in Porous Media, 2024)

Transient dynamics mask the resilience of coral reefs - Karlo Hock; Alan Hastings; Christopher Doropoulos; Russell C. Babcock; Juan C. Ortiz; Angus Thompson; Peter J. Mumby (Theoretical Ecology, 2024)
Coral reefs are model systems for studies of ecological resilience, with communities generally exhibiting multiple stable states and more resilient regions trending towards a single, coral-dominated, regime. We expand the theory of ecological resilience beyond the concepts of distinct stable states to integrate emerging ideas from transient dynamics as long-term intermediate states with no pronounced trend towards equilibria. We show that low coral abundance, together with stochastic larval supply and disturbance, can trap otherwise resilient reefs in a persistent intermediate state whose long-term outcome is difficult to predict. Common metrics, such as the ecosystem slowing down before crossing tipping points and using historical coral cover trends, may become unreliable predictors of future behaviour. Helping reefs out of transient states requires agile management that allows for short-term, targeted interventions after which natural ecological feedbacks can take over.

Woody Plant–Soil Relationships in Interstitial Spaces Have Implications for Future Forests Within and Beyond Urban Areas - Gisselle A. Mejía; Peter M. Groffman; Meghan L. Avolio; Anika R. Bratt; Jeannine Cavender-Bares; Noortje H. Grijseels; Sharon J. Hall; James Heffernan; Sarah E. Hobbie; Susannah B. Lerman; Jennifer L. Morse; Desiree L. Narango; et al. (Ecosystems, 2024)

Assessment of biomass and carbon storage of a Populus simonii windbreak located in the Western Cape Province, South Africa - Jonathan P. Sheppard; Elena Larysch; Claudio J. Cuaranhua; Zoe Schindler; Ben du Toit; Gideon F. Malherbe; Anton Kunneke; Christopher Morhart; Rafael Bohn Reckziegel; Thomas Seifert; Hans-Peter Kahle (Agroforestry Systems, 2024)
The integration of trees within agricultural systems delivers the opportunity to provide multiple benefits over those afforded by agriculture without trees. The use of windbreaks as a form of agroforestry, in water scarce environments, is primarily used to reduce windspeeds in order to decrease evapotranspiration. Quick growing poplar species such as Populus simonii ((Carrière) Wesm.) are frequently utilised within windbreak structures, but to date, few allometric equations are available to quantify biomass production and to make inferences about carbon storage potential of this species, and none outside the forest. To fill this knowledge gap, we destructively sampled 17 P. simonii growing within a windbreak on a wine estate in the Western Cape Provence, South Africa. Power functions were constructed to explain tree height, whole tree aboveground woody biomass, stem and branch biomass as a function of stem diameter at 1.3 m. Additional functions were developed to predict individual branch length and biomass based on branch stub diameter. The presented models explained each variable with high significance. The models could be used to estimate carbon stock per km of windbreak for the given example. Furthermore, bark percentage predicted by stem sectional diameter was modelled to provide a function that can separate wood and bark fractions as a further outlook for the species’ utilisation.

Differentiation of Bulinus senegalensis and Bulinus forskalii Snails in West Africa Using Morphometric Analysis - Peter S. Andrus; Ebrima Joof; Christopher M. Wade (Acta Parasitologica, 2024)
Purpose Accurate identification of medically important intermediate host and vector species is crucial for understanding disease transmission and control. Identifying Bulinus snails which act as intermediate host species for the transmission of schistosomiasis is typically undertaken using conchological and genital morphology as well as molecular methods. Methods Here, a landmark-based morphometric analysis of shell morphology was undertaken to determine its utility to distinguish the closely related and morphologically similar sister species Bulinus senegalensis and Bulinus forskalii . The method was developed to increase the accuracy of conchological morphology methods to identify Bulinus species in the field. Both species are found in West Africa, but only B. senegalensis is implicated in the transmission of urogenital schistosomiasis. Results We found when scaled down to the same length, 3-whorl and 4-whorl (juvenile) B. senegalensis shells had a longer spire, narrower body whorl and shorter aperture than B. forskalii . In contrast, 5-whorl (adult) B. senegalensis had a shorter spire, but still had a shorter aperture and narrower body whorl than B. forskalii . Canonical Variate Analysis (CVA) showed minimal overlap between B. senegalensis and B. forskalii for 3-whorl and 4-whorl shells, with a clear separation for 5-whorl shells. Overall, B. senegalensis had a consistently shorter aperture size and narrower body whorl than B. forskalii for all development stages. Spire length was variable depending on the stage of development, with 3-whorl and 4-whorl shells having the opposite trends of adult shells. Conclusions Our study demonstrates the applicability of landmark-based morphometrics in distinguishing the medically important, Bulinus senegalensis from its morphologically similar sister species, Bulinus forskalii . We recommend using measurements based on spire length, penultimate whorl length, body whorl width and aperture size to differentiate B. senegalensis and B. forskalii , when used with the appropriate information for each shell’s development stage.

The paradigm change from reactive medical services to 3PM in ischemic stroke: a holistic approach utilising tear fluid multi-omics, mitochondria as a vital biosensor and AI-based multi-professional data interpretation - Olga Golubnitschaja; Jiri Polivka; Pavel Potuznik; Martin Pesta; Ivana Stetkarova; Alena Mazurakova; Lenka Lackova; Peter Kubatka; Martina Kropp; Gabriele Thumann; Carl Erb; Holger Fröhlich; et al. (EPMA Journal, 2024)
Worldwide stroke is the second leading cause of death and the third leading cause of death and disability combined. The estimated global economic burden by stroke is over US$891 billion per year. Within three decades (1990–2019), the incidence increased by 70%, deaths by 43%, prevalence by 102%, and DALYs by 143%. Of over 100 million people affected by stroke, about 76% are ischemic stroke (IS) patients recorded worldwide. Contextually, ischemic stroke moves into particular focus of multi-professional groups including researchers, healthcare industry, economists, and policy-makers. Risk factors of ischemic stroke demonstrate sufficient space for cost-effective prevention interventions in primary (suboptimal health) and secondary (clinically manifested collateral disorders contributing to stroke risks) care. These risks are interrelated. For example, sedentary lifestyle and toxic environment both cause mitochondrial stress, systemic low-grade inflammation and accelerated ageing; inflammageing is a low-grade inflammation associated with accelerated ageing and poor stroke outcomes. Stress overload, decreased mitochondrial bioenergetics and hypomagnesaemia are associated with systemic vasospasm and ischemic lesions in heart and brain of all age groups including teenagers. Imbalanced dietary patterns poor in folate but rich in red and processed meat, refined grains, and sugary beverages are associated with hyperhomocysteinaemia, systemic inflammation, small vessel disease, and increased IS risks. Ongoing 3PM research towards vulnerable groups in the population promoted by the European Association for Predictive, Preventive and Personalised Medicine (EPMA) demonstrates promising results for the holistic patient-friendly non-invasive approach utilising tear fluid-based health risk assessment, mitochondria as a vital biosensor and AI-based multi-professional data interpretation as reported here by the EPMA expert group. Collected data demonstrate that IS-relevant risks and corresponding molecular pathways are interrelated. For examples, there is an evident overlap between molecular patterns involved in IS and diabetic retinopathy as an early indicator of IS risk in diabetic patients. Just to exemplify some of them such as the 5-aminolevulinic acid/pathway, which are also characteristic for an altered mitophagy patterns, insomnia, stress regulation and modulation of microbiota-gut-brain crosstalk. Further, ceramides are considered mediators of oxidative stress and inflammation in cardiometabolic disease, negatively affecting mitochondrial respiratory chain function and fission/fusion activity, altered sleep–wake behaviour, vascular stiffness and remodelling. Xanthine/pathway regulation is involved in mitochondrial homeostasis and stress-driven anxiety-like behaviour as well as molecular mechanisms of arterial stiffness. In order to assess individual health risks, an application of machine learning (AI tool) is essential for an accurate data interpretation performed by the multiparametric analysis. Aspects presented in the paper include the needs of young populations and elderly, personalised risk assessment in primary and secondary care, cost-efficacy, application of innovative technologies and screening programmes, advanced education measures for professionals and general population—all are essential pillars for the paradigm change from reactive medical services to 3PM in the overall IS management promoted by the EPMA.

Developing expert scientific consensus on the environmental and societal effects of marine artificial structures prior to decommissioning - Antony M. Knights; Anaëlle J. Lemasson; Louise B. Firth; Todd Bond; Jeremy Claisse; Joop W.P. Coolen; Andrea Copping; Jennifer Dannheim; Michela De Dominicis; Steven Degraer; Michael Elliott; Paul G. Fernandes; et al. (Journal of Environmental Management, 2024)

202 years of changes in Mediterranean fire regime in Pinus nigra forest, Corsica - Justin Badeau; Frédéric Guibal; Peter Z. Fulé; Sandrine Chauchard; Pasquale Moneglia; Christopher Carcaillet (Forest Ecology and Management, 2024)

Understanding temporal variability across trophic levels and spatial scales in freshwater ecosystems - Tadeu Siqueira; Charles P. Hawkins; Julian D. Olden; Jonathan Tonkin; Lise Comte; Victor S. Saito; Thomas L. Anderson; Gedimar P. Barbosa; Núria Bonada; Claudia C. Bonecker; Miguel Cañedo‐Argüelles; Thibault Datry; et al. (Ecology, 2024)
A tenet of ecology is that temporal variability in ecological structure and processes tends to decrease with increasing spatial scales (from locales to regions) and levels of biological organization (from populations to communities). However, patterns in temporal variability across trophic levels and the mechanisms that produce them remain poorly understood. Here we analyzed the abundance time series of spatially structured communities (i.e., metacommunities) spanning basal resources to top predators from 355 freshwater sites across three continents. Specifically, we used a hierarchical partitioning method to disentangle the propagation of temporal variability in abundance across spatial scales and trophic levels. We then used structural equation modeling to determine if the strength and direction of relationships between temporal variability, synchrony, biodiversity, and environmental and spatial settings depended on trophic level and spatial scale. We found that temporal variability in abundance decreased from producers to tertiary consumers but did so mainly at the local scale. Species population synchrony within sites increased with trophic level, whereas synchrony among communities decreased. At the local scale, temporal variability in precipitation and species diversity were associated with population variability (linear partial coefficient, β = 0.23) and population synchrony (β = −0.39) similarly across trophic levels, respectively. At the regional scale, community synchrony was not related to climatic or spatial predictors, but the strength of relationships between metacommunity variability and community synchrony decreased systematically from top predators (β = 0.73) to secondary consumers (β = 0.54), to primary consumers (β = 0.30) to producers (β = 0). Our results suggest that mobile predators may often stabilize metacommunities by buffering variability that originates at the base of food webs. This finding illustrates that the trophic structure of metacommunities, which integrates variation in organismal body size and its correlates, should be considered when investigating ecological stability in natural systems. More broadly, our work advances the notion that temporal stability is an emergent property of ecosystems that may be threatened in complex ways by biodiversity loss and habitat fragmentation.

The Cerebellar Cognitive Affective/Schmahmann Syndrome Scale in Spinocerebellar Ataxias - Louisa P. Selvadurai; Susan L. Perlman; Tetsuo Ashizawa; George R. Wilmot; Chiadi U. Onyike; Liana S. Rosenthal; Vikram G. Shakkottai; Henry L. Paulson; Sub H. Subramony; Khalaf O. Bushara; Sheng-Han Kuo; Cameron Dietiker; et al. (The Cerebellum, 2024)

Need and vision for global medium-resolution Landsat and Sentinel-2 data products - Volker C. Radeloff; David P. Roy; Michael A. Wulder; Martha Anderson; Bruce Cook; Christopher J. Crawford; Mark Friedl; Feng Gao; Noel Gorelick; Matthew Hansen; Sean Healey; Patrick Hostert; et al. (Remote Sensing of Environment, 2024)

Dilated pore of Winer in a dog - Christopher P. Champion; Heather D. Edginton; Jeanine Peters-Kennedy (Journal of Comparative Pathology, 2024)

Intraspecific genetic lineages of a marine mussel show behavioural divergence when exposed to microplastic leachates - Lorenzo Cozzolino; Katy R. Nicastro; Peter C. Hubbard; Laurent Seuront; Christopher D. McQuaid; Gerardo I. Zardi (Environmental Pollution, 2024)

Navigating tensions in inclusive conservation: Learning from the Utrechtse Heuvelrug National Park in the Netherlands - Ciska Ulug; Miguel A. Cebrián-Piqueras; Marc Metzger; Christopher M. Raymond; Peter H. Verburg (Environmental Science & Policy, 2024)

Unravelling the fluorescence kinetics of light-harvesting proteins with simulated measurements - Callum Gray; Lekshmi Kailas; Peter G. Adams; Christopher D.P. Duffy (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

First evidence of mouse predation killing adult great albatrosses - Maëlle Connan; Christopher W. Jones; Michelle M. Risi; Lucy K. Smyth; Steffen Oppel; Vonica Perold; Kim L. Stevens; Roelf Daling; Peter G. Ryan (Biological Invasions, 2024)
Invasive rodents threaten native species in numerous ecosystems, especially oceanic islands. The House Mouse Mus musculus is the only introduced mammal species on sub-Antarctic Gough and Marion Islands. Ample evidence exists of mice preying upon seabird chicks on these two islands, but there have been only a few reports of attacks on adult seabirds, none of which has been fatal. We report the first deaths of adult great albatrosses due to mouse attacks. On Gough Island, three Tristan Albatrosses Diomedea dabbenena (Critically Endangered) brooding small chicks were observed with wounds typical of mouse attacks in March–April 2021; two likely abandoned their chick, causing breeding failure, and the third was found dead eight days after discovery with large blowfly larvae in the wound. On Marion Island, two wounded and eight dead adult Wandering Albatrosses D. exulans (Vulnerable) were found in April 2023. Inspection of the wounded individuals, as well as the injuries on the fresh carcasses strongly suggest that mouse predation was the cause of death. Gough Island is home to virtually all Tristan Albatrosses, and Marion Island is the single most important breeding site for Wandering Albatrosses, home to about a quarter of all breeding birds. The death of breeding adults of these long-lived species emphasizes the urgent need to eradicate introduced mice from these islands.

MAKING WAVES: Effluent to estuary: Does sunshine or shade reduce downstream footprints of cities? - Michael Hutchins; Andrew Sweetman; Christopher Barry; Peter Berg; Charles George; Amy Pickard; Yueming Qu (Water Research, 2023)

Peptide mass fingerprinting as a tool to assess micromammal biodiversity in Pleistocene South Africa: The case of Klipdrift Shelter - Turid Hillestad Nel; Carli Peters; Kristine Korzow Richter; Christopher Henshilwood; Karen van Niekerk; Katerina Douka (Quaternary Science Reviews, 2023)

Practical Guide to Measuring Wetland Carbon Pools and Fluxes - Sheel Bansal; Irena F. Creed; Brian A. Tangen; Scott D. Bridgham; Ankur R. Desai; Ken W. Krauss; Scott C. Neubauer; Gregory B. Noe; Donald O. Rosenberry; Carl Trettin; Kimberly P. Wickland; Scott T. Allen; et al. (Wetlands, 2023)
Wetlands cover a small portion of the world, but have disproportionate influence on global carbon (C) sequestration, carbon dioxide and methane emissions, and aquatic C fluxes. However, the underlying biogeochemical processes that affect wetland C pools and fluxes are complex and dynamic, making measurements of wetland C challenging. Over decades of research, many observational, experimental, and analytical approaches have been developed to understand and quantify pools and fluxes of wetland C. Sampling approaches range in their representation of wetland C from short to long timeframes and local to landscape spatial scales. This review summarizes common and cutting-edge methodological approaches for quantifying wetland C pools and fluxes. We first define each of the major C pools and fluxes and provide rationale for their importance to wetland C dynamics. For each approach, we clarify what component of wetland C is measured and its spatial and temporal representativeness and constraints. We describe practical considerations for each approach, such as where and when an approach is typically used, who can conduct the measurements (expertise, training requirements), and how approaches are conducted, including considerations on equipment complexity and costs. Finally, we review key covariates and ancillary measurements that enhance the interpretation of findings and facilitate model development. The protocols that we describe to measure soil, water, vegetation, and gases are also relevant for related disciplines such as ecology. Improved quality and consistency of data collection and reporting across studies will help reduce global uncertainties and develop management strategies to use wetlands as nature-based climate solutions.

Using citizen science data to investigate annual survival rates of resident birds in relation to noise and light pollution - Lauren D. Pharr; Caren B. Cooper; Brian Evans; Christopher E. Moorman; Margaret A. Voss; Jelena Vukomanovic; Peter P. Marra (Urban Ecosystems, 2023)
Exponential increases in anthropogenic noise and light pollution have accompanied growth of the built environment. Noise and light cause negative consequences for birds, such as disrupted navigation during migration, mortality from collisions with windows and other infrastructure, and reduced reproductive success, as well as some positive consequences, such as expanded night niches for behaviors associated with feeding, territoriality, and mating. Relatively less is known about noise and light effects on annual survival of non-migratory birds, so we conducted an exploratory study to examine variation in adult survival rates of seven avian species in relation to noise and light pollution. We used 20 years of band-resight data collected as a part of the Neighborhood Nestwatch Program (NN), a citizen science project run by the Smithsonian Migratory Bird Center, at 242 sites in greater Washington, D.C. USA. We estimated apparent survival and documented species-specific relationships with light and noise. Gray Catbird ( Dumetella carolinensis ) and House Wren ( Thryothorus aedon ) survival decreased and American Robin ( Turdus migratorius ) survival increased with greater amounts of anthropogenic light. Anthropogenic noise had no relationship with apparent survival for any of the seven species. Life-history trade-offs between survival and reproduction may account for differences in species-specific effects of light pollution. Future research should examine the availability of other fine scale environmental conditions, such as tree canopy cover, that might buffer avian exposure to noise and light pollution.

Correction to: The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

Fertilisation kinetics among common Indo-Pacific broadcast spawning corals with distinct and shared functional traits - Elizabeth Buccheri; Gerard F. Ricardo; Russell C. Babcock; Peter J. Mumby; Christopher Doropoulos (Coral Reefs, 2023)
Indo-Pacific corals predominantly reproduce using synchronous mass spawning events to maximise fertilisation. However, as disturbances continue to thin population densities, the quantities of gametes released declines and colonies become more isolated, reducing the likelihood of cross-fertilisation. Local hydrodynamic conditions can promote or inhibit gamete contact; thus, the interaction between the abiotic environment and sperm density will determine the amount of time gametes interact. In this study, we investigated the sensitivity of reproduction to manipulations of two key limiting factors of fertilisation: sperm concentration and contact time between gametes. We explored fertilisation kinetics of phylogenetically and functionally similar and diverse coral taxa on the Great Barrier Reef and Western Australia ( Acropora digitifera, A. tenuis ; Coelastrea aspera, Platygyra daedalea ). Results indicate that fertilisation is optimised at sperm concentrations > 10 3 sperm mL −1 and contact times > 30 s, but the extent of these relationships is species-specific. All species showed clear differences in fertilisation success across contact times, although these differences were less distinct for A. tenuis and P. daedalea at very high sperm concentrations. Acropora digitifera and P. daedalea exhibited nonlinear trends with steep slopes of increased fertilisation success once sperm concentration surpassed values of 10 4 sperm mL −1 and 10 2 sperm mL −1 , respectively, followed by slight declines. Acropora tenuis and A. digitifera had the highest maximum fertilisation success, likely owing to beneficial evolved functional traits like large egg sizes. The present analysis underpins studies of fertilisation kinetics in natural reef populations to help inform management and restoration practices that assist population resilience and recovery.

Systematic Analysis of PTFE Monocusp Leaflet Design in a Patient-Based 3D in-Vitro Model of Tetralogy of Fallot - Xiaoya Zhang; Shannen B. Kizilski; Dominic P. Recco; Martha D. Chaillo Lizarraga; Nicholas E. Kneier; Noah E. Schulz; Christopher W. Baird; Peter E. Hammer; David M. Hoganson (Cardiovascular Engineering and Technology, 2023)

Elemental analysis of vertebrae discerns diadromous movements of threatened non‐marine elasmobranchs - Michael I. Grant; Peter M. Kyne; Julie James; Yi Hu; Sushmita Mukherji; Yolarnie Amepou; Leontine Baje; Andrew Chin; Grant Johnson; Tegan Lee; Brandon Mahan; Christopher Wurster; et al. (Journal of Fish Biology, 2023)
River sharks ( Glyphis spp.) and some sawfishes (Pristidae) inhabit riverine environments, although their long‐term habitat use patterns are poorly known. We investigated the diadromous movements of the northern river shark ( Glyphis garricki ), speartooth shark ( Glyphis glyphis ), narrow sawfish ( Anoxypristis cuspidata ), and largetooth sawfish ( Pristis pristis ) using in situ laser ablation inductively coupled plasma mass spectrometry (LA‐ICP‐MS) on vertebrae to recover elemental ratios over each individual's lifetime. We also measured elemental ratios for the bull shark ( Carcharhinus leucas ) and a range of inshore and offshore stenohaline marine species to assist in interpretation of results. Barium (Ba) was found to be an effective indicator of freshwater use, whereas lithium (Li) and strontium (Sr) were effective indicators of marine water use. The relationships between Ba and Li and Ba and Sr were negatively correlated, whereas the relationship between Li and Sr was positively correlated. Both river shark species had elemental signatures indicative of prolonged use of upper‐estuarine environments, whereas adults appear to mainly use lower‐estuarine environments rather than marine environments. Decreases in Li:Ba and Sr:Ba at the end of the prenatal growth zone of P. pristis samples indicated that parturition likely occurs in fresh water. There was limited evidence of prolonged riverine habitat use for A. cuspidata . The results of this study support elemental–environment relationships observed in teleost otoliths and indicate that in situ LA‐ICP‐MS elemental characterization is applicable to a wide range of elasmobranch species as a discriminator for use and movement across salinity gradients. A greater understanding of processes that lead to element incorporation in vertebrae, and relative concentrations in vertebrae with respect to the ambient environment, will improve the applicability of elemental analysis to understand movements across the life history of elasmobranchs into the future.

Association between major histocompatibility complex haplotypes and susceptibility of unvaccinated and vaccinated cattle to paratuberculosis - Anabel A. Garcia; Karren M. Plain; Peter C. Thomson; Aaron J. Thomas; Christopher J. Davies; Jenny-Ann L.M.L. Toribio; Richard J. Whittington (Veterinary Immunology and Immunopathology, 2023)

The potential of Burkholderia thailandensis E264 for co-valorization of C5 and C6 sugars into multiple value-added bio-products - Warren Blunt; Catherine Blanchard; Christopher Doyle; Vinicio Vasquez; Mengwei Ye; Peter Adewale; Yali Liu; Krista Morley; Fanny Monteil-Rivera (Bioresource Technology, 2023)

High-pressure melting in metapelites of a 2 Ga old subducted oceanic crust (Usagaran belt, Tanzania): implications from melt inclusions, fluid inclusions and thermodynamic modelling - Petra Herms; Peter Raase; Christopher Giehl; László E. Aradi; Tobias Fußwinkel; Arno Rohrbach; Andreas Möller (Contributions to Mineralogy and Petrology, 2023)
Investigation of polymineralic melt inclusions preserved in garnet of eclogite-facies metapelites of the Usagaran belt, Tanzania, is of particular importance as these metapelites, intercalated in oceanic metabasites, document the rare case of partial melting at high temperatures in a subducted oceanic crust. With an age of 2 Ga the rocks represent one of the oldest oceanic crusts and confirm a subduction process already at Paleoproterozoic times. Partial melting probably was initiated by dehydration melting under the presence of a CO 2 -rich fluid phase. The melt is preserved in siliceous polymineralic inclusions, while CO 2 locally reacted with the garnet host to form dolomite-quartz-kyanite inclusions. During this reaction, the REE spectrum of garnet is adopted by the dolomite. Furthermore, graphite inclusions in garnet must have precipitated from the CO 2 fluid by reduction. The highly ordered graphite structure indicates a formation temperature of at least 700 °C. Rehomogenization experiments of the siliceous polymineralic inclusions yield a homogeneous melt of rhyolitic, peraluminous composition. Thermodynamic modelling enables to deduce a P–T path in accordance with high P–T conditions (minimum 2.0 GPa, 900 °C) where a partial melt formed due to phengite breakdown leading to the preserved peak mineral assemblage garnet, alkali feldspar, kyanite, quartz and rutile. A very fast uplift of the oceanic crustal rocks can be deduced from the occurrence of very finely exsolved metastable ternary feldspar and from the preserved prograde zoning in garnet.

Distribution and structure of deep-sea demersal fish assemblages across the central and western Pacific Ocean using data from undersea imagery - Gina M. Selig; Jeffrey C. Drazen; Peter J. Auster; Bruce C. Mundy; Christopher D. Kelley (Frontiers in Marine Science, 2023)
Demersal deep-sea fish assemblages from islands and seamounts are poorly described, even in the Hawaiian archipelago. Knowledge across all depths, in similar settings, is even sparser for other archipelagos in the central and western Pacific. However, recent remotely operated vehicle (ROV) explorations and archived video from human-occupied submersible dives conducted by the Hawai`i Undersea Research Laboratory (HURL) provide an opportunity to explore the structure of these assemblages. Here we describe demersal fish assemblages across the central and western Pacific, including in four Marine National Monuments, and examine the relationship of the assemblages to depth and environmental conditions. We used data collected from 227 underwater vehicle dives resulting in the identification of 24,837 individuals belonging to 89 families and 175 genera. The most frequently occurring genera at depths of 250-500 m were Epigonus , Setarches , Polymixia , and Antigonia , between 500-1000 m were Chlorophthalmus , Aldrovandia , and Neocyttus , and between 1000-3000 m were Synaphobranchus , Kumba , Halosaurus , Ilyophis , and Ipnops . There are strong changes in the fish assemblages with depth and region, and assemblages become more similar between regions with greater depth. Depth and region explained the most variance in assemblage structure followed by seafloor particulate organic carbon flux (a food supply proxy), concentrations of dissolved oxygen, and salinity. The Line Islands and Tokelau Ridge had the highest values of seafloor particulate organic carbon flux for all depth zones investigated (250-3000 m) and the highest abundance of fishes at 250-500 m and 500-1000 m, respectively. Taxon accumulation curves indicated that diversity at the genus level within all regions and depth bins (except 1000-2000 m and 2000-3000 m) had not been reached with the existing sampling effort. However, when combining samples from all regions, diversity generally appeared to decrease with depth. Overall, this study demonstrates that there are significant regional differences in the composition of the deep-sea fish fauna as well as differences across depth. Such distribution patterns suggest that the four Marine National Monuments (Papahānaumokuākea, Marianas Trench, Pacific Remote Islands, and Rose Atoll Marine National Monuments, encompassing an area of 3,063,223 km 2 ) are not replicates of diversity, but complementary components of the regional fauna.

Why humans kill animals and why we cannot avoid it - Benjamin L. Allen; Christopher Bobier; Stuart Dawson; Peter J.S. Fleming; Jordan Hampton; David Jachowski; Graham I.H. Kerley; John D.C. Linnell; Kelly Marnewick; Liaan Minnie; Mike Muthersbaugh; M. Justin O'Riain; et al. (Science of The Total Environment, 2023)

Hypoxia vulnerability in the salmon watersheds of Southeast Alaska - Christopher J. Sergeant; J. Ryan Bellmore; Rebecca A. Bellmore; Jeffrey A. Falke; Franz J. Mueter; Peter A.H. Westley (Science of The Total Environment, 2023)

Comparative analyses of covariance matrix adaptation and iterative ensemble smoother on high-dimensional inverse problems in high-resolution groundwater modeling - Shuo Yang; Frank T.-C. Tsai; Peter Bacopoulos; Christopher E. Kees (Journal of Hydrology, 2023)

Cell-wise robust covariance estimation for compositions, with application to geochemical data - Christopher Rieser; Kamila Fačevicová; Peter Filzmoser (Journal of Geochemical Exploration, 2023)

Sustainability of bioenergy – Mapping the risks & benefits to inform future bioenergy systems - Andrew James Welfle; Alberto Almena; Muhammad Naveed Arshad; Scott William Banks; Isabela Butnar; Katie Jane Chong; SamuelJ.G. Cooper; Helen Daly; Samira Garcia Freites; Fatih Güleç; Christopher Hardacre; Robert Holland; et al. (Biomass and Bioenergy, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Assessing efficiency of fine-mapping obesity-associated variants through leveraging ancestry architecture and functional annotation using PAGE and UKBB cohorts - Mohammad Yaser Anwar; Mariaelisa Graff; Heather M. Highland; Roelof Smit; Zhe Wang; Victoria L. Buchanan; Kristin L. Young; Eimear E. Kenny; Lindsay Fernandez-Rhodes; Simin Liu; Themistocles Assimes; David O. Garcia; et al. (Human Genetics, 2023)

Transcatheter Pulmonary Artery Banding in High-Risk Neonates: In-Vitro Study Provoked by Initial Clinical Experience - Shannen B. Kizilski; Dominic P. Recco; Francesca Sperotto; Nora Lang; Peter E. Hammer; Christopher W. Baird; Nicola Maschietto; David M. Hoganson (Cardiovascular Engineering and Technology, 2023)

A marine protected area network does not confer community structure resilience to a marine heatwave across coastal ecosystems - Joshua G. Smith; Christopher M. Free; Cori Lopazanski; Julien Brun; Clarissa R. Anderson; Mark H. Carr; Joachim Claudet; Jenifer E. Dugan; Jacob G. Eurich; Tessa B. Francis; Scott L. Hamilton; David Mouillot; et al. (Global Change Biology, 2023)
Marine protected areas (MPAs) have gained attention as a conservation tool for enhancing ecosystem resilience to climate change. However, empirical evidence explicitly linking MPAs to enhanced ecological resilience is limited and mixed. To better understand whether MPAs can buffer climate impacts, we tested the resistance and recovery of marine communities to the 2014–2016 Northeast Pacific heatwave in the largest scientifically designed MPA network in the world off the coast of California, United States. The network consists of 124 MPAs (48 no‐take state marine reserves, and 76 partial‐take or special regulation conservation areas) implemented at different times, with full implementation completed in 2012. We compared fish, benthic invertebrate, and macroalgal community structure inside and outside of 13 no‐take MPAs across rocky intertidal, kelp forest, shallow reef, and deep reef nearshore habitats in California's Central Coast region from 2007 to 2020. We also explored whether MPA features, including age, size, depth, proportion rock, historic fishing pressure, habitat diversity and richness, connectivity, and fish biomass response ratios (proxy for ecological performance), conferred climate resilience for kelp forest and rocky intertidal habitats spanning 28 MPAs across the full network. Ecological communities dramatically shifted due to the marine heatwave across all four nearshore habitats, and MPAs did not facilitate habitat‐wide resistance or recovery. Only in protected rocky intertidal habitats did community structure significantly resist marine heatwave impacts. Community shifts were associated with a pronounced decline in the relative proportion of cold water species and an increase in warm water species. MPA features did not explain resistance or recovery to the marine heatwave. Collectively, our findings suggest that MPAs have limited ability to mitigate the impacts of marine heatwaves on community structure. Given that mechanisms of resilience to climate perturbations are complex, there is a clear need to expand assessments of ecosystem‐wide consequences resulting from acute climate‐driven perturbations, and the potential role of regulatory protection in mitigating community structure changes.

The unroofing of Archean crustal domes as recorded by detrital zircon and apatite - Anthony J.I. Clarke; Christopher L. Kirkland; Stijn Glorie; Jack Gillespie; Peter D. Kinny (Precambrian Research, 2023)

Field measurements of cable self-burial in a sandy marine environment - Christopher A. Unsworth; Martin J. Austin; Katrien J.J. Van Landeghem; Amelia J. Couldrey; Richard J.S. Whitehouse; Ben Lincoln; Siobhan Doole; Peter Worrall (Coastal Engineering, 2023)

The Ontology of Biological Attributes (OBA)—computational traits for the life sciences - Ray Stefancsik; James P. Balhoff; Meghan A. Balk; Robyn L. Ball; Susan M. Bello; Anita R. Caron; Elissa J. Chesler; Vinicius de Souza; Sarah Gehrke; Melissa Haendel; Laura W. Harris; Nomi L. Harris; et al. (Mammalian Genome, 2023)
Existing phenotype ontologies were originally developed to represent phenotypes that manifest as a character state in relation to a wild-type or other reference. However, these do not include the phenotypic trait or attribute categories required for the annotation of genome-wide association studies (GWAS), Quantitative Trait Loci (QTL) mappings or any population-focussed measurable trait data. The integration of trait and biological attribute information with an ever increasing body of chemical, environmental and biological data greatly facilitates computational analyses and it is also highly relevant to biomedical and clinical applications. The Ontology of Biological Attributes (OBA) is a formalised, species-independent collection of interoperable phenotypic trait categories that is intended to fulfil a data integration role. OBA is a standardised representational framework for observable attributes that are characteristics of biological entities, organisms, or parts of organisms. OBA has a modular design which provides several benefits for users and data integrators, including an automated and meaningful classification of trait terms computed on the basis of logical inferences drawn from domain-specific ontologies for cells, anatomical and other relevant entities. The logical axioms in OBA also provide a previously missing bridge that can computationally link Mendelian phenotypes with GWAS and quantitative traits. The term components in OBA provide semantic links and enable knowledge and data integration across specialised research community boundaries, thereby breaking silos.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Narrow root cone angle promotes deeper rooting, cooler canopy temperatures and higher grain yield in a rice (Oryza sativa L.) recombinant inbred line population grown under different water availabilities in aerobic production systems - Ricky Vinarao; Christopher Proud; Peter Snell; Shu Fukai; Jaquie Mitchell (Field Crops Research, 2023)

The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

Dissolved inorganic and organic carbon export from tile-drained midwestern agricultural systems - Keith E. Schilling; Matthew T. Streeter; Christopher S. Jones; Peter J. Jacobson (Science of The Total Environment, 2023)

Forested watersheds provide the highest water quality among all land cover types, but the benefit of this ecosystem service depends on landscape context - Peter V. Caldwell; Katherine L. Martin; James M. Vose; Justin S. Baker; Travis W. Warziniack; Jennifer K. Costanza; Gregory E. Frey; Arpita Nehra; Christopher M. Mihiar (Science of The Total Environment, 2023)

Use-up day and flexible recipes: Reducing household food waste by helping families prepare food they already have - A. Cooper; R. Lion; O.E. Rodriguez-Sierra; P. Jeffrey; D. Thomson; K. Peters; L. Christopher; M.J.H. Zhu; L. Wistrand; P. van der Werf; E. van Herpen (Resources, Conservation and Recycling, 2023)

Lichens as spatially transferable bioindicators for monitoring nitrogen pollution - Jay Delves; Jason E.J. Lewis; Niaz Ali; Saeed A. Asad; Sudipto Chatterjee; Peter D. Crittenden; Matthew Jones; Aysha Kiran; Bishnu Prasad Pandey; David Reay; Subodh Sharma; Dendup Tshering; et al. (Environmental Pollution, 2023)

Role of Indigenous and local knowledge in seasonal forecasts and climate adaptation: A case study of smallholder farmers in Chiredzi, Zimbabwe - Luckson Zvobgo; Peter Johnston; Oladapo M. Olagbegi; Nicholas P. Simpson; Christopher H. Trisos (Environmental Science & Policy, 2023)

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

Geochemical assessment and hydrocarbon potential of Oligocene–Pliocene source rocks from northeast onshore Nile Delta, Egypt - Ahmed Khairy; Waleed Sh. El Diasty; Clement N. Uguna; Kenneth E. Peters; Christopher H. Vane; Colin E. Snape; Will Meredith (International Journal of Coal Geology, 2023)

Perceptions of accountability and trust in the regulatory governance of wood burning stove sustainability: Survey evidence from the post-Brexit UK - Matthew Wood; Chantelle Wood; Peter Styring; Christopher R. Jones; Jeffery K. Smith; Marianne Day; Rohit Chakraborty; Gloria Mensah (Energy Policy, 2023)

Sprint cycling rate of torque development associates with strength measurement in trained cyclists - Shannon Connolly; Peter Peeling; Martyn J. Binnie; Paul S. R. Goods; Christopher Latella; Janet L. Taylor; Anthony J. Blazevich; Wouter P. Timmerman; Chris R. Abbiss (European Journal of Applied Physiology, 2023)
Purpose A cyclist’s rate of force/torque development (RFD/RTD) and peak force/torque can be measured during single-joint or whole-body isometric tests, or during cycling. However, there is limited understanding of the relationship between these measures, and of the mechanisms that contribute to each measure. Therefore, we examined the: (i) relationship between quadriceps central and peripheral neuromuscular function with RFD/RTD in isometric knee extension, isometric mid-thigh pull (IMTP), and sprint cycling; and (ii) relationship among RFD/RTD and peak force/torque between protocols. Methods Eighteen trained cyclists completed two familiarisation and two experimental sessions. Each session involved an isometric knee extension, IMTP, and sprint cycling protocol, where peak force/torque, average and peak RFD/RTD, and early (0–100 ms) and late (0–200 ms) RFD/RTD were measured. Additionally, measures of quadriceps central and peripheral neuromuscular function were assessed during the knee extension. Results Strong relationships were observed between quadriceps early EMG activity (EMG 50 /M) and knee extension RTD ( r or ρ = 0.51–0.65) and IMTP late RFD ( r = 0.51), and between cycling early or late RTD and peak twitch torque ( r or ρ = 0.70–0.75). Strong-to-very strong relationships were observed between knee extension, IMTP, and sprint cycling for peak force/torque, early and late RFD/RTD, and peak RFD/RTD ( r or ρ = 0.59–0.80). Conclusion In trained cyclists, knee extension RTD or IMTP late RFD are related to measures of quadriceps central neuromuscular function, while cycling RTD is related to measures of quadriceps peripheral neuromuscular function. Further, the strong associations among force/torque measures between tasks indicate a level of transferability across tasks.

Correction to: Prioritizing river basins for intensive monitoring and assessment by the US Geological Survey - Peter C. Van Metre; Sharon Qi; Jeffrey Deacon; Cheryl Dieter; Jessica M. Driscoll; Michael Fienen; Terry Kenney; Patrick Lambert; David Lesmes; Christopher A. Mason; Anke Mueller-Solger; Marylynn Musgrove; et al. (Environmental Monitoring and Assessment, 2023)

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Networking the forest infrastructure towards near real-time monitoring – A white paper - Roman Zweifel; Christoforos Pappas; Richard L. Peters; Flurin Babst; Daniel Balanzategui; David Basler; Ana Bastos; Mirela Beloiu; Nina Buchmann; Arun K. Bose; Sabine Braun; Alexander Damm; et al. (Science of The Total Environment, 2023)

The phylogeny and global biogeography of Primulaceae based on high-throughput DNA sequence data - Drew A. Larson; Andre S. Chanderbali; Olivier Maurin; Deise J.P. Gonçalves; Christopher W. Dick; Douglas E. Soltis; Pamela S. Soltis; Peter W. Fritsch; James J. Clarkson; Aurélie Grall; Nina M.J. Davies; Isabel Larridon; et al. (Molecular Phylogenetics and Evolution, 2023)

Environmental surveillance detects circulating vaccine-derived poliovirus type 2 that was undetected by acute flaccid paralysis surveillance in 2021 in Uganda - Phionah Tushabe; Josephine Bwogi; James Peter Eliku; Francis Aine; Molly Birungi; Joseph Gaizi; Lucy Nakabazzi; Theopista Kabaliisa; Irene Turyahabwe; Prossy Namuwulya; Mary Bridget Nanteza; Henry Bukenya; et al. (Archives of Virology, 2023)
The success of the global polio eradication initiative is threatened by the genetic instability of the oral polio vaccine, which can result in the emergence of pathogenic vaccine-derived polioviruses following prolonged replication in the guts of individuals with primary immune deficiencies or in communities with low vaccination coverage. Through environmental surveillance, circulating vaccine-derived poliovirus type 2 was detected in Uganda in the absence of detection by acute flaccid paralysis (AFP) surveillance. This underscores the sensitivity of environmental surveillance and emphasizes its usefulness in supplementing AFP surveillance for poliovirus infections in the race towards global polio eradication.

Inflammation and vascular remodeling in COVID-19 hearts - Christopher Werlein; Maximilian Ackermann; Helge Stark; Harshit R. Shah; Alexandar Tzankov; Jasmin Dinonne Haslbauer; Saskia von Stillfried; Roman David Bülow; Ali El-Armouche; Stephan Kuenzel; Jan Lukas Robertus; Marius Reichardt; et al. (Angiogenesis, 2023)
A wide range of cardiac symptoms have been observed in COVID-19 patients, often significantly influencing the clinical outcome. While the pathophysiology of pulmonary COVID-19 manifestation has been substantially unraveled, the underlying pathomechanisms of cardiac involvement in COVID-19 are largely unknown. In this multicentre study, we performed a comprehensive analysis of heart samples from 24 autopsies with confirmed SARS-CoV-2 infection and compared them to samples of age-matched Influenza H1N1 A ( n = 16), lymphocytic non-influenza myocarditis cases ( n = 8), and non-inflamed heart tissue ( n = 9). We employed conventional histopathology, multiplexed immunohistochemistry (MPX), microvascular corrosion casting, scanning electron microscopy, X-ray phase-contrast tomography using synchrotron radiation, and direct multiplexed measurements of gene expression, to assess morphological and molecular changes holistically. Based on histopathology, none of the COVID-19 samples fulfilled the established diagnostic criteria of viral myocarditis. However, quantification via MPX showed a significant increase in perivascular CD11b/TIE2 + —macrophages in COVID-19 over time, which was not observed in influenza or non-SARS-CoV-2 viral myocarditis patients. Ultrastructurally, a significant increase in intussusceptive angiogenesis as well as multifocal thrombi, inapparent in conventional morphological analysis, could be demonstrated. In line with this, on a molecular level, COVID-19 hearts displayed a distinct expression pattern of genes primarily coding for factors involved in angiogenesis and epithelial-mesenchymal transition (EMT), changes not seen in any of the other patient groups. We conclude that cardiac involvement in COVID-19 is an angiocentric macrophage-driven inflammatory process, distinct from classical anti-viral inflammatory responses, and substantially underappreciated by conventional histopathologic analysis. For the first time, we have observed intussusceptive angiogenesis in cardiac tissue, which we previously identified as the linchpin of vascular remodeling in COVID-19 pneumonia, as a pathognomic sign in affected hearts. Moreover, we identified CD11b + /TIE2 + macrophages as the drivers of intussusceptive angiogenesis and set forward a putative model for the molecular regulation of vascular alterations.

Australian consumers’ attitudes to packaged fresh meat products with added microbial bioprotective cultures for shelf-life extension - Michelle M. Xu; Mandeep Kaur; Christopher J. Pillidge; Peter J. Torley (Meat Science, 2023)

Contrasting topography of Rodinia and Gondwana recorded by continental-arc basalts - Gui-Mei Lu; Peter A. Cawood; Christopher J. Spencer; Andrey Bekker; Yi-Gang Xu; Zhuosen Yao; Wei Wang (Lithos, 2023)

Organic matter sulfurization and organic carbon burial in the Mesoproterozoic - Morgan Reed Raven; Peter W. Crockford; Malcolm S.W. Hodgskiss; Timothy W. Lyons; Christopher J. Tino; Samuel M. Webb (Geochimica et Cosmochimica Acta, 2023)

Runnels Reverse Mega-pool Expansion and Improve Marsh Resiliency in the Great Marsh, Massachusetts (USA) - J. Grant McKown; David M. Burdick; Gregg E. Moore; Christopher R. Peter; Andrew R. Payne; Jennifer L. Gibson (Wetlands, 2023)

SCAview: an Intuitive Visual Approach to the Integrative Analysis of Clinical Data in Spinocerebellar Ataxias - Mischa Uebachs; Philipp Wegner; Sebastian Schaaf; Simon Kugai; Heike Jacobi; Sheng-Han Kuo; Tetsuo Ashizawa; Juliane Fluck; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; Arron Cook; et al. (The Cerebellum, 2023)
With SCAview, we present a prompt and comprehensive tool that enables scientists to browse large datasets of the most common spinocerebellar ataxias intuitively and without technical effort. Basic concept is a visualization of data, with a graphical handling and filtering to select and define subgroups and their comparison. Several plot types to visualize all data points resulting from the selected attributes are provided. The underlying synthetic cohort is based on clinical data from five different European and US longitudinal multicenter cohorts in spinocerebellar ataxia type 1, 2, 3, and 6 (SCA1, 2, 3, and 6) comprising > 1400 patients with overall > 5500 visits. First, we developed a common data model to integrate the clinical, demographic, and characterizing data of each source cohort. Second, the available datasets from each cohort were mapped onto the data model. Third, we created a synthetic cohort based on the cleaned dataset. With SCAview, we demonstrate the feasibility of mapping cohort data from different sources onto a common data model. The resulting browser-based visualization tool with a thoroughly graphical handling of the data offers researchers the unique possibility to visualize relationships and distributions of clinical data, to define subgroups and to further investigate them without any technical effort. Access to SCAview can be requested via the Ataxia Global Initiative and is free of charge.

Nitrification rate in dairy cattle urine patches can be inhibited by changing soil bioavailable Cu concentration - Dumsane Themba Matse; Paramsothy Jeyakumar; Peter Bishop; Christopher W.N. Anderson (Environmental Pollution, 2023)

Residual correlation and ensemble modelling to improve crop and grassland models - Renáta Sándor; Fiona Ehrhardt; Peter Grace; Sylvie Recous; Pete Smith; Val Snow; Jean-François Soussana; Bruno Basso; Arti Bhatia; Lorenzo Brilli; Jordi Doltra; Christopher D. Dorich; et al. (Environmental Modelling & Software, 2023)

The impacts of a global pandemic on the efficacy and stability of contemporary wildlife conservation: South Africa as a case study - David A. Ehlers Smith; Yvette C. Ehlers Smith; Harriet T. Davies-Mostert; Lindy J. Thompson; Daniel M. Parker; Deon de Villiers; Dean Ricketts; Brent Coverdale; Peter J. Roberts; Christopher Kelly; Duncan N. Macfadyen; Nomthandazo S. Manqele; et al. (Ambio, 2023)
Conservationists speculated on potential benefits to wildlife of lockdown restrictions because of the COVID-19 pandemic but voiced concern that restrictions impeded nature conservation. We assessed the effects of lockdown restrictions on biodiversity conservation in South Africa, a biodiverse country with economic inequality and reliance on wildlife resources. We solicited expert opinion using the IUCN’s Threats Classification Scheme to structure a questionnaire and illustrated responses with individual case studies from government parastatal and non-governmental conservation organisations. The most highly reported threats were biological resource use, residential/commercial developments, invasive species, and human intrusions. The trends reported by 90 survey respondents were supported by case studies using environmental compliance data from parastatal conservation organisations. Lack of tourism revenue and funding were cited as hindrances to conservation. Mechanisms to prevent environmental degradation in the face of global emergencies must be implemented and ‘ring-fenced’ to ensure conservation is not a casualty during future global crises.

Breeding bird abundance and species diversity greatest in high-severity wildfire patches in central hardwood forests - Cathryn H. Greenberg; Christopher E. Moorman; Katherine J. Elliott; Katherine Martin; Mark Hopey; Peter V. Caldwell (Forest Ecology and Management, 2023)

Temperature mapping of non-photochemical quenching in Chlorella vulgaris - Andrei Herdean; Christopher Hall; David J. Hughes; Unnikrishnan Kuzhiumparambil; Bernardo Campos Diocaretz; Peter J. Ralph (Photosynthesis Research, 2023)
Light intensity and temperature independently impact all parts of the photosynthetic machinery in plants and algae. Yet to date, the vast majority of pulse amplitude modulated (PAM) chlorophyll a fluorescence measurements have been performed at well-defined light intensities, but rarely at well-defined temperatures. In this work, we show that PAM measurements performed at various temperatures produce vastly different results in the chlorophyte Chlorella vulgaris . Using a recently developed Phenoplate technique to map quantum yield of Photosystem II (Y(II)) and non-photochemical quenching (NPQ) as a function of temperature, we show that the fast-relaxing NPQ follows an inverse normal distribution with respect to temperature and appears insensitive to previous temperature acclimation. The slow-relaxing or residual NPQ after 5 minutes of dark recovery follows a normal distribution similar to Y(II) but with a peak in the higher temperature range. Surprisingly, higher slow- and fast-relaxing NPQ values were observed in high-light relative to low-light acclimated cultures. Y(II) values peaked at the adaptation temperature regardless of temperature or light acclimation. Our novel findings show the complete temperature working spectrum of Y(II) and how excess energy quenching is managed across a wide range of temperatures in the model microalgal species C. vulgaris . Finally, we draw attention to the fact that the effect of the temperature component in PAM measurements has been wildly underestimated, and results from experiments at room temperature can be misleading.

Edible algae allergenicity – a short report - Christopher A. James; Simon Welham; Peter Rose (Journal of Applied Phycology, 2023)
The use of seaweed and algal derived products in the food industry has grown rapidly in recent times. Major areas of expansion have been in Western countries where algae derived commodities are being utilised as edible foods or sources of high value ingredients. However, studies focused on potential allergenicity attributed to these food items, prevalence of allergenicity, and public health awareness are limited. Therefore, the current research summarises the existing literature focused on algal induced allergy in humans. Of the available literature, a total of 937 titles were identified, and 33 articles underwent subsequent full-text screening. Most research focused on prevalence and were derived from studies conducted in Europe (58%), North America and Canada (33%), and the remainder Australia and South Korea (9%). No studies addressed the need for public education or labelling of algal products. Our review reports that the available evidence identified points to algal derived products as being potential sources of allergens in the human food chain. Several components have been characterised that are shown to induce allergic responses in humans. Few studies have assessed the prevalence of algal allergenicity in the general population and as such further research is warranted given the increased usage of these products in the food industry.

High polygenic risk score for exceptional longevity is associated with a healthy metabolic profile - Mary Revelas; Anbupalam Thalamuthu; Anna Zettergren; Christopher Oldmeadow; Jenna Najar; Nazib M. Seidu; Nicola J. Armstrong; Carlos Riveros; John B. Kwok; Peter R. Schofield; Julian N. Trollor; Margda Waern; et al. (GeroScience, 2023)
Healthy metabolic measures in humans are associated with longevity. Dysregulation leads to metabolic syndrome (MetS) and negative health outcomes. Recent exceptional longevity (EL) genome wide association studies have facilitated estimation of an individual’s polygenic risk score (PRS) for EL. We tested the hypothesis that individuals with high ELPRS have a low prevalence of MetS. Participants were from five cohorts of middle-aged to older adults. The primary analyses were performed in the UK Biobank (UKBB) ( n = 407,800, 40–69 years). Replication analyses were undertaken using three Australian studies: Hunter Community Study ( n = 2122, 55–85 years), Older Australian Twins Study ( n = 539, 65–90 years) and Sydney Memory and Ageing Study ( n = 925, 70–90 years), as well as the Swedish Gothenburg H70 Birth Cohort Studies ( n = 2273, 70–93 years). MetS was defined using established criteria. Regressions and meta-analyses were performed with the ELPRS and MetS and its components. Generally, MetS prevalence (22–30%) was higher in the older cohorts. In the UKBB, high EL polygenic risk was associated with lower MetS prevalence (OR = 0.94, p = 1.84 × 10 –42 ) and its components ( p < 2.30 × 10 – 8 ). Meta-analyses of the replication cohorts showed nominal associations with MetS ( p = 0.028) and 3 MetS components ( p < 0.05). This work suggests individuals with a high polygenic risk for EL have a healthy metabolic profile promoting longevity.

Later growth onsets or reduced growth rates: What characterises legacy effects at the tree-ring level in conifers after the severe 2018 drought? - Tobias Walter Miller; Dominik Florian Stangler; Elena Larysch; Harald Honer; Heike Puhlmann; Dirk Schindler; Christopher Jung; Thomas Seifert; Andreas Rigling; Hans-Peter Kahle (Science of The Total Environment, 2023)

Genomic analyses reveal range‐wide devastation of sea otter populations - Annabel C. Beichman; Pooneh Kalhori; Christopher C. Kyriazis; Amber A. DeVries; Sergio Nigenda‐Morales; Gisela Heckel; Yolanda Schramm; Andrés Moreno‐Estrada; Douglas J. Kennett; Mark Hylkema; James Bodkin; Klaus‐Peter Koepfli; et al. (Molecular Ecology, 2023)
The genetic consequences of species‐wide declines are rarely quantified because the timing and extent of the decline varies across the species’ range. The sea otter ( Enhydra lutris ) is a unique model in this regard. Their dramatic decline from thousands to fewer than 100 individuals per population occurred range‐wide and nearly simultaneously due to the 18th–19th century fur trade. Consequently, each sea otter population represents an independent natural experiment of recovery after extreme population decline. We designed sequence capture probes for 50 Mb of sea otter exonic and neutral genomic regions. We sequenced 107 sea otters from five populations that span the species range to high coverage (18–76×) and three historical Californian samples from ~1500 and ~200 years ago to low coverage (1.5–3.5×). We observe distinct population structure and find that sea otters in California are the last survivors of a divergent lineage isolated for thousands of years and therefore warrant special conservation concern. We detect signals of extreme population decline in every surviving sea otter population and use this demographic history to design forward‐in‐time simulations of coding sequence. Our simulations indicate that this decline could lower the fitness of recovering populations for generations. However, the simulations also demonstrate how historically low effective population sizes prior to the fur trade may have mitigated the effects of population decline on genetic health. Our comprehensive approach shows how demographic inference from genomic data, coupled with simulations, allows assessment of extinction risk and different models of recovery.

Coral rubble dynamics in the Anthropocene and implications for reef recovery - Tania M. Kenyon; Christopher Doropoulos; Kennedy Wolfe; Gregory E. Webb; Sophie Dove; Daniel Harris; Peter J. Mumby (Limnology and Oceanography, 2023)
With rubble predicted to increase on coral reefs worldwide, we review the physical, biological, and ecological dynamics of rubble beds, with a focus on how rubble generation, mobilization, binding, and coral recruitment is expected to change on future reefs. Major disturbances, including storms and coral bleaching, are predicted to increase in intensity and frequency, and—like localized impacts including blast fishing and ship groundings—generate large quantities of coral rubble. Reefs will have increasingly smaller recovery windows between successive disturbances, leading to persistence of unstable rubble beds on reefs. With more severe storms and increased bioerosion on future reefs, rubble mobilization thresholds will be met more often as smaller, less complex rubble pieces are generated. If rubble remains stable for adequate time, it can be bound by organisms including sponges and coralline algae, and eventually be cemented. However, increasing rubble mobilization frequencies will reduce the time available for binding, while changing ocean chemistry could reduce the efficacy of calcifying binders. Ultimately, increased rubble cover will negatively impact coral recruitment into rubble beds. Rubble mobilization abrades and smothers corals, and rubble beds typically experience altered environmental and ecological conditions to the coral frameworks that precede them. Several knowledge gaps exist in relation to improved rubble mobilization thresholds, binding rates and strengths, and coral survival in varying rubble bed types and hydrodynamic regimes. Addressing these knowledge gaps will improve our ability to predict the recovery trajectory of rubble beds and assess the need for stabilization interventions.

Fatty acid profiles of more than 470 marine species from the Southern Hemisphere - Peter D. Nichols; Heidi R. Pethybridge; Bowen Zhang; Patti Virtue; Lauren Meyer; Zahirah Dhurmeea; Lara Marcus; Jessica A. Ericson; Nicole Hellessey; Sharon Every; Kathryn Wheatley; Christopher C. Parrish; et al. (Ecology, 2023)
Lipid and fatty acid datasets are commonly used to assess the nutritional composition of organisms, trophic ecology, and ecosystem dynamics. Lipids and their fatty acid constituents are essential nutrients to all forms of life because they contribute to biological processes such as energy flow and metabolism. Assessment of total lipids in tissues of organisms provides information on energy allocation and life‐history strategies and can be an indicator of nutritional condition. The analysis of an organism's fatty acids is a widely used technique for assessing nutrient and energy transfer, and dietary interactions in food webs. Although there have been many published regional studies that assessed lipid and fatty acid compositions, many only report the mean values of the most abundant fatty acids. There are limited individual records available for wider use in intercomparison or macro‐scale studies. This dataset consists of 4856 records of individual and pooled samples of at least 470 different marine consumer species sampled from tropical, temperate, and polar regions around Australia and in the Southern, Indian, and Pacific Oceans from 1989 to 2018. This includes data for a diverse range of taxa (zooplankton, fish, cephalopods, chondrichthyans, and marine mammals), size ranges (0.02 cm to ~13 m), and that cover a broad range of trophic positions (2.0–4.6). When known, we provide a record of species name, date of sampling, sampling location, body size, relative (%) measurements of tissue‐specific total lipid content and abundant fatty acids, and absolute content (mg 100 g −1 tissue) of eicosapentaenoic acid (EPA, 20:5n3) and docosahexaenoic acid (DHA, 22:6n3) as important long‐chain (≥C 20 ) polyunsaturated omega‐3 fatty acids. These records form a solid basis for comparative studies that will facilitate a broad understanding of the spatial and temporal distribution of marine lipids globally. The dataset also provides reference data for future dietary assessments of marine predators and model assessments of potential impacts of climate change on the availability of marine lipids and fatty acids. There are 480 data records within our data file for which the providers have requested that permission for reuse be granted, with the likely condition that they are included as a coauthor on the reporting of the dataset. Records with this condition are indicated by a “yes” under “Conditions_of_data_use” in Data S1: Marineconsumer_FAdata.csv (see Table 2 in Metadata S1 for more details). For all other data records marked as “No” under “Conditions_of_data_use,” there are no copyright restrictions for research and/or teaching purposes. We request that users acknowledge use of the data in publications, research proposals, websites, and other outlets via formal citation of this work and original data sources as applicable.

Correction to: Clinical trial-ready patient cohorts for multiple system atrophy: coupling biospecimen and iPSC banking to longitudinal deep-phenotyping - Alain Ndayisaba; Ariana T. Pitaro; Ashlan S. Willett; Kristie A. Jones; Claudio Melo de Gusmao; Abby L. Olsen; Jisoo Kim; Eero Rissanen; Jared K. Woods; Sharan R. Srinivasan; Anna Nagy; Amanda Nagy; et al. (The Cerebellum, 2022)

Decadal forest soil respiration following stem girdling - Elizabeth A. Clippard; Samuel I. Haruna; Peter S. Curtis; Cameron Clay; Ben Bond-Lamberty; Kayla Mathes; Christoph S. Vogel; Christopher M. Gough (Trees, 2022)

A science-based policy for managing free-roaming cats - Christopher A. Lepczyk; David C. Duffy; David M. Bird; Michael Calver; Dmitry Cherkassky; Linda Cherkassky; Christopher R. Dickman; David Hunter; David Jessup; Travis Longcore; Scott R. Loss; Kerrie Anne T. Loyd; et al. (Biological Invasions, 2022)

Accuracy, realism and general applicability of European forest models - Mats Mahnken; Maxime Cailleret; Alessio Collalti; Carlo Trotta; Corrado Biondo; Ettore D'Andrea; Daniela Dalmonech; Gina Marano; Annikki Mäkelä; Francesco Minunno; Mikko Peltoniemi; Volodymyr Trotsiuk; et al. (Global Change Biology, 2022)
Forest models are instrumental for understanding and projecting the impact of climate change on forests. A considerable number of forest models have been developed in the last decades. However, few systematic and comprehensive model comparisons have been performed in Europe that combine an evaluation of modelled carbon and water fluxes and forest structure. We evaluate 13 widely used, state‐of‐the‐art, stand‐scale forest models against field measurements of forest structure and eddy‐covariance data of carbon and water fluxes over multiple decades across an environmental gradient at nine typical European forest stands. We test the models' performance in three dimensions: accuracy of local predictions (agreement of modelled and observed annual data), realism of environmental responses (agreement of modelled and observed responses of daily gross primary productivity to temperature, radiation and vapour pressure deficit) and general applicability (proportion of European tree species covered). We find that multiple models are available that excel according to our three dimensions of model performance. For the accuracy of local predictions, variables related to forest structure have lower random and systematic errors than annual carbon and water flux variables. Moreover, the multi‐model ensemble mean provided overall more realistic daily productivity responses to environmental drivers across all sites than any single individual model. The general applicability of the models is high, as almost all models are currently able to cover Europe's common tree species. We show that forest models complement each other in their response to environmental drivers and that there are several cases in which individual models outperform the model ensemble. Our framework provides a first step to capturing essential differences between forest models that go beyond the most commonly used accuracy of predictions. Overall, this study provides a point of reference for future model work aimed at predicting climate impacts and supporting climate mitigation and adaptation measures in forests.

Linking changes in species composition and biomass in a globally distributed grassland experiment - Emma Ladouceur; Shane A. Blowes; Jonathan M. Chase; Adam T. Clark; Magda Garbowski; Juan Alberti; Carlos Alberto Arnillas; Jonathan D. Bakker; Isabel C. Barrio; Siddharth Bharath; Elizabeth T. Borer; Lars A. Brudvig; et al. (Ecology Letters, 2022)
Global change drivers, such as anthropogenic nutrient inputs, are increasing globally. Nutrient deposition simultaneously alters plant biodiversity, species composition and ecosystem processes like aboveground biomass production. These changes are underpinned by species extinction, colonisation and shifting relative abundance. Here, we use the Price equation to quantify and link the contributions of species that are lost, gained or that persist to change in aboveground biomass in 59 experimental grassland sites. Under ambient (control) conditions, compositional and biomass turnover was high, and losses (i.e. local extinctions) were balanced by gains (i.e. colonisation). Under fertilisation, the decline in species richness resulted from increased species loss and decreases in species gained. Biomass increase under fertilisation resulted mostly from species that persist and to a lesser extent from species gained. Drivers of ecological change can interact relatively independently with diversity, composition and ecosystem processes and functions such as aboveground biomass due to the individual contributions of species lost, gained or persisting.

Temporal Stability of Seagrass Extent, Leaf Area, and Carbon Storage in St. Joseph Bay, Florida: a Semi-automated Remote Sensing Analysis - Marie Cindy Lebrasse; Blake A. Schaeffer; Megan M. Coffer; Peter J. Whitman; Richard C. Zimmerman; Victoria J. Hill; Kazi A. Islam; Jiang Li; Christopher L. Osburn (Estuaries and Coasts, 2022)
Seagrasses are globally recognized for their contribution to blue carbon sequestration. However, accurate quantification of their carbon storage capacity remains uncertain due, in part, to an incomplete inventory of global seagrass extent and assessment of its temporal variability. Furthermore, seagrasses are undergoing significant decline globally, which highlights the urgent need to develop change detection techniques applicable to both the scale of loss and the spatial complexity of coastal environments. This study applied a deep learning algorithm to a 30-year time series of Landsat 5 through 8 imagery to quantify seagrass extent, leaf area index (LAI), and belowground organic carbon (BGC) in St. Joseph Bay, Florida, between 1990 and 2020. Consistent with previous field-based observations regarding stability of seagrass extent throughout St. Joseph Bay, there was no temporal trend in seagrass extent (23 ± 3 km 2 , τ = 0.09, p = 0.59, n = 31), LAI (1.6 ± 0.2, τ = -0.13, p = 0.42, n = 31), or BGC (165 ± 19 g C m −2 , τ = - 0.01, p = 0.1, n = 31) over the 30-year study period. There were, however, six brief declines in seagrass extent between the years 2004 and 2019 following tropical cyclones, from which seagrasses recovered rapidly. Fine-scale interannual variability in seagrass extent, LAI, and BGC was unrelated to sea surface temperature or to climate variability associated with the El Niño-Southern Oscillation or the North Atlantic Oscillation. Although our temporal assessment showed that seagrass and its belowground carbon were stable in St. Joseph Bay from 1990 to 2020, forecasts suggest that environmental and climate pressures are ongoing, which highlights the importance of the method and time series presented here as a valuable tool to quantify decadal-scale variability in seagrass dynamics. Perhaps more importantly, our results can serve as a baseline against which we can monitor future change in seagrass communities and their blue carbon.

A novel method for identifying coded tags recorded on aquatic acoustic monitoring systems - Christopher D. Lowe; Nicolas J. C. Tregenza; Claudia J. Allen; Georgina E. Blow; Hanna Nuuttila; Chiara M. Bertelli; Anouska F. Mendzil; Thomas Stamp; Emma V. Sheehan; Peter Davies; Jonathan C. D. Gordon; Jonathan D. Bolland; et al. (Environmental Monitoring and Assessment, 2022)
Aquatic biotelemetry increasingly relies on using acoustic transmitters (‘tags’) that enable passive detection of tagged animals using fixed or mobile receivers. Both tracking methods are resource-limited, restricting the spatial area in which movements of highly mobile animals can be measured using proprietary detection systems. Transmissions from tags are recorded by underwater noise monitoring systems designed for other purposes, such as cetacean monitoring devices, which have been widely deployed in the marine environment; however, no tools currently exist to decode these detections, and thus valuable additional information on animal movements may be missed. Here, we describe simple hybrid methods, with potentially wide application, for obtaining information from otherwise unused data sources. The methods were developed using data from moored, acoustic cetacean detectors (C-PODs) and towed passive receiver arrays, often deployed to monitor the vocalisations of cetaceans, but any similarly formatted data source could be used. The method was applied to decode tag detections that were found to have come from two highly mobile fish species, bass ( Dicentrarchus labrax ) and Twaite shad ( Alosa fallax ), that had been tagged in other studies. Decoding results were validated using test tags; range testing data were used to demonstrate the relative efficiency of these receiver methods in detecting tags. This approach broadens the range of equipment from which acoustic tag detections can be decoded. Novel detections derived from the method could add significant value to past and present tracking studies at little additional cost, by providing new insights into the movement of mobile animals at sea.

Population genomics of a predatory mammal reveals patterns of decline and impacts of exposure to toxic toads - Brenton von Takach; Louis Ranjard; Christopher P. Burridge; Skye F. Cameron; Teigan Cremona; Mark D. B. Eldridge; Diana O. Fisher; Stephen Frankenberg; Brydie M. Hill; Rosemary Hohnen; Chris J. Jolly; Ella Kelly; et al. (Molecular Ecology, 2022)
Mammal declines across northern Australia are one of the major biodiversity loss events occurring globally. There has been no regional assessment of the implications of these species declines for genomic diversity. To address this, we conducted a species‐wide assessment of genomic diversity in the northern quoll ( Dasyurus hallucatus ), an Endangered marsupial carnivore. We used next generation sequencing methods to genotype 10,191 single nucleotide polymorphisms (SNPs) in 352 individuals from across a 3220‐km length of the continent, investigating patterns of population genomic structure and diversity, and identifying loci showing signals of putative selection. We found strong heterogeneity in the distribution of genomic diversity across the continent, characterized by (i) biogeographical barriers driving hierarchical population structure through long‐term isolation, and (ii) severe reductions in diversity resulting from population declines, exacerbated by the spread of introduced toxic cane toads ( Rhinella marina ). These results warn of a large ongoing loss of genomic diversity and associated adaptive capacity as mammals decline across northern Australia. Encouragingly, populations of the northern quoll established on toad‐free islands by translocations appear to have maintained most of the initial genomic diversity after 16 years. By mapping patterns of genomic diversity within and among populations, and investigating these patterns in the context of population declines, we can provide conservation managers with data critical to informed decision‐making. This includes the identification of populations that are candidates for genetic management, the importance of remnant island and insurance/translocated populations for the conservation of genetic diversity, and the characterization of putative evolutionarily significant units.

River chemistry constraints on the carbon capture potential of surficial enhanced rock weathering - Shuang Zhang; Noah J. Planavsky; Joachim Katchinoff; Peter A. Raymond; Yoshiki Kanzaki; Tom Reershemius; Christopher T. Reinhard (Limnology and Oceanography, 2022)
Technologies and approaches that remove and sequester carbon dioxide (CO 2 ) from Earth's atmosphere are likely to play a significant role in mitigating anthropogenic climate disruption in the coming century. Enhanced rock weathering (ERW) on the land surface is one extensively discussed approach toward carbon dioxide removal (CDR), but the capacity of rivers to carry dissolved products derived from ERW without CO 2 re‐release is largely unexplored, hindering a full understanding of the life cycle of ERW and its associated maximum CDR potential. Here, we use a conceptual model built upon river/stream carbonate chemistry to estimate the upper limits on the carbon transport potential (CTP) of rivers and groundwaters. Our model yields a riverine CTP ranging between 0.26–0.89 GtCO 2 yr −1 for the United States and 7.1–21.3 GtCO 2 yr −1 globally for accelerated silicate weathering, and between 0.090–0.37 GtCO 2 yr −1 for the United States and 2.5–8.8 GtCO 2 yr −1 globally for accelerated carbonate weathering. Although these limits will be challenging to achieve in practice, our results support the notion that the transport of dissolved constituents in surface waters is unlikely to be a primary bottleneck limiting the CDR potential of ERW. This supports the notion that accelerated mineral weathering should be considered as an additional component of greenhouse gas mitigation portfolios. However, future research on the kinetics of ERW reactions and river responses, along with consideration of possible added CO 2 emissions by activities needed to accomplish ERW, are needed for a more realistic quantification of the net CDR via ERW in the land–soil–river system.

Modeled approaches to estimating blue carbon accumulation with mangrove restoration to support a blue carbon accounting method for Australia - Catherine E. Lovelock; M. Fernanda Adame; Don W. Butler; Jeffrey J. Kelleway; Sabine Dittmann; Benedikt Fest; Karen J. King; Peter I. Macreadie; Katherine Mitchell; Mark Newnham; Anne Ola; Christopher J. Owers; et al. (Limnology and Oceanography, 2022)
The development and refinement of methods for estimating organic carbon accumulation in biomass and soils during mangrove restoration and rehabilitation can encourage uptake of restoration projects for their ecosystem services, including those of climate change mitigation, or blue carbon. To support the development of a blue carbon method for Australia under the Emission Reduction Fund scheme we investigated; (1) whether carbon accumulation data from natural mangroves could be used to estimate carbon accumulation during restoration; (2) modeling mangrove biomass accumulation; and (3) how modeled carbon accumulation could be achieved over heterogeneous sites. First, we assessed carbon accumulation in soil and biomass pools from the global literature, finding that estimating carbon accumulation using data from natural mangroves provided similar estimates as those for restored or rehabilitated mangroves. We assessed mangrove biomass accumulation from global chronosequence studies, which we used to develop regional models for estimating biomass accumulation with restoration in Australia using values from local natural mangroves. Estimating biomass carbon accumulation using site‐based means of stand biomass provided similar estimates as values estimated through use of regional means values stratified by elevation; and reduced overestimates of biomass carbon accumulation that were based on regional mean values. Modeling soil carbon accumulation over environmentally heterogeneous project sites can apply a similar approach, stratifying over variation in site elevation. Our analysis provides a strategy for modeling blue carbon pools for an Australian blue carbon method that accommodates regional differences and is based on data from natural mangroves.

A globally relevant change taxonomy and evidence‐based change framework for land monitoring - Richard M. Lucas; Sophia German; Graciela Metternicht; Rebecca K. Schmidt; Christopher J. Owers; Suzanne M. Prober; Anna E. Richards; Sally Tetreault‐Campbell; Kristen J. Williams; Norman Mueller; Belle Tissott; Sean M. T. Chua; et al. (Global Change Biology, 2022)
A globally relevant and standardized taxonomy and framework for consistently describing land cover change based on evidence is presented, which makes use of structured land cover taxonomies and is underpinned by the Driver‐Pressure‐State‐Impact‐Response (DPSIR) framework. The Global Change Taxonomy currently lists 246 classes based on the notation ‘impact (pressure)’, with this encompassing the consequence of observed change and associated reason(s), and uses scale‐independent terms that factor in time. Evidence for different impacts is gathered through temporal comparison (e.g., days, decades apart) of land cover classes constructed and described from Environmental Descriptors (EDs; state indicators) with pre‐defined measurement units (e.g., m, %) or categories (e.g., species type). Evidence for pressures, whether abiotic, biotic or human‐influenced, is similarly accumulated, but EDs often differ from those used to determine impacts. Each impact and pressure term is defined separately, allowing flexible combination into ‘impact (pressure)’ categories, and all are listed in an openly accessible glossary to ensure consistent use and common understanding. The taxonomy and framework are globally relevant and can reference EDs quantified on the ground, retrieved/classified remotely (from ground‐based, airborne or spaceborne sensors) or predicted through modelling. By providing capacity to more consistently describe change processes—including land degradation, desertification and ecosystem restoration—the overall framework addresses a wide and diverse range of local to international needs including those relevant to policy, socioeconomics and land management. Actions in response to impacts and pressures and monitoring towards targets are also supported to assist future planning, including impact mitigation actions.

Clinical Trial-Ready Patient Cohorts for Multiple System Atrophy: Coupling Biospecimen and iPSC Banking to Longitudinal Deep-Phenotyping - Alain Ndayisaba; Ariana T. Pitaro; Andrew S. Willett; Kristie A. Jones; Claudio Melo de Gusmao; Abby L. Olsen; Jisoo Kim; Eero Rissanen; Jared K. Woods; Sharan R. Srinivasan; Anna Nagy; Amanda Nagy; et al. (The Cerebellum, 2022)
Multiple system atrophy (MSA) is a fatal neurodegenerative disease of unknown etiology characterized by widespread aggregation of the protein alpha-synuclein in neurons and glia. Its orphan status, biological relationship to Parkinson’s disease (PD), and rapid progression have sparked interest in drug development. One significant obstacle to therapeutics is disease heterogeneity. Here, we share our process of developing a clinical trial-ready cohort of MSA patients (69 patients in 2 years) within an outpatient clinical setting, and recruiting 20 of these patients into a longitudinal “n-of-few” clinical trial paradigm. First, we deeply phenotype our patients with clinical scales (UMSARS, BARS, MoCA, NMSS, and UPSIT) and tests designed to establish early differential diagnosis (including volumetric MRI, FDG-PET, MIBG scan, polysomnography, genetic testing, autonomic function tests, skin biopsy) or disease activity (PBR06-TSPO). Second, we longitudinally collect biospecimens (blood, CSF, stool) and clinical, biometric, and imaging data to generate antecedent disease-progression scores. Third, in our Mass General Brigham SCiN study ( s tem c ells i n n eurodegeneration), we generate induced pluripotent stem cell (iPSC) models from our patients, matched to biospecimens, including postmortem brain. We present 38 iPSC lines derived from MSA patients and relevant disease controls (spinocerebellar ataxia and PD, including alpha-synuclein triplication cases), 22 matched to whole-genome sequenced postmortem brain. iPSC models may facilitate matching patients to appropriate therapies, particularly in heterogeneous diseases for which patient-specific biology may elude animal models. We anticipate that deeply phenotyped and genotyped patient cohorts matched to cellular models will increase the likelihood of success in clinical trials for MSA.

Biocompatible Cationic Lipoamino Acids as Counterions for Oral Administration of API-Ionic Liquids - Anthony Lai; Nathania Leong; Dan Zheng; Leigh Ford; Tri-Hung Nguyen; Hywel D. Williams; Hassan Benameur; Peter J. Scammells; Christopher J. H. Porter (Pharmaceutical Research, 2022)
Purpose The use of ionic liquids (ILs) in drug delivery has focused attention on non-toxic IL counterions. Cationic lipids can be used to form ILs with weakly acidic drugs to enhance drug loading in lipid-based formulations (LBFs). However, cationic lipids are typically toxic. Here we explore the use of lipoaminoacids (LAAs) as cationic IL counterions that degrade or digest in vivo to non-toxic components. Methods LAAs were synthesised via esterification of amino acids with fatty alcohols to produce potentially digestible cationic LAAs. The LAAs were employed to form ILs with tolfenamic acid (Tol) and the Tol ILs loaded into LBF and examined in vitro and in vivo . Results Cationic LAAs complexed with Tol to generate lipophilic Tol ILs with high drug loading in LBFs. Assessment of the LAA under simulated digestion conditions revealed that they were susceptible to enzymatic degradation under intestinal conditions, forming biocompatible FAs and amino acids. In vitro dispersion and digestion studies of Tol ILs revealed that formulations containing digestible Tol ILs were able to maintain drug dispersion and solubilisation whilst the LAA were breaking down under digesting conditions. Finally, in vivo oral bioavailability studies demonstrated that oral delivery of a LBF containing a Tol IL comprising a digestible cationic lipid counterion was able to successfully support effective oral delivery of Tol. Conclusions Digestible LAA cationic lipids are potential IL counterions for weakly acidic drug molecules and digest in situ to form non-toxic breakdown products.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

The conservation impacts of ecological disturbance: Time‐bound estimates of population loss and recovery for fauna affected by the 2019–2020 Australian megafires - Sarah Legge; Libby Rumpff; John C. Z. Woinarski; Nick S. Whiterod; Michelle Ward; Darren G. Southwell; Ben C. Scheele; Dale G. Nimmo; Mark Lintermans; Hayley M. Geyle; Stephen T. Garnett; Brittany Hayward‐Brown; et al. (Global Ecology and Biogeography, 2022)
Aim After environmental disasters, species with large population losses may need urgent protection to prevent extinction and support recovery. Following the 2019–2020 Australian megafires, we estimated population losses and recovery in fire‐affected fauna, to inform conservation status assessments and management. Location Temperate and subtropical Australia. Time period 2019–2030 and beyond. Major taxa Australian terrestrial and freshwater vertebrates; one invertebrate group. Methods From > 1,050 fire‐affected taxa, we selected 173 whose distributions substantially overlapped the fire extent. We estimated the proportion of each taxon’s distribution affected by fires, using fire severity and aquatic impact mapping, and new distribution mapping. Using expert elicitation informed by evidence of responses to previous wildfires, we estimated local population responses to fires of varying severity. We combined the spatial and elicitation data to estimate overall population loss and recovery trajectories, and thus indicate potential eligibility for listing as threatened, or uplisting, under Australian legislation. Results We estimate that the 2019–2020 Australian megafires caused, or contributed to, population declines that make 70–82 taxa eligible for listing as threatened; and another 21–27 taxa eligible for uplisting. If so‐listed, this represents a 22–26% increase in Australian statutory lists of threatened terrestrial and freshwater vertebrates and spiny crayfish, and uplisting for 8–10% of threatened taxa. Such changes would cause an abrupt worsening of underlying trajectories in vertebrates, as measured by Red List Indices. We predict that 54–88% of 173 assessed taxa will not recover to pre‐fire population size within 10 years/three generations. Main conclusions We suggest the 2019–2020 Australian megafires have worsened the conservation prospects for many species. Of the 91 taxa recommended for listing/uplisting consideration, 84 are now under formal review through national processes. Improving predictions about taxon vulnerability with empirical data on population responses, reducing the likelihood of future catastrophic events and mitigating their impacts on biodiversity, are critical.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

The role of indigenous knowledge and local knowledge in water sector adaptation to climate change in Africa: a structured assessment - Luckson Zvobgo; Peter Johnston; Portia Adade Williams; Christopher H. Trisos; Nicholas P. Simpson (Sustainability Science, 2022)
Evidence is increasing of human responses to the impacts of climate change in Africa. However, understanding of the effectiveness of these responses for adaptation to climate change across the diversity of African contexts is still limited. Despite high reliance on indigenous knowledge (IK) and local knowledge (LK) for climate adaptation by African communities, potential of IK and LK to contribute to adaptation through reducing climate risk or supporting transformative adaptation responses is yet to be established. Here, we assess the influence of IK and LK for the implementation of water sector adaptation responses in Africa to better understand the relationship between responses to climate change and indigenous and local knowledge systems. Eighteen (18) water adaptation response types were identified from the academic literature through the Global Adaptation Mapping Initiative (GAMI) and intended nationally determined contributions (iNDCs) for selected African countries. Southern, West, and East Africa show relatively high evidence of the influence of IK and LK on the implementation of water adaptation responses, while North and Central Africa show lower evidence. At country level, Zimbabwe displays the highest evidence (77.8%) followed by Ghana (53.6%), Kenya (46.2%), and South Africa (31.3%). Irrigation, rainwater harvesting, water conservation, and ecosystem-based measures, mainly agroforestry, were the most implemented measures across Africa. These were mainly household and individual measures influenced by local and indigenous knowledge. Adaptation responses with IK and LK influence recorded higher evidence of risk reduction compared to responses without IK and LK. Analysis of iNDCs shows the most implemented water adaptation actions in academic literature are consistent with water sector adaptation targets set by most African governments. Yet only 10.4% of the African governments included IK and LK in adaptation planning in the iNDCs. This study recommends a coordinated approach to adaptation that integrates multiple knowledge sources, including IK and LK, to ensure sustainability of both current and potential water adaptation measures in Africa.

The S-Factor, a New Measure of Disease Severity in Spinocerebellar Ataxia: Findings and Implications - Louisa P. Selvadurai; Susan L. Perlman; George R. Wilmot; Sub H. Subramony; Christopher M. Gomez; Tetsuo Ashizawa; Henry L. Paulson; Chiadi U. Onyike; Liana S. Rosenthal; Haris I. Sair; Sheng-Han Kuo; Eva-Maria Ratai; et al. (The Cerebellum, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Microbial biopreservatives for controlling the spoilage of beef and lamb meat: their application and effects on meat quality - Michelle M. Xu; Mandeep Kaur; Christopher J. Pillidge; Peter J. Torley (Critical Reviews in Food Science and Nutrition, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Investigating the contribution of white matter hyperintensities and cortical thickness to empathy in neurodegenerative and cerebrovascular diseases - Miracle Ozzoude; Brenda Varriano; Derek Beaton; Joel Ramirez; Melissa F. Holmes; Christopher J. M. Scott; Fuqiang Gao; Kelly M. Sunderland; Paula McLaughlin; Jennifer Rabin; Maged Goubran; Donna Kwan; et al. (GeroScience, 2022)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Editorial: Solving Complex Ocean Challenges Through Interdisciplinary Research: Advances from Early Career Marine Scientists - Stephanie Brodie; Charles Izuma Addey; Christopher Cvitanovic; Beatriz S. Dias; André Frainer; Sara García-Morales; Shan Jiang; Laura Kaikkonen; Jon Lopez; Sabine Mathesius; Kelly Ortega-Cisneros; Maria Grazia Pennino; et al. (Frontiers in Marine Science, 2022)

A stochastic simulation model for assessing the masking effects of road noise for wildlife, outdoor recreation, and bioacoustic monitoring - Cory A. Toth; Benjamin P. Pauli; Christopher J. W. McClure; Clinton D. Francis; Peter Newman; Jesse R. Barber; Kurt Fristrup (Oecologia, 2022)
Traffic noise is one of the leading causes of reductions in animal abundances near roads. Acoustic masking of conspecific signals and adventitious cues is one mechanism that likely causes animals to abandon loud areas. However, masking effects can be difficult to document in situ and the effects of infrequent noise events may be impractical to study. Here, we present the Soundscapes model, a stochastic individual-based model that dynamically models the listening areas of animals searching for acoustic resources (“searchers"). The model also studies the masking effects of noise for human detections of the searchers. The model is set in a landscape adjacent to a road. Noise produced by vehicles traveling on that road is represented by calibrated spectra that vary with speed. Noise propagation is implemented using ISO-9613 procedures. We present demonstration simulations that quantify declines in searcher efficiency and human detection of searchers at relatively low traffic volumes, fewer than 50 vehicles per hour. Traffic noise is pervasive, and the Soundscapes model offers an extensible tool to study the effects of noise on bioacoustics monitoring, point-count surveys, the restorative value of natural soundscapes, and auditory performance in an ecological context.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

“Spider Monkey Cotton”: Bridging Waiwai and Scientific Ontologies to Characterize Spider Monkey (Ateles paniscus) Filariasis in the Konashen Community Owned Conservation Area, Guyana - Christopher A. Shaffer; Marissa S. Milstein; Laramie L. Lindsey; Tiffany M. Wolf; Philip Suse; Elisha Marawanaru; Evan J. Kipp; Tyler Garwood; Dominic A. Travis; Karen A. Terio; Peter A. Larsen (International Journal of Primatology, 2022)

Bioavailable Cu can influence nitrification rate in New Zealand dairy farm soils - Dumsane Themba Matse; Paramsothy Jeyakumar; Peter Bishop; Christopher W. N. Anderson (Journal of Soils and Sediments, 2022)

Innovative method of utilising hydrogen peroxide for source water management of cyanobacteria - Jianyin Huang; Maximus Ghaly; Peter Hobson; Christopher W. K. Chow (Environmental Science and Pollution Research, 2022)

Using data calibration to reconcile outputs from different survey methods in long-term or large-scale studies - Christopher S. Jones; David H. Duncan; William K. Morris; Doug Robinson; Peter A. Vesk (Environmental Monitoring and Assessment, 2022)
Understanding the impact of management interventions on the environment over decadal and longer timeframes is urgently required. Longitudinal or large-scale studies with consistent methods are best practice, but more commonly, small datasets with differing methods are used to achieve larger coverage. Changes in methods and interpretation affect our ability to understand data trends through time or across space, so an ability to understand and adjust for such discrepancies between datasets is important for applied ecologists. Calibration or double sampling is the key to unlocking the value from disparate datasets, allowing us to account for the differences between datasets while acknowledging the uncertainties. We use a case study of livestock grazing impacts on riparian vegetation in southeastern Australia to develop a flexible and powerful approach to this problem. Using double sampling, we estimated changes in vegetation attributes over a 12-year period using a pseudo-quantitative visual method as the starting point, and the same technique plus point-intercept survey for the second round. The disparate nature of the datasets produced uncertain estimates of change over time, but accounting for this uncertainty explicitly is precisely the objective and highlights the need to look more closely at this very common problem in environmental management, as well as the potential benefits of the double sampling approach.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Cryptic coral recruits as dormant “seed banks”: An unrecognized mechanism of rapid reef recovery - Christopher Doropoulos; Yves‐Marie Bozec; Marine Gouezo; Mark A. Priest; Damian P. Thomson; Peter J. Mumby; George Roff (Ecology, 2022)

Two heads are better than one: current landscape of integrating QSP and machine learning - Tongli Zhang; Ioannis P. Androulakis; Peter Bonate; Limei Cheng; Tomáš Helikar; Jaimit Parikh; Christopher Rackauckas; Kalyanasundaram Subramanian; Carolyn R. Cho; Ioannis P. Androulakis; Peter Bonate; Ivan Borisov; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2022)
Quantitative systems pharmacology (QSP) modeling is applied to address essential questions in drug development, such as the mechanism of action of a therapeutic agent and the progression of disease. Meanwhile, machine learning (ML) approaches also contribute to answering these questions via the analysis of multi-layer ‘omics’ data such as gene expression, proteomics, metabolomics, and high-throughput imaging. Furthermore, ML approaches can also be applied to aspects of QSP modeling. Both approaches are powerful tools and there is considerable interest in integrating QSP modeling and ML. So far, a few successful implementations have been carried out from which we have learned about how each approach can overcome unique limitations of the other. The QSP + ML working group of the International Society of Pharmacometrics QSP Special Interest Group was convened in September, 2019 to identify and begin realizing new opportunities in QSP and ML integration. The working group, which comprises 21 members representing 18 academic and industry organizations, has identified four categories of current research activity which will be described herein together with case studies of applications to drug development decision making. The working group also concluded that the integration of QSP and ML is still in its early stages of moving from evaluating available technical tools to building case studies. This paper reports on this fast-moving field and serves as a foundation for future codification of best practices.

Extensive transcriptomic profiling of pupal diapause in a butterfly reveals a dynamic phenotype - Peter Pruisscher; Philipp Lehmann; Sören Nylin; Karl Gotthard; Christopher W. Wheat (Molecular Ecology, 2022)
Diapause is a common adaptation for overwintering in insects that is characterized by arrested development and increased tolerance to stress and cold. While the expression of specific candidate genes during diapause have been investigated, there is no general understanding of the dynamics of the transcriptional landscape as a whole during the extended diapause phenotype. Such a detailed temporal insight is important as diapause is a vital aspect of life cycle timing. Here, we performed a time‐course experiment using RNA‐Seq on the head and abdomen in the butterfly Pieris napi . In both body parts, comparing diapausing and nondiapausing siblings, differentially expressed genes are detected from the first day of pupal development and onwards, varying dramatically across these formative stages. During diapause there are strong gene expression dynamics present, revealing a preprogrammed transcriptional landscape that is active during the winter. Different biological processes appear to be active in the two body parts. Finally, adults emerging from either the direct or diapause pathways do not show large transcriptomic differences, suggesting the adult phenotype is strongly canalized.

Understanding the economic activity generated by recreational fishing in South Africa provides insights on the role of recreational fisheries for social development - Warren M. Potts; Melville Saayman; Andrea Saayman; Bruce Q. Mann; Peet Van der Merwe; Peter Britz; Christopher S. Bova (Fisheries Management and Ecology, 2022)
While the economic activity associated with recreational fishing is well assessed in the developed world, substantially less is known in developing countries. South Africa is a unique microcosm for applying economic evaluation frameworks as its dualist economy shares characteristics of both the developed and developing world. Understanding participation levels and the role of dualism in economic activity linked to recreational fisheries is a crucial step towards leveraging the sector for economic development. A total of 1320 face‐to‐face and online questionnaires were used to estimate annual economic spend by recreational fishers, and the economic activity associated with this spend was modelled using Social Accounting Matrix analysis. Recreational fishing participation estimates totalled 1,327,633, which contributed ZAR 32.6 billion (US$2.2 billion) per year to economic activity and sustained 94,070 full‐time jobs. However, less than 10% of the economic activity benefitted lower income households, suggesting that the “first” and “second” economies of this dualist economy are disconnected. This is likely similar in other developing nations with international tourism‐driven recreational fisheries. To reduce this disconnect, changes in tourism policies to focus on local development, the identification of recreational fisheries tourism hotspots and the development of local education, skills and appropriate infrastructure through public–private partnerships will be necessary.

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

Directional turnover towards larger‐ranged plants over time and across habitats - Ingmar R. Staude; Henrique M. Pereira; Gergana N. Daskalova; Markus Bernhardt‐Römermann; Martin Diekmann; Harald Pauli; Hans Van Calster; Mark Vellend; Anne D. Bjorkman; Jörg Brunet; Pieter De Frenne; Radim Hédl; et al. (Ecology Letters, 2022)
Species turnover is ubiquitous. However, it remains unknown whether certain types of species are consistently gained or lost across different habitats. Here, we analysed the trajectories of 1827 plant species over time intervals of up to 78 years at 141 sites across mountain summits, forests, and lowland grasslands in Europe. We found, albeit with relatively small effect sizes, displacements of smaller‐ by larger‐ranged species across habitats. Communities shifted in parallel towards more nutrient‐demanding species, with species from nutrient‐rich habitats having larger ranges. Because these species are typically strong competitors, declines of smaller‐ranged species could reflect not only abiotic drivers of global change, but also biotic pressure from increased competition. The ubiquitous component of turnover based on species range size we found here may partially reconcile findings of no net loss in local diversity with global species loss, and link community‐scale turnover to macroecological processes such as biotic homogenisation.

Virtual pruning of 3D trees as a tool for managing shading effects in agroforestry systems - Rafael Bohn Reckziegel; Jonathan P. Sheppard; Hans-Peter Kahle; Elena Larysch; Heinrich Spiecker; Thomas Seifert; Christopher Morhart (Agroforestry Systems, 2022)
Light is a limiting resource for crops within integrated land use systems especially those including woody perennials. The amount of available light at ground level can be modified by artificially pruning the overstory. Aiming to increase the understanding of light management strategies, we simulated the pruning of wild cherry trees and compared the shading effects of the resulting tree structures over a complete growing season, with fine spatiotemporal resolution. Original 3D-tree structures were retrieved employing terrestrial laser scanning and quantitative structure models, and subjected to two pruning treatments at low and high intensities. By using the ‘shadow model’, the analogous tree structures created diverse shaded scenarios varying in size and intensity of insolation reduction. Conventional pruning treatments reduced the crown structure to the uppermost portion of the tree bole, reducing the shading effects, and thus, shrinking the shaded area on the ground by up to 38%, together with the shading intensity. As an alternative, the selective removal of branches reduced the shading effects, while keeping a more similar spatial distribution compared to the unpruned tree. Hence, the virtual pruning of tree structures can support designing and selecting adequate tending operations for the management of light distribution in agroforestry systems. The evidence assembled in this study is highly relevant for agroecosystems and can be strategically used for maintaining, planning and designing integrated tree-crop agricultural systems.

Ocean System Science to Inform the Exploration of Ocean Worlds - Christopher German; Donna Blackman; Andrew Fisher; Peter Girguis; Kevin Hand; Tori Hoehler; Julie Huber; John Marshall; Kathryn Pietro; Jeffrey Seewald; Everett Shock; Christophe Sotin; et al. (Oceanography, 2022)
Ocean worlds provide fascinating opportunities for future ocean research. They allow us to test our understanding of processes we consider fundamental to Earth’s ocean and simultaneously provide motivation to explore our ocean further and develop new technologies to do so. In parallel, ocean worlds research offers opportunities for ocean scientists to provide meaningful contributions to novel investigations in the coming decades that will search for life beyond Earth. Key to the contributions that oceanographers can make to this field is that studies of all other ocean worlds remain extremely data limited. Here, we describe an approach based on ocean systems science in which theoretical modeling can be used, in concert with targeted laboratory experimentation and direct observations in Earth’s ocean, to predict what processes (including those essential to support life) might be occurring on other ocean worlds. In turn, such an approach would help identify new technologies that might be required for future space missions as well as appropriate analog studies that could be conducted on Earth to develop and validate such technologies. Our approach is both integrative and interdisciplinary and considers multiple domains, from processes active in the subseafloor to those associated with ocean-ice feedbacks.

Sick and tired: sickness behaviour, polyparasitism and food stress in a gregarious mammal - Rosemary Blersch; Tyler R. Bonnell; Andre Ganswindt; Christopher Young; Louise Barrett; S. Peter Henzi (Behavioral Ecology and Sociobiology, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Benthic micro‐ and macro‐community succession and coral recruitment under overfishing and nutrient enrichment - Nicolas R. Evensen; Inka Vanwonterghem; Christopher Doropoulos; Marine Gouezo; Emmanuelle S. Botté; Nicole S. Webster; Peter J. Mumby (Ecology, 2021)
Herbivory and nutrient availability are fundamental drivers of benthic community succession in shallow marine systems, including coral reefs. Despite the importance of early community succession for coral recruitment and recovery, studies characterizing the impact of top‐down and bottom‐up drivers on micro‐ and macrobenthic communities at scales relevant to coral recruitment are lacking. Here, a combination of tank and field experiments were used to assess the effects of herbivore exclusion and nutrient enrichment on micro‐ to macrobenthic community succession and subsequent coral recruitment success. Herbivore exclusion had the strongest effect on micro‐ and macrobenthic community succession, including a community shift toward copiotrophic and potentially opportunistic/pathogenic microorganisms, an increased cover of turf and macroalgae, and decreased cover of crustose coralline algae. Yet, when corals settled prior to the development of a macrobenthic community, rates of post‐settlement survival increased when herbivores were excluded, benefiting from the predation refugia provided by cages during their vulnerable early post‐settlement stage. Interestingly, survival on open tiles was negatively correlated with the relative abundance of the bacterial order Rhodobacterales , an opportunistic microbial group previously associated with stressed and diseased corals. Development of micro‐ and macrobenthic communities in the absence of herbivory, however, led to reduced coral settlement. In turn, there were no differences in post‐settlement survival between open and caged treatments for corals settled on tiles with established benthic communities. As a result, open tiles experienced marginally higher recruitment rates, driven primarily by the higher initial number of settlers on open tiles compared to caged tiles. Overall, we reveal that the primary interaction driving coral recruitment is the positive effect of herbivory in creating crustose coralline algae (CCA)‐dominated habitats, free of fleshy algae and associated opportunistic microbes, to enhance coral settlement. The negative direct and indirect impact of fish predation on newly settled corals was outweighed by the positive effect of herbivory on the initial rate of coral settlement. In turn, the addition of nutrients further altered benthic community succession in the absence of herbivory, reducing coral post‐settlement survival. However, the overall impact of nutrients on coral recruitment dynamics was minor relative to herbivory.

Identification of Mineralization in Geochemistry for Grid Sampling Using Generalized Additive Models - Dominika Mikšová; Christopher Rieser; Peter Filzmoser; Maarit Middleton; Raimo Sutinen (Mathematical Geosciences, 2021)

Identification of Mineralization in Geochemistry Along a Transect Based on the Spatial Curvature of Log-Ratios - Dominika Mikšová; Christopher Rieser; Peter Filzmoser (Mathematical Geosciences, 2021)

Genetic diversity of whitefly (Bemisia spp.) on crop and uncultivated plants in Uganda: implications for the control of this devastating pest species complex in Africa - Habibu Mugerwa; John Colvin; Titus Alicai; Christopher A. Omongo; Richard Kabaalu; Paul Visendi; Peter Sseruwagi; Susan E. Seal (Journal of Pest Science, 2021)
Over the past three decades, highly increased whitefly ( Bemisia tabaci ) populations have been observed on the staple food crop cassava in eastern Africa and associated with ensuing viral disease pandemics and food insecurity. Increased whitefly numbers have also been observed in other key agricultural crops and weeds. Factors behind the population surges on different crops and their interrelationships are unclear, although in cassava they have been associated with specific populations within the Bemisia tabaci species complex known to infest cassava crops in Africa. This study carried out an in-depth survey to understand the distribution of B. tabaci populations infesting crops and uncultivated plant hosts in Uganda, a centre of origin for this pest complex. Whitefly samples were collected from 59 identified plant species and 25 unidentified weeds in a countrywide survey. Identities of 870 individual adult whiteflies were determined through mitochondrial cytochrome oxidase 1 sequences (651 bp) in the 3′ barcode region used for B. tabaci systematics. Sixteen B. tabaci and five related whitefly putative species were identified based on > 4.0% nucleotide divergence, of which three are proposed as novel B. tabaci putative species and four as novel closely related whitefly species. The most prevalent whiteflies were classified as B. tabaci MED-ASL (30.5% of samples), sub-Saharan Africa 1 (SSA1, 22.7%) and Bemisia Uganda1 (12.1%). These species were also indicated to be the most polyphagous occurring on 33, 40 and 25 identified plant species, respectively. Multiple (≥ 3) whitefly species occurred on specific crops (bean, eggplant, pumpkin and tomato) and weeds ( Sida acuta and Ocimum gratissimum ). These plants may have increased potential to act as reservoirs for mixed infections of whitefly-vectored viruses. Management of whitefly pest populations in eastern Africa will require an integration of approaches that consider their degree of polyphagy and a climate that enables the continuous presence of crop and uncultivated plant hosts.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Determinants of community compositional change are equally affected by global change - Meghan L. Avolio; Kimberly J. Komatsu; Scott L. Collins; Emily Grman; Sally E. Koerner; Andrew T. Tredennick; Kevin R. Wilcox; Sara Baer; Elizabeth H. Boughton; Andrea J. Britton; Bryan Foster; Laura Gough; et al. (Ecology Letters, 2021)
Global change is impacting plant community composition, but the mechanisms underlying these changes are unclear. Using a dataset of 58 global change experiments, we tested the five fundamental mechanisms of community change: changes in evenness and richness, reordering, species gains and losses. We found 71% of communities were impacted by global change treatments, and 88% of communities that were exposed to two or more global change drivers were impacted. Further, all mechanisms of change were equally likely to be affected by global change treatments—species losses and changes in richness were just as common as species gains and reordering. We also found no evidence of a progression of community changes, for example, reordering and changes in evenness did not precede species gains and losses. We demonstrate that all processes underlying plant community composition changes are equally affected by treatments and often occur simultaneously, necessitating a wholistic approach to quantifying community changes.

The deep sea is a hot spot of fish body shape evolution - Christopher M. Martinez; Sarah T. Friedman; Katherine A. Corn; Olivier Larouche; Samantha A. Price; Peter C. Wainwright (Ecology Letters, 2021)
Deep‐sea fishes have long captured our imagination with striking adaptations to life in the mysterious abyss, raising the possibility that this cold, dark ocean region may be a key hub for physiological and functional diversification. We explore this idea through an analysis of body shape evolution across ocean depth zones in over 3000 species of marine teleost fishes. We find that the deep ocean contains twice the body shape disparity of shallow waters, driven by elevated rates of evolution in traits associated with locomotion. Deep‐sea fishes display more frequent adoption of forms suited to slow and periodic swimming, whereas shallow living species are concentrated around shapes conferring strong, sustained swimming capacity and manoeuvrability. Our results support long‐standing impressions of the deep sea as an evolutionary hotspot for fish body shape evolution and highlight that factors like habitat complexity and ecological interactions are potential drivers of this adaptive diversification.

Genome sequencing in families with congenital limb malformations - Jonas Elsner; Martin A. Mensah; Manuel Holtgrewe; Jakob Hertzberg; Stefania Bigoni; Andreas Busche; Marie Coutelier; Deepthi C. de Silva; Nursel Elçioglu; Isabel Filges; Erica Gerkes; Katta M. Girisha; et al. (Human Genetics, 2021)
The extensive clinical and genetic heterogeneity of congenital limb malformation calls for comprehensive genome-wide analysis of genetic variation. Genome sequencing (GS) has the potential to identify all genetic variants. Here we aim to determine the diagnostic potential of GS as a comprehensive one-test-for-all strategy in a cohort of undiagnosed patients with congenital limb malformations. We collected 69 cases (64 trios, 1 duo, 5 singletons) with congenital limb malformations with no molecular diagnosis after standard clinical genetic testing and performed genome sequencing. We also developed a framework to identify potential noncoding pathogenic variants. We identified likely pathogenic/disease-associated variants in 12 cases (17.4%) including four in known disease genes, and one repeat expansion in HOXD13 . In three unrelated cases with ectrodactyly, we identified likely pathogenic variants in UBA2 , establishing it as a novel disease gene. In addition, we found two complex structural variants (3%). We also identified likely causative variants in three novel high confidence candidate genes. We were not able to identify any noncoding variants. GS is a powerful strategy to identify all types of genomic variants associated with congenital limb malformation, including repeat expansions and complex structural variants missed by standard diagnostic approaches. In this cohort, no causative noncoding SNVs could be identified.

Land cover and nutrient enrichment regulates low‐molecular weight dissolved organic matter turnover in freshwater ecosystems - Francesca L. Brailsford; Helen C. Glanville; Miles R. Marshall; Christopher A. Yates; Alun T. Owen; Peter N. Golyshin; Penny J. Johnes; Davey L. Jones (Limnology and Oceanography, 2021)
Dissolved organic matter (DOM) is a complex mixture of carbon‐containing compounds. The low‐molecular weight (LMW) fraction constitutes thousands of different compounds and represents a substantial proportion of DOM in aquatic ecosystems. The turnover rates of this LMW DOM can be extremely high. Due to the challenges of measuring this pool at a molecular scale, comparatively little is known of the fate of LMW DOM compounds in lotic systems. This study addresses this knowledge gap, investigating the microbial processing of LMW DOM across 45 sites representing a range of physicochemical gradients and dominant land covers in the United Kingdom. Radioisotope tracers representing LMW dissolved organic carbon (DOC) (glucose), dissolved organic nitrogen (DON) (amino acid mixture), dissolved organic phosphorus (DOP) (glucose‐6‐phosphate), and soluble reactive phosphorus (SRP, measured as orthophosphate) were used to measure the microbial uptake of different DOM compounds in river waters. The amount of DOM biodegradation varied between different components (DON ≥ DOC > DOP), with the rate of turnover of all three increasing along a gradient of N and P enrichment across the range of sites. Conversely, the uptake of SRP decreased along this same gradient. This was ascribed to preferential utilization of DOP over SRP. Dominant land cover had a significant effect on DOM use as a resource, due to its control of nutrient enrichment within the catchments. We conclude that nutrient enrichment of river waters will lead to further DOM removal from the water column, increased microbial growth, and a decrease in stream oxygen saturation, exacerbating the effects of eutrophication in rivers.

Disturbance type and species life history predict mammal responses to humans - Justin P. Suraci; Kaitlyn M. Gaynor; Maximilian L. Allen; Peter Alexander; Justin S. Brashares; Sara Cendejas‐Zarelli; Kevin Crooks; L. Mark Elbroch; Tavis Forrester; Austin M. Green; Jeffrey Haight; Nyeema C. Harris; et al. (Global Change Biology, 2021)
Human activity and land use change impact every landscape on Earth, driving declines in many animal species while benefiting others. Species ecological and life history traits may predict success in human‐dominated landscapes such that only species with “winning” combinations of traits will persist in disturbed environments. However, this link between species traits and successful coexistence with humans remains obscured by the complexity of anthropogenic disturbances and variability among study systems. We compiled detection data for 24 mammal species from 61 populations across North America to quantify the effects of (1) the direct presence of people and (2) the human footprint (landscape modification) on mammal occurrence and activity levels. Thirty‐three percent of mammal species exhibited a net negative response (i.e., reduced occurrence or activity) to increasing human presence and/or footprint across populations, whereas 58% of species were positively associated with increasing disturbance. However, apparent benefits of human presence and footprint tended to decrease or disappear at higher disturbance levels, indicative of thresholds in mammal species’ capacity to tolerate disturbance or exploit human‐dominated landscapes. Species ecological and life history traits were strong predictors of their responses to human footprint, with increasing footprint favoring smaller, less carnivorous, faster‐reproducing species. The positive and negative effects of human presence were distributed more randomly with respect to species trait values, with apparent winners and losers across a range of body sizes and dietary guilds. Differential responses by some species to human presence and human footprint highlight the importance of considering these two forms of human disturbance separately when estimating anthropogenic impacts on wildlife. Our approach provides insights into the complex mechanisms through which human activities shape mammal communities globally, revealing the drivers of the loss of larger predators in human‐modified landscapes.

Microbial diversity and activity in Southern California salterns and bitterns: analogues for remnant ocean worlds - Benjamin Klempay; Nestor Arandia‐Gorostidi; Anne E. Dekas; Douglas H. Bartlett; Christopher E. Carr; Peter T. Doran; Avishek Dutta; Natalia Erazo; Luke A. Fisher; Jennifer B. Glass; Alexandra Pontefract; Sanjoy M. Som; et al. (Environmental Microbiology, 2021)
Summary Concurrent osmotic and chaotropic stress make MgCl 2 ‐rich brines extremely inhospitable environments. Understanding the limits of life in these brines is essential to the search for extraterrestrial life on contemporary and relict ocean worlds, like Mars, which could host similar environments. We sequenced environmental 16S rRNA genes and quantified microbial activity across a broad range of salinity and chaotropicity at a Mars‐analogue salt harvesting facility in Southern California, where seawater is evaporated in a series of ponds ranging from kosmotropic NaCl brines to highly chaotropic MgCl 2 brines. Within NaCl brines, we observed a proliferation of specialized halophilic Euryarchaeota, which corresponded closely with the dominant taxa found in salterns around the world. These communities were characterized by very slow growth rates and high biomass accumulation. As salinity and chaotropicity increased, we found that the MgCl 2 ‐rich brines eventually exceeded the limits of microbial activity. We found evidence that exogenous genetic material is preserved in these chaotropic brines, producing an unexpected increase in diversity in the presumably sterile MgCl 2 ‐saturated brines. Because of their high potential for biomarker preservation, chaotropic brines could therefore serve as repositories of genetic biomarkers from nearby environments (both on Earth and beyond) making them prime targets for future life‐detection missions.

Spatiotemporal patterns of ENSO‐precipitation relationships in the tropical Andes of southern Peru and Bolivia - Joseph A. Jonaitis; L. Baker Perry; Peter T. Soulé; Christopher Thaxton; Marcos F. Andrade‐Flores; Tania Ita Vargas; Laura Ticona (International Journal of Climatology, 2021)
Precipitation in the outer tropical Andes is highly seasonal, exhibits considerable interannual variability, and is vital for regulating freshwater availability, flooding, glacier mass balance, and droughts. The primary driver of interannual variability is El Niño Southern Oscillation (ENSO), with most investigations reporting that the El Niño (La Niña) results in negative (positive) precipitation anomalies across the region. Recent investigations, however, have identified substantial spatiotemporal differences in ENSO‐precipitation relationships. Motivated by the dissimilarity of these findings, this study examines a carefully selected data set (≥ 90% completeness) of ground‐based precipitation observations from 75 high‐elevation (≥ 2,500 m above sea level) meteorological stations in the tropical Andes of southern Peru and Bolivia for the period 1972–2016. Distinct groups of stations and associated variability in precipitation characteristics (e.g., total seasonal precipitation, wet season onset, and wet season length) are identified. Using no spatial constraints, the K‐Means algorithm optimally grouped stations into five easily identifiable groups. The groups farthest from the Amazon basin had significant negative (positive) precipitation anomalies ( p

Spatial Variation in Pelagic Wildlife Assemblages in the Ascension Island Marine Protected Area: Implications for Monitoring and Management - Christopher D. H. Thompson; Jessica J. Meeuwig; Judith Brown; Andrew J. Richardson; Alan M. Friedlander; Peter I. Miller; Sam B. Weber (Frontiers in Marine Science, 2021)
Bathymetric features such as islands and seamounts, as well as dynamic ocean features such as fronts often harbour rich marine communities. We deployed mid-water baited remote underwater video systems on three expeditions in Ascension Island’s Exclusive Economic Zone (EEZ), surveying the waters associated with six different bathymetric and dynamic ocean features: Ascension Island, two shallow seamounts (summits ≤ 101 m), one deeper seamount (summit > 250 m), apparent fronts, and haphazardly sampled open ocean areas. At Ascension Island, the pelagic assemblage consisted of a moderate proportion of predators and a diverse range of other taxa, including turtles, dolphins, and large non-piscivores. At the two shallow seamounts, sharks, tunas, billfish, and other large pelagic predators formed the vast majority of the assemblage, contributing > 99.9% of biomass and > 86% of abundance. At the deeper seamount, the pelagic community was comparatively depauperate, however the functional composition of its assemblage indicated some similarities to the shallow seamounts. Apparent fronts did not significantly differ from random offshore sites for metrics such as total abundance and taxonomic richness. However, they harboured assemblages with more abundant sharks, tunas, and large piscivores than random ocean open locations and these differences may be driven by certain front-associated species. Our results illustrate that pelagic assemblages vary markedly among different physical and oceanographic features and that seamounts appear particularly important for pelagic predators. The diversity and abundance of the assemblage, as well as the threatened status of many of the species observed, serve to highlight the conservation value of the Ascension Island EEZ. Our results also provide important baseline information of pelagic wildlife assemblages against which the performance of the recently implemented Ascension Island Marine Protected Area can be evaluated.

Lipophilic Salts and Lipid-Based Formulations: Enhancing the Oral Delivery of Octreotide - Peng Li; Leigh Ford; Shadabul Haque; Mitchell P. McInerney; Hywel D. Williams; Peter J. Scammells; Philip E. Thompson; Vincent Jannin; Christopher J. H. Porter; Hassan Benameur; Colin W. Pouton (Pharmaceutical Research, 2021)

Recent advances toward the sustainable management of invasive Xylosandrus ambrosia beetles - Antonio Gugliuzzo; Peter H. W. Biedermann; Daniel Carrillo; Louela A. Castrillo; James P. Egonyu; Diego Gallego; Khalid Haddi; Jiri Hulcr; Hervé Jactel; Hisashi Kajimura; Naoto Kamata; Nicolas Meurisse; et al. (Journal of Pest Science, 2021)
We provide an overview of both traditional and innovative control tools for management of three Xylosandrus ambrosia beetles (Coleoptera: Curculionidae: Scolytinae), invasive species with a history of damage in forests, nurseries, orchards and urban areas. Xylosandrus compactus , X. crassiusculus and X. germanus are native to Asia, and currently established in several countries around the globe. Adult females bore galleries into the plant xylem inoculating mutualistic ambrosia fungi that serve as food source for the developing progeny. Tunneling activity results in chewed wood extrusion from entry holes, sap outflow, foliage wilting followed by canopy dieback, and branch and trunk necrosis. Maintaining plant health by reducing physiological stress is the first recommendation for long-term control. Baited traps, ethanol-treated bolts, trap logs and trap trees of selected species can be used to monitor Xylosandrus species. Conventional pest control methods are mostly ineffective against Xylosandrus beetles because of the pests’ broad host range and rapid spread. Due to challenges with conventional control, more innovative control approaches are being tested, such as the optimization of the push–pull strategy based on specific attractant and repellent combinations, or the use of insecticide-treated netting. Biological control based on the release of entomopathogenic and mycoparasitic fungi, as well as the use of antagonistic bacteria, has yielded promising results. However, these technologies still require validation in real field conditions. Overall, we suggest that management efforts should primarily focus on reducing plant stress and potentially be combined with a multi-faceted approach for controlling Xylosandrus damage.

Disruption of duplicated yellow genes in Bactrocera tryoni modifies pigmentation colouration and impacts behaviour - Thu N. M. Nguyen; Vivian Mendez; Christopher Ward; Peter Crisp; Alexie Papanicolaou; Amanda Choo; Phillip W. Taylor; Simon W. Baxter (Journal of Pest Science, 2021)

Wi-fi related radiofrequency electromagnetic fields (RF-EMF): a pilot experimental study of personal exposure and risk perception - Berihun M. Zeleke; Christopher Brzozek; Chhavi R. Bhatt; Michael J. Abramson; Frederik Freudenstein; Rodney J. Croft; Peter Wiedemann; Geza Benke (Journal of Environmental Health Science and Engineering, 2021)
The impact of providing people with an objectively measured personal radiofrequency electromagnetic fields (RF-EMF) exposure information on the risk perception of people is not well understood. We conducted an experimental study, among three groups of participants, to investigate the risk perception of people towards RF-EMF from Wi-Fi sources (ISM 2.4 GHz) by providing participants with either basic text, precautionary information, or a summary of their personal RF-EMF exposure measurement levels. Participants provided with personal RF-EMF exposure measurement information were more confident in protecting themselves from RF-EMF exposure, compared to those provided with only basic information. Nonetheless, neither the exposure perception nor the risk perception of people to Wi-Fi related RF-EMF differed by the type of information provided. The measured Wi-Fi signal levels were far below international exposure limits. Furthermore, self-rated levels of personal RF-EMF exposure perception were not associated with objectively measured RF-EMF exposure levels. Providing people with objectively measured information may help them build confidence in protecting themselves from Wi-Fi related RF-EMF exposure.

Trace and rare earth element geochemistry of the black and grey shales of the Calabar Flank, Southeastern Nigeria: constraints on the depositional environment and the degree of metal enrichment - Christopher Iorfa Adamu; Benjamin Odey Omang; Oluwaseye Peter Oyetade; Otu Johnson; Therese Ntonzi Nganje (Acta Geochimica, 2021)

Investigating the effects of healthy cognitive aging on brain functional connectivity using 4.7 T resting-state functional magnetic resonance imaging - Stanislau Hrybouski; Ivor Cribben; John McGonigle; Fraser Olsen; Rawle Carter; Peter Seres; Christopher R. Madan; Nikolai V. Malykhin (Brain Structure and Function, 2021)

Recognize fish as food in policy discourse and development funding - Abigail Bennett; Xavier Basurto; John Virdin; Xinyan Lin; Samantha J. Betances; Martin D. Smith; Edward H. Allison; Barbara A. Best; Kelly D. Brownell; Lisa M. Campbell; Christopher D. Golden; Elizabeth Havice; et al. (Ambio, 2021)
The international development community is off-track from meeting targets for alleviating global malnutrition. Meanwhile, there is growing consensus across scientific disciplines that fish plays a crucial role in food and nutrition security. However, this ‘fish as food’ perspective has yet to translate into policy and development funding priorities. We argue that the traditional framing of fish as a natural resource emphasizes economic development and biodiversity conservation objectives, whereas situating fish within a food systems perspective can lead to innovative policies and investments that promote nutrition-sensitive and socially equitable capture fisheries and aquaculture. This paper highlights four pillars of research needs and policy directions toward this end. Ultimately, recognizing and working to enhance the role of fish in alleviating hunger and malnutrition can provide an additional long-term development incentive, beyond revenue generation and biodiversity conservation, for governments, international development organizations, and society more broadly to invest in the sustainability of capture fisheries and aquaculture.

A common soil temperature threshold for the upper limit of alpine grasslands in European mountains - Sarah Bürli; Jean-Paul Theurillat; Manuela Winkler; Andrea Lamprecht; Harald Pauli; Christian Rixen; Klaus Steinbauer; Sonja Wipf; Otar Abdaladze; Christopher Andrews; Peter Barančok; José Luis Benito-Alonso; et al. (Alpine Botany, 2021)
While climatic research about treeline has a long history, the climatic conditions corresponding to the upper limit of closed alpine grasslands remain poorly understood. Here, we propose a climatic definition for this limit, the ‘grassline’, in analogy to the treeline, which is based on the growing season length and the soil temperature. Eighty-seven mountain summits across ten European mountain ranges, covering three biomes (boreal, temperate, Mediterranean), were inventoried as part of the GLORIA project. Vascular plant cover was estimated visually in 326 plots of 1 × 1 m. Soil temperatures were measured in situ for 2–7 years, from which the length of the growing season and mean temperature were derived. The climatic conditions corresponding to 40% plant cover were defined as the thresholds for alpine grassland. Closed vegetation was present in locations with a mean growing season soil temperature warmer than 4.9 °C, or a minimal growing season length of 85 days, with the growing season defined as encompassing days with daily mean ≥ 1 °C. Hence, the upper limit of closed grasslands was associated with a mean soil temperature close to that previously observed at the treeline, and in accordance with physiological thresholds to growth in vascular plants. In contrast to trees, whose canopy temperature is coupled with air temperature, small-stature alpine plants benefit from the soil warmed by solar radiation and consequently, they can grow at higher elevations. Since substrate stability is necessary for grasslands to occur at their climatic limit, the grassline rarely appears as a distinct linear feature.

Origin of non-native Xylosandrus germanus, an invasive pest ambrosia beetle in Europe and North America - Marek Dzurenko; Christopher M. Ranger; Jiri Hulcr; Juraj Galko; Peter Kaňuch (Journal of Pest Science, 2021)

Preparedness, Planning, and Advances in Operational Response - David Westerholm; Cameron Ainsworth; Christopher Barker; Peter Brewer; John Farrington; Dubravko Justić; Vassiliki Kourafalou; Steven Murawski; John Shepherd; Helena Solo-Gabriele (Oceanography, 2021)
During the last 50 years, the numbers and sizes of oil spills have been significantly reduced through prevention. But spills still occur, and it is critical to prepare for these events through planning and exercises. Operational decisions are designed to expedite cleanup and minimize overall impacts, yet they often involve complex trade-offs between a multitude of competing interests. It is imperative to apply the best technology and science when events occur. However, while planning and response tactics have evolved over time, determining what may be most at risk is often confounded by sparse background data, modeling limitations, scalability, or research gaps. Since 2010, the Gulf of Mexico Research Initiative (GoMRI) and other oil spill research helped address many issues and propelled advances in spill modeling. As a result, there is an increased understanding of environmental impacts, how to assess damages, and the unintended consequences of spill countermeasures. The unprecedented amount of information resulting from this research has strengthened the bridge between the academic community and operational responders and brought improvements in preparedness, planning, and operations. This paper focuses primarily on GoMRI research and advances that relate to operational activities, as well as limitations and opportunities for gap-filling future research.

A juvenile Tristan albatross (Diomedea dabbenena) on land at the Crozet Islands - Alexander L. Bond; Christopher Taylor; David Kinchin-Smith; Derren Fox; Emma Witcutt; Peter G. Ryan; Simon P. Loader; Henri Weimerskirch (Polar Biology, 2021)
Albatrosses and other seabirds are generally highly philopatric, returning to natal colonies when they achieve breeding age. This is not universal, however, and cases of extraordinary vagrancy are rare. The Tristan Albatross ( Diomedea dabbenena ) breeds on Gough Island in the South Atlantic Ocean, with a small population on Inaccessible Island, Tristan da Cunha, ca 380 km away. In 2015, we observed an adult male albatross in Gonydale, Gough Island, which had been ringed on Ile de la Possession, Crozet Islands in 2009 when it was assumed to be an immature Wandering Albatross ( D. exulans ). We sequenced 1109 bp of the cytochrome b mitochondrial gene from this bird, and confirmed it to be a Tristan Albatross, meaning its presence on Crozet 6 years previous, and nearly 5000 km away, was a case of prospecting behaviour in a heterospecific colony. Given the challenges in identifying immature Diomedea albatrosses, such dispersal events may be more common than thought previously.

Global root traits (GRooT) database - Nathaly R. Guerrero‐Ramírez; Liesje Mommer; Grégoire T. Freschet; Colleen M. Iversen; M. Luke McCormack; Jens Kattge; Hendrik Poorter; Fons van der Plas; Joana Bergmann; Thom W. Kuyper; Larry M. York; Helge Bruelheide; et al. (Global Ecology and Biogeography, 2021)
Motivation Trait data are fundamental to the quantitative description of plant form and function. Although root traits capture key dimensions related to plant responses to changing environmental conditions and effects on ecosystem processes, they have rarely been included in large‐scale comparative studies and global models. For instance, root traits remain absent from nearly all studies that define the global spectrum of plant form and function. Thus, to overcome conceptual and methodological roadblocks preventing a widespread integration of root trait data into large‐scale analyses we created the Global Root Trait (GRooT) Database. GRooT provides ready‐to‐use data by combining the expertise of root ecologists with data mobilization and curation. Specifically, we (a) determined a set of core root traits relevant to the description of plant form and function based on an assessment by experts, (b) maximized species coverage through data standardization within and among traits, and (c) implemented data quality checks. Main types of variables contained GRooT contains 114,222 trait records on 38 continuous root traits. Spatial location and grain Global coverage with data from arid, continental, polar, temperate and tropical biomes. Data on root traits were derived from experimental studies and field studies. Time period and grain Data were recorded between 1911 and 2019. Major taxa and level of measurement GRooT includes root trait data for which taxonomic information is available. Trait records vary in their taxonomic resolution, with subspecies or varieties being the highest and genera the lowest taxonomic resolution available. It contains information for 184 subspecies or varieties, 6,214 species, 1,967 genera and 254 families. Owing to variation in data sources, trait records in the database include both individual observations and mean values. Software format GRooT includes two csv files. A GitHub repository contains the csv files and a script in R to query the database.

LC‐IMPACT: A regionalized life cycle damage assessment method - Francesca Verones; Stefanie Hellweg; Assumpció Antón; Ligia B. Azevedo; Abhishek Chaudhary; Nuno Cosme; Stefano Cucurachi; Laura de Baan; Yan Dong; Peter Fantke; Laura Golsteijn; Michael Hauschild; et al. (Journal of Industrial Ecology, 2020)

Commentaries on Top-Cited Boundary-Layer Meteorology Articles - John Garratt; James Wilczak; Albert Holtslag; Hans Peter Schmid; Andrey Grachev; Anton Beljaars; Thomas Foken; Fei Chen; Christopher Fairall; Bruce Hicks; Hiroyuki Kusaka; Alberto Martilli; et al. (Boundary-Layer Meteorology, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

COSORE: A community database for continuous soil respiration and other soil‐atmosphere greenhouse gas flux data - Ben Bond‐Lamberty; Danielle S. Christianson; Avni Malhotra; Stephanie C. Pennington; Debjani Sihi; Amir AghaKouchak; Hassan Anjileli; M. Altaf Arain; Juan J. Armesto; Samaneh Ashraf; Mioko Ataka; Dennis Baldocchi; et al. (Global Change Biology, 2020)
Globally, soils store two to three times as much carbon as currently resides in the atmosphere, and it is critical to understand how soil greenhouse gas (GHG) emissions and uptake will respond to ongoing climate change. In particular, the soil‐to‐atmosphere CO 2 flux, commonly though imprecisely termed soil respiration ( R S ), is one of the largest carbon fluxes in the Earth system. An increasing number of high‐frequency R S measurements (typically, from an automated system with hourly sampling) have been made over the last two decades; an increasing number of methane measurements are being made with such systems as well. Such high frequency data are an invaluable resource for understanding GHG fluxes, but lack a central database or repository. Here we describe the lightweight, open‐source COSORE (COntinuous SOil REspiration) database and software, that focuses on automated, continuous and long‐term GHG flux datasets, and is intended to serve as a community resource for earth sciences, climate change syntheses and model evaluation. Contributed datasets are mapped to a single, consistent standard, with metadata on contributors, geographic location, measurement conditions and ancillary data. The design emphasizes the importance of reproducibility, scientific transparency and open access to data. While being oriented towards continuously measured R S , the database design accommodates other soil‐atmosphere measurements (e.g. ecosystem respiration, chamber‐measured net ecosystem exchange, methane fluxes) as well as experimental treatments (heterotrophic only, etc.). We give brief examples of the types of analyses possible using this new community resource and describe its accompanying R software package.

A Marine Biodiversity Observation Network for Genetic Monitoring of Hard-Bottom Communities (ARMS-MBON) - Matthias Obst; Katrina Exter; A. Louise Allcock; Christos Arvanitidis; Alizz Axberg; Maria Bustamante; Ibon Cancio; Diego Carreira-Flores; Eva Chatzinikolaou; Giorgos Chatzigeorgiou; Nathan Chrismas; Melody S. Clark; et al. (Frontiers in Marine Science, 2020)
Marine hard-bottom communities are undergoing severe change under the influence of multiple drivers, notably climate change, extraction of natural resources, pollution and eutrophication, habitat degradation, and invasive species. Monitoring marine biodiversity in such habitats is, however, challenging as it typically involves expensive, non-standardized, and often destructive sampling methods that limit its scalability. Differences in monitoring approaches furthermore hinders inter-comparison among monitoring programs. Here, we announce a Marine Biodiversity Observation Network (MBON) consisting of Autonomous Reef Monitoring Structures (ARMS) with the aim to assess the status and changes in benthic fauna with genomic-based methods, notably DNA metabarcoding, in combination with image-based identifications. This article presents the results of a 30-month pilot phase in which we established an operational and geographically expansive ARMS-MBON. The network currently consists of 20 observatories distributed across European coastal waters and the polar regions, in which 134 ARMS have been deployed to date. Sampling takes place annually, either as short-term deployments during the summer or as long-term deployments starting in spring. The pilot phase was used to establish a common set of standards for field sampling, genetic analysis, data management, and legal compliance, which are presented here. We also tested the potential of ARMS for combining genetic and image-based identification methods in comparative studies of benthic diversity, as well as for detecting non-indigenous species. Results show that ARMS are suitable for monitoring hard-bottom environments as they provide genetic data that can be continuously enriched, re-analyzed, and integrated with conventional data to document benthic community composition and detect non-indigenous species. Finally, we provide guidelines to expand the network and present a sustainability plan as part of the European Marine Biological Resource Centre ( www.embrc.eu ).

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Correction to: Reef-associated fishes have more maneuverable body shapes at a macroevolutionary scale - Olivier Larouche; Bailey Benton; Katherine A. Corn; Sarah T. Friedman; Dominique Gross; Mikayla Iwan; Brian Kessler; Christopher M. Martinez; Sierra Rodriguez; Hannah Whelpley; Peter C. Wainwright; Samantha A. Price (Coral Reefs, 2020)

Reef-associated fishes have more maneuverable body shapes at a macroevolutionary scale - Olivier Larouche; Bailey Benton; Katherine A. Corn; Sarah T. Friedman; Dominique Gross; Mikayla Iwan; Brian Kessler; Christopher M. Martinez; Sierra Rodriguez; Hannah Whelpley; Peter C. Wainwright; Samantha A. Price (Coral Reefs, 2020)

Exploring movement patterns and changing distributions of baleen whales in the western North Atlantic using a decade of passive acoustic data - Genevieve E. Davis; Mark F. Baumgartner; Peter J. Corkeron; Joel Bell; Catherine Berchok; Julianne M. Bonnell; Jacqueline Bort Thornton; Solange Brault; Gary A. Buchanan; Danielle M. Cholewiak; Christopher W. Clark; Julien Delarue; et al. (Global Change Biology, 2020)
Six baleen whale species are found in the temperate western North Atlantic Ocean, with limited information existing on the distribution and movement patterns for most. There is mounting evidence of distributional shifts in many species, including marine mammals, likely because of climate‐driven changes in ocean temperature and circulation. Previous acoustic studies examined the occurrence of minke ( Balaenoptera acutorostrata ) and North Atlantic right whales (NARW; Eubalaena glacialis ). This study assesses the acoustic presence of humpback ( Megaptera novaeangliae ), sei ( B. borealis ), fin ( B. physalus ), and blue whales ( B. musculus ) over a decade, based on daily detections of their vocalizations. Data collected from 2004 to 2014 on 281 bottom‐mounted recorders, totaling 35,033 days, were processed using automated detection software and screened for each species' presence. A published study on NARW acoustics revealed significant changes in occurrence patterns between the periods of 2004–2010 and 2011–2014; therefore, these same time periods were examined here. All four species were present from the Southeast United States to Greenland; humpback whales were also present in the Caribbean. All species occurred throughout all regions in the winter, suggesting that baleen whales are widely distributed during these months. Each of the species showed significant changes in acoustic occurrence after 2010. Similar to NARWs, sei whales had higher acoustic occurrence in mid‐Atlantic regions after 2010. Fin, blue, and sei whales were more frequently detected in the northern latitudes of the study area after 2010. Despite this general northward shift, all four species were detected less on the Scotian Shelf area after 2010, matching documented shifts in prey availability in this region. A decade of acoustic observations have shown important distributional changes over the range of baleen whales, mirroring known climatic shifts and identifying new habitats that will require further protection from anthropogenic threats like fixed fishing gear, shipping, and noise pollution.

Multispecific coral spawning events and extended breeding periods on an equatorial reef - Marine Gouezo; Christopher Doropoulos; Katharina Fabricius; Dawnette Olsudong; Victor Nestor; Haruko Kurihara; Yimnang Golbuu; Peter Harrison (Coral Reefs, 2020)

Landscape simplification shapes pathogen prevalence in plant‐pollinator networks - Laura L. Figueroa; Heather Grab; Wee Hao Ng; Christopher R. Myers; Peter Graystock; Quinn S. McFrederick; Scott H. McArt (Ecology Letters, 2020)
Species interaction networks, which play an important role in determining pathogen transmission and spread in ecological communities, can shift in response to agricultural landscape simplification. However, we know surprisingly little about how landscape simplification‐driven changes in network structure impact epidemiological patterns. Here, we combine mathematical modelling and data from eleven bipartite plant‐pollinator networks observed along a landscape simplification gradient to elucidate how changes in network structure shape disease dynamics. Our empirical data show that landscape simplification reduces pathogen prevalence in bee communities via increased diet breadth of the dominant species. Furthermore, our empirical data and theoretical model indicate that increased connectance reduces the likelihood of a disease outbreak and decreases variance in prevalence among bee species in the community, resulting in a dilution effect. Because infectious diseases are implicated in pollinator declines worldwide, a better understanding of how land use change impacts species interactions is therefore critical for conserving pollinator health.

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Prioritizing river basins for intensive monitoring and assessment by the US Geological Survey - Peter C. Van Metre; Sharon Qi; Jeffrey Deacon; Cheryl Dieter; Jessica M. Driscoll; Michael Fienen; Terry Kenney; Patrick Lambert; David Lesmes; Christopher A. Mason; Anke Mueller-Solger; Marylynn Musgrove; et al. (Environmental Monitoring and Assessment, 2020)
The US Geological Survey (USGS) is currently (2020) integrating its water science programs to better address the nation’s greatest water resource challenges now and into the future. This integration will rely, in part, on data from 10 or more intensively monitored river basins from across the USA. A team of USGS scientists was convened to develop a systematic, quantitative approach to prioritize candidate basins for this monitoring investment to ensure that, as a group, the 10 basins will support the assessment and forecasting objectives of the major USGS water science programs. Candidate basins were the level-4 hydrologic units (HUC04) with some of the smaller HUC04s being combined; median candidate-basin area is 46,600 km 2 . Candidate basins for the contiguous United States (CONUS) were grouped into 18 hydrologic regions. Ten geospatial variables representing land use, climate change, water use, water-balance components, streamflow alteration, fire risk, and ecosystem sensitivity were selected to rank candidate basins within each of the 18 hydrologic regions. The two highest ranking candidate basins in each of the 18 regions were identified as finalists for selection as “Integrated Water Science Basins”; final selection will consider input from a variety of stakeholders. The regional framework, with only one basin selected per region, ensures that as a group, the basins represent the range in major drivers of the hydrologic cycle. Ranking within each region, primarily based on anthropogenic stressors of water resources, ensures that settings representing important water-resource challenges for the nation will be studied.

Age distribution and longevity in a breeding population of Swainson’s Hawks, Buteo swainsoni - Sarah A. Kane; Christopher R. Vennum; Brian Woodbridge; Michael W. Collopy; Peter H. Bloom; Christopher W. Briggs (Journal of Ornithology, 2020)

Characterizing Exposure to and Sharing Knowledge of Drivers of Environmental Change in the St. Lawrence System in Canada - David Beauchesne; Rémi M. Daigle; Steve Vissault; Dominique Gravel; Andréane Bastien; Simon Bélanger; Pascal Bernatchez; Marjolaine Blais; Hugo Bourdages; Clément Chion; Peter S. Galbraith; Benjamin S. Halpern; et al. (Frontiers in Marine Science, 2020)

Increased yield and CO 2 sequestration potential with the C 4 cereal Sorghum bicolor cultivated in basaltic rock dust‐amended agricultural soil - Mike E. Kelland; Peter W. Wade; Amy L. Lewis; Lyla L. Taylor; Binoy Sarkar; M. Grace Andrews; Mark R. Lomas; T. E. Anne Cotton; Simon J. Kemp; Rachael H. James; Christopher R. Pearce; Sue E. Hartley; et al. (Global Change Biology, 2020)
Land‐based enhanced rock weathering (ERW) is a biogeochemical carbon dioxide removal (CDR) strategy aiming to accelerate natural geological processes of carbon sequestration through application of crushed silicate rocks, such as basalt, to croplands and forested landscapes. However, the efficacy of the approach when undertaken with basalt, and its potential co‐benefits for agriculture, require experimental and field evaluation. Here we report that amending a UK clay‐loam agricultural soil with a high loading (10 kg/m 2 ) of relatively coarse‐grained crushed basalt significantly increased the yield (21 ± 9.4%, SE ) of the important C 4 cereal Sorghum bicolor under controlled environmental conditions, without accumulation of potentially toxic trace elements in the seeds. Yield increases resulted from the basalt treatment after 120 days without P‐ and K‐fertilizer addition. Shoot silicon concentrations also increased significantly (26 ± 5.4%, SE ), with potential benefits for crop resistance to biotic and abiotic stress. Elemental budgets indicate substantial release of base cations important for inorganic carbon removal and their accumulation mainly in the soil exchangeable pools. Geochemical reactive transport modelling, constrained by elemental budgets, indicated CO 2 sequestration rates of 2–4 t CO 2 /ha, 1–5 years after a single application of basaltic rock dust, including via newly formed soil carbonate minerals whose long‐term fate requires assessment through field trials. This represents an approximately fourfold increase in carbon capture compared to control plant–soil systems without basalt. Our results build support for ERW deployment as a CDR technique compatible with spreading basalt powder on acidic loamy soils common across millions of hectares of western European and North American agriculture.

Ecological segregation of two superabundant, morphologically similar, sister seabird taxa breeding in sympatry - Christopher W. Jones; Richard A. Phillips; W. James Grecian; Peter G. Ryan (Marine Biology, 2020)

Invasive non‐native species likely to threaten biodiversity and ecosystems in the Antarctic Peninsula region - Kevin A. Hughes; Oliver L. Pescott; Jodey Peyton; Tim Adriaens; Elizabeth J. Cottier‐Cook; Gillian Key; Wolfgang Rabitsch; Elena Tricarico; David K. A. Barnes; Naomi Baxter; Mark Belchier; Denise Blake; et al. (Global Change Biology, 2020)
The Antarctic is considered to be a pristine environment relative to other regions of the Earth, but it is increasingly vulnerable to invasions by marine, freshwater and terrestrial non‐native species. The Antarctic Peninsula region (APR), which encompasses the Antarctic Peninsula, South Shetland Islands and South Orkney Islands, is by far the most invaded part of the Antarctica continent. The risk of introduction of invasive non‐native species to the APR is likely to increase with predicted increases in the intensity, diversity and distribution of human activities. Parties that are signatories to the Antarctic Treaty have called for regional assessments of non‐native species risk. In response, taxonomic and Antarctic experts undertook a horizon scanning exercise using expert opinion and consensus approaches to identify the species that are likely to present the highest risk to biodiversity and ecosystems within the APR over the next 10 years. One hundred and three species, currently absent in the APR, were identified as relevant for review, with 13 species identified as presenting a high risk of invading the APR. Marine invertebrates dominated the list of highest risk species, with flowering plants and terrestrial invertebrates also represented; however, vertebrate species were thought unlikely to establish in the APR within the 10 year timeframe. We recommend (a) the further development and application of biosecurity measures by all stakeholders active in the APR, including surveillance for species such as those identified during this horizon scanning exercise, and (b) use of this methodology across the other regions of Antarctica. Without the application of appropriate biosecurity measures, rates of introductions and invasions within the APR are likely to increase, resulting in negative consequences for the biodiversity of the whole continent, as introduced species establish and spread further due to climate change and increasing human activity.

Feeding Whole Thraustochytrid Biomass to Cultured Atlantic Salmon (Salmo salar) Fingerlings: Culture Performance and Fatty Acid Incorporation - Kim Jye Lee Chang; Christopher C. Parrish; Cedric J. Simon; Andrew T. Revill; Peter D. Nichols (Journal of Marine Science and Engineering, 2020)
Replacement of fish oil by 5% thraustochytrid whole cell biomass in diets for Atlantic salmon had no ill effect on fish growth performance, carcass total lipid and total fatty acid content. Carcass fatty acid composition indicated incorporation of the dietary thraustochytrid-derived fatty acids. This was confirmed by compound specific stable isotope analysis (CSIA) which revealed significantly 13C-depleted (δ13C value of −24‰) ω3 long-chain (≥C20) polyunsaturated fatty acids (ω3 LC-PUFAs) in the fingerlings fed the thraustochytrid biomass containing diet, reflecting the highly 13C-depleted glycerol used to grow the thraustochytrid cultures. This finding demonstrates the bioavailability of the ω3 LC-PUFA of the Australian strain thraustochytrid culture (TC) 20 from the whole cell biomass that was partly cultivated on crude glycerol produced during biodiesel manufacturing. This paper demonstrates the value of Australian thraustochytrid strains grown heterotrophically for their wider biotechnological potential including as a source of higher value lipids, in particular the health-benefitting ω3 LC-PUFA, for use in aquaculture and other applications.

Patient- and area-level predictors of prostate cancer among South Carolina veterans: a spatial analysis - Peter Georgantopoulos; Jan M. Eberth; Bo Cai; Christopher Emrich; Gowtham Rao; Charles L. Bennett; Kathlyn S. Haddock; James R. Hébert (Cancer Causes & Control, 2020)

Tissue toxicants and prespawn mortality in Willamette River Chinook salmon - Matthew L. Keefer; George P. Naughton; Tami S. Clabough; Matthew J. Knoff; Timothy J. Blubaugh; Mark R. Morasch; Peter G. Green; Christopher C. Caudill (Environmental Biology of Fishes, 2020)

Male characteristics as predictors of genital color and display variation in vervet monkeys - Mirjam M. I. Young; Sandra Winters; Christopher Young; Brigitte M. Weiß; Jolyon Troscianko; André Ganswindt; Louise Barrett; S. Peter Henzi; James P. Higham; Anja Widdig (Behavioral Ecology and Sociobiology, 2020)
In the animal kingdom, conspicuous colors are often used for inter- and intra-sexual communication. Even though primates are the most colorful mammalian taxon, many questions, including what potential information color signals communicate to social partners, are not fully understood. Vervet monkeys ( Chlorocebus pygerythrus ) are ideal to examine the covariates of color signals. Males have multi-colored genitals, which they present during distinctive male-male interactions, known as the “Red-White-and-Blue” (RWB) display, but the genitals are also visible across a variety of other contexts, and it is unclear what this color display signals to recipients. We recorded genital color presentations and standardized digital photos of male genitals ( N = 405 photos) over one mating season for 20 adult males in three groups at the Samara Private Game Reserve, South Africa. We combined these with data on male characteristics (dominance, age, tenure length, injuries, and fecal glucocorticoid metabolite concentrations). Using visual modeling methods, we measured single colors (red, white, blue) but also the contrasts between colors. We assessed the frequency of the RWB genital display and male variation in genital coloration and linked this to male characteristics. Our data suggest that the number of genital displays increased with male dominance. However, none of the variables investigated explained the inter- and intra-individual variation in male genital coloration. These results suggest that the frequency of the RWB genital display, but not its color value, is related to dominance, providing valuable insights on covariation in color signals and their display in primates. Significance statement Conspicuous colors in animals often communicate individual quality to mates and rivals. By investigating vervet monkeys, a primate species in which males present their colorful genitals within several behavioral displays, we aim to identify the covariates of such colorful signals and their behavioral display. Using visual modeling methods for the color analysis and combining behavioral display data and color data with male characteristics, we found that high-ranking males displayed their colorful genitals more frequently than lower-ranking ones. In contrast, color variation was not influenced by male dominance, age, tenure length, or health. Our results can serve as a basis for future investigations on the function of colorful signals and behavioral displays, such as a badge of status or mate choice in primates.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

A conceptual framework for the identification and characterization of lacustrine spawning habitats for native lake charr Salvelinus namaycush - Stephen C. Riley; J. Ellen Marsden; Mark S. Ridgway; Christopher P. Konrad; Steven A. Farha; Thomas R. Binder; Trevor A. Middel; Peter C. Esselman; Charles C. Krueger (Environmental Biology of Fishes, 2019)

Sequence stratigraphic analysis and reservoir quality assessment of an onshore field, Central Swamp Depobelt, Niger Delta Basin, Nigeria - Okwudiri Aloysius Anyiam; Joseph Nanaoweikule Eradiri; Ayonma Wilfred Mode; Chukwudike Gabriel Okeugo; Ikenna Christopher Okwara; Peter Onyedikachi Ibemesi (Arabian Journal of Geosciences, 2019)

Persistence of an endangered native duck, feral mallards, and multiple hybrid swarms across the main Hawaiian Islands - Caitlin P. Wells; Philip Lavretsky; Michael D. Sorenson; Jeffrey L. Peters; Jeffrey M. DaCosta; Stephen Turnbull; Kimberly J. Uyehara; Christopher P. Malachowski; Bruce D. Dugger; John M. Eadie; Andrew Engilis (Molecular Ecology, 2019)
Interspecific hybridization is recognized as an important process in the evolutionary dynamics of both speciation and the reversal of speciation. However, our understanding of the spatial and temporal patterns of hybridization that erode versus promote species boundaries is incomplete. The endangered, endemic koloa maoli (or Hawaiian duck, Anas wyvilliana ) is thought to be threatened with genetic extinction through ongoing hybridization with an introduced congener, the feral mallard ( A. platyrhynchos ). We investigated spatial and temporal variation in hybrid prevalence in populations throughout the main Hawaiian Islands, using genomic data to characterize population structure of koloa, quantify the extent of hybridization, and compare hybrid proportions over time. To accomplish this, we genotyped 3,308 double‐digest restriction‐site‐associated DNA (ddRAD) loci in 425 putative koloa, mallards, and hybrids from populations across the main Hawaiian Islands. We found that despite a population decline in the last century, koloa genetic diversity is high. There were few hybrids on the island of Kauaʻi, home to the largest population of koloa. By contrast, we report that sampled populations outside of Kauaʻi can now be characterized as hybrid swarms, in that all individuals sampled were of mixed koloa × mallard ancestry. Further, there is some evidence that these swarms are stable over time. These findings demonstrate spatial variation in the extent and consequences of interspecific hybridization, and highlight how islands or island‐like systems with small population sizes may be especially prone to genetic extinction when met with a congener that is not reproductively isolated.

Defining a spectrum of integrative trait‐based vegetation canopy structural types - Robert T. Fahey; Jeff W. Atkins; Christopher M. Gough; Brady S. Hardiman; Lucas E. Nave; Jason M. Tallant; Knute J. Nadehoffer; Christoph Vogel; Cynthia M. Scheuermann; Ellen Stuart‐Haëntjens; Lisa T. Haber; Alexander T. Fotis; et al. (Ecology Letters, 2019)
Vegetation canopy structure is a fundamental characteristic of terrestrial ecosystems that defines vegetation types and drives ecosystem functioning. We use the multivariate structural trait composition of vegetation canopies to classify ecosystems within a global canopy structure spectrum. Across the temperate forest sub‐set of this spectrum, we assess gradients in canopy structural traits, characterise canopy structural types (CST) and evaluate drivers and functional consequences of canopy structural variation. We derive CSTs from multivariate canopy structure data, illustrating variation along three primary structural axes and resolution into six largely distinct and functionally relevant CSTs. Our results illustrate that within‐ecosystem successional processes and disturbance legacies can produce variation in canopy structure similar to that associated with sub‐continental variation in forest types and eco‐climatic zones. The potential to classify ecosystems into CSTs based on suites of structural traits represents an important advance in understanding and modelling structure–function relationships in vegetated ecosystems.

The next generation of satellite laser ranging systems - Matthew Wilkinson; Ulrich Schreiber; Ivan Procházka; Christopher Moore; John Degnan; Georg Kirchner; Zhang Zhongping; Peter Dunn; Victor Shargorodskiy; Mikhail Sadovnikov; Clément Courde; Hiroo Kunimori (Journal of Geodesy, 2019)

Belowground Biomass Response to Nutrient Enrichment Depends on Light Limitation Across Globally Distributed Grasslands - Elsa E. Cleland; Eric M. Lind; Nicole M. DeCrappeo; Elizabeth DeLorenze; Rachel Abbott Wilkins; Peter B. Adler; Jonathan D. Bakker; Cynthia S. Brown; Kendi F. Davies; Ellen Esch; Jennifer Firn; Scott Gressard; et al. (Ecosystems, 2019)

Taiwan salmon or salmon in Taiwan? Celebrating the 100th anniversary of the discovery of Formosa landlocked salmon - Francis Juanes; Peter S. Rand; Christopher P. Burridge (Ichthyological Research, 2019)

Can urban greening increase vector abundance in cities? The impact of mowing, local vegetation, and landscape composition on adult mosquito populations - Liu Yang; Katherine J. Turo; Christopher B. Riley; Edna Alfaro Inocente; Jiaxuan Tian; Nicole C. Hoekstra; Peter M. Piermarini; Mary M. Gardiner (Urban Ecosystems, 2019)

Age-Related Decrease in Tyrosine Hydroxylase Immunoreactivity in the Substantia Nigra and Region-Specific Changes in Microglia Morphology in HIV-1 Tg Rats - David R. Goulding; Andrew Kraft; Peter R. Mouton; Christopher A. McPherson; Valeria Avdoshina; Italo Mocchetti; G. Jean Harry (Neurotoxicity Research, 2019)

A Bioluminescence Reporter Assay for Retinoic Acid Control of Translation of the GluR1 Subunit of the AMPA Glutamate Receptor - Thabat Khatib; Andrew Whiting; David R. Chisholm; Christopher Redfern; Berndt Müller; Peter McCaffery (Molecular Neurobiology, 2019)

Pattern and scale: evaluating generalities in crab distributions and marsh dynamics from small plots to a national scale - Kerstin Wasson; Kenneth Raposa; Monica Almeida; Kathryn Beheshti; Jeffrey A. Crooks; Anna Deck; Nikki Dix; Caitlin Garvey; Jason Goldstein; David Samuel Johnson; Scott Lerberg; Pamela Marcum; et al. (Ecology, 2019)
The generality of ecological patterns depends inextricably on the scale at which they are examined. We investigated patterns of crab distribution and the relationship between crabs and vegetation in salt marshes at multiple scales. By using consistent monitoring protocols across 15 U.S. National Estuarine Research Reserves, we were able to synthesize patterns from the scale of quadrats to the entire marsh landscape to regional and national scales. Some generalities emerged across marshes from our overall models, and these are useful for informing broad coastal management policy. We found that crab burrow distribution within a marsh could be predicted by marsh elevation, distance to creek and soil compressibility. While these physical factors also affected marsh vegetation cover, we did not find a strong or consistent overall effect of crabs at a broad scale in our multivariate model, though regressions conducted separately for each site revealed that crab burrows were negatively correlated with vegetation cover at 4 out of 15 sites. This contrasts with recent smaller‐scale studies and meta‐analyses synthesizing such studies that detected strong negative effects of crabs on marshes, likely because we sampled across the entire marsh landscape, while targeted studies are typically limited to low‐lying areas near creeks, where crab burrow densities are highest. Our results suggest that sea‐level rise generally poses a bigger threat to marshes than crabs, but there will likely be interactions between these physical and biological factors. Beyond these generalities across marshes, we detected some regional differences in crab community composition, richness, and abundance. However, we found striking differences among sites within regions, and within sites, in terms of crab abundance and relationships to marsh integrity. Although generalities are broadly useful, our findings indicate that local managers cannot rely on data from other nearby systems, but rather need local information for developing salt marsh management strategies.

Combining sediment fingerprinting with age-dating sediment using fallout radionuclides for an agricultural stream, Walnut Creek, Iowa, USA - Allen C. Gellis; Christopher C. Fuller; Peter Van Metre; Christopher T. Filstrup; Mark D. Tomer; Kevin J. Cole; Timur Y. Sabitov (Journal of Soils and Sediments, 2019)

Global in situ Observations of Essential Climate and Ocean Variables at the Air–Sea Interface - Luca R. Centurioni; Jon Turton; Rick Lumpkin; Lancelot Braasch; Gary Brassington; Yi Chao; Etienne Charpentier; Zhaohui Chen; Gary Corlett; Kathleen Dohan; Craig Donlon; Champika Gallage; et al. (Frontiers in Marine Science, 2019)

Observational Needs of Sea Surface Temperature - Anne G. O’Carroll; Edward M. Armstrong; Helen M. Beggs; Marouan Bouali; Kenneth S. Casey; Gary K. Corlett; Prasanjit Dash; Craig J. Donlon; Chelle L. Gentemann; Jacob L. Høyer; Alexander Ignatov; Kamila Kabobah; et al. (Frontiers in Marine Science, 2019)

Plumage and bill abnormalities in albatross chicks on Marion Island - Michelle M. Risi; Christopher W. Jones; Stefan Schoombie; Peter G. Ryan (Polar Biology, 2019)

The state of Western Australia’s coral reefs - James P. Gilmour; Kylie L. Cook; Nicole M. Ryan; Marjetta L. Puotinen; Rebecca H. Green; George Shedrawi; Jean-Paul A. Hobbs; Damian P. Thomson; Russell C. Babcock; Joanna Buckee; Taryn Foster; Zoe T. Richards; et al. (Coral Reefs, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Taxonomy of the order Bunyavirales: update 2019 - Abulikemu Abudurexiti; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; et al. (Archives of Virology, 2019)

High indirect fitness benefits for helpers across the nesting cycle in the tropical paper wasp Polistes canadensis - Robin J. Southon; Emily F. Bell; Peter Graystock; Christopher D. R. Wyatt; Andrew N. Radford; Seirian Sumner (Molecular Ecology, 2019)
Explaining the evolution of helping behaviour in the eusocial insects where nonreproductive (“worker”) individuals help raise the offspring of other individuals (“queens”) remains one of the most perplexing phenomena in the natural world. Polistes paper wasps are popular study models, as workers retain the ability to reproduce: such totipotency is likely representative of the early stages of social evolution. Polistes is thought to have originated in the tropics, where seasonal constraints on reproductive options are weak and social groups are effectively perennial. Yet, most Polistes research has focused on nontropical species, where seasonality causes family groups to disperse; cofoundresses forming new nests the following spring are often unrelated, leading to the suggestion that direct fitness through nest inheritance is key in the evolution of helping behaviour. Here, we present the first comprehensive genetic study of social structure across the perennial nesting cycle of a tropical Polistes — Polistes canadensis . Using both microsatellites and newly developed single nucleotide polymorphism markers, we show that adult cofoundresses are highly related and that brood production is monopolized by a single female across the nesting cycle. Nonreproductive cofoundresses in tropical Polistes therefore have the potential to gain high indirect fitness benefits as helpers from the outset of group formation, and these benefits persist through the nesting cycle. Direct fitness may have been less important in the origin of Polistes sociality than previously suggested. These findings stress the importance of studying a range of species with diverse life history and ecologies when considering the evolution of reproductive strategies.

Stage-specific effects of Lobophora on the recruitment success of a reef-building coral - Nicolas R. Evensen; Christopher Doropoulos; Kelly J. Wong; Peter J. Mumby (Coral Reefs, 2019)

What is marine justice? - Jennifer A. Martin; Summer Gray; Eréndira Aceves-Bueno; Peter Alagona; Tammy L. Elwell; Angela Garcia; Zach Horton; David Lopez-Carr; Jessica Marter-Kenyon; Karly Marie Miller; Christopher Severen; Teresa Shewry; et al. (Journal of Environmental Studies and Sciences, 2019)

Identification and characterization of a novel anti-inflammatory lipid isolated from Mycobacterium vaccae, a soil-derived bacterium with immunoregulatory and stress resilience properties - David G. Smith; Roberta Martinelli; Gurdyal S. Besra; Petr A. Illarionov; Istvan Szatmari; Peter Brazda; Mary A. Allen; Wenqing Xu; Xiang Wang; László Nagy; Robin D. Dowell; Graham A. W. Rook; et al. (Psychopharmacology, 2019)

Pulse Arrival Time and Pulse Interval as Accurate Markers to Detect Mechanical Alternans - Stefan van Duijvenboden; Ben Hanson; Nick Child; Pier D. Lambiase; Christopher A. Rinaldi; Gill Jaswinder; Peter Taggart; Michele Orini (Annals of Biomedical Engineering, 2019)

Large birds travel farther in homogeneous environments - Marlee A. Tucker; Olga Alexandrou; Richard O. Bierregaard; Keith L. Bildstein; Katrin Böhning‐Gaese; Chloe Bracis; John N. Brzorad; Evan R. Buechley; David Cabot; Justin M. Calabrese; Carlos Carrapato; Andre Chiaradia; et al. (Global Ecology and Biogeography, 2019)
Aim Animal movement is an important determinant of individual survival, population dynamics and ecosystem structure and function. Nonetheless, it is still unclear how local movements are related to resource availability and the spatial arrangement of resources. Using resident bird species and migratory bird species outside the migratory period, we examined how the distribution of resources affects the movement patterns of both large terrestrial birds (e.g., raptors, bustards and hornbills) and waterbirds (e.g., cranes, storks, ducks, geese and flamingos). Location Global. Time period 2003–2015. Major taxa studied Birds. Methods We compiled GPS tracking data for 386 individuals across 36 bird species. We calculated the straight‐line distance between GPS locations of each individual at the 1‐hr and 10‐day time‐scales. For each individual and time‐scale, we calculated the median and 0.95 quantile of displacement. We used linear mixed‐effects models to examine the effect of the spatial arrangement of resources, measured as enhanced vegetation index homogeneity, on avian movements, while accounting for mean resource availability, body mass, diet, flight type, migratory status and taxonomy and spatial autocorrelation. Results We found a significant effect of resource spatial arrangement at the 1‐hr and 10‐day time‐scales. On average, individual movements were seven times longer in environments with homogeneously distributed resources compared with areas of low resource homogeneity. Contrary to previous work, we found no significant effect of resource availability, diet, flight type, migratory status or body mass on the non‐migratory movements of birds. Main conclusions We suggest that longer movements in homogeneous environments might reflect the need for different habitat types associated with foraging and reproduction. This highlights the importance of landscape complementarity, where habitat patches within a landscape include a range of different, yet complementary resources. As habitat homogenization increases, it might force birds to travel increasingly longer distances to meet their diverse needs.

Individual and Population Level Variation in the Reproductive Potential of Deep-Sea Corals From Different Regions Within the Gulf of Maine - Christopher Tyler Fountain; Rhian G. Waller; Peter J. Auster (Frontiers in Marine Science, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

The North Atlantic Aerosol and Marine Ecosystem Study (NAAMES): Science Motive and Mission Overview - Michael J. Behrenfeld; Richard H. Moore; Chris A. Hostetler; Jason Graff; Peter Gaube; Lynn M. Russell; Gao Chen; Scott C. Doney; Stephen Giovannoni; Hongyu Liu; Christopher Proctor; Luis M. Bolaños; et al. (Frontiers in Marine Science, 2019)

First evidence of mouse attacks on adult albatrosses and petrels breeding on sub-Antarctic Marion and Gough Islands - Christopher W. Jones; Michelle M. Risi; Jaimie Cleeland; Peter G. Ryan (Polar Biology, 2019)

A Seasonally Dynamic Estuarine Ecosystem Provides a Diverse Prey Base for Elasmobranchs - Sharon L. Every; Christopher J. Fulton; Heidi R. Pethybridge; Peter M. Kyne; David A. Crook (Estuaries and Coasts, 2019)

Transient Grazing and the Dynamics of an Unanticipated Coral–Algal Phase Shift - Yves-Marie Bozec; Christopher Doropoulos; George Roff; Peter J. Mumby (Ecosystems, 2019)

Taxonomy of the order Bunyavirales: second update 2018 - Piet Maes; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; Matthew J. Ballinger; Dennis A. Bente; Martin Beer; Éric Bergeron; Carol D. Blair; Thomas Briese; Michael J. Buchmeier; Felicity J. Burt; et al. (Archives of Virology, 2019)

How commercial fishing effort is managed - Christopher M. Anderson; Melissa J. Krigbaum; Martin C. Arostegui; Megan L. Feddern; John Zachary Koehn; Peter T. Kuriyama; Christina Morrisett; Caitlin I. Allen Akselrud; Melanie J. Davis; Courtney Fiamengo; Ava Fuller; Qi Lee; et al. (Fish and Fisheries, 2019)
Wild capture fisheries produce 90 million tonnes of food each year and have the potential to provide sustainable livelihoods for nearly 40 million people around the world ( http://www.fao.org/3/a-i5555e.pdf ). After decades of overfishing since industrialization, many global fish stocks have recovered, a change brought about through effective management. We provide a synthetic overview of three approaches that managers use to sustain stocks: regulating catch and fishing mortality, regulating effort and regulating spatial access. Within each of these approaches, we describe common restrictions, how they alter incentives to change fishing behaviour, and the resultant ecological, economic and community‐level outcomes. For each approach, we present prominent case‐studies that illustrate behaviour and the corresponding performance. These case‐studies show that sustaining target stocks requires a hard limit on fishing mortality under most conditions, but that additional measures are required to generate economic benefits. Different systems for allocation allow stakeholder communities to strike a locally acceptable balance between profitability and employment.

Melanin mitigates the accelerated decay of mycorrhizal necromass with peatland warming - Christopher W. Fernandez; Katherine Heckman; Randall Kolka; Peter G. Kennedy (Ecology Letters, 2019)

Growth, Photosynthesis, and Cold Tolerance of Eucalyptus benthamii Planted in the Piedmont of North Carolina - John R Butnor; Kurt H Johnsen; Peter H Anderson; Kevin B Hall; Joshua M Halman; Gary J Hawley; Christopher A Maier; Paul G Schaberg (Forest Science, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Colour pattern divergence in reef fish species is rapid and driven by both range overlap and symmetry - Christopher R. Hemingson; Peter F. Cowman; Jennifer R. Hodge; David R. Bellwood (Ecology Letters, 2019)
Signal divergence is an important process underpinning the diversification of lineages. Research has shown that signal divergence is greatest in species pairs that possess high geographic range overlap. However, the influence of range‐size differences within pairs is less understood. We investigated how these factors have shaped signal divergence within brightly coloured coral reef butterflyfishes (genus: Chaetodon ). Using a novel digital imaging methodology, we quantified both colouration and pattern using 250 000 sample points on each fish image. Surprisingly, evolutionary age did not affect colour pattern dissimilarity between species pairs, with average differences arising in just 300 000 years. However, the effect of range overlap and range symmetry was significant. Species‐pair colour patterns become more different with increasing overlap, but only when ranges are similar in size. When ranges differ markedly in area, species‐pair colour patterns become more similar with increasing overlap. This suggests that species with small ranges may maintain non‐colour‐based species boundaries.

Cannabis Addiction and the Brain: a Review - Amna Zehra; Jamie Burns; Christopher Kure Liu; Peter Manza; Corinde E. Wiers; Nora D. Volkow; Gene-Jack Wang (Journal of Neuroimmune Pharmacology, 2018)

Ambient changes exceed treatment effects on plant species abundance in global change experiments - J. Adam Langley; Samantha K. Chapman; Kimberly J. La Pierre; Meghan Avolio; William D. Bowman; David S. Johnson; Forest Isbell; Kevin R. Wilcox; Bryan L. Foster; Mark J. Hovenden; Alan K. Knapp; Sally E. Koerner; et al. (Global Change Biology, 2018)
The responses of species to environmental changes will determine future community composition and ecosystem function. Many syntheses of global change experiments examine the magnitude of treatment effect sizes, but we lack an understanding of how plant responses to treatments compare to ongoing changes in the unmanipulated (ambient or background) system. We used a database of long‐term global change studies manipulating CO 2 , nutrients, water, and temperature to answer three questions: (a) How do changes in plant species abundance in ambient plots relate to those in treated plots? (b) How does the magnitude of ambient change in species‐level abundance over time relate to responsiveness to global change treatments? (c) Does the direction of species‐level responses to global change treatments differ from the direction of ambient change? We estimated temporal trends in plant abundance for 791 plant species in ambient and treated plots across 16 long‐term global change experiments yielding 2,116 experiment–species–treatment combinations. Surprisingly, for most species (57%) the magnitude of ambient change was greater than the magnitude of treatment effects. However, the direction of ambient change, whether a species was increasing or decreasing in abundance under ambient conditions, had no bearing on the direction of treatment effects. Although ambient communities are inherently dynamic, there is now widespread evidence that anthropogenic drivers are directionally altering plant communities in many ecosystems. Thus, global change treatment effects must be interpreted in the context of plant species trajectories that are likely driven by ongoing environmental changes.

Attraction and repulsion of mobile wild organisms to finfish and shellfish aquaculture: a review - Myriam D. Callier; Carrie J. Byron; David A. Bengtson; Peter J. Cranford; Stephen F. Cross; Ulfert Focken; Henrice M. Jansen; Pauline Kamermans; Anders Kiessling; Thomas Landry; Francis O'Beirn; Erik Petersson; et al. (Reviews in Aquaculture, 2018)
Knowledge of aquaculture–environment interactions is essential for the development of a sustainable aquaculture industry and efficient marine spatial planning. The effects of fish and shellfish farming on sessile wild populations, particularly infauna, have been studied intensively. Mobile fauna, including crustaceans, fish, birds and marine mammals, also interact with aquaculture operations, but the interactions are more complex and these animals may be attracted to (attraction) or show an aversion to (repulsion) farm operations with various degrees of effects. This review outlines the main mechanisms and effects of attraction and repulsion of wild animals to/from marine finfish cage and bivalve aquaculture, with a focus on effects on fisheries‐related species. Effects considered in this review include those related to the provision of physical structure (farm infrastructure acting as fish aggregating devices ( FAD s) or artificial reefs ( AR s), the provision of food (e.g. farmed animals, waste feed and faeces, fouling organisms associated with farm structures) and some farm activities (e.g. boating, cleaning). The reviews show that the distribution of mobile organisms associated with farming structures varies over various spatial (vertical and horizontal) and temporal scales (season, feeding time, day/night period). Attraction/repulsion mechanisms have a variety of direct and indirect effects on wild organisms at the level of individuals and populations and may have implication for the management of fisheries species and the ecosystem in the context of marine spatial planning. This review revealed considerable uncertainties regarding the long‐term and ecosystem‐wide consequences of these interactions. The use of modelling may help better understand consequences, but long‐term studies are necessary to better elucidate effects.

Vanishing refuge? Testing the forest refuge hypothesis in coastal East Africa using genome‐wide sequence data for seven amphibians - Christopher D. Barratt; Beryl A. Bwong; Robert Jehle; H. Christoph Liedtke; Peter Nagel; Renske E. Onstein; Daniel M. Portik; Jeffrey W. Streicher; Simon P. Loader (Molecular Ecology, 2018)
High‐throughput sequencing data have greatly improved our ability to understand the processes that contribute to current biodiversity patterns. The “vanishing refuge” diversification model is speculated for the coastal forests of eastern Africa, whereby some taxa have persisted and diversified between forest refugia, while others have switched to becoming generalists also present in non‐forest habitats. Complex arrangements of geographical barriers (hydrology and topography) and ecological gradients between forest and non‐forest habitats may have further influenced the region's biodiversity, but elucidation of general diversification processes has been limited by lack of suitable data. Here, we explicitly test alternative diversification modes in the coastal forests using genome‐wide single nucleotide polymorphisms, mtDNA, spatial and environmental data for three forest ( Arthroleptis xenodactyloides , Leptopelis flavomaculatus and Afrixalus sylvaticus ) and four generalist ( Afrixalus fornasini , A. delicatus , Leptopelis concolor and Leptopelis argenteus ) amphibians. Multiple analyses provide insight about divergence times, spatial population structure, dispersal barriers, environmental stability and demographic history. We reveal highly congruent intra‐specific diversity and population structure across taxa, with most divergences occurring during the late Pliocene and Pleistocene. Although stability models support the existence of some forest refugia, dispersal barriers and demographic models point towards idiosyncratic diversification modes across taxa. We identify a consistent role for riverine barriers in the diversification of generalist taxa, but mechanisms of diversification are more complex for forest taxa and potentially include topographical barriers, forest refugia and ecological gradients. Our work demonstrates the complexity of diversification processes in this region, which vary between forest and generalist taxa, but also for ecologically similar species with shared population boundaries.

Rare loss of function variants in candidate genes and risk of colorectal cancer - Elisabeth A. Rosenthal; Brian H. Shirts; Laura M. Amendola; Martha Horike-Pyne; Peggy D. Robertson; Fuki M. Hisama; Robin L. Bennett; Michael O. Dorschner; Deborah A. Nickerson; Ian B. Stanaway; Rami Nassir; Kathy T. Vickers; et al. (Human Genetics, 2018)

Effects of urbanization on the population structure of freshwater turtles across the United States - David R. Bowne; Bradley J. Cosentino; Laurel J. Anderson; Christopher P. Bloch; Sandra Cooke; Patrick W. Crumrine; Jason Dallas; Alexandra Doran; Jerald J. Dosch; Daniel L. Druckenbrod; Richard D. Durtsche; Danielle Garneau; et al. (Conservation Biology, 2018)
Landscape‐scale alterations that accompany urbanization may negatively affect the population structure of wildlife species such as freshwater turtles. Changes to nesting sites and higher mortality rates due to vehicular collisions and increased predator populations may particularly affect immature turtles and mature female turtles. We hypothesized that the proportions of adult female and immature turtles in a population will negatively correlate with landscape urbanization. As a collaborative effort of the Ecological Research as Education Network (EREN), we sampled freshwater turtle populations in 11 states across the central and eastern United States. Contrary to expectations, we found a significant positive relationship between proportions of mature female painted turtles ( Chrysemys picta ) and urbanization. We did not detect a relationship between urbanization and proportions of immature turtles. Urbanization may alter the thermal environment of nesting sites such that more females are produced as urbanization increases. Our approach of creating a collaborative network of scientists and students at undergraduate institutions proved valuable in terms of testing our hypothesis over a large spatial scale while also allowing students to gain hands‐on experience in conservation science.

AMMI analysis of cassava response to contrasting environments: case study of genotype by environment effect on pests and diseases, root yield, and carotenoids content in Cameroon - Apollin Kuate Fotso; Rachid Hanna; Peter Kulakow; Elisabeth Parkes; Peter Iluebbey; Francis Ajebesone Ngome; Christopher Suh; Jacques Massussi; Ibrahim Choutnji; Venasius Lendzemo Wirnkar (Euphytica, 2018)

Genetic variation underlying local adaptation of diapause induction along a cline in a butterfly - Peter Pruisscher; Sören Nylin; Karl Gotthard; Christopher W. Wheat (Molecular Ecology, 2018)
Diapause is a life history strategy allowing individuals to arrest development until favourable conditions return, and it is commonly induced by shortened day length that is latitude specific for local populations. Although understanding the evolutionary dynamics of a threshold trait like diapause induction provides insights into the adaptive process and adaptive potential of populations, the genetic mechanism of variation in photoperiodic induction of diapause is not well understood. Here, we investigate genetic variation underlying latitudinal variation in diapause induction and the selection dynamics acting upon it. Using a genomewide scan for divergent regions between two populations of the butterfly Pararge aegeria that differ strongly in their induction thresholds, we identified and investigated the patterns of variation in those regions. We then tested the association of these regions with diapause induction using between‐population crosses, finding significant SNP associations in four genes present in two chromosomal regions, one with the gene period , and the other with the genes kinesin , carnitine O‐acetyltransferase and timeless . Patterns of allele frequencies in these two regions in population samples along a latitudinal cline suggest strong selection against heterozygotes at two genes within these loci ( period, timeless ). Evidence for additional loci modifying the diapause decision was found in patterns of allelic change in relation to induction thresholds over the cline, as well as in backcross analyses. Taken together, population‐specific adaptations of diapause induction appear to be due to a combination of alleles of larger and smaller effect size, consistent with an exponential distribution of effect sizes involved in local adaption.

Correction to: Organochlorine Chemical Residues in Northern Cardinal (Cardinalis cardinalis) Eggs from Greater Washington, DC USA - Christopher J. Schmitt; Kathy R. Echols; Paul H. Peterman; Carl E. Orazio; K. Christiana Grim; Shirlee Tan; Nora E. Diggs; Peter P. Marra (Bulletin of Environmental Contamination and Toxicology, 2018)

Taxonomy of the family Arenaviridae and the order Bunyavirales: update 2018 - Piet Maes; Sergey V. Alkhovsky; Yīmíng Bào; Martin Beer; Monica Birkhead; Thomas Briese; Michael J. Buchmeier; Charles H. Calisher; Rémi N. Charrel; Il Ryong Choi; Christopher S. Clegg; Juan Carlos de la Torre; et al. (Archives of Virology, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Consensus guidelines for the use and interpretation of angiogenesis assays - Patrycja Nowak-Sliwinska; Kari Alitalo; Elizabeth Allen; Andrey Anisimov; Alfred C. Aplin; Robert Auerbach; Hellmut G. Augustin; David O. Bates; Judy R. van Beijnum; R. Hugh F. Bender; Gabriele Bergers; Andreas Bikfalvi; et al. (Angiogenesis, 2018)

Prediction of enteric methane production, yield, and intensity in dairy cattle using an intercontinental database - Mutian Niu; Ermias Kebreab; Alexander N. Hristov; Joonpyo Oh; Claudia Arndt; André Bannink; Ali R. Bayat; André F. Brito; Tommy Boland; David Casper; Les A. Crompton; Jan Dijkstra; et al. (Global Change Biology, 2018)
Enteric methane ( CH 4 ) production from cattle contributes to global greenhouse gas emissions. Measurement of enteric CH 4 is complex, expensive, and impractical at large scales; therefore, models are commonly used to predict CH 4 production. However, building robust prediction models requires extensive data from animals under different management systems worldwide. The objectives of this study were to (1) collate a global database of enteric CH 4 production from individual lactating dairy cattle; (2) determine the availability of key variables for predicting enteric CH 4 production (g/day per cow), yield [g/kg dry matter intake ( DMI )], and intensity (g/kg energy corrected milk) and their respective relationships; (3) develop intercontinental and regional models and cross‐validate their performance; and (4) assess the trade‐off between availability of on‐farm inputs and CH 4 prediction accuracy. The intercontinental database covered Europe ( EU ), the United States ( US ), and Australia ( AU ). A sequential approach was taken by incrementally adding key variables to develop models with increasing complexity. Methane emissions were predicted by fitting linear mixed models. Within model categories, an intercontinental model with the most available independent variables performed best with root mean square prediction error ( RMSPE ) as a percentage of mean observed value of 16.6%, 14.7%, and 19.8% for intercontinental, EU , and United States regions, respectively. Less complex models requiring only DMI had predictive ability comparable to complex models. Enteric CH 4 production, yield, and intensity prediction models developed on an intercontinental basis had similar performance across regions, however, intercepts and slopes were different with implications for prediction. Revised CH 4 emission conversion factors for specific regions are required to improve CH 4 production estimates in national inventories. In conclusion, information on DMI is required for good prediction, and other factors such as dietary neutral detergent fiber ( NDF ) concentration, improve the prediction. For enteric CH 4 yield and intensity prediction, information on milk yield and composition is required for better estimation.

Reach and messages of the world's largest ivory burn - Alexander Braczkowski; Matthew H. Holden; Christopher O'Bryan; Chi‐Yeung Choi; Xiaojing Gan; Nicholas Beesley; Yufang Gao; James Allan; Peter Tyrrell; Daniel Stiles; Peadar Brehony; Revocatus Meney; et al. (Conservation Biology, 2018)
Recent increases in ivory poaching have depressed African elephant populations. Successful enforcement has led to ivory stockpiling. Stockpile destruction is becoming increasingly popular, and most destruction has occurred in the last 5 years. Ivory destruction is intended to send a strong message against ivory consumption, both in promoting a taboo on ivory use and catalyzing policy change. However, there has been no effort to establish the distribution and extent of media reporting on ivory destruction events globally. We analyzed media coverage of the largest ivory destruction event in history (Kenya, 30 April 2016) across 11 nation states connected to ivory trade. We used an online‐media crawling tool to search online media outlets and subjected 5 of the largest print newspapers (by circulation) in 5 nations of interest to content analysis. Most online news on the ivory burn came from the United States (81% of 1944 articles), whereas most of the print news articles came from Kenya (61% of 157 articles). Eighty‐six to 97% of all online articles reported the burn as a positive conservation action, whereas 4–50% discussed ivory burning as having a negative impact on elephant conservation. Most articles discussed law enforcement and trade bans as effective for elephant conservation. There was more relative search interest globally in the 2016 Kenyan ivory burn than any other burn in 5 years. Ours is the first attempt to track the reach of media coverage relative to an ivory burn and provides a case study in tracking the effects of a conservation‐marketing event.

Size-related shifts in carbon gain and growth responses to light differ among rainforest evergreens of contrasting shade tolerance - Kerrie M. Sendall; Peter B. Reich; Christopher H. Lusk (Oecologia, 2018)

Historical and current patterns of gene flow in the butterfly Pararge aegeria - Luca Livraghi; Raluca Vodă; Luke Christopher Evans; Melanie Gibbs; Vlad Dincă; Peter W.H. Holland; Tim G. Shreeve; Roger Vila; Leonardo Dapporto; Casper J. Breuker (Journal of Biogeography, 2018)
Aim We have investigated the phylogeography and genetic structure of the Speckled Wood butterfly ( Pararge aegeria ) across its entire distribution range and studied its dispersal both on mainland and across sea straits. The apparent lack of gene flow between Sardinia and Corsica was further investigated by means of mating experiments. Location Europe and North Africa. Methods We sampled 345 individuals and sequenced one mitochondrial gene ( Cytochrome c Oxidase subunit I , COI ) for all samples and two nuclear genes ( wingless and zerknullt ) for a subset of the specimens. A total of 22 females from Corsica and Sardinia were used to establish a series of crosses to investigate reproductive compatibility and were screened for the presence of Wolbachia . Bayesian inference ( BI ) and haplotype networks were employed to infer phylogenetic relationships and a Principal Coordinate Analysis ( PC oA) was used to represent geographical patterns of genetic diversity. Mating and courtship data were analysed using linear mixed effect models. Results We detected two main COI lineages separated by the Mediterranean Sea and maintained over relatively short sea straits. While nuclear gene variation was generally in agreement with that of COI , this was not the case in all areas (e.g. Iberian Peninsula and Corsica/Sardinia). Mating experiments revealed no evidence of reproductive isolation between the lineages, nor clear relation to Wolbachia infection status. Main conclusions We propose that following the post‐glacial recolonization of Europe, the ancestral COI lineage of P. aegeria was maintained in North Africa and Mediterranean islands, while a new lineage colonized from Eastern Europe, replacing and apparently out‐competing the ancestral variant. Several hypotheses are discussed that may explain the local discordance between the nuclear genes and COI , including sex‐specific dispersal, selection and differential rates of gene evolution.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Organochlorine Chemical Residues in Northern Cardinal (Cardinalis cardinalis) Eggs from Greater Washington, DC USA - Christopher J. Schmitt; Kathy R. Echols; Paul H. Peterman; Carl E. Orazio; K. Christiana Grim; Shirlee Tan; Nora E. Diggs; Peter P. Marra (Bulletin of Environmental Contamination and Toxicology, 2018)

Selection for rapid germination and emergence may improve wheat seedling establishment in the presence of soil surface crusts - Monia Anzooman; Jack Christopher; Michael Mumford; Yash P. Dang; Neal W. Menzies; Peter M. Kopittke (Plant and Soil, 2018)

The atmospheric hydrologic cycle in the ACME v0.3 model - Christopher R. Terai; Peter M. Caldwell; Stephen A. Klein; Qi Tang; Marcia L. Branstetter (Climate Dynamics, 2018)

Transformation in a changing climate: a research agenda - Ioan Fazey; Peter Moug; Simon Allen; Kate Beckmann; David Blackwood; Mike Bonaventura; Kathryn Burnett; Mike Danson; Ruth Falconer; Alexandre S. Gagnon; Rachel Harkness; Anthony Hodgson; et al. (Climate and Development, 2018)

Groundwater Hydrology and Quality in Drained Wetlands of the Des Moines Lobe in Iowa - Keith E. Schilling; Peter J. Jacobson; Matthew T. Streeter; Christopher S. Jones (Wetlands, 2018)

Managing cropland and rangeland for climate mitigation: an expert elicitation on soil carbon in California - Charlotte Y. Stanton; Katharine J. Mach; Peter A. Turner; Seth J. Lalonde; Daniel L. Sanchez; Christopher B. Field (Climatic Change, 2018)

Neurogenesis in Response to Synthetic Retinoids at Different Temporal Scales - Hesham Haffez; Thabat Khatib; Peter McCaffery; Stefan Przyborski; Christopher Redfern; Andrew Whiting (Molecular Neurobiology, 2018)

Update to ‘Re: Tarazona et al. (2017): glyphosate toxicity and carcinogenicity: a review of the scientific basis of the European Union assessment and its differences with IARC. doi: 10.1007/s00204-017-1962-5’ - Christopher J. Portier; Peter Clausing (Archives of Toxicology, 2018)

Biodiversity and climate determine the functioning of Neotropical forests - Lourens Poorter; Masha T. van der Sande; Eric J. M. M. Arets; Nataly Ascarrunz; Brian Enquist; Bryan Finegan; Juan Carlos Licona; Miguel Martínez‐Ramos; Lucas Mazzei; Jorge A. Meave; Rodrigo Muñoz; Christopher J. Nytch; et al. (Global Ecology and Biogeography, 2018)

Efficacy of remote underwater video cameras for monitoring tropical wetland fishes - Alison J. King; Amy George; Duncan J. Buckle; Peter A. Novak; Christopher J. Fulton (Hydrobiologia, 2018)

Assessing uncertainties in crop and pasture ensemble model simulations of productivity and N 2 O emissions - Fiona Ehrhardt; Jean‐François Soussana; Gianni Bellocchi; Peter Grace; Russel McAuliffe; Sylvie Recous; Renáta Sándor; Pete Smith; Val Snow; Massimiliano de Antoni Migliorati; Bruno Basso; Arti Bhatia; et al. (Global Change Biology, 2018)
Simulation models are extensively used to predict agricultural productivity and greenhouse gas emissions. However, the uncertainties of (reduced) model ensemble simulations have not been assessed systematically for variables affecting food security and climate change mitigation, within multi‐species agricultural contexts. We report an international model comparison and benchmarking exercise, showing the potential of multi‐model ensembles to predict productivity and nitrous oxide (N 2 O) emissions for wheat, maize, rice and temperate grasslands. Using a multi‐stage modelling protocol, from blind simulations (stage 1) to partial (stages 2–4) and full calibration (stage 5), 24 process‐based biogeochemical models were assessed individually or as an ensemble against long‐term experimental data from four temperate grassland and five arable crop rotation sites spanning four continents. Comparisons were performed by reference to the experimental uncertainties of observed yields and N 2 O emissions. Results showed that across sites and crop/grassland types, 23%–40% of the uncalibrated individual models were within two standard deviations ( SD ) of observed yields, while 42 (rice) to 96% (grasslands) of the models were within 1 SD of observed N 2 O emissions. At stage 1, ensembles formed by the three lowest prediction model errors predicted both yields and N 2 O emissions within experimental uncertainties for 44% and 33% of the crop and grassland growth cycles, respectively. Partial model calibration (stages 2–4) markedly reduced prediction errors of the full model ensemble E‐median for crop grain yields (from 36% at stage 1 down to 4% on average) and grassland productivity (from 44% to 27%) and to a lesser and more variable extent for N 2 O emissions. Yield‐scaled N 2 O emissions (N 2 O emissions divided by crop yields) were ranked accurately by three‐model ensembles across crop species and field sites. The potential of using process‐based model ensembles to predict jointly productivity and N 2 O emissions at field scale is discussed.

Evaluating Tidal Wetland Restoration Performance Using National Estuarine Research Reserve System Reference Sites and the Restoration Performance Index (RPI) - Kenneth B. Raposa; Scott Lerberg; Craig Cornu; John Fear; Nina Garfield; Christopher Peter; Robin L.J. Weber; Gregg Moore; David Burdick; Michelle Dionne (Estuaries and Coasts, 2018)

The PPARα-dependent rodent liver tumor response is not relevant to humans: addressing misconceptions - J. Christopher Corton; Jeffrey M. Peters; James E. Klaunig (Archives of Toxicology, 2018)

Range position and climate sensitivity: The structure of among‐population demographic responses to climatic variation - Staci M. Amburgey; David A. W. Miller; Evan H. Campbell Grant; Tracy A. G. Rittenhouse; Michael F. Benard; Jonathan L. Richardson; Mark C. Urban; Ward Hughson; Adrianne B. Brand; Christopher J. Davis; Carmen R. Hardin; Peter W. C. Paton; et al. (Global Change Biology, 2018)
Species’ distributions will respond to climate change based on the relationship between local demographic processes and climate and how this relationship varies based on range position. A rarely tested demographic prediction is that populations at the extremes of a species’ climate envelope (e.g., populations in areas with the highest mean annual temperature) will be most sensitive to local shifts in climate (i.e., warming). We tested this prediction using a dynamic species distribution model linking demographic rates to variation in temperature and precipitation for wood frogs ( Lithobates sylvaticus ) in North America. Using long‐term monitoring data from 746 populations in 27 study areas, we determined how climatic variation affected population growth rates and how these relationships varied with respect to long‐term climate. Some models supported the predicted pattern, with negative effects of extreme summer temperatures in hotter areas and positive effects on recruitment for summer water availability in drier areas. We also found evidence of interacting temperature and precipitation influencing population size, such as extreme heat having less of a negative effect in wetter areas. Other results were contrary to predictions, such as positive effects of summer water availability in wetter parts of the range and positive responses to winter warming especially in milder areas. In general, we found wood frogs were more sensitive to changes in temperature or temperature interacting with precipitation than to changes in precipitation alone. Our results suggest that sensitivity to changes in climate cannot be predicted simply by knowing locations within the species’ climate envelope. Many climate processes did not affect population growth rates in the predicted direction based on range position. Processes such as species‐interactions, local adaptation, and interactions with the physical landscape likely affect the responses we observed. Our work highlights the need to measure demographic responses to changing climate.

Toward N-nitrosamines free water: Formation, prevention, and removal - Peter Adeniyi Alaba; Yahaya Muhammad Sani; Sunday Felix Olupinla; Wan Mohd Wan Daud; Isah Yakub Mohammed; Christopher C. Enweremadu; Olubunmi O. Ayodele (Critical Reviews in Environmental Science and Technology, 2017)

Endocytic Uptake, Transport and Macromolecular Interactions of Anionic PAMAM Dendrimers within Lung Tissue - Christopher J. Morris; Ghaith Aljayyoussi; Omar Mansour; Peter Griffiths; Mark Gumbleton (Pharmaceutical Research, 2017)

Activity of temocillin and 15 other agents, including fosfomycin and colistin, against Enterobacteriaceae in Hong Kong - Margaret Ip; Christopher K. Lai; Kitty S. C. Fung; K-Tak Wong; Chendi Zhu; Sebastien Van de Velde; Dominic N. Tsang; Peter Hawkey (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

The Influence of Legacy P on Lake Water Quality in a Midwestern Agricultural Watershed - Melissa Motew; Xi Chen; Eric G. Booth; Stephen R. Carpenter; Pavel Pinkas; Samuel C. Zipper; Steven P. Loheide; Simon D. Donner; Kai Tsuruta; Peter A. Vadas; Christopher J. Kucharik (Ecosystems, 2017)

Celebrating 30 Years of Ocean Science and Technology at the Monterey Bay Aquarium Research Institute - Francisco Chavez; Peter Brewer; Christopher Scholin (Oceanography, 2017)

Biodiversity and climate determine the functioning of Neotropical forests - Lourens Poorter; Masha T. van der Sande; Eric J. M. M. Arets; Nataly Ascarrunz; Brian J. Enquist; Bryan Finegan; Juan Carlos Licona; Miguel Martínez‐Ramos; Lucas Mazzei; Jorge A. Meave; Rodrigo Muñoz; Christopher J. Nytch; et al. (Global Ecology and Biogeography, 2017)
Aim Tropical forests account for a quarter of the global carbon storage and a third of the terrestrial productivity. Few studies have teased apart the relative importance of environmental factors and forest attributes for ecosystem functioning, especially for the tropics. This study aims to relate aboveground biomass (AGB) and biomass dynamics (i.e., net biomass productivity and its underlying demographic drivers: biomass recruitment, growth and mortality) to forest attributes (tree diversity, community‐mean traits and stand basal area) and environmental conditions (water availability, soil fertility and disturbance). Location Neotropics. Methods We used data from 26 sites, 201 1‐ha plots and >92,000 trees distributed across the Neotropics. We quantified for each site water availability and soil total exchangeable bases and for each plot three key community‐weighted mean functional traits that are important for biomass stocks and productivity. We used structural equation models to test the hypothesis that all drivers have independent, positive effects on biomass stocks and dynamics. Results Of the relationships analysed, vegetation attributes were more frequently associated significantly with biomass stocks and dynamics than environmental conditions (in 67 vs. 33% of the relationships). High climatic water availability increased biomass growth and stocks, light disturbance increased biomass growth, and soil bases had no effect. Rarefied tree species richness had consistent positive relationships with biomass stocks and dynamics, probably because of niche complementarity, but was not related to net biomass productivity. Community‐mean traits were good predictors of biomass stocks and dynamics. Main conclusions Water availability has a strong positive effect on biomass stocks and growth, and a future predicted increase in (atmospheric) drought might, therefore, potentially reduce carbon storage. Forest attributes, including species diversity and community‐weighted mean traits, have independent and important relationships with AGB stocks, dynamics and ecosystem functioning, not only in relatively simple temperate systems, but also in structurally complex hyper‐diverse tropical forests.

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Indigenous arthropod natural enemies of the invasive brown marmorated stink bug in North America and Europe - Paul K. Abram; Kim A. Hoelmer; Angelita Acebes-Doria; Heather Andrews; Elizabeth H. Beers; J. Christopher Bergh; Ric Bessin; David Biddinger; Paul Botch; Matthew L. Buffington; Mary L. Cornelius; Elena Costi; et al. (Journal of Pest Science, 2017)

Laboratory rearing of Halyomorpha halys: methods to optimize survival and fitness of adults during and after diapause - Christopher M. Taylor; Peter L. Coffey; Kelly A. Hamby; Galen P. Dively (Journal of Pest Science, 2017)

Re: Tarazona et al. (2017): Glyphosate toxicity and carcinogenicity: a review of the scientific basis of the European Union assessment and its differences with IARC. doi: 10.1007/s00204-017-1962-5 - Christopher J. Portier; Peter Clausing (Archives of Toxicology, 2017)

Dynamics of direct inter-pack encounters in endangered African wild dogs - Neil R Jordan; Christopher Buse; Alan M Wilson; Krystyna A Golabek; Peter J Apps; John C Lowe; Leanne K Van der Weyde; J Weldon McNutt (Behavioral Ecology and Sociobiology, 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Site Selection: a Case Study in the Identification of Optimal Cysteine Engineered Antibody Drug Conjugates - L. Nathan Tumey; Fengping Li; Brian Rago; Xiaogang Han; Frank Loganzo; Sylvia Musto; Edmund I. Graziani; Sujiet Puthenveetil; Jeffrey Casavant; Kimberly Marquette; Tracey Clark; Jack Bikker; et al. (The AAPS Journal, 2017)

Trans-ethnic fine-mapping of genetic loci for body mass index in the diverse ancestral populations of the Population Architecture using Genomics and Epidemiology (PAGE) Study reveals evidence for multiple signals at established loci - Lindsay Fernández-Rhodes; Jian Gong; Jeffrey Haessler; Nora Franceschini; Mariaelisa Graff; Katherine K. Nishimura; Yujie Wang; Heather M. Highland; Sachiko Yoneyama; William S. Bush; Robert Goodloe; Marylyn D. Ritchie; et al. (Human Genetics, 2017)

Happiness and footprints: assessing the relationship between individual well-being and carbon footprints - Christopher L. Ambrey; Peter Daniels (Environment, Development and Sustainability, 2017)

Markers of physiological stress during exercise under conditions of normoxia, normobaric hypoxia, hypobaric hypoxia, and genuine high altitude - David Richard Woods; John Paul O’Hara; Christopher John Boos; Peter David Hodkinson; Costas Tsakirides; Neil Edward Hill; Darren Jose; Amanda Hawkins; Kelly Phillipson; Antonia Hazlerigg; Nicola Arjomandkhah; Liam Gallagher; et al. (European Journal of Applied Physiology, 2017)

A global database of nitrogen and phosphorus excretion rates of aquatic animals - Michael J. Vanni; Peter B. McIntyre; Dennis Allen; Diane L. Arnott; Jonathan P. Benstead; David J. Berg; Åge Brabrand; Sébastien Brosse; Paul A. Bukaveckas; Adriano Caliman; Krista A. Capps; Luciana S. Carneiro; et al. (Ecology, 2017)
Animals can be important in modulating ecosystem‐level nutrient cycling, although their importance varies greatly among species and ecosystems. Nutrient cycling rates of individual animals represent valuable data for testing the predictions of important frameworks such as the Metabolic Theory of Ecology ( MTE ) and ecological stoichiometry ( ES ). They also represent an important set of functional traits that may reflect both environmental and phylogenetic influences. Over the past two decades, studies of animal‐mediated nutrient cycling have increased dramatically, especially in aquatic ecosystems. Here we present a global compilation of aquatic animal nutrient excretion rates. The dataset includes 10,534 observations from freshwater and marine animals of N and/or P excretion rates. These observations represent 491 species, including most aquatic phyla. Coverage varies greatly among phyla and other taxonomic levels. The dataset includes information on animal body size, ambient temperature, taxonomic affiliations, and animal body N:P. This data set was used to test predictions of MTE and ES , as described in Vanni and McIntyre (2016; Ecology DOI : 10.1002/ecy.1582 ).

Diffusion Tensor Tractography of the Cerebellar Peduncles in Prematurely Born 7-Year-Old Children - Eilon Shany; Terrie E. Inder; Sharon Goshen; Iris Lee; Jeffrey J. Neil; Christopher D. Smyser; Lex W. Doyle; Peter J. Anderson; Joshua S. Shimony (The Cerebellum, 2017)

Ammonia toxicity: from head to toe? - Srinivasan Dasarathy; Rajeshwar P. Mookerjee; Veronika Rackayova; Vinita Rangroo Thrane; Balasubramaniyan Vairappan; Peter Ott; Christopher F. Rose (Metabolic Brain Disease, 2017)

Ectomycorrhizal fungal response to warming is linked to poor host performance at the boreal‐temperate ecotone - Christopher W. Fernandez; Nhu H. Nguyen; Artur Stefanski; Ying Han; Sarah E. Hobbie; Rebecca A. Montgomery; Peter B. Reich; Peter G. Kennedy (Global Change Biology, 2017)
Rising temperatures associated with climate change have been shown to negatively affect the photosynthetic rates of boreal forest tree saplings at their southern range limits. To quantify the responses of ectomycorrhizal ( EM ) fungal communities associated with poorly performing hosts, we sampled the roots of Betula papyrifera and Abies balsamea saplings growing in the B4Warmed (Boreal Forest Warming at an Ecotone in Danger) experiment. EM fungi on the root systems of both hosts were compared from ambient and +3.4 °C air and soil warmed plots at two sites in northern Minnesota. EM fungal communities were assessed with high‐throughput sequencing along with measures of plant photosynthesis, soil temperature, moisture, and nitrogen. Warming selectively altered EM fungal community composition at both the phylum and genus levels, but had no significant effect on EM fungal operational taxonomic unit ( OTU ) diversity. Notably, warming strongly favored EM Ascomycetes and EM fungi with short‐contact hyphal exploration types. Declining host photosynthetic rates were also significantly inversely correlated with EM Ascomycete and EM short‐contact exploration type abundance, which may reflect a shift to less carbon demanding fungi due to lower photosynthetic capacity. Given the variation in EM host responses to warming, both within and between ecosystems, better understanding the link between host performance and EM fungal community structure will to clarify how climate change effects cascade belowground.

Controls of nitrogen cycling evaluated along a well‐characterized climate gradient - Christian von Sperber; Oliver A. Chadwick; Karen L. Casciotti; Kabir G. Peay; Christopher A. Francis; Amy E. Kim; Peter M. Vitousek (Ecology, 2017)
The supply of nitrogen (N) constrains primary productivity in many ecosystems, raising the question “what controls the availability and cycling of N”? As a step toward answering this question, we evaluated N cycling processes and aspects of their regulation on a climate gradient on Kohala Volcano, Hawaii, USA. The gradient extends from sites receiving 3,000 mm/yr, and the pedology and dynamics of rock‐derived nutrients in soils on the gradient are well understood. In particular, there is a soil process domain at intermediate rainfall within which ongoing weathering and biological uplift have enriched total and available pools of rock‐derived nutrients substantially; sites at higher rainfall than this domain are acid and infertile as a consequence of depletion of rock‐derived nutrients, while sites at lower rainfall are unproductive and subject to wind erosion. We found elevated rates of potential net N mineralization in the domain where rock‐derived nutrients are enriched. Higher‐rainfall sites have low rates of potential net N mineralization and high rates of microbial N immobilization, despite relatively high rates of gross N mineralization. Lower‐rainfall sites have moderately low potential net N mineralization, relatively low rates of gross N mineralization, and rates of microbial N immobilization sufficient to sequester almost all the mineral N produced. Bulk soil δ 15 N also varied along the gradient, from +4‰ at high rainfall sites to +14‰ at low rainfall sites, indicating differences in the sources and dynamics of soil N. Our analysis shows that there is a strong association between N cycling and soil process domains that are defined using soil characteristics independent of N along this gradient, and that short‐term controls of N cycling can be understood in terms of the supply of and demand for N.

Testing and deployment of C-VISS (cetacean-borne video camera and integrated sensor system) on wild dolphins - Heidi C. Pearson; Peter W. Jones; Mridula Srinivasan; David Lundquist; Christopher J. Pearson; Karen A. Stockin; Gabriel E. Machovsky-Capuska (Marine Biology, 2017)

Efficacy of entomopathogenic nematodes for control of large pine weevil, Hylobius abietis: effects of soil type, pest density and spatial distribution - Apostolos Kapranas; Ben Malone; Sarajane Quinn; Louise Mc Namara; Christopher D. Williams; Padraig O’Tuama; Arne Peters; Christine T. Griffin (Journal of Pest Science, 2017)

Transitions in climate and energy discourse between Hurricanes Katrina and Sandy - Emily M. Cody; Jennie C. Stephens; James P. Bagrow; Peter Sheridan Dodds; Christopher M. Danforth (Journal of Environmental Studies and Sciences, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Sensitivity of coral recruitment to subtle shifts in early community succession - Christopher Doropoulos; George Roff; Mart‐Simone Visser; Peter J. Mumby (Ecology, 2017)
Community succession following disturbance depends on positive and negative interactions, the strength of which change along environmental gradients. To investigate how early succession affects coral reef recovery, we conducted an 18‐month experiment in Palau, using recruitment tiles and herbivore exclusion cages. One set of reefs has higher wave exposure and had previously undergone a phase shift to macroalgae following a major typhoon, whereas the other set of reefs have lower wave exposure and did not undergo a macroalgal phase shift. Similar successional trajectories were observed at all sites when herbivores were excluded: turf algae dominated early succession, followed by shifts to foliose macroalgae and heterotrophic invertebrates. However, trajectories differed in the presence of herbivores. At low wave exposure reefs, herbivores promoted coralline algae and limited turf and encrusting fleshy algae in crevice microhabitats, facilitating optimal coral recruitment. Under medium wave exposure, relatively higher but still low coverage of turf and encrusting fleshy algae (15–25%) found in crevice microhabitats inhibited coral recruitment, persisting throughout multiple recruitment events. Our results indicate that altered interaction strength in different wave environments following disturbance can drive subtle changes in early succession that cascade to alter secondary succession to coral recruitment and system recovery.

Influence of Numerical Cementation on Multiphase Displacement in Rough Fractures - Adenike Tokan-Lawal; Maša Prodanović; Christopher J. Landry; Peter Eichhubl (Transport in Porous Media, 2017)

Performance on the Cogstate Brief Battery Is Related to Amyloid Levels and Hippocampal Volume in Very Mild Dementia - Yen Ying Lim; Victor L. Villemagne; Simon M. Laws; Robert H. Pietrzak; David Ames; Christopher Fowler; Stephanie Rainey-Smith; Peter J. Snyder; Pierrick Bourgeat; Ralph N. Martins; Olivier Salvado; Christopher C. Rowe; et al. (Journal of Molecular Neuroscience, 2016)

The Role of Ocean Tides on Groundwater-Surface Water Exchange in a Mangrove-Dominated Estuary: Shark River Slough, Florida Coastal Everglades, USA - Christopher G. Smith; René M. Price; Peter W. Swarzenski; Jeremy C. Stalker (Estuaries and Coasts, 2016)

Bioreactor conditioning of valve scaffolds seeded internally with adult stem cells - Allison Kennamer; Leslie Sierad; Richard Pascal; Nicholas Rierson; Christopher Albers; Marius Harpa; Ovidiu Cotoi; Lucian Harceaga; Peter Olah; Preda Terezia; Agneta Simionescu; Dan Simionescu (Tissue Engineering and Regenerative Medicine, 2016)

Rainfall and topography predict gene flow among populations of the declining northern quoll (Dasyurus hallucatus) - Rosemary Hohnen; Katherine D. Tuft; Sarah Legge; Mia Hillyer; Peter B.S. Spencer; Ian J. Radford; Christopher N. Johnson; Christopher P. Burridge (Conservation Genetics, 2016)

Uniting paradigms of connectivity in marine ecology - Christopher J. Brown; Alastair R. Harborne; Claire B. Paris; Peter J. Mumby (Ecology, 2016)
The connectivity of marine organisms among habitat patches has been dominated by two independent paradigms with distinct conservation strategies. One paradigm is the dispersal of larvae on ocean currents, which suggests networks of marine reserves. The other is the demersal migration of animals from nursery to adult habitats, requiring the conservation of connected ecosystem corridors. Here, we suggest that a common driver, wave exposure, links larval and demersal connectivity across the seascape. To study the effect of linked connectivities on fish abundance at reefs, we parameterize a demographic model for The Bahamas seascape using maps of habitats, empirically forced models of wave exposure and spatially realistic three‐dimensional hydrological models of larval dispersal. The integrated empirical‐modeling approach enabled us to study linked connectivity on a scale not currently possible by purely empirical studies. We find sheltered environments not only provide greater nursery habitat for juvenile fish but larvae spawned on adjacent reefs have higher retention, thereby creating a synergistic increase in fish abundance. Uniting connectivity paradigms to consider all life stages simultaneously can help explain the evolution of nursery habitat use and simplifies conservation advice: Reserves in sheltered environments have desirable characteristics for biodiversity conservation and can support local fisheries through adult spillover.

Climate change impacts on a pine stand in Central Siberia - Felicitas Suckow; Petra Lasch-Born; Friedrich-Wilhelm Gerstengarbe; Peter C. Werner; Christopher P. O. Reyer (Regional Environmental Change, 2016)

Ageing with elegans: a research proposal to map healthspan pathways - Walter Luyten; Peter Antal; Bart P. Braeckman; Jake Bundy; Francesca Cirulli; Christopher Fang-Yen; Georg Fuellen; Armand Leroi; Qingfei Liu; Patricia Martorell; Andres Metspalu; Markus Perola; et al. (Biogerontology, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

The effects of intranasal oxytocin in opioid-dependent individuals and healthy control subjects: a pilot study - Josh D. Woolley; Peter A. Arcuni; Christopher S. Stauffer; Daniel Fulford; Dean S. Carson; Steve Batki; Sophia Vinogradov (Psychopharmacology, 2016)

The impacts of increasing drought on forest dynamics, structure, and biodiversity in the United States - James S. Clark; Louis Iverson; Christopher W. Woodall; Craig D. Allen; David M. Bell; Don C. Bragg; Anthony W. D'Amato; Frank W. Davis; Michelle H. Hersh; Ines Ibanez; Stephen T. Jackson; Stephen Matthews; et al. (Global Change Biology, 2016)
We synthesize insights from current understanding of drought impacts at stand‐to‐biogeographic scales, including management options, and we identify challenges to be addressed with new research. Large stand‐level shifts underway in western forests already are showing the importance of interactions involving drought, insects, and fire. Diebacks, changes in composition and structure, and shifting range limits are widely observed. In the eastern US , the effects of increasing drought are becoming better understood at the level of individual trees, but this knowledge cannot yet be confidently translated to predictions of changing structure and diversity of forest stands. While eastern forests have not experienced the types of changes seen in western forests in recent decades, they too are vulnerable to drought and could experience significant changes with increased severity, frequency, or duration in drought. Throughout the continental United States, the combination of projected large climate‐induced shifts in suitable habitat from modeling studies and limited potential for the rapid migration of tree populations suggests that changing tree and forest biogeography could substantially lag habitat shifts already underway. Forest management practices can partially ameliorate drought impacts through reductions in stand density, selection of drought‐tolerant species and genotypes, artificial regeneration, and the development of multistructured stands. However, silvicultural treatments also could exacerbate drought impacts unless implemented with careful attention to site and stand characteristics. Gaps in our understanding should motivate new research on the effects of interactions involving climate and other species at the stand scale and how interactions and multiple responses are represented in models. This assessment indicates that, without a stronger empirical basis for drought impacts at the stand scale, more complex models may provide limited guidance.

A mouse model of the 15q13.3 microdeletion syndrome shows prefrontal neurophysiological dysfunctions and attentional impairment - Simon R. O. Nilsson; Pau Celada; Kim Fejgin; Jonas Thelin; Jacob Nielsen; Noemí Santana; Christopher J. Heath; Peter H. Larsen; Vibeke Nielsen; Brianne A. Kent; Lisa M. Saksida; Tine B. Stensbøl; et al. (Psychopharmacology, 2016)

Inter-subunit disulfide locking of the human P2X3 receptor elucidates ectodomain movements associated with channel gating - Gabriele Stephan; Maria Kowalski-Jahn; Christopher Zens; Günther Schmalzing; Peter Illes; Ralf Hausmann (Purinergic Signalling, 2016)

Models for the red blood cell lifespan - Rajiv P. Shrestha; Joseph Horowitz; Christopher V. Hollot; Michael J. Germain; John A. Widness; Donald M. Mock; Peter Veng-Pedersen; Yossi Chait (Journal of Pharmacokinetics and Pharmacodynamics, 2016)

Gut Wall Metabolism. Application of Pre-Clinical Models for the Prediction of Human Drug Absorption and First-Pass Elimination - Christopher R. Jones; Oliver J. D. Hatley; Anna-Lena Ungell; Constanze Hilgendorf; Sheila Annie Peters; Amin Rostami-Hodjegan (The AAPS Journal, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Bioaugmentation in a pilot-scale constructed wetland to treat domestic wastewater in summer and autumn - Haiyan Pei; Yuanyuan Shao; Christopher Peter Chanway; Wenrong Hu; Panpan Meng; Zheng Li; Yang Chen; Guangxiang Ma (Environmental Science and Pollution Research, 2016)

Long-range fine particulate matter from the 2002 Quebec forest fires and daily mortality in Greater Boston and New York City - Ke Zu; Ge Tao; Christopher Long; Julie Goodman; Peter Valberg (Air Quality, Atmosphere & Health, 2016)

Population genomics of the filarial nematode parasite Wuchereria bancrofti from mosquitoes - Scott T. Small; Lisa J. Reimer; Daniel J. Tisch; Christopher L. King; Bruce M. Christensen; Peter M. Siba; James W. Kazura; David Serre; Peter A. Zimmerman (Molecular Ecology, 2016)
Wuchereria bancrofti is a parasitic nematode and the primary cause of lymphatic filariasis – a disease specific to humans. W. bancrofti currently infects over 90 million people throughout the tropics and has been acknowledged by the world health organization as a vulnerable parasite. Current research has focused primarily on the clinical manifestations of disease and little is known about the evolutionary history of W. bancrofti . To improve upon knowledge of the evolutionary history of W. bancrofti , we whole genome sequenced 13 W. bancrofti larvae. We circumvent many of the difficulties of multiple infections by sampling larvae directly from mosquitoes that were experimentally inoculated with infected blood. To begin, we used whole genome data to reconstruct the historical population size. Our results support a history of fluctuating population sizes that can be correlated with human migration and fluctuating mosquito abundances. Next, we reconstructed the putative pedigree of W. bancrofti worms within an infection using the kinship coefficient. We deduced that there are full‐sib and half‐sib relationships residing within the same larval cohort. Through combined analysis of the mitochondrial and nuclear genomes we concluded that this is likely a results of polyandrous mating, the first time reported for W. bancrofti . Lastly, we scanned the genomes for signatures of natural selection. Annotation of putative selected regions identified proteins that may have aided in a parasitic life style or may have evolved to protect against current drug treatments. We discuss our results in the greater context of understanding the biology of an animal with a unique life history and ecology.

Altered relaxin family receptors RXFP1 and RXFP3 in the neocortex of depressed Alzheimer’s disease patients - Jasinda H. Lee; Shu Qing Koh; Simone Guadagna; Paul T. Francis; Margaret M. Esiri; Christopher P. Chen; Peter T.-H. Wong; Gavin S. Dawe; Mitchell K. P. Lai (Psychopharmacology, 2016)

Evaluation of cystatin C as an early biomarker of cadmium nephrotoxicity in the rat - Walter C. Prozialeck; Aaron VanDreel; Christopher D. Ackerman; Ian Stock; Alexander Papaeliou; Christian Yasmine; Kristen Wilson; Peter C. Lamar; Victoria L. Sears; Joshua Z. Gasiorowski; Karyn M. DiNovo; Vishal S. Vaidya; et al. (BioMetals, 2016)

Transportable data from non-target arthropod field studies for the environmental risk assessment of genetically modified maize expressing an insecticidal double-stranded RNA - Aqeel Ahmad; Ignacio Negri; Wladecir Oliveira; Christopher Brown; Peter Asiimwe; Bernard Sammons; Michael Horak; Changjian Jiang; David Carson (Transgenic Research, 2016)

Meta-studies in land use science: Current coverage and prospects - Jasper van Vliet; Nicholas R. Magliocca; Bianka Büchner; Elizabeth Cook; José M. Rey Benayas; Erle C. Ellis; Andreas Heinimann; Eric Keys; Tien Ming Lee; Jianguo Liu; Ole Mertz; Patrick Meyfroidt; et al. (Ambio, 2016)

Contributions of a global network of tree diversity experiments to sustainable forest plantations - Kris Verheyen; Margot Vanhellemont; Harald Auge; Lander Baeten; Christopher Baraloto; Nadia Barsoum; Simon Bilodeau-Gauthier; Helge Bruelheide; Bastien Castagneyrol; Douglas Godbold; Josephine Haase; Andy Hector; et al. (Ambio, 2016)
The area of forest plantations is increasing worldwide helping to meet timber demand and protect natural forests. However, with global change, monospecific plantations are increasingly vulnerable to abiotic and biotic disturbances. As an adaption measure we need to move to plantations that are more diverse in genotypes, species, and structure, with a design underpinned by science. TreeDivNet, a global network of tree diversity experiments, responds to this need by assessing the advantages and disadvantages of mixed species plantations. The network currently consists of 18 experiments, distributed over 36 sites and five ecoregions. With plantations 1–15 years old, TreeDivNet can already provide relevant data for forest policy and management. In this paper, we highlight some early results on the carbon sequestration and pest resistance potential of more diverse plantations. Finally, suggestions are made for new, innovative experiments in understudied regions to complement the existing network.

Elevated carbon dioxide accelerates the spatial turnover of soil microbial communities - Ye Deng; Zhili He; Jinbo Xiong; Hao Yu; Meiying Xu; Sarah E. Hobbie; Peter B. Reich; Christopher W. Schadt; Angela Kent; Elise Pendall; Matthew Wallenstein; Jizhong Zhou (Global Change Biology, 2016)
Although elevated CO 2 ( eCO 2 ) significantly affects the α ‐diversity, composition, function, interaction and dynamics of soil microbial communities at the local scale, little is known about eCO 2 impacts on the geographic distribution of micro‐organisms regionally or globally. Here, we examined the β ‐diversity of 110 soil microbial communities across six free air CO 2 enrichment ( FACE ) experimental sites using a high‐throughput functional gene array. The β ‐diversity of soil microbial communities was significantly ( P CO 2 conditions, but declined significantly ( P eCO 2 with a slope of −0.0250 than at ambient CO 2 ( aCO 2 ) with a slope of −0.0231 although it varied within each individual site, indicating that the spatial turnover rate of soil microbial communities was accelerated under eCO 2 at a larger geographic scale (e.g. regionally). Both distance and soil properties significantly ( P β ‐diversity. This study provides new hypotheses for further understanding their assembly mechanisms that may be especially important as global CO 2 continues to increase.

Past and future adaptation pathways - Ioan Fazey; Russell M. Wise; Christopher Lyon; Claudia Câmpeanu; Peter Moug; Tammy E. Davies (Climate and Development, 2016)

A New MRI-Based Pediatric Subcortical Segmentation Technique (PSST) - Wai Yen Loh; Alan Connelly; Jeanie L. Y. Cheong; Alicia J. Spittle; Jian Chen; Christopher Adamson; Zohra M. Ahmadzai; Lillian Gabra Fam; Sandra Rees; Katherine J. Lee; Lex W. Doyle; Peter J. Anderson; et al. (Neuroinformatics, 2016)

Effects of common carp (Cyprinus carpio) on sediment mixing depth and mobile phosphorus mass in the active sediment layer of a shallow lake - Brian J. Huser; Przemyslaw G. Bajer; Christopher J. Chizinski; Peter W. Sorensen (Hydrobiologia, 2016)

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

Discovery of QTL for stay-green and heat-stress in barley (Hordeum vulgare) grown under simulated abiotic stress conditions - Peter W. Gous; Lee Hickey; Jack T. Christopher; Jerome Franckowiak; Glen P. Fox (Euphytica, 2016)

Becoming less tolerant with age: sugar maple, shade, and ontogeny - Kerrie M. Sendall; Christopher H. Lusk; Peter B. Reich (Oecologia, 2015)

A genome-wide association study for colorectal cancer identifies a risk locus in 14q23.1 - Mathieu Lemire; Conghui Qu; Lenora W. M. Loo; Syed H. E. Zaidi; Hansong Wang; Sonja I. Berndt; Stéphane Bézieau; Hermann Brenner; Peter T. Campbell; Andrew T. Chan; Jenny Chang-Claude; Mengmeng Du; et al. (Human Genetics, 2015)

The mineralogy and fabric of ‘Brickearths’ in Kent, UK and their relationship to engineering behaviour - Antoni E. Milodowski; Kevin J. Northmore; Simon J. Kemp; David C. Entwisle; David A. Gunn; Peter D. Jackson; David I. Boardman; Aris Zoumpakis; Christopher D. F. Rogers; Neil Dixon; Ian Jefferson; Ian J. Smalley; et al. (Bulletin of Engineering Geology and the Environment, 2015)

Disease insights through cross-species phenotype comparisons - Melissa A. Haendel; Nicole Vasilevsky; Matthew Brush; Harry S. Hochheiser; Julius Jacobsen; Anika Oellrich; Christopher J. Mungall; Nicole Washington; Sebastian Köhler; Suzanna E. Lewis; Peter N. Robinson; Damian Smedley (Mammalian Genome, 2015)

Seascape drivers of M acrocystis pyrifera population genetic structure in the northeast P acific - Mattias L. Johansson; Filipe Alberto; Daniel C. Reed; Peter T. Raimondi; Nelson C. Coelho; Mary A. Young; Patrick T. Drake; Christopher A. Edwards; Kyle Cavanaugh; Jorge Assis; Lydia B. Ladah; Tom W. Bell; et al. (Molecular Ecology, 2015)
At small spatial and temporal scales, genetic differentiation is largely controlled by constraints on gene flow, while genetic diversity across a species' distribution is shaped on longer temporal and spatial scales. We assess the hypothesis that oceanographic transport and other seascape features explain different scales of genetic structure of giant kelp, M acrocystis pyrifera . We followed a hierarchical approach to perform a microsatellite‐based analysis of genetic differentiation in M acrocystis across its distribution in the northeast P acific. We used seascape genetic approaches to identify large‐scale biogeographic population clusters and investigate whether they could be explained by oceanographic transport and other environmental drivers. We then modelled population genetic differentiation within clusters as a function of oceanographic transport and other environmental factors. Five geographic clusters were identified: A laska/ C anada, central C alifornia, continental S anta B arbara, C alifornia C hannel I slands and mainland southern C alifornia/ B aja C alifornia peninsula. The strongest break occurred between central and southern C alifornia, with mainland S anta B arbara sites forming a transition zone between the two. Breaks between clusters corresponded approximately to previously identified biogeographic breaks, but were not solely explained by oceanographic transport. An isolation‐by‐environment ( IBE ) pattern was observed where the northern and southern C hannel I slands clustered together, but not with closer mainland sites, despite the greater distance between them. The strongest environmental association with this IBE pattern was observed with light extinction coefficient, which extends suitable habitat to deeper areas. Within clusters, we found support for previous results showing that oceanographic connectivity plays an important role in the population genetic structure of M acrocystis in the Northern hemisphere.

Exposure-driven macroalgal phase shift following catastrophic disturbance on coral reefs - George Roff; Iliana Chollett; Christopher Doropoulos; Yimnang Golbuu; Robert S. Steneck; Adelle L. Isechal; Robert van Woesik; Peter J. Mumby (Coral Reefs, 2015)

Phylogeography of six codistributed New Zealand cicadas and their relationship to multiple biogeographical boundaries suggest a re‐evaluation of the Taupo Line - Emily A. Ellis; David C. Marshall; Kathy B. R. Hill; Christopher L. Owen; Peter J. J. Kamp; Chris Simon (Journal of Biogeography, 2015)
Aim Comparative biogeographers question the extent to which codistributed species respond similarly to environmental change. Such responses should create similar, appropriately timed patterns of cladogenesis among codistributed taxa compared to evolutionary independence, which may limit the predictions that can be made for unstudied species. Here, we compare phylogeographical patterns across ecologically divergent, codistributed taxa in the light of New Zealand's palaeohistory. Location North Island, New Zealand. Methods Mitochondrial DNA from six codistributed cicada species ( Kikihia ochrina , K. cutora , K. laneorum , K. cauta , K. scutellaris and K. dugdalei ) was analysed using phylogenetic methods and molecular dating techniques. We analysed phylogeographical distributions using analysis of molecular variance ( AMOVA ) to determine the significance of hypothesized biogeographical boundaries for clade differentiation and spatial distribution of genetic diversity. Results Five species ( Kikihia ochrina , K. cutora , K. laneorum , K. cauta and K. scutellaris ) show various degrees of intraspecific concordance with biogeographical boundaries found in previously studied taxa – the Kauri Line, the Northland Line and the newly identified Cockayne's Line. Clade splits of forest species correlate with the Kauri Line and/or Northland Line, whereas splits of scrub/hill species correlate with Cockayne's Line. Four species ( Kikihia ochrina , K. cutora , K. laneorum and K. cauta ) diversified before the Last Glacial Maximum ( LGM , 20 ka), whereas two species ( K. scutellaris and K. dugdalei ) show only post‐ LGM diversification. Main conclusions Despite species idiosyncrasies, we see the imprint of shared palaeoclimatic/geological events. We distinguish between (1) the importance of biogeographical lines as the demarcation between older genetically diverse and newer genetically depauperate populations, and (2) the importance of lines as biogeographical boundaries between sister clades. We also stress the importance of dating clade splits to ensure consistency with explanations for the biogeographical lines in question. We suggest that the Taupo Line has been overemphasized as a biogeographical boundary, whereas the importance of the mountain axis running north‐east to south‐west (‘Cockayne's Line’) has been overlooked.

Net primary production of a temperate deciduous forest exhibits a threshold response to increasing disturbance severity - Ellen J. Stuart-Haëntjens; Peter S. Curtis; Robert T. Fahey; Christoph S. Vogel; Christopher M. Gough (Ecology, 2015)
The global carbon (C) balance is vulnerable to disturbances that alter terrestrial C storage. Disturbances to forests occur along a continuum of severity, from low‐intensity disturbance causing the mortality or defoliation of only a subset of trees to severe stand‐replacing disturbance that kills all trees; yet considerable uncertainty remains in how forest production changes across gradients of disturbance intensity. We used a gradient of tree mortality in an upper Great Lakes forest ecosystem to: (1) quantify how aboveground wood net primary production (ANPP w ) responds to a range of disturbance severities; and (2) identify mechanisms supporting ANPP w resistance or resilience following moderate disturbance. We found that ANPP w declined nonlinearly with rising disturbance severity, remaining stable until >60% of the total tree basal area senesced. As upper canopy openness increased from disturbance, greater light availability to the subcanopy enhanced the leaf‐level photosynthesis and growth of this formerly light‐limited canopy stratum, compensating for upper canopy production losses and a reduction in total leaf area index (LAI). As a result, whole‐ecosystem production efficiency (ANPP w /LAI) increased with rising disturbance severity, except in plots beyond the disturbance threshold. These findings provide a mechanistic explanation for a nonlinear relationship between ANPP w and disturbance severity, in which the physiological and growth enhancement of undisturbed vegetation is proportional to the level of disturbance until a threshold is exceeded. Our results have important ecological and management implications, demonstrating that in some ecosystems moderate levels of disturbance minimally alter forest production.

Phase shift facilitation following cyclone disturbance on coral reefs - George Roff; Christopher Doropoulos; Mirta Zupan; Alice Rogers; Robert S. Steneck; Yimnang Golbuu; Peter J. Mumby (Oecologia, 2015)

GPCR structure, function, drug discovery and crystallography: report from Academia-Industry International Conference (UK Royal Society) Chicheley Hall, 1–2 September 2014 - Alexander Heifetz; Gebhard F. X. Schertler; Roland Seifert; Christopher G. Tate; Patrick M. Sexton; Vsevolod V. Gurevich; Daniel Fourmy; Vadim Cherezov; Fiona H. Marshall; R. Ian Storer; Isabel Moraes; Irina G. Tikhonova; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Migrating Tundra Peregrine Falcons accumulate polycyclic aromatic hydrocarbons along Gulf of Mexico following Deepwater Horizon oil spill - William S. Seegar; Michael A. Yates; Gregg E. Doney; J. Peter Jenny; Tom C. M. Seegar; Christopher Perkins; Matthew Giovanni (Ecotoxicology, 2015)

Past, present, and future of arenavirus taxonomy - Sheli R. Radoshitzky; Yīmíng Bào; Michael J. Buchmeier; Rémi N. Charrel; Anna N. Clawson; Christopher S. Clegg; Joseph L. DeRisi; Sébastien Emonet; Jean-Paul Gonzalez; Jens H. Kuhn; Igor S. Lukashevich; Clarence J. Peters; et al. (Archives of Virology, 2015)

Derek Bendall (1930–2014) - Christopher J. Howe; Peter R. Rich; Marcellus Ubbink (Photosynthesis Research, 2015)

Soil warming and CO 2 enrichment induce biomass shifts in alpine tree line vegetation - Melissa A. Dawes; Christopher D. Philipson; Patrick Fonti; Peter Bebi; Stephan Hättenschwiler; Frank Hagedorn; Christian Rixen (Global Change Biology, 2015)
Responses of alpine tree line ecosystems to increasing atmospheric CO 2 concentrations and global warming are poorly understood. We used an experiment at the Swiss tree line to investigate changes in vegetation biomass after 9 years of free air CO 2 enrichment (+200 ppm; 2001–2009) and 6 years of soil warming (+4 °C; 2007–2012). The study contained two key tree line species, Larix decidua and Pinus uncinata , both approximately 40 years old, growing in heath vegetation dominated by dwarf shrubs. In 2012, we harvested and measured biomass of all trees (including root systems), above‐ground understorey vegetation and fine roots. Overall, soil warming had clearer effects on plant biomass than CO 2 enrichment, and there were no interactive effects between treatments. Total plant biomass increased in warmed plots containing Pinus but not in those with Larix . This response was driven by changes in tree mass (+50%), which contributed an average of 84% (5.7 kg m −2 ) of total plant mass. Pinus coarse root mass was especially enhanced by warming (+100%), yielding an increased root mass fraction. Elevated CO 2 led to an increased relative growth rate of Larix stem basal area but no change in the final biomass of either tree species. Total understorey above‐ground mass was not altered by soil warming or elevated CO 2 . However, Vaccinium myrtillus mass increased with both treatments, graminoid mass declined with warming, and forb and nonvascular plant (moss and lichen) mass decreased with both treatments. Fine roots showed a substantial reduction under soil warming (−40% for all roots CO 2 enrichment. Our findings suggest that enhanced overall productivity and shifts in biomass allocation will occur at the tree line, particularly with global warming. However, individual species and functional groups will respond differently to these environmental changes, with consequences for ecosystem structure and functioning.

Erratum to: Coupling thermodynamic modeling and high-resolution in situ LA-ICP-MS monazite geochronology: evidence for Barrovian metamorphism late in the Grenvillian history of southeastern Ontario - Travis McCarron; Fred Gaidies; Christopher R. M. McFarlane; R. Michael Easton; Peter Jones (Mineralogy and Petrology, 2015)

Implementing Dried Blood Spot Sampling for Clinical Pharmacokinetic Determinations: Considerations from the IQ Consortium Microsampling Working Group - Christopher Evans; Mark Arnold; Peter Bryan; Jeffrey Duggan; Christopher A James; Wenkui Li; Steve Lowes; Luca Matassa; Timothy Olah; Philip Timmerman; Xiaomin Wang; Enaksha Wickremsinhe; et al. (The AAPS Journal, 2015)

A systematic heritability analysis of the human whole blood transcriptome - Tianxiao Huan; Chunyu Liu; Roby Joehanes; Xiaoling Zhang; Brian H. Chen; Andrew D. Johnson; Chen Yao; Paul Courchesne; Christopher J. O’Donnell; Peter J. Munson; Daniel Levy (Human Genetics, 2015)

Anticipative management for coral reef ecosystem services in the 21st century - Alice Rogers; Alastair R. Harborne; Christopher J. Brown; Yves‐Marie Bozec; Carolina Castro; Iliana Chollett; Karlo Hock; Cheryl A. Knowland; Alyssa Marshell; Juan C. Ortiz; Tries Razak; George Roff; et al. (Global Change Biology, 2015)
Under projections of global climate change and other stressors, significant changes in the ecology, structure and function of coral reefs are predicted. Current management strategies tend to look to the past to set goals, focusing on halting declines and restoring baseline conditions. Here, we explore a complementary approach to decision making that is based on the anticipation of future changes in ecosystem state, function and services. Reviewing the existing literature and utilizing a scenario planning approach, we explore how the structure of coral reef communities might change in the future in response to global climate change and overfishing. We incorporate uncertainties in our predictions by considering heterogeneity in reef types in relation to structural complexity and primary productivity. We examine 14 ecosystem services provided by reefs, and rate their sensitivity to a range of future scenarios and management options. Our predictions suggest that the efficacy of management is highly dependent on biophysical characteristics and reef state. Reserves are currently widely used and are predicted to remain effective for reefs with high structural complexity. However, when complexity is lost, maximizing service provision requires a broader portfolio of management approaches, including the provision of artificial complexity, coral restoration, fish aggregation devices and herbivore management. Increased use of such management tools will require capacity building and technique refinement and we therefore conclude that diversification of our management toolbox should be considered urgently to prepare for the challenges of managing reefs into the 21st century.

Direct determination of fatty acids in fish tissues: quantifying top predator trophic connections - Christopher C. Parrish; Peter D. Nichols; Heidi Pethybridge; Jock W. Young (Oecologia, 2015)

Coupling thermodynamic modeling and high-resolution in situ LA-ICP-MS monazite geochronology: evidence for Barrovian metamorphism late in the Grenvillian history of southeastern Ontario - Travis McCarron; Fred Gaidies; Christopher R. M. McFarlane; R. Michael Easton; Peter Jones (Mineralogy and Petrology, 2014)

Evaluating the causal basis of ecological success within the scleractinia: an integral projection model approach - Peter J. Edmunds; Scott C. Burgess; Hollie M. Putnam; Marissa L. Baskett; Lorenzo Bramanti; Nick S. Fabina; Xueying Han; Michael P. Lesser; Joshua S. Madin; Christopher B. Wall; Denise M. Yost; Ruth D. Gates (Marine Biology, 2014)

Infilled Ditches are Hotspots of Landscape Methane Flux Following Peatland Re-wetting - Mark. D. A. Cooper; Christopher. D. Evans; Piotr Zielinski; Peter. E. Levy; Alan Gray; Mike Peacock; David Norris; Nathalie Fenner; Christopher Freeman (Ecosystems, 2014)

Molecular characterization of African swine fever virus from domestic pigs in northern Tanzania during an outbreak in 2013 - Gerald Misinzo; David E. Kwavi; Christopher D. Sikombe; Mariam Makange; Emma Peter; Amandus P. Muhairwa; Michael J. Madege (Tropical Animal Health and Production, 2014)

Optimising diet decisions and urban agriculture using linear programming - James D. Ward; Peter J. Ward; Evangeline Mantzioris; Christopher Saint (Food Security, 2014)

Acute hypoxic exercise does not alter post-exercise iron metabolism in moderately trained endurance athletes - Andrew D. Govus; Chris R. Abbiss; Laura A. Garvican-Lewis; Dorine W. Swinkels; Coby M. Laarakkers; Christopher J. Gore; Peter Peeling (European Journal of Applied Physiology, 2014)

Fine-Scale Detection of Estuarine Water Quality with Managed Freshwater Releases - Christopher Buzzelli; Brian Boutin; Mayra Ashton; Barbara Welch; Patricia Gorman; Yongshan Wan; Peter Doering (Estuaries and Coasts, 2014)

Reef-scale failure of coral settlement following typhoon disturbance and macroalgal bloom in Palau, Western Pacific - Christopher Doropoulos; George Roff; Mirta Zupan; Victor Nestor; Adelle L. Isechal; Peter J. Mumby (Coral Reefs, 2014)

On-Command Drug Release from Nanochains Inhibits Growth of Breast Tumors - Pubudu M. Peiris; Morgan Tam; Peter Vicente; Aaron Abramowski; Randall Toy; Lisa Bauer; Aaron Mayer; Jenna Pansky; Elizabeth Doolittle; Samantha Tucci; Erik Schmidt; Christopher Shoup; et al. (Pharmaceutical Research, 2014)

Heart failure in congenital heart disease: the role of genes and hemodynamics - Rachel D. Vanderlaan; Christopher A. Caldarone; Peter H. Backx (Pflügers Archiv - European Journal of Physiology, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Observations on the crystal structures of lueshite - Roger H. Mitchell; Peter C. Burns; Kevin S. Knight; Christopher J. Howard; Anton R. Chakhmouradian (Physics and Chemistry of Minerals, 2014)

Stand-replacing wildfires increase nitrification for decades in southwestern ponderosa pine forests - Valerie J. Kurth; Stephen C. Hart; Christopher S. Ross; Jason P. Kaye; Peter Z. Fulé (Oecologia, 2014)

Human-resource subsidies alter the dietary preferences of a mammalian top predator - Thomas M. Newsome; Guy-Anthony Ballard; Peter J. S. Fleming; Remy van de Ven; Georgeanna L. Story; Christopher R. Dickman (Oecologia, 2014)

Influence of post-exercise hypoxic exposure on hepcidin response in athletes - Claire E. Badenhorst; Brian Dawson; Carmel Goodman; Marc Sim; Gregory R. Cox; Christopher J. Gore; Harold Tjalsma; Dorine W. Swinkels; Peter Peeling (European Journal of Applied Physiology, 2014)

Exercise-induced oxidative stress and hypoxic exercise recovery - Christopher Ballmann; Graham McGinnis; Bridget Peters; Dustin Slivka; John Cuddy; Walter Hailes; Charles Dumke; Brent Ruby; John Quindry (European Journal of Applied Physiology, 2014)

Physical activity and prostate gene expression in men with low-risk prostate cancer - Mark Jesus M. Magbanua; Erin L. Richman; Eduardo V. Sosa; Lee W. Jones; Jeff Simko; Katsuto Shinohara; Christopher M. Haqq; Peter R. Carroll; June M. Chan (Cancer Causes & Control, 2014)

Animating the Carbon Cycle - Oswald J. Schmitz; Peter A. Raymond; James A. Estes; Werner A. Kurz; Gordon W. Holtgrieve; Mark E. Ritchie; Daniel E. Schindler; Amanda C. Spivak; Rod W. Wilson; Mark A. Bradford; Villy Christensen; Linda Deegan; et al. (Ecosystems, 2014)

Somatische Tumormutationen eröffnen neue Therapieoptionen - Christopher Schroeder; Peter Bauer; Falko Fend; Olaf Riess (BIOspektrum, 2014)

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

SoilTrEC: a global initiative on critical zone research and integration - Manoj Menon; Svetla Rousseva; Nikolaos P. Nikolaidis; Pauline van Gaans; Panos Panagos; Danielle Maia de Souza; Kristin Vala Ragnarsdottir; Georg J. Lair; Liping Weng; Jaap Bloem; Pavel Kram; Martin Novak; et al. (Environmental Science and Pollution Research, 2014)

Mitonuclear discordance in genetic structure across the Atlantic/Indian Ocean biogeographical transition zone - Peter R. Teske; Isabelle Papadopoulos; Nigel P. Barker; Christopher D. McQuaid; Luciano B. Beheregaray (Journal of Biogeography, 2014)
Aim Based on mitochondrial DNA (mt DNA ) data, many organisms with ranges spanning multiple biogeographical regions exhibit genetic structure across the transition zones between these regions, while others appear to be genetically homogenous. No clear link has been found between the presence or absence of such spatial genetic discontinuities and species' dispersal potential, confounding the formulation of general predictions concerning genetic structure. The fact that discrepancies between mt DNA and nuclear markers are common across semi‐permeable barriers suggests that a lack of structure could be attributable to mt DNA ‐specific properties of inheritance. We re‐examined genetic structure in the coastal crab Hymenosoma orbiculare , a species that is represented by a single mt DNA lineage across the Atlantic/Indian Ocean biogeographical transition zone, by comparing mt DNA data with nuclear DNA data. Location South Africa's cool‐temperate and warm‐temperate marine biogeographical provinces. Methods DNA sequence data from the mitochondrial COI gene and the intron of the nuclear ANT gene were generated for 150 individuals of H. orbiculare . For each locus, we determined whether the sharing of alleles between provinces was the result of either the retention of ancestral polymorphism or of secondary contact. Results We recovered two nuclear intron lineages whose spatial genetic structure reflects contemporary biogeographical and oceanographical conditions, indicating that the existence of a single mt DNA lineage is not a function of unexpectedly high levels of dispersal. Main conclusions Mt DNA ‐based genetic homogeneity is increasingly being reported in coastal organisms with ranges spanning biogeographical transition zones that define distinct evolutionary lineages in other species. Our results stress the importance of revisiting single‐locus data sets by means of multilocus genetic approaches before any conclusions can be drawn about the role of biogeographical transition zones in driving genetic structure.

Modelling macronutrients in shelf sea sediments: fitting model output to experimental data using a genetic algorithm - Christopher C. Wood; Peter J. Statham; Boris A. Kelly-Gerreyn; Adrian P. Martin (Journal of Soils and Sediments, 2014)

Delayed life history effects, multilevel selection, and evolutionary trade‐offs in the California tiger salamander - Christopher A. Searcy; Levi N. Gray; Peter C. Trenham; H. Bradley Shaffer (Ecology, 2014)
Delayed life history effects (DLHEs) occur when fitness in one life stage affects fitness in subsequent life stages. Given their biphasic life cycle, pond‐breeding amphibians provide a natural system for studying DLHEs, although these effects are not restricted to species with biphasic life histories. In this study, we used multiple mark–recapture techniques enabled by a large trapping array to monitor components of fitness and resulting DLHEs in a population of the endangered California tiger salamander ( Ambystoma californiense ). We found that DLHEs are prominent across all life stage transitions and that there is variation in whether selection acts primarily at the individual or cohort level. We also demonstrated that there is more than an order of magnitude variation in mean cohort fitness, providing tremendous variation for DLHEs to act upon. We documented an evolutionary trade‐off between mass at emergence and date of emergence, which may play a role in maintaining the variation in mass (fitness) at emergence. A literature review revealed that such high levels of intercohort variation occur in many other pond‐breeding amphibians, and that appropriately documenting the magnitude of intercohort variation requires long‐term studies (roughly two population turnovers). Given the profound effect that DLHEs can have on population dynamics, quantifying intercohort variation in mean fitness and the level(s) at which selection acts will be very important for developing accurate models of population dynamics. In general, when developing models of population dynamics, more attention should be paid to variation in mean fitness and not just variation in total numbers.

Multi-species predator eradication within a predator-proof fence at Ka‘ena Point, Hawai‘i - Lindsay C. Young; Eric A. VanderWerf; Michael T. Lohr; Christopher J. Miller; Andrew J. Titmus; Darren Peters; Lindsay Wilson (Biological Invasions, 2013)

Brooded coral larvae differ in their response to high temperature and elevated pCO2 depending on the day of release - Vivian R. Cumbo; Peter J. Edmunds; Christopher B. Wall; Tung-Yung Fan (Marine Biology, 2013)

Novel deletion of RPL15 identified by array-comparative genomic hybridization in Diamond–Blackfan anemia - Michael Landowski; Marie-Françoise O’Donohue; Christopher Buros; Roxanne Ghazvinian; Nathalie Montel-Lehry; Adrianna Vlachos; Colin A. Sieff; Peter E. Newburger; Edyta Niewiadomska; Michal Matysiak; Bertil Glader; Eva Atsidaftos; et al. (Human Genetics, 2013)

Antagonism of PDGF-BB suppresses subretinal neovascularization and enhances the effects of blocking VEGF-A - Aling Dong; Christopher Seidel; Daniel Snell; Savira Ekawardhani; Julia K. J. Ahlskog; Michael Baumann; Jikui Shen; Takeshi Iwase; Jing Tian; Rebecca Stevens; Sean F. Hackett; Michael T. Stumpp; et al. (Angiogenesis, 2013)

Simulation of Potential Oyster Density with Variable Freshwater Inflow (1965–2000) to the Caloosahatchee River Estuary, Southwest Florida, USA - Christopher Buzzelli; Peter H. Doering; Yongshan Wan; Patricia Gorman; Aswani Volety (Environmental Management, 2013)

nif gene sequence and arrangement in the endophytic diazotroph Paenibacillus polymyxa strain P2b-2R - Richa Anand; Christopher Peter Chanway (Biology and Fertility of Soils, 2013)

Modeling Physical-Biological Responses to Climate Change in the California Current System - Peter Franks; Emanuele Di Lorenzo; Nicole Goebel; Fanny Chenillat; Pascal Riviere; Christopher Edwards; Arthur Miller (Oceanography, 2013)

Interannual variability of net ecosystem productivity in forests is explained by carbon flux phenology in autumn - Chaoyang Wu; Jing M. Chen; T. Andrew Black; David T. Price; Werner A. Kurz; Ankur R. Desai; Alemu Gonsamo; Rachhpal S. Jassal; Christopher M. Gough; Gil Bohrer; Danilo Dragoni; Mathias Herbst; et al. (Global Ecology and Biogeography, 2013)
Aim To investigate the importance of autumn phenology in controlling interannual variability of forest net ecosystem productivity ( NEP ) and to derive new phenological metrics to explain the interannual variability of NEP . Location N orth A merica and E urope. Method Flux data from nine deciduous broadleaf forests ( DBF ) and 13 evergreen needleleaf forests ( ENF ) across N orth A merica and E urope (212 site‐years) were used to explore the relationships between the yearly anomalies of annual NEP and several carbon flux based phenological indicators, including the onset/end of the growing season, onset/end of the carbon uptake period, the spring lag (time interval between the onset of growing season and carbon uptake period) and the autumn lag (time interval between the end of the carbon uptake period and the growing season). Meteorological variables, including global shortwave radiation, air temperature, soil temperature, soil water content and precipitation, were also used to explain the phenological variations. Results We found that interannual variability of NEP can be largely explained by autumn phenology, i.e. the autumn lag. While variation in neither annual gross primary productivity ( GPP ) nor in annual ecosystem respiration ( R e ) alone could explain this variability, the negative relationship between annual NEP and autumn lag was due to a larger R e / GPP ratio in years with a prolonged autumn lag. For DBF sites, a longer autumn lag coincided with a significant decrease in annual GPP but showed no correlation with annual R e . However, annual GPP was insensitive to a longer autumn lag in ENF sites but annual R e increased significantly. Main conclusions These results demonstrate that autumn phenology plays a more direct role than spring phenology in regulating interannual variability of annual NEP . In particular, the importance of respiration may be potentially underestimated in deriving phenological indicators.

Humans, megafauna and environmental change in tropical Australia - MICHAEL I. BIRD; LINDSAY B. HUTLEY; MICHAEL J. LAWES; JON LLOYD; JON G. LULY; PETER V. RIDD; RICHARD G. ROBERTS; SEAN ULM; CHRISTOPHER M. WURSTER (Journal of Quaternary Science, 2013)
Debate concerning the environmental impact of human arrival in Australia has continued for more than a century. Here we review the evidence for human impact and the mechanisms by which humans may have affected the environment of tropical Australia. We limit our review to tropical Australia because, over three decades ago, it was proposed that the imposition of an anthropogenic fire regime upon human occupation of the Australian continent may have resulted in profound changes in regional vegetation and climate across this region. We conclude that ecological processes and vegetation–fire–climate–human feedbacks do exist that could have driven a significant shift in boundary conditions and ecosystem state at the sub‐continental scale through the sustained imposition of an anthropogenic fire regime over tens of millennia. These potential feedbacks operate through the inhibition of forest expansion both directly, by targeted burning at established forest edges and newly irrupted forest patches, and indirectly, through lengthening of the dry season because of changes to the timing of burning. However, the impact of any such anthropogenic forcing may have been entirely overshadowed by the effects of natural climate change and variability, as well as the generally low nutrient status of Australian soils. A robust assessment of the degree to which the environment of tropical Australia at the large scale has been modified from its ‘natural’ state because of human occupation will require new, coordinated collaborations between indigenous traditional landowners, archaeologists, anthropologists, geochronologists, geoscientists, ecologists, climatologists and modellers.

Community well-being as a critical component of urban lake ecosystem health - Christopher Walker; Jane-Louise Lampard; Anne Roiko; Neil Tindale; Aaron Wiegand; Peter Duncan (Urban Ecosystems, 2013)

Three-dimensional Quantification of Femoral Head Shape in Controls and Patients with Cam-type Femoroacetabular Impingement - Michael D. Harris; Shawn P. Reese; Christopher L. Peters; Jeffrey A. Weiss; Andrew E. Anderson (Annals of Biomedical Engineering, 2013)

Ecosystem respiration: Drivers of daily variability and background respiration in lakes around the globe - Christopher T. Solomon; Denise A. Bruesewitz; David C. Richardson; Kevin C. Rose; Matthew C. Van de Bogert; Paul C. Hanson; Timothy K. Kratz; Bret Larget; Rita Adrian; Brenda Leroux Babin; Chih-Yu Chiu; David P. Hamilton; et al. (Limnology and Oceanography, 2013)
We assembled data from a global network of automated lake observatories to test hypotheses regarding the drivers of ecosystem metabolism. We estimated daily rates of respiration and gross primary production (GPP) for up to a full year in each lake, via maximum likelihood fits of a free‐water metabolism model to continuous high‐frequency measurements of dissolved oxygen concentrations. Uncertainties were determined by a bootstrap analysis, allowing lake‐days with poorly constrained rate estimates to be down‐weighted in subsequent analyses. GPP and respiration varied considerably among lakes and at seasonal and daily timescales. Mean annual GPP and respiration ranged from 0.1 to 5.0 mg O 2 L −1 d −1 and were positively related to total phosphorus but not dissolved organic carbon concentration. Within lakes, significant day‐to‐day differences in respiration were common despite large uncertainties in estimated rates on some lake‐days. Daily variation in GPP explained 5% to 85% of the daily variation in respiration after temperature correction. Respiration was tightly coupled to GPP at a daily scale in oligotrophic and dystrophic lakes, and more weakly coupled in mesotrophic and eutrophic lakes. Background respiration ranged from 0.017 to 2.1 mg O 2 L −1 d −1 and was positively related to indicators of recalcitrant allochthonous and autochthonous organic matter loads, but was not clearly related to an indicator of the quality of allochthonous organic matter inputs.

Predicting System-Scale Impacts of Oyster Clearance on Phytoplankton Productivity in a Small Subtropical Estuary - Christopher Buzzelli; Melanie Parker; Stephen Geiger; Yongshan Wan; Peter Doering; Daniel Haunert (Environmental Modeling & Assessment, 2013)

The Critical Richardson Number and Limits of Applicability of Local Similarity Theory in the Stable Boundary Layer - Andrey A. Grachev; Edgar L Andreas; Christopher W. Fairall; Peter S. Guest; P. Ola G. Persson (Boundary-Layer Meteorology, 2013)

Delphinid whistle production and call matching during playback of simulated military sonar - Stacy L. DeRuiter; Ian L. Boyd; Diane E. Claridge; Christopher W. Clark; Chuck Gagnon; Brandon L. Southall; Peter L. Tyack (Marine Mammal Science, 2013)
In 2007 and 2008, controlled exposure experiments were performed in the Bahamas to study behavioral responses to simulated mid‐frequency active sonar (MFA) by three groups of odontocetes: false killer whales, Pseudorca crassidens ; short‐finned pilot whales, Globicephala macrorhynchus ; and melon‐headed whales, Peponocephala electra . An individual in each group was tagged with a Dtag to record acoustic and movement data. During exposures, some individuals produced whistles that seemed similar to the experimental MFA stimulus. Statistical tests were thus applied to investigate whistle‐MFA similarity and the relationship between whistle production rate and MFA reception time. For the false killer whale group, overall whistle rate and production rate of the most MFA‐like whistles decreased with time since last MFA reception. Despite quite low whistle rates overall by the melon‐headed whales, statistical results indicated minor transient silencing after each signal reception. There were no apparent relationships between pilot whale whistle rates and MFA sounds within the exposure period. This variability of responses suggests that changes in whistle production in response to acoustic stimuli depend not only on species and sound source, but also on the social, behavioral, or environmental contexts of exposure.

Changes in Australian fire weather between 1973 and 2010 - Hamish Clarke; Christopher Lucas; Peter Smith (International Journal of Climatology, 2013)
A data set of observed fire weather in Australia from 1973–2010 is analysed for trends using the McArthur Forest Fire Danger Index (FFDI). Annual cumulative FFDI, which integrates daily fire weather across the year, increased significantly at 16 of 38 stations. Annual 90th percentile FFDI increased significantly at 24 stations over the same period. None of the stations examined recorded a significant decrease in FFDI. There is an overall bias in the number of significant increases towards the southeast of the continent, while the largest trends occur in the interior of the continent and the smallest occur near the coast. The largest increases in seasonal FFDI occurred during spring and autumn, although with different spatial patterns, while summer recorded the fewest significant trends. These trends suggest increased fire weather conditions at many locations across Australia, due to both increased magnitude of FFDI and a lengthened fire season. Although these trends are consistent with projected impacts of climate change on FFDI, this study cannot separate the influence of climate change, if any, with that of natural variability. Copyright © 2012 Royal Meteorological Society

Spatial mapping of extracellular oxidant production by a white rot basidiomycete on wood reveals details of ligninolytic mechanism - Christopher G. Hunt; Carl J. Houtman; Don C. Jones; Peter Kitin; Premsagar Korripally; Kenneth E. Hammel (Environmental Microbiology, 2013)
Summary Oxidative cleavage of the recalcitrant plant polymer lignin is a crucial step in global carbon cycling, and is accomplished most efficiently by fungi that cause white rot of wood. These basidiomycetes secrete many enzymes and metabolites with proposed ligninolytic roles, and it is not clear whether all of these agents are physiologically important during attack on natural lignocellulosic substrates. One new approach to this problem is to infer properties of ligninolytic oxidants from their spatial distribution relative to the fungus on the lignocellulose. We grew P hanerochaete chrysosporium on wood sections in the presence of oxidant‐sensing beads based on the ratiometric fluorescent dye BODIPY 581/591. The beads, having fixed locations relative to the fungal hyphae, enabled spatial mapping of cumulative extracellular oxidant distributions by confocal fluorescence microscopy. The results showed that oxidation gradients occurred around the hyphae, and data analysis using a mathematical reaction–diffusion model indicated that the dominant oxidant during incipient white rot had a half‐life under 0.1 s. The best available hypothesis is that this oxidant is the cation radical of the secreted P . chrysosporium metabolite veratryl alcohol.

Quantitative structure–activity relationships for organophosphates binding to acetylcholinesterase - Christopher D. Ruark; C. Eric Hack; Peter J. Robinson; Paul E. Anderson; Jeffery M. Gearhart (Archives of Toxicology, 2013)

Preparation and testing of homocubyl amines as therapeutic NMDA receptor antagonists - Anna S. Sklyarova; Vladimir N. Rodionov; Christopher G. Parsons; Günter Quack; Peter R. Schreiner; Andrey A. Fokin (Medicinal Chemistry Research, 2013)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Detection of GFP-labeled Paenibacillus polymyxa in autofluorescing pine seedling tissues - Richa Anand; Christopher Peter Chanway (Biology and Fertility of Soils, 2013)

Trait-dependent declines of species following conversion of rain forest to oil palm plantations - Michael J. M. Senior; Keith C. Hamer; Simon Bottrell; David P. Edwards; Tom M. Fayle; Jennifer M. Lucey; Peter J. Mayhew; Robert Newton; Kelvin S.-H. Peh; Frederick H. Sheldon; Christopher Stewart; Alison R. Styring; et al. (Biodiversity and Conservation, 2013)

Cardiac electrophysiological imaging systems scalable for high-throughput drug testing - Peter Lee; Ken Wang; Christopher E. Woods; Ping Yan; Peter Kohl; Paul Ewart; Leslie M. Loew; Derek A. Terrar; Christian Bollensdorff (Pflügers Archiv - European Journal of Physiology, 2012)

Monitoring and Modeling of Syringodium filiforme (Manatee Grass) in Southern Indian River Lagoon - Christopher Buzzelli; Rebecca Robbins; Peter Doering; Zhiqiang Chen; Detong Sun; Yongshan Wan; Barbara Welch; Arthur Schwarzschild (Estuaries and Coasts, 2012)

Public health in the Canadian Arctic: contributions from International Polar Year research - Sandra Owens; Philippe De Wals; Grace Egeland; Christopher Furgal; Yang Mao; Gerald Y. Minuk; Paul A. Peters; Manon Simard; Éric Dewailly (Climatic Change, 2012)

Balanced placebo design with marijuana: Pharmacological and expectancy effects on impulsivity and risk taking - Jane Metrik; Christopher W. Kahler; Brady Reynolds; John E. McGeary; Peter M. Monti; Margaret Haney; Harriet de Wit; Damaris J. Rohsenow (Psychopharmacology, 2012)

The Effects of Local Ecological Knowledge, Minimum-Impact Knowledge, and Prior Experience on Visitor Perceptions of the Ecological Impacts of Backcountry Recreation - Ashley D’Antonio; Christopher Monz; Peter Newman; Steve Lawson; Derrick Taff (Environmental Management, 2012)

Interactions among chronic and acute impacts on coral recruits: the importance of size‐escape thresholds - Christopher Doropoulos; Selina Ward; Alyssa Marshell; Guillermo Diaz-Pulido; Peter J. Mumby (Ecology, 2012)
Newly settled recruits typically suffer high mortality from disturbances, but rapid growth reduces their mortality once size‐escape thresholds are attained. Ocean acidification (OA) reduces the growth of recruiting benthic invertebrates, yet no direct effects on survivorship have been demonstrated. We tested whether the reduced growth of coral recruits caused by OA would increase their mortality by prolonging their vulnerability to an acute disturbance: fish herbivory on surrounding algal turf. After two months' growth in ambient or elevated CO 2 levels, the linear extension and calcification of coral ( Acropora millepora ) recruits decreased as CO 2 partial pressure ( p CO 2 ) increased. When recruits were subjected to incidental fish grazing, their mortality was inversely size dependent. However, we also found an additive effect of p CO 2 such that recruit mortality was higher under elevated p CO 2 irrespective of size. Compared to ambient conditions, coral recruits needed to double their size at the highest p CO 2 to escape incidental grazing mortality. This general trend was observed with three groups of predators (blenny, surgeonfish, and parrotfish), although the magnitude of the fish treatment varied among species. Our study demonstrates the importance of size‐escape thresholds in early recruit survival and how OA can shift these thresholds, potentially intensifying population bottlenecks in benthic invertebrate recruitment.

Climate change adaptation and sustainable regional development: a case study for the Federal State of Brandenburg, Germany - Christopher Reyer; Johann Bachinger; Ralf Bloch; Fred F. Hattermann; Pierre L. Ibisch; Stefan Kreft; Petra Lasch; Wolfgang Lucht; Christoph Nowicki; Peter Spathelf; Manfred Stock; Martin Welp (Regional Environmental Change, 2012)

Variation in native micro-predator abundance explains recruitment of a mobile invasive fish, the common carp, in a naturally unstable environment - Przemyslaw G. Bajer; Christopher J. Chizinski; Justin J. Silbernagel; Peter W. Sorensen (Biological Invasions, 2012)

Ecosystem Carbon Remains Low for Three Decades Following Fire and Constrains Soil CO2 Responses to Precipitation in Southwestern Ponderosa Pine Forests - Christopher S. Ross; Jason P. Kaye; Margot W. Kaye; Valerie J. Kurth; Rachel Brimmer; Stephen C. Hart; Peter Z. Fulé (Ecosystems, 2012)

Outlier Problem in Evaluating Similarity Functions in the Stable Atmospheric Boundary Layer - Andrey A. Grachev; Edgar L. Andreas; Christopher W. Fairall; Peter S. Guest; P. Ola G. Persson (Boundary-Layer Meteorology, 2012)

Changes in character of organics in the receiving environment of effluent from a sulphite pulp mill - John A. van Leeuwen; Rosmala Lewis; Peter Goonan; Naomi Struve; Andrew Everson; Steven Nothrop; Ronald J. Smernik; Christopher W. K. Chow; Rolando Fabris; Madhawa Rupasinghe (Environmental Science and Pollution Research, 2012)

Erratum: An investigation of submarine groundwater‐borne nutrient fluxes to the west Florida shelf and recurrent harmful algal blooms - Christopher G. Smith; Peter W. Swarzenski (Limnology and Oceanography, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Ocean acidification reduces coral recruitment by disrupting intimate larval‐algal settlement interactions - Christopher Doropoulos; Selina Ward; Guillermo Diaz‐Pulido; Ove Hoegh‐Guldberg; Peter J. Mumby (Ecology Letters, 2012)
Ecology Letters (2012) 15 : 338–346 Abstract Successful recruitment in shallow reef ecosystems often involves specific cues that connect planktonic invertebrate larvae with particular crustose coralline algae (CCA) during settlement. While ocean acidification (OA) can reduce larval settlement and the abundance of CCA, the impact of OA on the interactions between planktonic larvae and their preferred settlement substrate are unknown. Here, we demonstrate that CO 2 concentrations (800 and 1300 μatm) predicted to occur by the end of this century significantly reduce coral ( Acropora millepora ) settlement and CCA cover by ≥ 45%. The CCA important for inducing coral settlement ( Titanoderma spp., Hydrolithon spp.) were the most deleteriously affected by OA. Surprisingly, the only preferred settlement substrate ( Titanoderma ) in the experimental controls was avoided by coral larvae as p CO 2 increased, and other substrata selected. Our results suggest OA may reduce coral population recovery by reducing coral settlement rates, disrupting larval settlement behaviour, and reducing the availability of the most desirable coralline algal species for successful coral recruitment.

Do brain cancer rates correlate with ambient exposure levels of criteria air pollutants or hazardous air pollutants (HAPs)? - Peter A. Valberg; Christopher M. Long (Air Quality, Atmosphere & Health, 2012)

An investigation of submarine groundwater—borne nutrient fluxes to the west Florida shelf and recurrent harmful algal blooms - Christopher G. Smith; Peter W. Swarzenski (Limnology and Oceanography, 2012)
A cross‐shelf, water‐column mass balance of radon‐222 ( 222 Rn) provided estimates of submarine groundwater discharge (SGD), which were then used to quantify benthic nutrient fluxes. Surface water and groundwater were collected along a shore‐normal transect that extended from Tampa Bay, Florida, across the Pinellas County peninsula, to the 10‐m isobath in the Gulf of Mexico. Samples were analyzed for 222 Rn and radium‐223,224,226 ( 223,224,226 Ra) activities as well as inorganic and organic nutrients. Cross‐shore gradients of 222 Rn and 223,224,226 Ra activities indicate a nearshore source for these isotopes, which mixes with water characterized by low activities offshore. Radon‐based SGD rates vary between 2.5 and 15 cm d −1 proximal to the shoreline and decrease offshore. The source of SGD is largely shallow exchange between surface and pore waters, although deeper groundwater cycling may also be important. Enrichment of total dissolved nitrogen and soluble reactive phosphorus in pore water combined with SGD rates results in specific nutrient fluxes comparable to or greater than estuarine fluxes from Tampa Bay. The significance of these fluxes to nearshore blooms of Karenia brevis is highlighted by comparison with prescribed nutrient demands for bloom maintenance and growth. Whereas our flux estimates do not indicate SGD and benthic fluxes as the dominant nutrient source to the harmful algal blooms, SGD‐derived loads do narrow the deficit between documented nutrient supplies and bloom demands.

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Transdisciplinary research in sustainability science: practice, principles, and challenges - Daniel J. Lang; Arnim Wiek; Matthias Bergmann; Michael Stauffacher; Pim Martens; Peter Moll; Mark Swilling; Christopher J. Thomas (Sustainability Science, 2012)

Aerobic and anaerobic de-epoxydation of mycotoxin deoxynivalenol by bacteria originating from agricultural soil - Rafiqul Islam; Ting Zhou; J. Christopher Young; Paul H. Goodwin; K. Peter Pauls (World Journal of Microbiology and Biotechnology, 2012)

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Consulting Forestry / Certification and Ecosystem Services - James Coufal; Carl Wiedemann; Jacob Gorman; Larry Teeter; Yaoqi Zhang; Michael Kilgore; Kristell Miller; Stephanie Snyder; Sun Chang; Miriam Davis; Stanley Asah; J. Mark Fly; et al. (Journal of Forestry, 2011)
45The industrialization of the United States throughout the 19th century resulted in the exploitation of millions of acres of timberland across the country. Logging during that era was described by critics as “cut out and get out” because the land was usually abandoned after the merchantable timber was exhausted. Concern about future timber supplies and the effect of logging on watersheds spurred the development of professional forestry after the Civil War. The first forestry leaders, including Bernhard Fernow and Gifford Pinchot, encouraged private non-industrial forest owners to sustainably manage their woodlands and specifically warned against destructive logging practices—including “cutting the best and leaving the rest”—aka high-grading. During the 1920s and 30s both the Forest Service and SAF spurred initiatives to encourage sustainable timber harvesting practices on private forestland. Although great progress has been made in forest management, logging on most private non-industrial forest land in the east has not changed significantly since the 19th century. Landowners usually sell timber without using the services of a forester, allowing the buyer to selectively cut the most valuable trees in the woodlot. Although this can reduce future value by 70-90%, it remains common practice because both the landowner and the timber buyer maximize short term income. The timber value and productivity of millions of acres of woodland throughout the United States have been significantly degraded as a result. This paper will trace the history of high-grading as described by forestry leaders from the 19th century through the 21st and will show that much work remains unfinished.

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

c-Abl in Neurodegenerative Disease - Sarah D. Schlatterer; Christopher M. Acker; Peter Davies (Journal of Molecular Neuroscience, 2011)

Singing Under the Influence: Examining the Effects of Nutrition and Addiction on a Learned Vocal Behavior - Peter V. Lovell; Christopher R. Olson; Claudio V. Mello (Molecular Neurobiology, 2011)

Cross-Spectrum of Wind Speed for Meso-Gamma Scales in the Upper Surface Layer over South-Eastern Australia - Milton J. Woods; Robert J. Davy; Christopher J. Russell; Peter A. Coppin (Boundary-Layer Meteorology, 2011)

On the utility of identification schemes for digital earth science data: an assessment and recommendations - Ruth E. Duerr; Robert R. Downs; Curt Tilmes; Bruce Barkstrom; W. Christopher Lenhardt; Joseph Glassy; Luis E. Bermudez; Peter Slaughter (Earth Science Informatics, 2011)

Measurement of the Thermal Conductivity of Carbon Nanotube–Tissue Phantom Composites with the Hot Wire Probe Method - Saugata Sarkar; Kristen Zimmermann; Weinan Leng; Peter Vikesland; Jianfei Zhang; Harry Dorn; Thomas Diller; Christopher Rylander; Marissa Nichole Rylander (Annals of Biomedical Engineering, 2011)

Functional analysis of frequently expressed Chinese rhesus macaque MHC class I molecules Mamu-A1*02601 and Mamu-B*08301 reveals HLA-A2 and HLA-A3 supertypic specificities - Scott Southwood; Christopher Solomon; Ilka Hoof; Richard Rudersdorf; John Sidney; Bjoern Peters; Angela Wahl; Oriana Hawkins; William Hildebrand; Bianca R. Mothé; Alessandro Sette (Immunogenetics, 2011)

A kinetic analysis of three modified novel nitroreductases - Christopher D. Gwenin; Maher Kalaji; Peter A. Williams; Catherine M. Kay (Biodegradation, 2011)

The developmental impact of prenatal stress, prenatal dexamethasone and postnatal social stress on physiology, behaviour and neuroanatomy of primate offspring: studies in rhesus macaque and common marmoset - Christopher R. Pryce; Yves Aubert; Claudia Maier; Peter C. Pearce; Eberhard Fuchs (Psychopharmacology, 2011)

Germline PKHD1 mutations are protective against colorectal cancer - Christopher J. Ward; Yanhong Wu; Ruth A. Johnson; John R. Woollard; Eric J. Bergstralh; Mine S. Cicek; Jason Bakeberg; Sandro Rossetti; Christina M. Heyer; Gloria M. Petersen; Noralene M. Lindor; Stephen N. Thibodeau; et al. (Human Genetics, 2011)

The green ribbon: Multiscale physical control of phytoplankton productivity and community structure over a narrow continental shelf - Andrew J. Lucas; Christopher L. Dupont; Vera Tai; John L. Largier; Brian Palenik; Peter J. S. Franks (Limnology and Oceanography, 2011)
Chlorophyll concentration, phytoplankton biomass, and total and nitrate‐fueled primary productivity increase toward the coast over the 12‐km‐wide continental shelf of the southern portion of the Southern California Bight. These gradients are accompanied by changes in phytoplankton community composition: the outer shelf is characterized by offshore assemblages including pelagophytes and oligotrophic Synechococcus ecotypes while the inner shelf is dominated by diatoms, coastal Synechococcus ecotypes, and the picoeukaryote Ostreococcus . Across the small horizontal scale of the shelf, large changes in the vertical distribution and flux of nitrate maintain elevated productivity, driving variability in the vertical distribution of biomass and the integrated biomass and productivity of the entire shelf. Temporal variability from hours to days in chlorophyll fluorescence as measured by an autonomous profiling vehicle demonstrates that phytoplankton respond vigorously and rapidly to physical variability. The interaction of physical processes at different temporal and spatial scales is responsible for the observed biological gradients. These dynamics include: (1) vertical shear in the alongshore currents, (2) local wind forcing, (3) the internal tide, and (4) remote, large‐scale variability. Individually, these mechanisms rarely or never explain the phytoplankton community composition and metabolic rate gradients. These results and a reanalysis of historical data suggest that monitoring thermal stratification at the shelf break and the tilt of the thermocline across the shelf will augment our ability to predict phytoplankton productivity, community composition, and biomass, thereby improving our understanding of fisheries dynamics and carbon cycling in the coastal ocean.

Differential involvement of hippocampal serotonin1A receptors and re-uptake sites in non-cognitive behaviors of Alzheimer’s disease - Mitchell K. P. Lai; Shirley W. Tsang; Margaret M. Esiri; Paul T. Francis; Peter T.-H. Wong; Christopher P. Chen (Psychopharmacology, 2011)

Estimating soil strength in the rooting zone of wheat - Andrew Peter Whitmore; W. Richard Whalley; Nigel R. A. Bird; Christopher W. Watts; Andrew S. Gregory (Plant and Soil, 2011)

Old and stable soil organic matter is not necessarily chemically recalcitrant: implications for modeling concepts and temperature sensitivity - MARKUS KLEBER; PETER S. NICO; ALAIN PLANTE; TIMOTHY FILLEY; MARC KRAMER; CHRISTOPHER SWANSTON; PHILLIP SOLLINS (Global Change Biology, 2011)
Soil carbon turnover models generally divide soil carbon into pools with varying intrinsic decomposition rates. Although these decomposition rates are modified by factors such as temperature, texture, and moisture, they are rationalized by assuming chemical structure is a primary controller of decomposition. In the current work, we use near edge X‐ray absorption fine structure (NEXAFS) spectroscopy in combination with differential scanning calorimetry (DSC) and alkaline cupric oxide (CuO) oxidation to explore this assumption. Specifically, we examined material from the 2.3–2.6 kg L −1 density fraction of three soils of different type (Oxisol, Alfisol, Inceptisol). The density fraction with the youngest 14 C age (Oxisol, 107 years) showed the highest relative abundance of aromatic groups and the lowest O ‐alkyl C/aromatic C ratio as determined by NEXAFS. Conversely, the fraction with the oldest C (Inceptisol, 680 years) had the lowest relative abundance of aromatic groups and highest O ‐alkyl C/aromatic C ratio. This sample also had the highest proportion of thermally labile materials as measured by DSC, and the highest ratio of substituted fatty acids to lignin phenols as indicated by CuO oxidation. Therefore, the organic matter of the Inceptisol sample, with a 14 C age associated with ‘passive’ pools of carbon (680 years), had the largest proportion of easily metabolizable organic molecules with low thermodynamic stability, whereas the organic matter of the much younger Oxisol sample (107 years) had the highest proportion of supposedly stable organic structures considered more difficult to metabolize. Our results demonstrate that C age is not necessarily related to molecular structure or thermodynamic stability, and we suggest that soil carbon models would benefit from viewing turnover rate as codetermined by the interaction between substrates, microbial actors, and abiotic driving variables. Furthermore, assuming that old carbon is composed of complex or ‘recalcitrant’ compounds will erroneously attribute a greater temperature sensitivity to those materials than they may actually possess.

Nutritional supplements, COX-2 and IGF-1 expression in men on active surveillance for prostate cancer - June M. Chan; Vivian Weinberg; Mark J. Magbanua; Eduardo Sosa; Jeffry Simko; Katsuto Shinohara; Scot Federman; Mike Mattie; Millie Hughes-Fulford; Christopher Haqq; Peter R. Carroll (Cancer Causes & Control, 2011)

Biophysical costs associated with tetrodotoxin resistance in the sodium channel pore of the garter snake, Thamnophis sirtalis - Chong Hyun Lee; David K. Jones; Christopher Ahern; Maen F. Sarhan; Peter C. Ruben (Journal of Comparative Physiology A, 2011)

Increased rate of D1 repair in coral symbionts during bleaching is insufficient to counter accelerated photo‐inactivation - Ross Hill; Christopher M. Brown; Katrina DeZeeuw; Douglas A. Campbell; Peter J. Ralph (Limnology and Oceanography, 2011)
We dissect the primary photo‐inactivation and the counteracting metabolic repair rates in fragments of the scleractinian coral, Pocillopora damicornis , subjected to a combined stress of a shift to elevated temperature (from 26°C to 32°C) and increased light (from 200 µmol photons m −2 s −1 to 400 µmol photons m −2 s −1 ) to induce bleaching. During the bleaching treatment the dinoflagellate symbionts showed a 5.5‐fold acceleration in their photosystem II (PSII) repair rate constant, demonstrating that they maintain strong metabolic capacity to clear and replace photo‐damaged D1 protein at the elevated temperature and light conditions. Nevertheless, the symbionts concurrently suffered a seven‐fold increase in the rate constant for PSII photo‐inactivation. This rapid photo‐inactivation exceeded the PSII repair capacity, therefore tipping the symbionts, and by implication the symbiosis, into net photo‐inhibition. Increased photo‐inactivation in hospite, rather than an inhibition of PSII repair, is the principle trigger for net photo‐inhibition under bleaching conditions.

Comparison of satellite‐derived TOA shortwave clear‐sky fluxes to estimates from GCM simulations constrained by satellite observations of land surface characteristics - Valentine G. Anantharaj; Udaysankar S. Nair; Peter Lawrence; Thomas N. Chase; Sundar Christopher; Thomas Jones (International Journal of Climatology, 2010)
Clear‐sky, upwelling shortwave flux at the top of the atmosphere $\left(S_{\rm {TOA}}^{\uparrow}\right)$ , simulated using the atmospheric and land model components of the Community Climate System Model 3 (CCSM3), is compared to corresponding observational estimates from the Clouds and Earth's Radiant Energy System (CERES) sensor. Improvements resulting from the use of land surface albedo derived from Moderate Resolution Imaging Spectroradiometer (MODIS) to constrain the simulations are also examined. Compared to CERES observations, CCSM3 overestimates global, annual averaged $S_{\rm {TOA}}^{\uparrow}$ over both land and oceans. However, regionally, CCSM3 overestimates $S_{\rm {TOA}}^{\uparrow}$ over some land and ocean areas while underestimating it over other sites. CCSM3 underestimates $S_{\rm {TOA}}^{\uparrow}$ over the Saharan and Arabian Deserts and substantial differences exist between CERES observations and CCSM3 over agricultural areas. Over selected sites, after using ground‐based observations to remove systematic biases that exist in CCSM computation of $S_{\rm {TOA}}^{\uparrow}$ , it is found that use of MODIS albedo improves the simulation of $S_{\rm {TOA}}^{\uparrow}$ . Inability of coarse resolution CCSM3 simulation to resolve spatial heterogeneity of snowfall over high altitude sites such as the Tibetan Plateau causes overestimation of $S_{\rm {TOA}}^{\uparrow}$ in these areas. Discrepancies also exist in the simulation of $S_{\rm {TOA}}^{\uparrow}$ over ocean areas as CCSM3 does not account for the effect of wind speed on ocean surface albedo. This study shows that the radiative energy budget at the TOA is improved through the use of MODIS albedo in Global Climate Models. Copyright © 2010 Royal Meteorological Society

Divergence genetics analysis reveals historical population genetic processes leading to contrasting phylogeographic patterns in co‐distributed species - TAMARA M. McGOVERN; CARSON C. KEEVER; CHRISTOPHER A. SASKI; MICHAEL W. HART; PETER B. MARKO (Molecular Ecology, 2010)
Coalescent samplers are computational time machines for inferring the historical demographic genetic processes that have given rise to observable patterns of spatial genetic variation among contemporary populations. We have used traditional characterizations of population structure and coalescent‐based inferences about demographic processes to reconstruct the population histories of two co‐distributed marine species, the frilled dog whelk, Nucella lamellosa , and the bat star, Patiria miniata . Analyses of population structure were consistent with previous work in both species except that additional samples of N. lamellosa showed a larger regional genetic break on Vancouver Island (VI) rather than between the southern Alexander Archipelago as in P. miniata . Our understanding of the causes, rather than just the patterns, of spatial genetic variation was dramatically improved by coalescent analyses that emphasized variation in population divergence times. Overall, gene flow was greater in bat stars (planktonic development) than snails (benthic development) but spatially homogeneous within species. In both species, these large phylogeographic breaks corresponded to relatively ancient divergence times between populations rather than regionally restricted gene flow. Although only N. lamellosa shows a large break on VI, population separation times on VI are congruent between species, suggesting a similar response to late Pleistocene ice sheet expansion. The absence of a phylogeographic break in P. miniata on VI can be attributed to greater gene flow and larger effective population size in this species. Such insights put the relative significance of gene flow into a more comprehensive historical biogeographic context and have important implications for conservation and landscape genetic studies that emphasize the role of contemporary gene flow and connectivity in shaping patterns of population differentiation.

Can Plant Competition and Diversity Reduce the Growth and Survival of Exotic Phragmites australis Invading a Tidal Marsh? - Christopher Robert Peter; David M. Burdick (Estuaries and Coasts, 2010)

A direct comparison between extracted tooth and filter-membrane biofilm models of endodontic irrigation using Enterococcus faecalis - Christopher K. Hope; Stuart G. Garton; Qian Wang; Girvan Burnside; Peter J. Farrelly (Archives of Microbiology, 2010)

Increased protein synthesis by cells exposed to a 1,800-MHz radio-frequency mobile phone electromagnetic field, detected by proteome profiling - Christopher Gerner; Verena Haudek; Ulla Schandl; Editha Bayer; Nina Gundacker; Hans Peter Hutter; Wilhelm Mosgoeller (International Archives of Occupational and Environmental Health, 2010)

The most common Chinese rhesus macaque MHC class I molecule shares peptide binding repertoire with the HLA-B7 supertype - Christopher Solomon; Scott Southwood; Ilka Hoof; Richard Rudersdorf; Bjoern Peters; John Sidney; Clemencia Pinilla; Maria Cecilia Garibaldi Marcondes; Binhua Ling; Preston Marx; Alessandro Sette; Bianca R. Mothé (Immunogenetics, 2010)

Mitochondrial Dysfunction: Common Final Pathway in Brain Aging and Alzheimer’s Disease—Therapeutic Aspects - Walter E. Müller; Anne Eckert; Christopher Kurz; Gunter Peter Eckert; Kristina Leuner (Molecular Neurobiology, 2010)

The effect of sodicity on cotton: plant response to solutions containing high sodium concentrations - Kylie Dodd; Christopher Guppy; Peter Lockwood; Ian Rochester (Plant and Soil, 2010)

Temporal and Spatial Variability of Mesozooplankton in a Shallow Sub-Tropical Bay: Influence of Top-Down Control - Christopher R. Kelble; Peter B. Ortner; Gary L. Hitchcock; Michael J. Dagg; Joseph N. Boyer (Estuaries and Coasts, 2010)

Rapid photoprotection in sea‐ice diatoms from the East Antarctic pack ice - Katherina Petrou; Ross Hill; Christopher M. Brown; Douglas A. Campbell; Martina A. Doblin; Peter J. Ralph (Limnology and Oceanography, 2010)
Photoinhibition and D1 protein re‐synthesis were investigated in bottom‐dwelling sea‐ice microalgal communities from the East Antarctic pack ice during early spring. Bottom‐dwelling sea‐ice microalgal communities were dominated by diatoms that exhibited rapid photoprotection when exposed to a range of different light levels (10 µmol photons m −2 s −1 , 50 µmol photons m −2 s −1 , 100 µmol photons m −2 s −1 , and 200 µ;mol photons m −2 s −1 ). Photosynthetic capacity of photosystem II (PSII) dropped significantly over 3 h under 200 −mol photons m −2 s −1 , but largely recovered when placed in a low‐light environment (10 µmol photons m −2 s −1 ) for an additional 3 h. PSII repair rates increased with increasing irradiance, and the D1‐protein pool remained steady even under high light (200 µmol photons m −2 s −1 ). Sea‐ice diatoms showed a low intrinsic susceptibility to photoinactivation of PSII across all the light treatments, and a strong and irradiance‐dependent induction of nonphotochemical quenching, which did not depend upon chloroplast protein synthesis, was also seen. These highly plastic organisms, once thought to be adapted to shade, are in fact well equipped to withstand rapid and relatively large changes in light at low temperatures with minimal long‐term effect on their photosynthetic machinery.

How to capture wild passerine species to study baseline corticosterone levels - Frédéric Angelier; Christopher M. Tonra; Rebecca L. Holberton; Peter P. Marra (Journal of Ornithology, 2010)

Statistical Downscaling of Wind Variability from Meteorological Fields - Robert J. Davy; Milton J. Woods; Christopher J. Russell; Peter A. Coppin (Boundary-Layer Meteorology, 2010)

What Conservation Biologists Can Do to Counter Trap‐Neuter‐Return: Response to Longcore et al. - CHRISTOPHER A. LEPCZYK; NICO DAUPHINÉ; DAVID M. BIRD; SHEILA CONANT; ROBERT J. COOPER; DAVID C. DUFFY; PAMELA JO HATLEY; PETER P. MARRA; ELIZABETH STONE; STANLEY A. TEMPLE (Conservation Biology, 2010)

Policosanols as Nutraceuticals: Fact or Fiction - Christopher P. F. Marinangeli; Peter J. H. Jones; Amira N. Kassis; Michael N. A. Eskin (Critical Reviews in Food Science and Nutrition, 2010)

Case studies on decapod crustaceans from the Philippines reveal deep, steep underwater slopes as prime habitats for ‘rare’ species - Jose Christopher E. Mendoza; Tohru Naruse; Swee-Hee Tan; Tin-Yam Chan; Bertrand Richer de Forges; Peter K. L. Ng (Biodiversity and Conservation, 2010)

Mapping SNP-anchored genes using high-resolution melting analysis in almond - Shu-Biao Wu; Iraj Tavassolian; Gholamreza Rabiei; Peter Hunt; Michelle Wirthensohn; John P. Gibson; Christopher M. Ford; Margaret Sedgley (Molecular Genetics and Genomics, 2009)

APPLICATIONS IN COASTAL MODELING AND FORECASTING - Pierre De Mey; Peter Craig; Fraser Davidson; Christopher Edwards; Yoichi Ishikawa; John Kindle; Roger Proctor; Keith Thompson; Jiang Zhu (Oceanography, 2009)

THE GODAE HIGH-RESOLUTION SEA SURFACE TEMPERATURE PILOT PROJECT - Craig Donlon; Kenneth Casey; Ian Robinson; Chelle Gentemann; Richard Reynolds; Ian Barton; Olivier Arino; John Stark; Nick Rayner; Pierre LeBorgne; David Poulter; Jorge Vazquez-Cuervo; et al. (Oceanography, 2009)

Detection of disease-associated deletions in case–control studies using SNP genotypes with application to rheumatoid arthritis - Chih-Chieh Wu; Sanjay Shete; Wei V. Chen; Bo Peng; Annette T. Lee; Jianzhong Ma; Peter K. Gregersen; Christopher I. Amos (Human Genetics, 2009)

Understanding Causes and Impacts of the Dinoflagellate, Cochlodinium polykrikoides, Blooms in the Chesapeake Bay - Margaret R. Mulholland; Ryan E. Morse; George E. Boneillo; Peter W. Bernhardt; Katherine C. Filippino; Leo A. Procise; Jose L. Blanco-Garcia; Harold G. Marshall; Todd A. Egerton; William S. Hunley; Kenneth A. Moore; Dianna L. Berry; et al. (Estuaries and Coasts, 2009)

Acute sleep restriction alters neuroendocrine hormones and appetite in healthy male adults - Christopher A MAGEE; Xu-Feng HUANG; Donald C IVERSON; Peter CAPUTI (Sleep and Biological Rhythms, 2009)

Photophysics and Electrochemistry of some Thione Far-Red/Near-IR Triplet Emitters - Rachel C. Evans; Peter Douglas; Christopher J. Winscom (Journal of Fluorescence, 2009)

Descriptions of five new species of false spider crabs (Decapoda: Brachyura: Hymenosomatidae) from the Philippines - Tohru Naruse; Jose Christopher E. Mendoza; Peter K. L. Ng (Marine Biology Research, 2008)

Reference-dose place conditioning with ethanol in mice: empirical and theoretical analysis - Peter A. Groblewski; Laura S. Bax; Christopher L. Cunningham (Psychopharmacology, 2008)

An investigation of the dimensionality of the Pittsburgh Sleep Quality Index in Australian adults - Christopher A MAGEE; Peter CAPUTI; Donald C IVERSON; Xu-Feng HUANG (Sleep and Biological Rhythms, 2008)

Contrasting genetic structuring between colonies of the World’s smallest penguin, Eudyptula minor (Aves: Spheniscidae) - Rebecca L. Overeem; Amanda J. Peucker (nee Mitchelson); Christopher M. Austin; Peter Dann; Christopher P. Burridge (Conservation Genetics, 2008)

Trans-radial upper extremity amputees are capable of adapting to a novel dynamic environment - Christopher N. Schabowsky; Alexander W. Dromerick; Rahsaan J. Holley; Brian Monroe; Peter S. Lum (Experimental Brain Research, 2008)

In vivo deuteration strategies for neutron scattering analysis of bacterial polyhydroxyoctanoate - Robert A. Russell; Peter J. Holden; Karyn L. Wilde; Christopher J. Garvey; Kerie M. Hammerton; L. John R. Foster (European Biophysics Journal, 2008)

Polyhydroxybutyrate accumulation by a Serratia sp. - Harriet Lugg; Rachel L. Sammons; Peter M. Marquis; Christopher J. Hewitt; Ping Yong; Marion Paterson-Beedle; Mark D. Redwood; Artemis Stamboulis; Mitra Kashani; Mike Jenkins; Lynne E. Macaskie (Biotechnology Letters, 2008)

Turbulent measurements in the stable atmospheric boundary layer during SHEBA: ten years after - Andrey A. Grachev; Edgar L. Andreas; Christopher W. Fairall; Peter S. Guest; P. Ola G. Persson (Acta Geophysica, 2008)

Genotypic variation in seedling root architectural traits and implications for drought adaptation in wheat (Triticum aestivum L.) - Ahmad M. Manschadi; Graeme L. Hammer; John T. Christopher; Peter deVoil (Plant and Soil, 2008)

Macroinvertebrate drift density in relation to abiotic factors in the Missouri River - Christopher H. Hay; Thomas G. Franti; David B. Marx; Edward J. Peters; Larry W. Hesse (Hydrobiologia, 2008)

Late Quaternary speleothem pollen in the British Isles - Christopher J. Caseldine; Siobhán F. McGarry; Andy Baker; Chris Hawkesworth; Peter L. Smart (Journal of Quaternary Science, 2008)
As with many terrestrial areas, the British Quaternary sequence is characterised by incomplete, fragmentary records, whose correlation is based on stratigraphic or biostratigraphic techniques due to the lack of radiometric ages beyond the ∼40 kyr limit of 14 C dating. Speleothems (secondary cave calcite deposits) offer a significant advantage over many sources of palaeoenvironmental information; they can be dated to a high precision and accuracy by uranium‐thorium ( 238 U‐ 230 Th) thermal ionisation and inductively coupled plasma (ICP) mass spectrometry in the time period back to 500 kyr. They may also contain sufficient well‐preserved pollen representative of contemporary vegetation above the cave to allow palaeoenvironmental reconstruction. This study adopts the novel approach of combining pollen and thermal ionisation mass spectrometric (TIMS) U‐Th dating of British speleothems to produce well‐constrained palaeoenvironmental records. We report for the first time precisely dated records of pollen assemblages from speleothems suggesting the presence of thermophilous arboreal species in phases previously considered to have been consistently cool or cold and devoid of trees. Copyright © 2007 John Wiley & Sons, Ltd.

A Temporally Explicit Production Efficiency Model for Fuel Load Allocation in Southern Africa - Christelle Hély; Kelly K. Caylor; Peter Dowty; Samuel Alleaume; Robert J. Swap; Hank H. Shugart; Christopher O. Justice (Ecosystems, 2007)

Limited impact of elevated levels of polyphenol oxidase on tree-feeding caterpillars: assessing individual plant defenses with transgenic poplar - Raymond V. Barbehenn; Christopher P. Jones; Lynn Yip; Lan Tran; C. Peter Constabel (Oecologia, 2007)

Effects of day-length and temperature on floral structure and fertility restoration in a season-dependent male-sterile Solanum villosum Mill. mutant - Christopher O. Ojiewo; Kenji Murakami; Peter W. Masinde; Stephen G. Agong; Masaharu Masuda (Euphytica, 2007)

Greater reliance on impedance control in the nondominant arm compared with the dominant arm when adapting to a novel dynamic environment - Christopher N. Schabowsky; Joseph M. Hidler; Peter S. Lum (Experimental Brain Research, 2007)

Porphyrobacter meromictius sp. nov., an Appendaged Bacterium, That Produces Bacteriochlorophyll a - Christopher Rathgeber; Natalia Yurkova; Erko Stackebrandt; Peter Schumann; Elaine Humphrey; J. Thomas Beatty; Vladimir Yurkov (Current Microbiology, 2007)

Product quality research institute evaluation of cascade impactor profiles of pharmaceutical aerosols, part 3: Final report on a statistical procedure for determining equivalence - David Christopher; Wallace Adams; Anthony Amann; Craig Bertha; Peter R. Byron; William Doub; Craig Dunbar; Walter Hauck; Svetlana Lyapustina; Jolyon Mitchell; Beth Morgan; Steve Nichols; et al. (AAPS PharmSciTech, 2007)

OCCURRENCE, COMPOSITION, AND POTENTIAL FUNCTIONS OF NORTH ATLANTIC RIGHT WHALE ( EUBALAENA GLACIALIS ) SURFACE ACTIVE GROUPS - Susan E. Parks; Moira W. Brown; Lisa A. Conger; Philip K. Hamilton; Amy R. Knowlton; Scott D. Kraus; Christopher K. Slay; Peter L. Tyack (Marine Mammal Science, 2007)
Marine mammal social interactions are poorly understood primarily because of the difficulty of observing these behaviors in the wild. Observations of copulations in North Atlantic right whale surface active groups (SAGs) have led to the hypothesis that the function of these groups is for conception. The occurrence and composition of SAGs sighted from 1992 to 2001 were investigated on the basis of age, sex, and reproductive status of individuals. A total of 918 SAG events were documented. SAGs were observed in all habitat areas and in all months in which right whales were sighted. Group compositions revealed both potentially conceptive groups and nonconceptive groups. Of right whales whose age was known, 93% were first sighted in SAGs as juveniles, and more than half of all observed groups contained at least one juvenile whale. The group composition and timing of occurrence of SAGs do not support the hypothesis that all groups serve a purely conceptive function. Their functional role is likely much broader. Other potential functions include play, mating practice, or maintenance of social bonds.

On the turbulent Prandtl number in the stable atmospheric boundary layer - Andrey A. Grachev; Edgar L Andreas; Christopher W. Fairall; Peter S. Guest; P. Ola G. Persson (Boundary-Layer Meteorology, 2007)

Corrigendum: 2007 highlights of advances in the pharmaceutical sciences: An American Association of Pharmaceutical Scientists (AAPS) perspective - Marilyn N. Martinez; Peter Bonate; Robert L. Chapman; Anne De Groot; Susan D'Souza; Naushad Ghilazi; Vivian Gray; Vishal K. Gupta; Kim Huynh-Ba; Sunil Iyer; Arya Jayatilaka; Amita Joshi; et al. (The AAPS Journal, 2007)

Pharmacological effects of naltrexone and intravenous alcohol on craving for cigarettes among light smokers: a pilot study - Lara A. Ray; Robert Miranda; Christopher W. Kahler; Adam M. Leventhal; Peter M. Monti; Robert Swift; Kent E. Hutchison (Psychopharmacology, 2007)

Swimming behavior of juvenile anchovies (Anchoa spp.) in an episodically hypoxic estuary: implications for individual energetics and trophic dynamics - J. Christopher Taylor; Peter S. Rand; Jacqueline Jenkins (Marine Biology, 2007)

Traces of ancient range shifts in a mountain plant group ( Androsace halleri complex, Primulaceae) - CHRISTOPHER J. DIXON; PETER SCHÖNSWETTER; GERALD M. SCHNEEWEISS (Molecular Ecology, 2007)
Phylogeographical studies frequently detect range shifts, both expansions (including long‐distance dispersal) and contractions (including vicariance), in the studied taxa. These processes are usually inferred from the patterns and distribution of genetic variation, with the potential pitfall that different historical processes may result in similar genetic patterns. Using a combination of DNA sequence data from the plastid genome, AFLP fingerprinting, and rigorous phylogenetic and coalescence‐based hypothesis testing, we show that Androsace halleri (currently distributed disjunctly in the northwestern Iberian Cordillera Cantábrica, the eastern Pyrenees, and the French Massif Central and Vosges), or its ancestor, was once more widely distributed in the Pyrenees. While there, it hybridized with Androsace laggeri and Androsace pyrenaica , both of which are currently allopatric with A. halleri . The common ancestor of A. halleri and the north Iberian local endemic Androsace rioxana probably existed in the north Iberian mountain ranges with subsequent range expansion (to the French mountain ranges of the Massif Central and the Vosges) and allopatric speciation ( A. rioxana , A. halleri in the eastern Pyrenees, A. halleri elsewhere). We have thus been able to use the reticulate evolution in this species group to help elucidate its phylogeographical history, including evidence of range contraction.

The legacy of harvest and fire on ecosystem carbon storage in a north temperate forest - CHRISTOPHER M. GOUGH; CHRISTOPH S. VOGEL; KATHERINE H. HARROLD; KRISTEN GEORGE; PETER S. CURTIS (Global Change Biology, 2007)
Forest harvesting and wildfire were widespread in the upper Great Lakes region of North America during the early 20th century. We examined how long this legacy of disturbance constrains forest carbon (C) storage rates by quantifying C pools and fluxes after harvest and fire in a mixed deciduous forest chronosequence in northern lower Michigan, USA. Study plots ranged in age from 6 to 68 years and were created following experimental clear‐cut harvesting and fire disturbance. Annual C storage was estimated biometrically from measurements of wood, leaf, fine root, and woody debris mass, mass losses to herbivory, soil C content, and soil respiration. Maximum annual C storage in stands that were disturbed by harvest and fire twice was 26% less than a reference stand receiving the same disturbance only once. The mechanism for this reduction in annual C storage was a long‐lasting decrease in site quality that endured over the 62‐year timeframe examined. However, during regrowth the harvested and burned forest rapidly became a net C sink, storing 0.53 Mg C ha −1 yr −1 after 6 years. Maximum net ecosystem production (1.35 Mg C ha −1 yr −1 ) and annual C increment (0.95 Mg C ha −1 yr −1 ) were recorded in the 24‐ and 50‐year‐old stands, respectively. Net primary production averaged 5.19 Mg C ha −1 yr −1 in experimental stands, increasing by −1 yr −1 in the 6‐year‐old stand to 4.56 Mg C ha −1 yr −1 in the 68‐year‐old stand. These results suggest that harvesting and fire disturbances broadly distributed across the region decades ago caused changes in site quality and successional status that continue to limit forest C storage rates.

Influence of Plant and Soil Chemistry on Food Selection, Ranging Patterns, and Biomass of Colobus guereza in Kakamega Forest, Kenya - Peter J. Fashing; Ellen S. Dierenfeld; Christopher B. Mowry (International Journal of Primatology, 2007)

SHEBA flux–profile relationships in the stable atmospheric boundary layer - Andrey A. Grachev; Edgar L Andreas; Christopher W. Fairall; Peter S. Guest; P. Ola G. Persson (Boundary-Layer Meteorology, 2007)

2007 highlights of advances in the pharmaceutical sciences: An American Association of Pharmaceutical Scientists (AAPS) perspective - Marilyn N. Martinez; Peter Bonate; Robert L. Chapman; Anne De Groot; Susan D'Souza; Naushad Ghilazi; Vivian Gray; Vishal K. Gupta; Kim Huynh-Ba; Sunil Iyer; Arya Jayatilaka; Amita Joshi; et al. (The AAPS Journal, 2007)

The use of7Be and210Pbxs to differentiate fine suspended sediment sources in South Slough, Oregon - Christopher G. Wilson; Gerald Matisoff; Peter J. Whiting (Estuaries and Coasts, 2007)

Structure, dynamics and topology of membrane polypeptides by oriented 2H solid-state NMR spectroscopy - Christopher Aisenbrey; Philippe Bertani; Peter Henklein; Burkhard Bechinger (European Biophysics Journal, 2007)

Molecular and functional characterization of Kv4.2 and KChIP2 expressed in the porcine left ventricle - Jobst-Hendrik Schultz; Tilmann Volk; Peter Bassalaý; J. Christopher Hennings; Christian A. Hübner; Heimo Ehmke (Pflügers Archiv - European Journal of Physiology, 2007)

Scalar concentration reduction in a contaminant cloud - Thomas Peter Schopflocher; Christopher J. Smith; Paul J. Sullivan (Boundary-Layer Meteorology, 2007)

The economic viability and potential of a novel poultry agroforestry system - Christopher Yates; Peter Dorward; Gabriel Hemery; Paul Cook (Agroforestry Systems, 2007)

Degradation of water quality in Lough Neagh, Northern Ireland, by diffuse nitrogen flux from a phosphorus‐rich catchment - Lynda Bunting; Peter R. Leavitt; Christopher E. Gibson; Edward J. McGee; Valerie A. Hall (Limnology and Oceanography, 2007)
Annually resolved fossil records of nitrogen (N) inputs (as sedimentary δ 15 N, N content), aquatic production (δ 13 C, C content), and algal abundance and gross community composition (pigments, nonsiliceous microfossils) from Lough Neagh, Northern Ireland (NI), were compared with annual records of climatic variability, atmospheric and urban nutrient loading, whole‐catchment nutrient budgets, and limnological monitoring data to identify the unique effects of N on the eutrophication of a phosphorus (P)‐rich lake during ca. 1933‐1995. Cluster analysis revealed two major biostratigraphic zones. Zone I (ca. 1933–1955) was characterized by moderate lake production, as inferred from low concentrations of most fossil pigments and reduced δ 15 N signatures but elevated δ 13 C values and chlorophyte microfossil concentrations. In contrast, Zone II (ca. 1955‐1995) exhibited greatly increased contents of 15 N, N, C, and algal pigments, combined with strongly reduced δ 13 C ratios and chlorophyte fossil abundance, a pattern consistent with recent severe eutrophication. Overall, microfossils of diazotrophic cyanobacteria were most abundant during the transition period between zones (ca. 1955‐1964). Regression analysis revealed that past N influx to the lake (as δ 15 N; r 2 = 0.916, p 2 = 0.837, p 2 = 0.388, p 2 δ 15 N = 0.503, p 2 cyanobacteria = 0.296, p 2 total algae = 0.046, p

Calcium Additions and Microbial Nitrogen Cycle Processes in a Northern Hardwood Forest - Peter M. Groffman; Melany C. Fisk; Charles T. Driscoll; Gene E. Likens; Timothy J. Fahey; Christopher Eagar; Linda H. Pardo (Ecosystems, 2006)

Interactive Effects of Fire, Elevated Carbon Dioxide, Nitrogen Deposition, and precipitation on a California Annual Grassland - Hugh A. L. Henry; Nona R. Chiariello; Peter M. Vitousek; Harold A. Mooney; Christopher B. Field (Ecosystems, 2006)

Metalloid Reducing Bacteria Isolated from Deep Ocean Hydrothermal Vents of the Juan de Fuca Ridge, Pseudoalteromonas telluritireducens sp. nov. and Pseudoalteromonas spiralis sp. nov - Christopher Rathgeber; Natalia Yurkova; Erko Stackebrandt; Peter Schumann; Elaine Humphrey; J. Thomas Beatty; Vladimir Yurkov (Current Microbiology, 2006)

C-type natriuretic peptide and its receptor are downregulated in pulmonary epithelium following birth - Christopher A. D’Angelis; Peter A. Nickerson; Rita M. Ryan; Daniel D. Swartz; Bruce A. Holm (Histochemistry and Cell Biology, 2006)

Molecular provenance analysis for shy and white-capped albatrosses killed by fisheries interactions in Australia, New Zealand, and South Africa - Cathryn L. Abbott; Michael C. Double; Rosemary Gales; G. Barry Baker; Anna Lashko; Christopher J. R. Robertson; Peter G. Ryan (Conservation Genetics, 2006)

Genome-wide meta-analysis for rheumatoid arthritis - Carol J. Etzel; Wei V. Chen; Neil Shepard; Damini Jawaheer; Francois Cornelis; Michael F. Seldin; Peter K. Gregersen; Christopher I. Amos (Human Genetics, 2006)

Detailed characterization of the peptide binding specificity of five common Patr class I MHC molecules - John Sidney; Shinichi Asabe; Bjoern Peters; Kelly-Anne Purton; Josan Chung; Timothy J. Pencille; Robert Purcell; Christopher M. Walker; Francis V. Chisari; Alessandro Sette (Immunogenetics, 2006)

Testing metabolic ecology theory for allometric scaling of tree size, growth and mortality in tropical forests - Helene C. Muller‐Landau; Richard S. Condit; Jerome Chave; Sean C. Thomas; Stephanie A. Bohlman; Sarayudh Bunyavejchewin; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; Kyle E. Harms; Terese Hart; et al. (Ecology Letters, 2006)
The theory of metabolic ecology predicts specific relationships among tree stem diameter, biomass, height, growth and mortality. As demographic rates are important to estimates of carbon fluxes in forests, this theory might offer important insights into the global carbon budget, and deserves careful assessment. We assembled data from 10 old‐growth tropical forests encompassing censuses of 367 ha and > 1.7 million trees to test the theory's predictions. We also developed a set of alternative predictions that retained some assumptions of metabolic ecology while also considering how availability of a key limiting resource, light, changes with tree size. Our results show that there are no universal scaling relationships of growth or mortality with size among trees in tropical forests. Observed patterns were consistent with our alternative model in the one site where we had the data necessary to evaluate it, and were inconsistent with the predictions of metabolic ecology in all forests.

Comparing tropical forest tree size distributions with the predictions of metabolic ecology and equilibrium models - Helene C. Muller‐Landau; Richard S. Condit; Kyle E. Harms; Christian O. Marks; Sean C. Thomas; Sarayudh Bunyavejchewin; George Chuyong; Leonardo Co; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; et al. (Ecology Letters, 2006)
Tropical forests vary substantially in the densities of trees of different sizes and thus in above‐ground biomass and carbon stores. However, these tree size distributions show fundamental similarities suggestive of underlying general principles. The theory of metabolic ecology predicts that tree abundances will scale as the −2 power of diameter. Demographic equilibrium theory explains tree abundances in terms of the scaling of growth and mortality. We use demographic equilibrium theory to derive analytic predictions for tree size distributions corresponding to different growth and mortality functions. We test both sets of predictions using data from 14 large‐scale tropical forest plots encompassing censuses of 473 ha and > 2 million trees. The data are uniformly inconsistent with the predictions of metabolic ecology. In most forests, size distributions are much closer to the predictions of demographic equilibrium, and thus, intersite variation in size distributions is explained partly by intersite variation in growth and mortality.

Herbivore control of annual grassland composition in current and future environments - Halton A. Peters; Elsa E. Cleland; Harold A. Mooney; Christopher B. Field (Ecology Letters, 2006)
Selective consumption by herbivores influences the composition and structure of a range of plant communities. Anthropogenically driven global environmental changes, including increased atmospheric carbon dioxide (CO 2 ), warming, increased precipitation, and increased N deposition, directly alter plant physiological properties, which may in turn modify herbivore consumption patterns. In this study, we tested the hypothesis that responses of annual grassland composition to global changes can be predicted exclusively from environmentally induced changes in the consumption patterns of a group of widespread herbivores, the terrestrial gastropods. This was done by: (1) assessing gastropod impacts on grassland composition under ambient conditions; (2) quantifying environmentally induced changes in gastropod feeding behaviour; (3) predicting how grassland composition would respond to global‐change manipulations if influenced only by herbivore consumption preferences; and (4) comparing these predictions to observed responses of grassland community composition to simulated global changes. Gastropod herbivores consume nearly half of aboveground production in this system. Global changes induced species‐specific changes in plant leaf characteristics, leading gastropods to alter the relative amounts of different plant types consumed. These changes in gastropod feeding preferences consistently explained global‐change‐induced responses of functional group abundance in an intact annual grassland exposed to simulated future environments. For four of the five global change scenarios, gastropod impacts explained > 50% of the quantitative changes, indicating that herbivore preferences can be a major driver of plant community responses to global changes.

Cuticular Hydrocarbons of Buffalo Fly, Haematobia exigua, and Chemotaxonomic Differentiation from Horn Fly, H. irritans - Rudolf Urech; Geoffrey W. Brown; Christopher J. Moore; Peter E. Green (Journal of Chemical Ecology, 2005)

AMP-forming acetyl-CoA synthetase from the extremely halophilic archaeon Haloarcula marismortui: purification, identification and expression of the encoding gene, and phylogenetic affiliation - Christopher Bräsen; Peter Schönheit (Extremophiles, 2005)

Interactive effects of elevated CO 2 , N deposition and climate change on extracellular enzyme activity and soil density fractionation in a California annual grassland - Hugh A. L. Henry; John D. Juarez; Christopher B. Field; Peter M. Vitousek (Global Change Biology, 2005)
Elevated CO 2 , N deposition and climate change can alter ecosystem‐level nutrient cycling both directly and indirectly. We explored the interactive effects of these environmental changes on extracellular enzyme activity and organic matter fractionation in soils of a California annual grassland. The activities of hydrolases (polysaccharide‐degrading enzymes and phosphatase) increased significantly in response to nitrate addition, which coincided with an increase in soluble C concentrations under ambient CO 2 . Water addition and elevated CO 2 had negative but nonadditive effects on the activities of these enzymes. In contrast, water addition resulted in an increase in the activities of lignin‐degrading enzymes (phenol oxidase and peroxidase), and a decrease in the free light fraction (FLF) of soil organic matter. Independent of treatment effects, lignin content in the FLF was negatively correlated with the quantity of FLF across all samples. Lignin concentrations were lower in the aggregate‐occluded light fraction (OLF) than the FLF, and there was no correlation between percent lignin and OLF quantity, which was consistent with the protection of soil organic matter in aggregates. Elevated CO 2 decreased the quantity of OLF and increased the OLF lignin concentration, however, which is consistent with increased degradation resulting from increased turnover of soil aggregates. Overall, these results suggest that the effects of N addition on hydrolase activity are offset by the interactive effects of water addition and elevated CO 2 , whereas water and elevated CO 2 may cause an increase in the breakdown of soil organic matter as a result of their effects on lignin‐degrading enzymes and soil aggregation, respectively.

Modulation of leaf economic traits and trait relationships by climate - Ian J. Wright; Peter B. Reich; Johannes H. C. Cornelissen; Daniel S. Falster; Philip K. Groom; Kouki Hikosaka; William Lee; Christopher H. Lusk; Ülo Niinemets; Jacek Oleksyn; Noriyuki Osada; Hendrik Poorter; et al. (Global Ecology and Biogeography, 2005)
Aim Our aim was to quantify climatic influences on key leaf traits and relationships at the global scale. This knowledge provides insight into how plants have adapted to different environmental pressures, and will lead to better calibration of future vegetation–climate models. Location The data set represents vegetation from 175 sites around the world. Methods For more than 2500 vascular plant species, we compiled data on leaf mass per area (LMA), leaf life span (LL), nitrogen concentration (N mass ) and photosynthetic capacity (A mass ). Site climate was described with several standard indices. Correlation and regression analyses were used for quantifying relationships between single leaf traits and climate. Standardized major axis (SMA) analyses were used for assessing the effect of climate on bivariate relationships between leaf traits. Principal components analysis (PCA) was used to summarize multidimensional trait variation. Results At hotter, drier and higher irradiance sites, (1) mean LMA and leaf N per area were higher; (2) average LL was shorter at a given LMA, or the increase in LL was less for a given increase in LMA (LL–LMA relationships became less positive); and (3) A mass was lower at a given N mass , or the increase in A mass was less for a given increase in N mass . Considering all traits simultaneously, 18% of variation along the principal multivariate trait axis was explained by climate. Main conclusions Trait‐shifts with climate were of sufficient magnitude to have major implications for plant dry mass and nutrient economics, and represent substantial selective pressures associated with adaptation to different climatic regimes.

Stable Boundary-Layer Scaling Regimes: The Sheba Data - Andrey A. Grachev; Christopher W. Fairall; P. Ola G. Persson; Edgar L. Andreas; Peter S. Guest (Boundary-Layer Meteorology, 2005)

Temporal stability of aquatic food webs: partitioning the effects of species diversity, species composition and enrichment - Christopher F. Steiner; Zachary T. Long; Jennifer A. Krumins; Peter J. Morin (Ecology Letters, 2005)
Theory predicts that species diversity can enhance stability of community‐level biomass while simultaneously decreasing population‐level stability. Enrichment can theoretically destabilize communities but effects may become weaker with increasing diversity because of the inclusion of consumer‐resistant prey. Few experiments using direct manipulations of species diversity have tested these predictions. We used laboratory‐based aquatic food webs to examine the effects of species composition, diversity and enrichment on temporal variability of population‐ and community‐level biomass. We found weak effects of enrichment on population‐ and community‐level stability. However, diversity enhanced community‐level stability while species composition had no influence. In contrast, composition effects outweighed diversity effects when stability was measured at the population level. We found no negative effects of diversity on population‐level stability, in opposition to theory. Our results indicate that diversity can enhance stability in multitrophic systems, but effects vary with the scale of biological organization at which stability is measured.

Vegetation, landscape and human activity in Midland Ireland: mire and lake records from the Lough Kinale-Derragh Lough area, Central Ireland - Antony G. Brown; Jackie Hatton; Charlotte E. O’Brien; Katherine A. Selby; Peter G. Langdon; Ingelisa Stuijts; Christopher J. Caseldine (Vegetation History and Archaeobotany, 2005)

Interactive effects of elevated CO2, N deposition and climate change on plant litter quality in a California annual grassland - Hugh A. L. Henry; Elsa E. Cleland; Christopher B. Field; Peter M. Vitousek (Oecologia, 2005)

Climate factors influencing bacterial count in background air samples - Roy M. Harrison; Alan M. Jones; Peter D. E. Biggins; Nigel Pomeroy; Christopher S. Cox; Stephen P. Kidd; Jon L. Hobman; Nigel L. Brown; Alan Beswick (International Journal of Biometeorology, 2005)

Hyporheic macroinvertebrates in riffle and pool areas of temporary streams in south eastern Australia - Grant Christopher hose; Peter Jones; Richard P. Lim (Hydrobiologia, 2005)

Response of epilithic diatom assemblages to urbanization influences - Peter Newall; Christopher J. Walsh (Hydrobiologia, 2005)

Effects of curing, moisture, leaf removal, and artificial inoculation with soft-rotting bacteria on the incidence of bacterial soft rot of onion ( Allium cepa ) bulbs in storage - Peter J. Wright; Christopher M. Triggs (Australasian Plant Pathology, 2005)

Sediment Dynamics in the Adriatic Sea Investigated with Coupled Models - Christopher Sherwood; Jeffrey Book; Sandro Carniel; Luigi Cavaleri; Jacopo Chiggiato; Himangshu Das; James Doyle; Courtney Harris; Alan Niedoroda; Henry Perkins; Pierre-Marie Poulain; Julie Pullen; et al. (Oceanography, 2004)

Gene expression profiling of systemically wound-induced defenses in hybrid poplar - Mary E. Christopher; Manoela Miranda; Ian T. Major; C. Peter Constabel (Planta, 2004)

Quantitative trait loci for steady-state platelet count in mice - Carol C. Cheung; Ian C.A. Martin; Kyall R. Zenger; Jenny A. Donald; Peter C. Thomson; Christopher Moran; Michael F. Buckley (Mammalian Genome, 2004)

Unusual ADP-forming acetyl-coenzyme A synthetases from the mesophilic halophilic euryarchaeon Haloarcula marismortui and from the hyperthermophilic crenarchaeon Pyrobaculum aerophilum - Christopher Brsen; Peter Schnheit (Archives of Microbiology, 2004)

Influence of host plant-derived and abiotic environmental parameters on the composition of the diazotroph assemblage associated with roots of Juncus roemerianus - Jeannine R. LaRocque; Peter W. Bergholz; Christopher E. Bagwell; Charles R. Lovell (Antonie van Leeuwenhoek, 2004)

Phytoplankton nutrient competition under dynamic light regimes - Elena Litchman; Christopher A. Klausmeier; Peter Bossard (Limnology and Oceanography, 2004)
Many physiological processes in phytoplankton, including nutrient uptake, vary on a number of temporal scales. Experiments show that the daily cycle in irradiance affects nutrient uptake rates. We used a Droop‐based model of resource competition to investigate how diel variability in nutrient uptake influences phytoplankton competition and community structure. The analytical approximation we derive shows that if nutrient uptake is light dependent, the minimum nutrient requirements and, hence, nutrient competitive abilities depend on light regime in a species‐specific way. Consequently, daily variations in irradiance may slow rates of competitive exclusion or reverse the identity of the superior competitor but not allow stable coexistence. Irradiance‐induced fluctuations in the maximum nutrient uptake rate of the superior competitor can lead to fluctuations in ambient nutrient concentration and an increase in the average nutrient concentration compared to constant light conditions. This can enhance nutrient use by inferior competitors. These results may be applicable to bacteria‐phytoplankton nutrient competition as well. Depending on the costs and benefits of maintaining nutrient uptake in the dark, different strategies of nutrient use are optimal under different light regimes. Our results suggest that by mediating limiting nutrient use, fluctuations in irradiance may alter the structure of phytoplankton communities.

Diurnal cycling of glutathione in marine phytoplankton: Field and culture studies - Christopher L. Dupont; Tyler J. Goepfert; Peter Lo; Liping Wei; Beth A. Ahner (Limnology and Oceanography, 2004)
Glutathione is an abundant intracellular thiol that is involved in the detoxification of reactive oxygen species generated in the presence of light. We used short‐term continuous cultures of Emiliania huxleyi and Thalassiosira pseudonana to show that a diurnal light cycle causes intracellular glutathione to undergo at least twofold variations, with maximum concentrations occurring during light periods. Cysteine concentrations also appear to vary in E. huxleyi to a similar extent, with the highest concentrations occurring at night. A complementary field study conducted at Salt Pond in Falmouth, Massachusetts, yielded a similar diurnal cycle of glutathione concentrations in particulate samples. This cycling is important to consider when measuring particulate thiols in both culture and field studies and provides additional evidence that glutathione plays an important role as an antioxidant in eukaryotic marine phytoplankton.

Soxhlet extraction of organic compounds associated with soil water repellency - Christopher T. Llewellyn; Stefan H. Doerr; Peter Douglas; Christopher P. Morley; Kathryn A. Mainwaring (Environmental Chemistry Letters, 2004)

Role of heavy polar organic compounds for water repellency of sandy soils - Kathryn A. Mainwaring; Christopher P. Morley; Stefan H. Doerr; Peter Douglas; Christopher T. Llewellyn; Gareth Llewellyn; Ian Matthews; Bridget K. Stein (Environmental Chemistry Letters, 2004)

A study into the anti-microbial properties of an amino functionalised polymer using multi-parameter flow cytometry - Christopher J. Hewitt; Robert Franke; Achim Marx; Beate Kossmann; Peter Ottersbach (Biotechnology Letters, 2004)

Using genetic markers to estimate the pollen dispersal curve - Frederic Austerlitz; Christopher W. Dick; Cyril Dutech; Etienne K. Klein; Sylvie Oddou‐Muratorio; Peter E. Smouse; Victoria L. Sork (Molecular Ecology, 2004)
Pollen dispersal is a critical process that shapes genetic diversity in natural populations of plants. Estimating the pollen dispersal curve can provide insight into the evolutionary dynamics of populations and is essential background for making predictions about changes induced by perturbations. Specifically, we would like to know whether the dispersal curve is exponential, thin‐tailed (decreasing faster than exponential), or fat‐tailed (decreasing slower than the exponential). In the latter case, rare events of long‐distance dispersal will be much more likely. Here we generalize the previously developed twogener method, assuming that the pollen dispersal curve belongs to particular one‐ or two‐parameter families of dispersal curves and estimating simultaneously the parameters of the dispersal curve and the effective density of reproducing individuals in the population. We tested this method on simulated data, using an exponential power distribution, under thin‐tailed, exponential and fat‐tailed conditions. We find that even if our estimates show some bias and large mean squared error (MSE), we are able to estimate correctly the general trend of the curve — thin‐tailed or fat‐tailed — and the effective density. Moreover, the mean distance of dispersal can be correctly estimated with low bias and MSE, even if another family of dispersal curve is used for the estimation. Finally, we consider three case studies based on forest tree species. We find that dispersal is fat‐tailed in all cases, and that the effective density estimated by our model is below the measured density in two of the cases. This latter result may reflect the difficulty of estimating two parameters, or it may be a biological consequence of variance in reproductive success of males in the population. Both the simulated and empirical findings demonstrate the strong potential of twogener for evaluating the shape of the dispersal curve and the effective density of the population ( d e ).

Lipopolysaccharide-induced hypoactivity and behavioral tolerance development are modulated by the light-dark cycle in male and female rats - Andrew E. Franklin; Christopher G. Engeland; Martin Kavaliers; Klaus-Peter Ossenkopp (Psychopharmacology, 2003)

Mechanisms of acetate formation and acetate activation in halophilic archaea - Christopher Brsen; Peter Schnheit (Archives of Microbiology, 2003)

Antimicrobial Activities and Matrix-Assisted Laser Desorption/Ionization Mass Spectrometry of Bacillus Isolates from the Marine Sponge Aplysina aerophoba - Christian T. Pabel; Joachim Vater; Christopher Wilde; Peter Franke; Jrgen Hofemeister; Barbara Adler; Gerhard Bringmann; Jrg Hacker; Ute Hentschel (Marine Biotechnology, 2003)

Poverty and Employment in Forest-Dependent Counties - Peter Berck; Christopher Costello; Louise Fortmann; Sandra Hoffmann (Forest Science, 2003)
One of the most controversial aspects of federal and state policies aimed at protecting old-growth ecosystems is the potential effect of job losses on local economic conditions. A fundamental question for historically forest-dependent areas is whether these policies will result in local economic stagnation and enduring pockets of poverty. This study uses monthly, multicounty time series data to estimate a vector autoregressive model of the experience of northern California counties during the 1980s and 1990s. It examines the long-run impact of changes in timber-related employment on other employment and participation in major federal poverty programs. It finds that employment base-multiplier effects of timber employment on other county employment are small and state economic conditions rather than local employment conditions are the principal driver behind local poverty.

Paleolimnology of Lake Tanganyika, East Africa, over the past 100 kyr - Christopher A. Scholz; John W. King; Geoffrey S. Ellis; Peter K. Swart; J. Curt Stager; Steven M. Colman (Journal of Paleolimnology, 2003)

Bacterial degradation of arsenobetaine via dimethylarsinoylacetate - Richard O. Jenkins; Alisdair W. Ritchie; John S. Edmonds; Walter Goessler; Nathalie Molenat; Doris Kuehnelt; Christopher F. Harrington; Peter G. Sutton (Archives of Microbiology, 2003)

Inhibition of interleukin-1β convertase is associated with decrease of neointimal hyperplasia after coronary artery stenting in pigs - Mariann Gyöngyösi; Wolfgang Sperker; Csaba Csonka; Diana Bonderman; Irene Lang; Christoph Strehblow; Christopher Adlbrecht; Maryam Shirazi; Ursula Windberger; Stephen Marlovits; Michael Gottsauner-Wolf; Paul Wexberg; et al. (Molecular and Cellular Biochemistry, 2003)

The natural abundance of 15N in mat-forming lichens - Christopher J. Ellis; Peter D. Crittenden; Charles M. Scrimgeour; Carl Ashcroft (Oecologia, 2003)

Complete sequence of the IncP‐9 TOL plasmid pWW0 from Pseudomonas putida - Alicia Greated; Lotte Lambertsen; Peter A. Williams; Christopher M. Thomas (Environmental Microbiology, 2002)
Summary The TOL plasmid pWW0 (117 kb) is the best studied catabolic plasmid and the archetype of the IncP‐9 plasmid incompatibility group from Pseudomonas . It carries the degradative ( xyl ) genes for toluenes and xylenes within catabolic transposons Tn 4651 and Tn 4653 . Analysis of the complete pWW0 nucleotide sequence revealed 148 putative open reading frames. Of these, 77 showed similarity to published sequences in the available databases predicting functions for: plasmid replication, stable maintenance and transfer; phenotypic determinants; gene regulation and expression; and transposition. All identifiable transposition functions lay within the boundaries of the 70 kb transposon Tn 4653 , leaving a 46 kb sector containing all the IncP‐9 core functions. The replicon and stable inheritance region was very similar to the mini‐replicon from IncP‐9 antibiotic resistance plasmid pM3, with their Rep proteins forming a novel group of initiation proteins. pWW0 transfer functions exist as two blocks encoding putative DNA processing and mating pair formation genes, with organizational and sequence similarity to IncW plasmids. In addition to the known Tn 4651 and IS 1246 elements, two additional transposable elements were identified as well as several putative transposition functions, which are probably genetic remnants from previous transposition events. Genes likely to be responsible for known resistance to ultraviolet light and free radicals were identified. Other putative phenotypic functions identified included resistance to mercury and other metal ions, as well as to quaternary ammonium compounds. The complexity and size of pWW0 is largely the result of the mosaic organization of the transposable elements that it carries, rather than the backbone functions of IncP‐9 plasmids.

Measuring the structure of dynamic visual signals - Richard A. Peters; Colin W.G. Clifford; Christopher S. Evans (Animal Behaviour, 2002)

Reproduction of hatchery-reared and transplanted wild bay scallops, Argopecten irradians irradians, relative to natural populations - Stephen T. Tettelbach; Christopher F. Smith; Peter Wenczel; Edward Decort (Aquaculture International, 2002)

A comparison of black smoker hydrothermal plume behavior at Monolith Vent and at Clam Acres Vent Field: Dependence on source configuration - Karen G. Bemis; Peter A. Rona; Darrell Jackson; Christopher Jones; Deborah Silver; Kyohiko Mitsuzawa (Marine Geophysical Research, 2002)

Surgery for Prostate Cancer: Rationale, Technique and Outcomes - Tracy M. Downs; Christopher J. Kane; Gary D. Grossfeld; Maxwell V. Meng; Peter R. Carroll (Cancer and Metastasis Reviews, 2002)

A computer image analysis system for microvessel density measurement in solid tumours - Jonathan Charles Goddard; Christopher Derek Sutton; Peter N. Furness; Roger Clive Kockelbergh; Kenneth John O'Byrne (Angiogenesis, 2002)

Tree Mortality in Gap Models: Application to Climate Change - Robert E. Keane; Mike Austin; Christopher Field; Andreas Huth; Manfred J. Lexer; Debra Peters; Allen Solomon; Peter Wyckoff (Climatic Change, 2001)

Population-Based Evaluation of the Ehrlichia Ruminantium MAP 1B Indirect ELISA - Trevor F. Peter; Christopher J. O'Callaghan; Graham F. Medley; Brian D. Perry; Shalt M. Semu; Suman M. Mahan (Experimental and Applied Acarology, 2001)

Calcitonin gene-related peptide is not essential for the development of pressure overload-induced hypertrophy in vivo - Martin E. Young; Kristen A. Okerberg; Christopher R. Wilson; Dario A. Deferrari; Jun Ying; Patrick Guthrie; Peter Razeghi; Fred J. Clubb; Heinrich Taegtmeyer (Molecular and Cellular Biochemistry, 2001)

A Kunitz trypsin inhibitor gene family from trembling aspen (Populus tremuloides Michx.): cloning, functional expression, and induction by wounding and herbivory - Miyoshi Haruta; Ian T. Major; Mary E. Christopher; Joseph J. Patton; C. Peter Constabel (Plant Molecular Biology, 2001)

Mechanisms of acetate formation and acetate activation in halophilic archaea - Christopher Brsen; Peter Schnheit (Archives of Microbiology, 2001)

A Simple Method for Predicting the Consequences of Land Management in Urban Habitats - CHRISTOPHER H. YOUNG; PETER J. JARVIS (Environmental Management, 2001)

Assessing the structural heterogeneity of urban areas: an example from the Black Country (UK) - Christopher H. Young; Peter J. Jarvis (Urban Ecosystems, 2001)

Subcellular distribution of CFTR in rat intestine supports a physiologic role for CFTR regulation by vesicle traffic - Nadia A. Ameen; Elly van Donselaar; George Posthuma; Hugo de Jonge; Gwenn McLaughlin; Hans J. Geuze; Christopher Marino; Peter J. Peters (Histochemistry and Cell Biology, 2000)

The Na + -dependent citrate carrier of Klebsiella pneumoniae : high-level expression and site-directed mutagenesis of asparagine-185 and glutamate-194 - Christopher N. Kästner; Peter Dimroth; Klaas M. Pos (Archives of Microbiology, 2000)

Ultrasound for the Visualization and Quantification of Tumor Microcirculation - F. Stuart Foster; Peter N. Burns; David H. Simpson; Stephanie R. Wilson; Donald A. Christopher; David E. Goertz (Cancer and Metastasis Reviews, 2000)

Gas and particle emissions from Soufrière Hills Volcano, Montserrat, West Indies: characterization and health hazard assessment - Andrew G. Allen; Peter J. Baxter; Christopher J. Ottley (Bulletin of Volcanology, 2000)

The bovine α-glucosidase gene: coding region, genomic structure, and mutations that cause bovine generalized glycogenosis - Julie A. Dennis; Christopher Moran; Peter J. Healy (Mammalian Genome, 2000)

Multicomponent NAPL Solidification Thermodynamics - Catherine A. Peters; Kristine H. Wammer; Christopher D. Knightes (Transport in Porous Media, 2000)

A GCSS Boundary-Layer Cloud Model Intercomparison Study Of The First Astex Lagrangian Experiment - Christopher S. Bretherton; Steven K. Krueger; Matthew C. Wyant; Peter Bechtold; Erik Van Meijgaard; Bjorn Stevens; Joao Teixeira (Boundary-Layer Meteorology, 1999)

A Plan for Outreach: Defining the Scope of Conservation Education - Christopher R. Pyke; Peter S. Alagona; Noah Goldstein; Britta Bierwagen; Jennifer Merrick; Heather Rosenberg; John Gallo (Conservation Biology, 1999)

Optical Thin-Film Sensors for the Determination of Aqueous Halide Ions - Chris D. Geddes; Peter Douglas; Christopher P. Moore; Trevor J. Wear; Peter L. Egerton (Journal of Fluorescence, 1999)

The photosynthesis – leaf nitrogen relationship at ambient and elevated atmospheric carbon dioxide: a meta‐analysis - Andrew G. Peterson; J. Timothy Ball; YiqI. Luo; Christopher B. Field; Peter B. Reich; Peter S. Curtis; Kevin L. Griffin; Carla A. Gunderson; Richard J. Norby; David T. Tissue; Manfred Forstreuter; AnA. Rey; et al. (Global Change Biology, 1999)
Estimation of leaf photosynthetic rate ( A ) from leaf nitrogen content ( N ) is both conceptually and numerically important in models of plant, ecosystem, and biosphere responses to global change. The relationship between A and N has been studied extensively at ambient CO 2 but much less at elevated CO 2 . This study was designed to (i) assess whether the A–N relationship was more similar for species within than between community and vegetation types, and (ii) examine how growth at elevated CO 2 affects the A–N relationship. Data were obtained for 39 C3 species grown at ambient CO 2 and 10 C3 species grown at ambient and elevated CO 2 . A regression model was applied to each species as well as to species pooled within different community and vegetation types. Cluster analysis of the regression coefficients indicated that species measured at ambient CO 2 did not separate into distinct groups matching community or vegetation type. Instead, most community and vegetation types shared the same general parameter space for regression coefficients. Growth at elevated CO 2 increased photosynthetic nitrogen use efficiency for pines and deciduous trees. When species were pooled by vegetation type, the A–N relationship for deciduous trees expressed on a leaf‐mass basis was not altered by elevated CO 2 , while the intercept increased for pines. When regression coefficients were averaged to give mean responses for different vegetation types, elevated CO 2 increased the intercept and the slope for deciduous trees but increased only the intercept for pines. There were no statistical differences between the pines and deciduous trees for the effect of CO 2 . Generalizations about the effect of elevated CO 2 on the A–N relationship, and differences between pines and deciduous trees will be enhanced as more data become available.

Forest Fire Prediction and Prevention in the Brazilian Amazon - Daniel Nepstad; Adriana Moreira; Adalberto Verissimo; Paul Lefebvre; Peter Schlesinger; Christopher Potter; Carlos Nobre; Alberto Setzer; Thelma Krug; Ana Cristina Barros; Ane Alencar; Joao Raposo Pereira (Conservation Biology, 1998)

Forest Fire Prediction and Prevention in the Brazilian Amazon - Daniel Nepstad; Adriana Moreira; Adalberto Verissimo; Paul Lefebvre; Peter Schlesinger; Christopher Potter; Carlos Nobre; Alberto Setzer; Thelma Krug; Ana Cristina Barros; Ane Alencar; Joao Raposo Pereira (Conservation Biology, 1998)

Ontogenetic diet shifts in Roeboides affinis with morphological comparisons - Christopher C. Peterson; Peter McIntyre (Environmental Biology of Fishes, 1998)

The influence of exogenous peptide on β 2 -microglobulin exchange in the HLA complex: analysis in real-time - Claire L. Morgan; Anita K. Ruprai; Alejandra Solache; Mark Lowdell; Christopher P. Price; Shara B. A. Cohen; Peter Parham; J. Alejandro Madrigal; David J. Newman (Immunogenetics, 1998)

Electron spin resonance spectroscopic detection of oxygen-centred radicals in human serum following exhaustive exercise - Tony Ashton; Christopher C. Rowlands; Eleri Jones; Ian S. Young; Simon K. Jackson; Bruce Davies; John R. Peters (European Journal of Applied Physiology, 1998)

Retroviral gene transfer for the assignment of Fanconi anemia (FA) patients to a FA complementation group - Kai-Ling Fu; Peter C. Thuß; Tadahiro Fujino; Martin Digweed; Johnson M. Liu; Christopher E. Walsh (Human Genetics, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

The NMDA antagonist, dizocilpine, enhances cocaine reinforcement without influencing mesoaccumbens dopamine transmission - R. Christopher Pierce; William M. Meil; Peter W. Kalivas (Psychopharmacology, 1997)

Geochemistry of Tertiary tholeiites and picrites from Qeqertarssuaq (Disko Island) and Nuussuaq, West Greenland with implications for the mineral potential of comagmatic intrusions - Peter C. Lightfoot; Christopher J. Hawkesworth; Kevin Olshefsky; Tony Green; Will Doherty; Reid R. Keays (Contributions to Mineralogy and Petrology, 1997)

Detection and quantification of Pseudo‐nitzschia australis in cultured and natural populations using LSU rRNA‐targeted probes - Christopher Scholin; Peter Miller; Kurt Buck; Francisco Chavez; Paul Harris; Paul Haydock; Judith Howard; Gerard Cangelosi (Limnology and Oceanography, 1997)
Pseudo‐nitzschia australis Frenguelli is a marine pennate diatom associated with the production of domoic acid— a neuroexcitatory amino acid linked to illness and mortality of humans and wildlife. Distinguishing P. australis from its co‐occurring congeners is labor intensive and time consuming because of a requirement for scanning electron microscopy. Here, we apply large‐subunit ribosomal RNA (LSU rRNA)‐targeted oligonucleotides in whole‐cell and sandwich hybridization formats to identify and enumerate this species collected from pure cultures and natural populations. Whole‐cell hybridization employed fluorescently labeled probes, filter‐based sample processing, and epifluorescence microscopy to enumerate labeled cells. In contrast, sandwich hybridization was accomplished by homogenizing cells in a chaotropic solution and performing two hybridization reactions: capture of LSU rRNA using an oligonucieotide coupled to a macroscopic solid support and binding of signal probe to a region of LSU rRNA near that of the capture site. Sandwich hybrids were detected colorimetrically; color intensity was proportional to the abundance of target species in the original sample. The sandwich hybridization assay was semiautomated with a robotic processor. Both whole‐cell and sandwich hybridization are useful techniques for identifying P. australis as it occurs in nature. Sandwich hybridization potentially offers the most rapid and simple means to accomplish this task when screening large numbers of environmental samples.

Perceptions of Species Abundance, Distribution, and Diversity: Lessons from Four Decades of Sampling on a Government-Managed Reserve - J. Whitfield Gibbons; Vincent J. Burke; Jeffrey E. Lovich; Raymond D. Semlitsch; Tracey D. Tuberville; J. Russell Bodie; Judith L. Greene; Peter H. Niewiarowski; Howard H. Whiteman; David E. Scott; Joseph H. K. Pechmann; Christopher R. Harrison; et al. (Environmental Management, 1997)

Rapid quantitative determination of fenitrothion on balsam fir foliage: Development of a colorimetric technique and its use in determining insecticide lifetimes on foliage - Peter J. Silk; Christopher M. Riley; Charles J. Wiesner (Archives of Environmental Contamination and Toxicology, 1988)

Enzyme markers in inbred rat strains: Genetics of new markers and strain profiles - Mark Adams; Peter R. Baverstock; Christopher H. S. Watts; George A. Gutman (Biochemical Genetics, 1984)

The effect of metabolic inhibitors on the loss of isocitrate lyase activity from Chlorella - Christopher F. Thurston; Peter C. L. John; Philip J. Syrett (Archives of Microbiology, 1972)